Descriptors based on the density of states for efficient machine learning of grain-boundary segregation energies - Dösinger, Christoph Alexander; Hammerschmidt, Thomas; Peil, Oleg E.; Scheiber, Daniel; Romaner, Lorenz (Computational materials science, 2025)
The segregation of alloying elements to grain-boundaries (GB) has a significant impact on mechanical and functional properties of materials. The process is controlled by the segregation energies, that can accurately be computed using ab-initio methods. Over the last years, ab-initio computations have been combined with machine-learning (ML) approaches for a reduction of computational cost. Here, we show how information from the electronic structure can be incorporated in the ML. To obtain the electronic structure we use two methods, (i) density functional theory (DFT), and (ii) a recursive solution of a tight-binding (TB) Hamiltonian. With the derived descriptors we train a linear model and a Gaussian process on ab-initio segregation data from 15 coincident site lattice GBs with -values up to 43, where the models are compared using cross-validation scores. Both the TB and DFT-derived descriptors are found to clearly outperform common structure-based features that have been used for ML segregation energies before. Furthermore, TB descriptors almost reach the same accuracy as DFT descriptors although their computational effort is significantly reduced. We test our approach on segregation of Ta and Re to GBs in a bcc-W matrix, which are materials of relevance for fusion-energy research.

Towards high-strength electrolyte-supported solid oxide fuel cells - Jana, Arijit; Kraleva, Irina; Schlacher, Josef; Supancic, Peter; Egger, Andreas; Bucher, Edith; Bermejo, Raul (Journal of the European Ceramic Society, 2025)
Publisher Copyright: © 2024 The Authors
Keywords: Ball-on-three-balls test; Biaxial strength; Ionic conductivity; Solid oxide fuel cell; Yttria-stabilized zirconia

Understanding the lower fracture resistance of cold sintered ceramics - Jabr, Abdullah; Ribul, Elija; Salamon, David; Bermejo, Raul (Journal of the European Ceramic Society, 2025)
Publisher Copyright: © 2024 The Authors
Keywords: Cold sintering; Fracture toughness; Rapid sintering; Strength; Zinc oxide

Variational Phase-Field Fracture Approach in Reactive Porous Media - Mollaali, Mostafa; Yoshioka, Keita; Lu, Renchao; Montoya, Vanessa; Vilarrasa, Victor; Kolditz, Olaf (International journal for numerical methods in engineering, 2025)

DigiTeRRI: Responsible Innovation in industry territories - Hörlesberger, Marianne; Kriszt, Brigitte (Routledge, 2025)

Roles of Responsible Research and Innovation keys in the additive manufacturing web of innovation value chains and business - Kriszt, Brigitte; Jimenez Iturriza, Izaskun; Hörlesberger, Marianne (Routledge, 2025)

Thermally Treated Residues and By-Products as Components of Waste-Based Alkali-Activated Materials - Steindl, Florian R.; Radinger, Stefanie; Hassan, Amr; Rudic, Ognjen; Weisser, Katharina; Krammer, Anna; Doschek-Held, Klaus; Ratz, Bettina; Zögl, Iris; Raič, Sara; Mittermayr, Florian; Vallazza-Grengg, Cyrill (RILEM Spring Convention & conference on advanced construction materials and processes for a carbon neutral society, 2025)
Publisher Copyright: © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.
Keywords: AAM; circular building economy; CO-reduced binders; SCM; upcycling

Qualitative insights into cultural heritage protection in Serbia: Addressing legal and institutional gaps for disaster risk resilience - Cvetković, Vladimir; Gole, Stefan; Renner, Renate; Jakovljevic, Vladimir; Lukić, Tin (Open Geosciences, 2024)
This research is dedicated to a comprehensive exploration of the strengths and weaknesses inherent in the legal and institutional measures established to safeguard cultural heritage in the Republic of Serbia against the adverse effects of disasters, including earthquakes, landslides, rockfalls, floods, torrents, storms, hail, and forest fires. The study seeks to identify key challenges and shortcomings within the existing legal and institutional framework while also highlighting and analyzing best practices and potential avenues for improvement in the protection system. The research posits a preliminary hypothesis suggesting that significant challenges exist within the current framework, potentially hindering effective response and recovery efforts following natural hazards. Data collection involved semi-structured interviews with field experts and an in-depth analysis of existing documentation. These methods were aimed at gathering critical data and insights to enhance the understanding of systemic issues and contribute to developing practical, viable solutions. The analysis and processing of the collected data were conducted using ATLAS. ti software, enabling a detailed and systematic examination of qualitative information. Moreover, assessing the current capacity of institutions to respond swiftly and effectively to natural hazards that threaten cultural heritage formed a central aspect of this study. The findings reveal notable deficiencies in the legal framework, inadequate institutional capacities, limited resources, and insufficient training for disaster response. The results underscore the pressing need for improved inter-institutional cooperation and the development of technical and logistical capabilities. To address these issues, the study recommends aligning legal frameworks with international standards, securing increased funding for technical resources, and implementing specialized training programs for institutional staff. This article makes a significant contribution to advancing the understanding and enhancement of the cultural heritage protection system in Serbia, offering actionable insights and a robust foundation for further research and strategic development in this critical area.

A Systematic Literary Review on Community Resilience Indicators - Milenković, Dalibor; Cvetković, Vladimir; Renner, Renate (International journal of disaster risk management, 2024)
Community resilience represents an important concept in the comprehensive approach to disaster management. It is assumed that optimal community resilience can mitigate negative impacts and enable adaptation, thereby reducing the negative consequences of future disasters. The measurement of community resilience to disasters has advanced over the past two decades, primarily through the use of indicators that measure community resilience indices. The Baseline Resilience Indicators for Communities (BRIC) represent an increasingly popular and frequently used quantitative method for measuring community resilience indices to disasters. This literature review was conducted to examine and assess the use and adaptation of the BRIC method in measuring community resilience. The review comprehensively analyzes relevant scientific papers, extracting and synthesizing the most important findings from the studies, which provided the necessary data to meet the objectives of the literature review. A total of 37 relevant studies were identified for analysis in the review. The indicators used were examined, including their selection, grouping, and evaluation procedures, as well as the calculation of the appropriate index. The review also covered the method of data collection needed to measure the impact of indicators on resilience, as well as the shortcomings of this process. The measurement of community resilience to disasters is a contemporary issue, with several detected shortcomings in the process itself. The need to adapt the BRIC method to the local context has been established. Improving the process of determining indicators and measuring indices would lead to broader use of the method in efforts to reduce disaster risk and enhance resilience to disasters.

Industrial Disasters and Hazards: From Causes to Consequences - Cvetković, Vladimir; Renner, Renate; Jakovljević, Vladimir (International journal of disaster risk management, 2024)
Starting from accelerated industrial development, industrial disasters (chemical spills, explosions, nuclear accidents, etc.), which fall under man-made (technological) disasters, increasingly threaten human lives, the environment, and property. Their complexity and far-reaching consequences, both at the local and global levels, require effective management of industrial risks and the disasters themselves (preparedness, mitigation, response, and recovery). For these reasons, the review paper aims to provide a holistic description of the diverse causes, dynamics, and multidimensional consequences of disasters. Additionally, it highlights and explains the key factors that directly or indirectly contribute to their occurrence. Furthermore, it could be said that the paper analyzes existing strategies for managing risks from industrial disasters and systematizes recommendations for improving preventive and reactive measures in high-risk industries. On the other side, the paper utilizes a comprehensive literature review, which involves the systematic identification, review, analysis, and critical evaluation of existing scientific papers, studies, reports, and regulatory documents on industrial disasters. Besides that, it also includes a detailed analysis of well-known industrial disaster cases such as Seveso (Italy, 1976), Bhopal (India, 1984), Chernobyl (Ukraine, then USSR, 1986), and Fukushima (Japan, 2011). The paper emphasizes that industrial disasters are often the result of the combined influence and interaction of technical failures, human errors, and inadequately developed safety procedures. Moreover, it can be highlighted that the design and implementation of preventive measures, such as regular maintenance of technical systems and systematic training and education of employees, are crucial for reducing the likelihood of such catastrophic events. The implications of this review paper are multifaceted and point to the following: the need to reassess current safety practices in industries; reconsider the potential for introducing innovations in preventive technical-technological solutions; examine the thorough implementation of innovative early warning systems, safety procedures, and modern equipment in facilities; improve cooperation between engineers, safety managers, and regulatory workers; reassess the need for additional updates and tightening of regulations regarding the storage, transport, and use of hazardous materials in industry; and improve the management of risks from industrial disasters.

Optimising Disaster Resilience Through Advanced Risk Management and Financial Analysis of Critical Infrastructure in the Serbian Defence Industry - Vidović, Nikola; Beriša, Hatidža; Cvetković, Vladimir (International journal of disaster risk management, 2024)
This paper presents a comprehensive analysis of the financial factors and risk management strategies essential for optimizing disaster resilience within the Serbian defence industry's critical infrastructure. The significance of this sector is multi-faceted, impacting national security, economic stability, and technological advancement. Primarily, the Serbian defence industry ensures the preservation of vital defence interests, maintaining Serbia's independence from foreign sources for weapons and military equipment in both peacetime and wartime. Economically, it is a significant employer of the working-age population, directly affecting local employment rates, fostering economic development, and ensuring the sustainable growth of this crucial sector. This, in turn, stimulates broader economic activity and enhances social cohesion while strengthening the national balance of payments through increased export potential. From a technological perspective, the defence industry drives scientific, technological, and industrial development, reinforcing Serbia's global political and military standing within the Western Balkans and on the international stage. Consequently, the paper aims to examine the risk management and protection of the Serbian defence industry's critical infrastructure, offering concrete and actionable measures to improve and develop these systems with a particular emphasis on security. The research's utility and contribution lie in identifying similarities and differences in the operational performance of defence industry companies, a vital segment of the national economy. The presentation of these findings focuses on the protection of critical infrastructure. The results will form the basis for further investigation into the underlying causes of business performance and the effective management of critical infrastructure security.

Assessing the hydrogen embrittlement susceptibility of an existing L360NB natural gas pipeline steel for 100 % hydrogen transport - Ahmed Hamed Mahmoud Eid Gouda, Ahmed Hamed Mahmoud Eid Gouda; Posch-Peperkorn, Christian; Maierhofer, Juergen; Beschliesser, Monika; Fink, Stefan; Mori, Gregor Karl (Corrosion science, 2024)
In this study, a section of an existing L360NB natural gas pipeline with a girth weld is sampled to evaluate the hydrogen embrittlement susceptibility upon repurposing for pure hydrogen transport. In various wet and dry hydrogen environments with and without H2S, the base and welded material are investigated by constant load tests. The applied load increases hydrogen uptake in the majority of the testing environments. The weld shows a higher hydrogen uptake compared to the base material in all testing environments. In wet H2S containing en- vironments under loading, the formed FeS layer helps in reducing the hydrogen uptake.
Publisher Copyright: © 2024 The Authors
Keywords: Hydrogen absorption; Hydrogen embrittlement; Hydrogen pipelines; Hydrogen transport

Integrated Rock Mass Characterization of the Lower Continental Crust Along the ICDP-DIVE 5071_1_B Borehole in the Ivrea-Verbano Zone - Li, Junjian; Caspari, Eva; Greenwood, Andrew; Pierdominici, S.; Lemke, K.; Venier, M.; Kück, J.; Baron, L.; Pistone, M.; Petri, B.; Ziberna, Luca; Hetényi, György (Geochemistry, geophysics, geosystems, 2024)
The first borehole 5071_1_B of the ICDP-Drilling the Ivrea-Verbano zonE (DIVE) project in Italy, which intersects the Massone antiform, provides a unique opportunity to integrate downhole geophysical measurements with observations from 100% recovered drill core in rarely drilled lithologies. The objective of this study is to petrophysically and structurally characterize the rock mass and constrain factors influencing the seismic velocity in the lower continental crust. A comprehensive data set, comprising core, well log and vertical seismic profiling data, was collected. The structural analysis indicates that the axial plane of the intersected tightly folded antiform is slightly tilted at the borehole location and thus the borehole intersects the hinge zone at the top and its limb in the lower part of 5071_1_B. Numerous open natural fractures with variable dips and two dominant dip azimuthal orientations are identified along the borehole, which affect the electrical and acoustic properties. The velocities at the core, well log and seismic scale are consistent but lower than intrinsic seismic velocities of the lower continental crust, since they are not only affected by fractures but also by micro cracks at the 5071_1_B in situ conditions. A systematic lithology correlation is not evident for these properties. However, a cluster analysis of gamma ray and magnetic susceptibility logs shows an excellent agreement with the logged core lithologies in the presence of remarkable spatial variability. Furthermore, the main lithologies are grouped into three distinct clusters, suggesting two types of kinzigites with distinct magnetic and radiogenic properties.

Microstructural insights into the coarse‑grained heat‑affected zone of a high‑strength all‑weld metal - Schrittwieser, Daniel; Marin Morales, David; Pahr, Hannes; Lumper-Wimler, Lea; Glushko, Oleksandr; Schnitzer, Ronald (Welding in the world, 2024)
The present study deals with the development of a continuous cooling transformation diagram corresponding to the coarse-grained heat-affected zone of a high-strength all-weld metal with a minimum yield strength of 1100 MPa fabricated via gas metal arc welding. Dilatometry tests were conducted to determine the transition temperatures. High-resolution imaging methods, such as transmission electron microscopy and atom probe tomography, as well as nanoindentation, were employed to resolve the microstructural constituents. At fast cooling rates (t 8/5 from 1.4 to 25 s), the microstructure comprises a mixture of martensite and coalesced bainite, with a slight increase in the content of coalesced bainite with faster cooling. This demonstrates that coalesced bainite cannot be avoided in the coarse-grained heat-affected zone of the current alloy by increasing the cooling rate. With slower cooling (t 8/5 ≥ 50 s), the microstructure becomes increasingly bainitic, accompanied by a marginal drop in Vickers hardness. At t 8/5 times of 500 s and 1000 s, the all-weld metal consists of granular bainite with significant amounts of retained austenite and different shaped martensite-austenite constituents. The coarser massive-type constituents contain body-centered cubic grains, sized in the hundreds of nanometers, with a hardness approximately twice as high as that of the surrounding bainitic matrix.
Publisher Copyright: © The Author(s) 2024.
Keywords: CCT diagram; Coalesced bainite; Granular bainite; High-strength weld metal; Martensite-austenite constituent; Weld metal HAZ

Strain rate-dependent failure modes of material extrusion-based additively manufactured PETG - Waly, Christoph; Schulnig, Sandra; Arbeiter, Florian (Theoretical and Applied Fracture Mechanics, 2024)
The layer-by-layer nature of fused filament fabrication (FFF) introduces interfaces along the build direction (z-axis). A crack approaching an interface may deflect or penetrate subsequent layers, based on the relative strengths of the interface and the matrix. This study evaluates the applicability of the Cook & Gordan (C&G) model for predicting crack deflection or penetration in glycol-modified poly(ethylene terephthalate) (PETG) printed structures, considering different print orientations and layer heights. The loading rate was varied between 0.1 and 1000 mm/min to identify potential rate-dependent effects. Interface and matrix strengths were determined through tensile testing, and their ratio was used to assess the validity of the C&G criterion. The results, supported by fracture mechanical validation experiments, indicate that the C&G model can effectively predict crack paths in FFF-printed PETG structures, provided that the assumptions of linear elastic fracture mechanics are not significantly violated. Accurate predictions were unattainable at the lowest loading rate (0.1 mm/min). For loading rates ≥ 10 mm/min the criterion appears plausible, aligning with previous studies.
Publisher Copyright: © 2024 The Author(s)
Keywords: Crack Deflection; Crack Penetration; FFF; Fracture Testing; Fused Filament Fabrication; Strain Rate Dependency; Tensile Testing

Artificial neural network model for estimating mold flux melting temperature - Mapelli, Carlo; Mombelli, Davide; Dall'osto, Gianluca; Cho, Jungwook; Gruber, Nathalie; Marschall, Irmtraud; Cornille, Maïte; Alloni, Marco; Carli, Ricardo (ISIJ international, 2024)
The accuracy of the current models for the calculation of the melting temperature of the mold flux shows that there is still room for improvement, given that their accuracy could not be satisfactory enough to keep up with the current industrial needs. In this work the use of artificial neural networks for data prediction is explored. The network acts as a "black box" capable to predict the melting temperature determined by complex physical interaction among the involved chemical species composing the flux. The network is trained by learning from real experimental data provided by different research groups through hot stage microscopy. The data was tested first within its respective batches and then tested as a single aggregate data batch. After testing and optimization of the networks' parameters, an acceptable level of accuracy was reached because the estimated melting temperatures point out an average error lower than 30 K if compared to measured data. This opens the possibility for the development of a standalone application that can be used for reference. In order to open the possibility for further improvements of this study the paper shares and makes public the values contained in the matrixes connecting the nodes of neural networks.
Publisher Copyright: © 2024 The Iron and Steel Institute of Japan.
Keywords: artificial neural network; continuous casting; liquidus temperature; mold powder

Impact of Cyber Space on Security in the Context of Armed Conflicts: Towards Disaster Risk Resilience - Milenković, Dalibor; Cvetković, Vladimir; Ivanov, Aleksandar; Renner, Renate (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
The rapid evolution of cyberspace has profoundly impacted security dynamics and the conduct of armed conflicts. As an integral domain in modern warfare, cyberspace intertwines with traditional conflict factors, such as human and material resources, space, time, and information, redefining their roles and interactions. This paper explores the influence of cyberspace on security within the context of armed conflicts, highlighting its dual nature as a battlefield and a tool for shaping strategic outcomes. Emphasis is placed on integrating advanced technologies, including artificial intelligence and the Internet of Things (IoT), in enhancing operational capabilities and addressing hybrid and informational warfare. Furthermore, the study examines the critical role of disaster risk resilience in mitigating the cascading effects of cyber-related disruptions during conflicts. The findings underscore the need for a comprehensive approach combining technical innovations, organizational strategies, and robust regulatory frameworks. The paper concludes that achieving resilience in cyberspace requires multidisciplinary collaboration, continuous capacity building, and the alignment of security policies with emerging technological challenges. The findings highlight the critical importance of integrating digital infrastructures, regulatory frameworks, and innovative technologies, such as artificial intelligence and the Internet of Things (IoT), to mitigate cascading effects during armed conflicts. By emphasizing adaptive strategies and capacity-building, the paper offers actionable insights for policymakers and practitioners aiming to strengthen societal and infrastructural resilience in the face of hybrid threats.

A Skorohod measurable universal functional representation of solutions to semimartingale SDEs - Przybyłowicz, Paweł; Schwarz, Verena; Steinicke, Alexander; Szölgyenyi, Michaela (Stochastic analysis and applications, 2024)
In this article, we show the existence of a universal Skorohod measurable functional representation for a large class of semimartingale-driven stochastic differential equations. For this, we prove that paths of the strong solutions of stochastic differential equations can be written as measurable functions of the paths of their driving processes into the space of all càdlàg functions equipped with the Borel sigma-field generated by all open sets with respect to the Skorohod metric. This result can be applied to calculate Malliavin derivatives for SDEs driven by pure-jump Lévy processes with drift.

Lead-free dielectric thin films - Kölbl, Lukas; Mehrabi, Mahdieh; Griesser, Thomas; Munnik, Frans; Mitterer, Christian (Journal of vacuum science & technology / A (JVST), 2024)
Growing environmental concerns have driven the switch from lead-containing dielectric perovskite ceramics to lead-free alternatives such as silver niobate tantalate [Ag(Nb1−xTax)O3], where tantalum (Ta) substitution for niobium (Nb) enhances energy-storage density. Thin film deposition presents a promising way for fabricating these materials for use in capacitors. In this study, Ag(Nb1−xTax)O3 (0 ≤ x ≤ 0.5) thin films are synthesized via combinatorial reactive dc magnetron sputtering from metallic targets. The chemical and phase compositions of the films are comprehensively analyzed using scanning electron microscopy coupled with energy dispersive x-ray spectroscopy, elastic recoil detection analysis, Rutherford backscattering spectrometry, x-ray diffraction, Raman spectroscopy, and x-ray photoelectron spectroscopy. The findings demonstrate that reactive dc magnetron sputtering is a feasible technique for producing complex perovskite oxide thin films with customized chemical composition and microstructure. By enhancing the understanding of the Ag(Nb1−xTax)O3 material system, this study aims to contribute to the development of environmentally benign high-performance dielectrics that could replace lead-based ceramics in energy-storage applications.

Site-specific femtosecond laser ablation - Tang, Jing; Renk, Oliver; Tkadletz, Michael (Materials characterization, 2024)
The exceptional chemical detection sensitivity and near-atomic scale resolution made atom probe tomography (APT) to an indispensable analytical tool to investigate the 3D chemical nature of crystal defects. However, this renders site-specific APT tip preparation necessary and a long-lasting challenge obvious. The current gold standard for site-specific APT tip preparation using focused ion beams (FIB) is very time and resource consuming. A possible premature tip fracture of the welding zone between tip and specimen carrier can further decrease the success rate. Facing these challenges, APT data sets are rarely of statistically relevant size as mostly only one or just a few sites (e.g., a single grain boundary) are analyzed at best. Here we tackle these issues by successfully implementing femtosecond laser ablation to site-specifically prepare APT tips directly into the specimen, rendering lift-out procedures unnecessary. Our approach drastically reduces preparation time, as before near-net shaping of the APT tips with the laser, only the features of interest have to be marked. The time for the tip ablation process further does not require personal assistance and is independent of the number of tips. Moreover, FIB time is reduced to a final tip sharpening process. The approach is extremely robust, as demonstrated by successful tip preparation of 100 % of the targeted features, including final analysis using field ion microscopy and APT. Thus, site-specific femtosecond laser ablation has the potential to develop APT towards a high-throughput characterization method.
Publisher Copyright: © 2024 The Author(s)
Keywords: Atom probe tomography (APT); Electron backscatter diffraction (EBSD); Field ion microscopy; High-throughput characterization; Site-specific APT tip preparation; Transmission Kikuchi diffraction (TKD)

Von Erdgas zu Wasserstoff, Teil II - Tichy, Stefan; Büchner, Karl; Pucher, Philip; Prillhofer, Bernd; Wibner, Stefan; Antrekowitsch, Helmut (International aluminium journal, 2024)

Ore Deposits - Melcher, Frank (2024)

Deformation and fracture of lithosphere-inspired polymeric multi-layer composites - Waly, Christoph; Höller, Rita; Griesser, Thomas; Arbeiter, Florian (Results in Engineering, 2024)
Inspired by the diversity of structures and patterns inherent in the earth's lithosphere, this study endeavors to enhance the interplay between stiffness and toughness through the introduction of a new class of polymeric multi-layer composite materials termed by the authors as "lithomers". Structured single-edge notched bending specimens were fabricated using a combination of additive manufacturing and casting, employing two different methacrylate-thiol resins. The outer layers exhibit a stiff and brittle characteristic, while the layer in between is compliant in nature. Three types of lithomers with wave-like structures and one with a rectilinear structure were investigated regarding their stiffness and toughness in a 3-point bending setup. The results were compared with those of a pure stiff matrix material. The findings revealed that fracture toughness increased regardless of the interlayer's shape compared to the pure matrix material. Correspondingly, this enhancement in fracture toughness correlated with a reduction in stiffness. The most balanced results in terms of stiffness and fracture toughness were achieved, with the lithomer having a wave-like structure in its initial stage. It exhibited a roughly 27 times improvement in fracture toughness with a moderate decrease in stiffness of approx. 1/5 compared to the pure matrix material.
Publisher Copyright: © 2024
Keywords: Biomimetics; Fracture toughness; Lithomers; Lithomimetics; Multi-layered structure

Enhancement of copper nanoparticle yield in magnetron sputter inert gas condensation by applying substrate bias voltage and its influence on thin film morphology - Knabl, Florian; Gutnik, Dominik; Patil, Prathamesh; Bandl, Christine; Vermeij, Tijmen; Pichler, Christian M.; Putz, Barbara; Mitterer, Christian (Vacuum, 2024)
Publisher Copyright: © 2024 The Authors
Keywords: Low energy ion scattering spectroscopy; Magnetron sputter inert gas condensation; Magnetron sputtering; Nanoparticle synthesis; Thin film

Scaffold microstructure evolution via freeze-casting and hydrothermal phase transformation of calcium phosphate - Siddiqui, Maliha; Salamon, David (Journal of the American Ceramic Society, 2024)
Publisher Copyright: © 2024 The American Ceramic Society.
Keywords: calcium phosphate; compressive strength freeze-casting; hydrothermal; scaffolds

Towards high strength SrTiO3-based composites fabricated at room temperature - Jabr, Abdullah; Kuzmić, Nina; Škapin, Srečo Davor; Jantunen, Heli; Nelo, Mikko; Spreitzer, Matjaž; Bermejo, Raul (Journal of the European Ceramic Society, 2024)
Publisher Copyright: © 2024
Keywords: Lithium molybdate; Room temperature fabrication; Sodium silicate; Strength; Strontium titanate

Unravelling nanometallurgy with in situ transmission electron microscopy - Coradini, Diego S. R.; Tunes, Matheus Araujo; Quick, Cameron R.; Willenshofer, Patrick; Kremmer, Thomas; Luidold, Stefan; Uggowitzer, Peter; Pogatscher, Stefan (Nano today, 2024)
Technological advances constantly set new challenges for materials development. The miniaturisation of electronic devices demands the migration of metallurgy from macro/micro to the nanoscale, thus requiring a re-definition of existing and classical concepts in this field. The present study reports on the behaviour of pure Cu nanowires with diameters ranging from 40 to 140 nm heated in a low-pressure environment within a transmission electron microscope. The response of Cu nanowires was investigated at different temperatures up to 1123 K and analysed using electron-microscopy techniques, revealing both volumetric and shape changes over time. Sublimation, with a steady-state length reduction of the nanowires, was identified as the dominant effect of such heating. Additionally, it was detected that sublimation occurred not only at temperatures above ≈ 1023 K, where Cu has a higher vapour pressure than the column pressure of the electron-microscope, but also at temperatures as low as 923 K. This behaviour is explained by the presence of active regions at sharply curved regions at the nanowire tip and the imbalance of evaporation and redeposition rates of Cu atoms due to the experimentally-induced loss of vapor atoms. The study of Cu nanowires at the nanoscale with the electron microscope facilitates the elucidation of some fundamental aspects of the emerging science of nanometallurgy.
Publisher Copyright: © 2024 The Authors
Keywords: Copper Nanowires; In situ Transmission Electron Microscopy; Nanometallurgy; Sublimation; Surface Diffusion

Evaluation of Six Phosphorus Extraction Methods for Compliance Testing of Recycled P Fertilizers - Hernandez-Mora, Alicia; Duboc, Olivier; Bünemann, Else K.; Ylivainio, Kari; Lombi, Enzo; Symanczik, Sarah; Horn, Dietmar; Delgado, Antonio; Abu Zahra, Nadine; Zuin, Lucia; Doolette, Casey L.; Eigner, Herbert; et al. (Environmental technology & innovation (OA), 2024)
Phosphorus (P) recycling for fertilizer production addresses the dependency on phosphate rock and mitigates P losses to the environment. However, predicting plant-available P in recycled fertilizers is challenging due to their diverse chemical composition. This study aimed at identifying the most suitable P extraction method for fertilizer compliance testing, considering their correlation with actual fertilization efficiency, as well as their simplicity, throughput, recognition and cost. Studies on fertilizer P compliance testing often lack recommendations on minimum P extractability threshold values. Here, thresholds are calculated based on actual fertilization efficiency of a large, chemically diverse set of recycled P fertilizers, many of which are already marketed. Thirty recycled P fertilizers were extracted with H2O, neutral ammonium citrate (NAC), electro-ultrafiltration (EUF), ferrihydrite-filled membranes (iron bag; IB), sodium bicarbonate (NaHCO3) and diffusive gradients in thin films (DGT). The mineral replacement value (MRV) of the fertilizer set was previously evaluated in three pot experiments at a fertilization rate of 50 mg kg−1 soil. MRV correlations with the extractions methods showed similar results for all besides H2O, which cannot be a reliable indicator for P availability. Fertilizers were classified as efficient or inefficient based on their MRV exceeding or falling below 60 % of the triple superphosphate reference value. The minimum P extractability threshold value (MPETV) for each method was based on the efficiency classification and it minimized the number of misclassified fertilizers. NAC, with a 60 % extractable minimum P threshold value, was the most adequate method for compliance testing, despite its overestimation of iron phosphate availability.

Pressure–temperature–time and REE mineral evolution in low- to medium-grade polymetamorphic units (Austroalpine Unit, Eastern Alps) - Hollinetz, Marianne Sophie; Huet, Benjamin; Schneider, David; McFarlane, Christopher R.M.; Schuster, Ralf; Rantitsch, Gerd; Schantl, Philip; Iglseder, Christoph; Reiser, Martin; Grasemann, Bernhard (European journal of mineralogy, 2024)
We investigated rare earth element (REE) minerals in low- to medium-grade metapelites sampled in two nappes of the Austroalpine Unit (Eastern Alps, Austria). Combining microstructural and chemical characterization of the main and REE minerals with thermodynamic forward modeling, Raman spectroscopy on carbonaceous material (RSCM) thermometry and in situ U–Th–Pb dating reveal a polymetamorphic evolution of all samples. In the hanging wall nappe, allanite and REE epidote formed during Permian metamorphism (275–261 Ma, 475–520 °C, 0.3–0.4 GPa). In one sample, Cretaceous (ca. 109 Ma) REE epidote formed at ∼440 °C and 0.4–0.8 GPa at the expense of Permian monazite clusters. In the footwall nappe, large, chemically zoned monazite porphyroblasts record both Permian (283–256 Ma, 560 °C, 0.4 GPa) and Cretaceous (ca. 87 Ma, 550 °C, 1.0–1.1 GPa) metamorphism. Polymetamorphism produced a wide range of complex REE-mineral-phase relationships and microstructures. Despite the complexity, we found that bulk rock Ca, Al and Na contents are the main factor controlling REE mineral stability; variations thereof explain differences in the REE mineral assemblages of samples with identical pressure and temperature (P–T) paths. Therefore, REE minerals are also excellent geochronometers to resolve the metamorphic evolution of low- to medium-grade rocks in complex tectonic settings. The recognition that the main metamorphic signature in the hanging wall is Permian implies a marked P–T difference of ∼250 °C and at least 0.5 GPa, requiring a major normal fault between the two nappes which accommodated the exhumation of the footwall in the Cretaceous. Due to striking similarities in setting and timing, we put this low-angle detachment in context with other Late Cretaceous low-angle detachments from the Austroalpine domain. Together, they form an extensive crustal structure that we tentatively term the “Austroalpine Detachment System”.

A Combined Investment and Operational Optimization Approach for Power-to-Methanol Plants - Akram, Nouman; Kienberger, Thomas (Energies, 2024)
In the global effort for industrial decarbonization, repurposing closed coal-fired power plants into power-to-methanol (PtM) plants offers a promising pathway to reduce CO₂ emissions while leveraging existing infrastructure. This study introduces a novel combined optimization approach using mixed-integer linear programming (MILP) to simultaneously optimize the investment and operation of a PtM plant, assessing its economic viability. The model incorporates the operational flexibility of proton exchange membrane (PEM) electrolyzers in response to fluctuating electricity prices through a piecewise linear representation of its load–efficiency characteristic curve. A case study of a repurposed coal plant in Austria demonstrates the model's applicability and practical relevance. The results show that larger electrolyzer capacities, i.e., 434 MW, with flexible part-load operation can significantly reduce methanol production costs, i.e., EUR 0.8/kg, achieving competitiveness under high CO₂ pricing scenarios, i.e., EUR 500/ton. A sensitivity analysis is performed to identify the critical factors influencing production costs. This study concludes that the combined investment and operational optimization approach effectively captures the essential elements of PtM systems, enabling faster, better, and operation-informed investment decisions for innovative technologies to support the ongoing energy transition. These findings indicate that PtM technologies can be a viable solution for asset repurposing, grid stabilization, and decarbonizing hard-to-abate sectors.
Keywords: power-to-methanol; mixed-integer linear programming; PEM; piecewise linearization

Comprehensive Databases on Natural and Man-Made (Technological) Hazards and Disasters: Mapping Risks and Challenges - Vladimir, Cvetković M.; Renner, Renate (2024)
Preface: In today’s world, where disasters—whether natural or man-made (technological)—are happening more often and with greater impact, it’s more important than ever to have solid, easy-to-access information on the risks we face. That’s where this monograph, "Comprehensive Databases on Natural and Man-Made (Technological) Hazards and Disasters: Mapping Risks and Challenges," comes in. Also, it pulls together a range of databases that cover all kinds of disasters, aiming to give a full picture of the risks out there. This publication represents a collaborative effort between disaster risk management experts from Serbia and Austria, each contributing their specialized expertise to enrich the work. The main goal is simple: to offer a valuable resource for anyone involved in disaster risk reduction—whether they’re researchers, policymakers, or on-the-ground practitioners. By mapping out the risks and challenges tied to different hazards, we hope to help create better strategies for reducing disaster impacts. On the other side, we’ve taken a broad approach, covering both natural hazards (like earthquakes, tsunamis, and storms) and man-made ones (like industrial accidents and nuclear incidents). This gives a complete view of the global risk landscape, so no major threat is overlooked. Each chapter focuses on specific types of hazards, breaking down the databases that track these events, how they gather data, and how that data is used. These databases are essential for understanding how often these events happen, where they tend to occur, and how severe they are. This info is critical for predicting future disasters and preparing for them. Furthermore, we don’t stop at just listing databases, we also dig into the challenges of gathering, sharing, and using disaster data. There’s a huge range of data sources, and with different standards and the need for real-time info, it can be tricky. We talk about these obstacles and suggest ways to make disaster data easier to access and more practical to use. Another big focus is the role of technology in disaster risk management. Techs like geospatial tools, remote sensing, and data analytics have changed the game when it comes to monitoring and responding to disasters. We highlight some of the coolest tools and platforms out there that are using these technologies to make disaster management better and faster. Collaboration is key in disaster risk management, and this monograph really pushes the importance of international cooperation. Sharing information and resources across borders helps everyone be better prepared and more resilient. When countries work together, they can better predict and handle the impact of disasters. In a nutshell, this monograph is your go-to guide for understanding the many databases that track both natural and human-made disasters. It takes a hard look at where we stand with disaster data, points out both the challenges and opportunities in the field, and emphasizes how crucial technology, teamwork, and education are in building a safer, stronger world. Our hope is that this work will be a helpful resource and spark more research and innovation in disaster risk management. The monograph starts with an introduction that sets the stage for exploring natural and human-made hazards. It explains why accurate, accessible data is so important for managing disaster risks and gives an overview of the content. From there, the monograph is split into two main sections: Natural Hazards and Man-Made (Technological) Hazards. The Natural Hazards section covers everything from geological events (like earthquakes and volcanic eruptions) to meteorological and biological hazards (like floods, storms, and disease outbreaks). We go deep into the databases that track these events, how they collect data, and how that data is used in risk assessment and disaster management. The Man-Made Hazards section focuses on things like industrial accidents, nuclear disasters, chemical spills, and building collapses. Just like with natural hazards, we break down the key databases and discuss how they help manage and reduce these risks. Introduction: Large-scale disasters, from naturally occurring events such as earthquakes and tsunamis through to man-made ones including industrial accidents and financial crises—have been increasing of late in frequency and intensity, with long-lasting effects on societies and infrastructures while bursting into the global economy. Some of the drivers underlying these challenges—such as climate change, rapid urbanization, technological changes, and geopolitical instability—are becoming increasingly urgent, hence making current risks more complex. This changing scenario requires much more sophisticated ways of managing risks and preventing disasters. Recently, much focus has been directed toward Disaster Risk Reduction, which focuses on reducing the impact of disasters through improved preparedness, mitigation strategies, and rapid response plans. Global frameworks, such as the Sendai Framework for Disaster Risk Reduction 2015–2030, draw attention to how data-driven risk assessments underpin resilience at levels ranging from the community to the nation-state and global levels. The increasing frequency and impact of disasters, further compelled by causes that are becoming increasingly interlinked, raise the need for accurate and comprehensive data to higher levels than ever before if risks are to be reduced effectively. The comprehensive mapping of risks and challenges of natural and artificial (technological) hazards and disasters, which was called for by the monograph entitled Comprehensive Databases on Natural and Man-Made (Technological) Hazards and Disasters: Mapping Risks and Challenges, discusses in some considerable detail the matter of pressing need for reliable data in disaster risk reduction. It goes on to give in-depth analysis regarding databases recording the occurrence of both natural hazards—such as earthquakes, floods, and storms—and human-made hazards that include industrial accidents and chemical spills. The effort here is to provide improved access to fundamental information necessary to reduce the impact of disasters and vulnerabilities worldwide by analyzing more than 50 of the most relevant databases. The authors would like to express their gratitude in this regard to Grammarly Premium and ChatGPT 4.0 for grammatical editing and reviewing this book chapter for clarity and quality in translation regarding English. Language improvement suggestions have been provided by the AI tools, but they have not been involved in the elaboration of the scientific content. Full responsibility for originality, validity, and integrity of the manuscript lies with the authors. The basis of any successful disaster risk management is having access to the right information at the right time. Forecasting natural disasters, monitoring environmental conditions that could cause industrial accidents, or tracking disease outbreaks—in all these areas, access to relevant information is key in making contextually informed decisions. However, this movement from pure response to proactive risk reduction has been prompted more than anything by leaps forward in the ways we can gather and integrate data and then analyze it. Data allows the professionals and the policymakers to predict when the events are likely to happen in the future owing to patterns from the past, weather trends, and geological insight in natural disasters. Seismic data, for example, informs the estimation of earthquake risk for areas around active fault lines; similarly, hydrologic models might forecast flood risk in heavy rain seasons. For man-made disasters, for instance, databases that track industrial process, hazardous material storage and safety protocols can find those most prone to accident and undertake precise preventative action before any accident occurs. Nevertheless, the availability and quality of disaster-related data still depend on the individual type of hazard, region, and local capacity for its collection. Whereas in most parts of the world certain risks, such as earthquakes or floods, are quantified, others—in particular, technological or economic hazards—are underreported, with no standardized data collection systems in place. The current monograph closes these gaps by means of a critical review of the diverse methodologies of the individual databases through pointing out strengths and weaknesses and by offering suggestions on how disaster data could be made more comprehensive and usable. Objectives of the Monograph: The primary goal of this monograph is to provide a thorough analysis of the available databases that track both natural and technological hazards. Specifically, it aims to: a) Offer a detailed overview of the most prominent databases that monitor various hazards, focusing on their scope, data collection methods, sources, and relevance to disaster risk management. b) Investigate the challenges associated with collecting, integrating, and utilizing disaster data, with a particular focus on issues of data quality, accessibility, and real-time application. c) Examine how technological advancements—such as satellite imagery, geospatial analysis, and real-time monitoring—are improving the way disaster data is collected and analyzed. d) Provide practical recommendations for enhancing disaster-related data systems, emphasizing the importance of data sharing, standardized reporting, and the incorporation of emerging technologies. e) Promote collaboration between researchers, policymakers, and disaster management professionals by creating a consolidated resource for understanding and utilizing disaster data effectively. Structure of the Monograph: The monograph is divided into two sections: Natural Hazards and Disasters and Man-Made (Technological) Hazards and Disasters. These contain several chapters covering specific kinds of hazards and the tracking and analysis databases for each. This is aimed at presenting the reader with a complete, systematic overview of the disaster data landscape for both natural and technological risks. This chapter, “Natural Hazards and Disasters,” presents a comprehensive analysis, of geological events like earthquakes and volcanic eruptions to hydrological and meteorological hazards, including floods, droughts, hurricanes, and biological hazards that affect human populations and ecosystems. Each chapter examines key databases for monitoring these hazards, discussing their role in disaster risk reduction, early warning systems, and response planning. a) Geological Hazards and Disasters: Seismic events, volcanic activity, and tsunamis are covered here, with databases like the USGS Earthquake Database and the Smithsonian Global Volcanism Program. These resources focus on assessing and improving early warning systems for geological hazards. b) Hydrological Hazards and Disasters: From floods to droughts, hydrological events can often be worsened by climate change. This section discusses databases like the Global Disaster Alert and Coordination System (GDACS) and the Netherlands Flood Database, which help monitor flood risks and improve water management. c) Meteorological Hazards and Disasters: Extreme weather events such as hurricanes, tornadoes, and heatwaves, influenced by climate change, are becoming more frequent and severe. This chapter reviews databases like the NOAA Storm Events Database and the World Meteorological Organization’s Severe Weather Database, which assist authorities in predicting and preparing for these atmospheric phenomena. d) Biological Hazards and Disasters: Epidemics, pandemics, and invasive species cause significant health crises and environmental damage. This chapter explores databases like the WHO’s Epidemic Data Platform and the Global Invasive Species Database (GISD), which monitor biological hazards and guide public health responses. This section “Man-Made (Technological) Hazards and Disasters” examines different man-made hazards that result from human activities, such as industrial operations, transportation systems, and urban development. These risks include industrial accidents, chemical spills, nuclear incidents, and urban disasters, all of which can cause significant harm to people, property, and the environment. a) Technological Hazards and Disasters: Industrial accidents, chemical spills, and nuclear incidents are explored in this chapter. It analyzes databases like the European Major Accident Reporting System (eMARS) and the International Atomic Energy Agency’s Nuclear Events Web-based System (NEWS), which provide insights into the causes, impacts, and preventive measures for technological disasters. b) Urban Hazards and Disasters: As cities grow, the risk of urban hazards—such as building collapses, fires, and traffic accidents—rises. This chapter looks at databases like the National Fire Incident Reporting System (NFIRS) and the Global Building Collapse Incident Database, which track urban risks and help shape urban planning and safety regulations. c) Social and Economic Hazards and Disasters: Social unrest, terrorism, and economic collapses are significant man-made hazards that can destabilize societies and economies. This chapter examines databases like the Global Terrorism Database (GTD) and the International Disaster Database (EM-DAT), which track incidents of terrorism, political instability, and economic crises, helping policymakers assess risks and develop mitigation strategies. This monograph uses a detailed, systematic approach, evaluating over 50 different databases that track disaster risks. We chose each database based on how relevant it is to specific hazards, its geographical coverage, how reliable the data is, and how easy it is to access. These databases cover a range of sectors, like public health, environmental science, industrial safety, and urban planning. We looked at each one closely, evaluating its effectiveness in disaster risk reduction, its strengths and weaknesses, and how well it could fit into larger data systems. We also dug deep into the challenges of collecting disaster-related data. Many of the issues stem from inconsistent standards across regions, difficulties with data sharing, and the hurdles of using real-time data. By identifying where current data systems fall short, we’ve made practical suggestions for improvement, aiming to add to the global conversation around disaster preparedness and resilience. Challenges and Opportunities in Disaster Data Collection: One of the biggest headaches with disaster data collection is the lack of consistency in how different regions, industries, and hazards report their information. Some databases provide detailed, real-time data, while others have significant gaps, outdated info, or cover only small areas. This monograph tackles these issues by pushing for standardized data collection methods that can work universally across different sectors and regions. On the flip side, new technologies like artificial intelligence (AI), machine learning, satellite imagery, and geospatial analysis are creating exciting opportunities. These tools improve the accuracy of disaster data, make real-time collection easier, and help create predictive models that aid decision-making. AI and machine learning, for instance, are changing how we identify risk patterns, forecast hazards more accurately, and issue timely alerts. Meanwhile, satellite imaging and remote sensing are game-changers for tracking natural disasters like floods, hurricanes, and wildfires, allowing emergency teams to respond more quickly. Geospatial analysis has become crucial for disaster risk reduction too, giving governments and organizations the insights they need to invest in the right mitigation efforts. Tools like Geographic Information Systems (GIS) layer multiple data sets to create detailed risk maps, showing vulnerable areas and forecasting how future disasters might play out. This tech is now widely used in disaster management, helping to better allocate resources and plan during crises. When it comes to managing disaster risks, international collaboration is crucial, especially because disasters often don’t respect borders and can impact several countries at once. Sharing data, research, and best practices among nations strengthens global efforts to improve early warning systems, disaster response strategies, and risk mitigation measures. This monograph emphasizes the importance of initiatives like the Sendai Framework for Disaster Risk Reduction, which promotes international cooperation in data collection and sharing. Platforms like the Global Disaster Alert and Coordination System (GDACS) combine data from various countries, offering real-time alerts and comprehensive risk assessments for all kinds of disasters. International organizations like the World Meteorological Organization (WMO) and the International Atomic Energy Agency (IAEA) are key players in setting global standards for data collection and encouraging cross-border cooperation. They offer platforms where disaster data can be shared transparently, making sure that countries have the information they need to respond effectively to emergencies. This monograph explores how these global efforts help build a more resilient world, especially for vulnerable populations.The monograph also looks at how integrating regional databases into global systems can improve disaster risk reduction. For example, databases like the European Major Accident Reporting System (eMARS) and the United States Geological Survey (USGS) provide localized data that, when integrated into global networks, enhance monitoring and response efforts. By combining regional and global insights, disaster preparedness becomes more coordinated, improving cross-border collaboration. Data Gaps and Future Directions Despite progress in disaster data collection, there are still big gaps, particularly in developing countries where resources for collecting and analyzing data are limited. This lack of accurate, timely data often leads to underreporting, incomplete datasets, and less capacity to address disaster risks globally. Certain hazards, like slow-onset disasters such as droughts, or complex risks involving technological failures, are also underrepresented in global databases because of the challenges in tracking and reporting them. This monograph highlights these gaps and suggests strategies to address them. Strengthening local capacity for data collection, investing in new technologies, and building international partnerships are critical steps toward filling these gaps. Additionally, non-traditional data sources, like social media and crowd-sourced information, can offer real-time, community-driven insights that complement traditional disaster monitoring systems. Looking ahead, there’s a lot of potential for new technologies to revolutionize disaster data systems. Blockchain, for instance, could improve secure data sharing, cloud computing could boost real-time data storage and analysis, and smart city technologies could integrate disaster risk management into urban planning. The Internet of Things (IoT) adds another layer of opportunity, with sensors monitoring environmental conditions and infrastructure in real-time, allowing preventive measures to be taken before disasters strike. Collecting and using disaster-related data comes with some serious ethical responsibilities. It’s crucial to make sure that the processes we use to gather this data respect people’s privacy and dignity, especially when we’re dealing with health-related information. For example, when tracking disease outbreaks, public health surveillance might need personal data, but it’s essential that this data is handled with care to protect individual privacy. International organizations, like the Global Health Security Initiative (GHSI), have set guidelines for how to ethically collect data during health emergencies, but these standards really need to be applied across all forms of disaster monitoring. Another big ethical issue is the gap between wealthy and poorer countries when it comes to accessing disaster-related data. Wealthier nations often have advanced systems to gather and analyze data, while developing countries might not have the infrastructure or resources to do the same. This imbalance puts vulnerable populations at even greater risk. Closing this gap will require international cooperation, capacity-building efforts, and data-sharing agreements that make sure all countries have the tools they need to manage disaster risks effectively. Lastly, we also need to think about who owns the data and how it’s controlled. With more private companies getting involved in data collection—whether it’s through satellite imagery, telecoms, or AI-powered analytics—there are valid concerns about who actually owns that data and how it’s being used. Governments and international organizations need to set clear rules to ensure that disaster-related data remains a public resource, available to all, and used for the good of society as a whole.
Cvetković, V., & Renner, R. (2024). Comprehensive Databases on Natural and Man-Made (Technological) Hazards and Disasters: Mapping Risks and Challenges. Belgrade: Scientific-Professional Society for Disaster Risk Management, 1-725.

Data-driven evaluation of the Paris’ law parameters in polyethylene pipe grades — Increasing the precision of fracture mechanical lifetime estimation - Messiha, Mario; Wiener, Johannes; Arbeiter, Florian; Pinter, Gerald (Engineering Fracture Mechanics, 2024)
The Paris’ Law parameters A and m are a necessity for predicting lifetimes of structural components under static or fatigue loading that fail due to crack initiation and propagation. Conventional methods require measurements of crack growth kinetics that involve direct or indirect monitoring of physical crack extension during long-term experiments. Usually, measurement series also involve multiple specimens in order to obtain a crack growth controlled failure diagram of an investigated material under relevant load conditions. In this contribution a combination of simple numerical, statistical and analytical approaches is presented to obtain A and m without the need to measure actual crack growth. This is accomplished by reformulating the Paris’ Law to express A as a function of m. The parameter m is varied within a reasonable range to generate an analytical function for A that solves the equation of the Paris’ Law based lifetime for a single specimen. A subsequent superposition of all available specimens reveals an intersection of all A functions at the technically relevant pair of A and m values that are capable of describing the lifetime of all specimens with a minimum error. The obtained best-fitting A and m are in good agreement with literature and are able to predict the lifetime of previously published sample data based upon cyclic Cracked Round Bar test results with an average error of 3.30 ± 2.67%.
Publisher Copyright: © 2024 The Authors
Keywords: Crack growth kinetics; Cracked Round Bar (CRB) test; Fracture mechanics; Numeric algorithm; Paris’ law; Reversed engineering approach

Investigation of fracture mechanical properties of a brass alloy with microstructural variations - Klaushofer, Martin; Stoschka, Michael; Maier, Bernd; Grün, Florian (Engineering Fracture Mechanics, 2024)
This study investigates the effect of microstructural variations on the mechanical properties of CuZn35Mn2Al1Fe1-C-GS brass alloy. Specimens taken from positions with different cooling rates in a large cast component exhibit coarse-grained (approximately 5 mm) and fine-grained (approximately 1 mm) microstructures. Fine-grained samples demonstrate at least a 7% increase in Ultimate Tensile Strength (UTS) and up to a 33% higher long crack threshold ΔKth,lc. Hardness measurements are similar between microstructures. The NASGRO model and cyclic R-curve are applied to fit crack propagation data, and fractographic analysis reveals distinct fracture mechanisms. The results indicate that a fine-grained microstructure enhances tensile strength and crack resistance, providing valuable insights for the design and maintenance of heavy machinery components made from cast brass.
Publisher Copyright: © 2024 The Authors
Keywords: Cast brass; Crack growth resistance; Microstructure characterization; Tensile strength

Magnetic moments in CrN-based systems are robust - Matas, Martin; Mayrhofer, Paul Heinz; Holec, David (Surface & coatings technology, 2024)
CrN belongs to a family of transition metal nitrides used as protective coatings. It has an antiferromagnetic (AFM) orthorhombic structure below the Néel temperature (T N) and adopts paramagnetic (PM) cubic B1 above T N. In the past, the PM state was often wrongly approximated by a non-magnetic (NM) configuration. First-principles calculations suggested interesting mechanical properties of this hypothetical NM-CrN phase. In this work, we use density functional theory to probe the hypothesis that alloying or spatial confinement can cause local quenching of the Cr magnetic moments and, hence, stabilize the NM-CrN phase. Our calculations show that the magnetic moments are extremely robust and remain almost intact irrespective of which of the group III B to group VI B elements is alloyed. Similarly, superlattices with AlN and TiN in various thickness ratios do not reveal any quenching of the local magnetic moments. We therefore conclude that it is unlikely that material design would promote the NM-CrN phase, which thereby remains a purely hypothetical construct.
Publisher Copyright: © 2024 The Author(s)
Keywords: Alloys; CrN; DFT; Magnetism; Superlattices

Polyethylene pipes for distribution of gaseous hydrogen - Arbeiter, Florian; Bredács, Márton; Fechtig, Daniel; Bradler, Patrick (32. Leobener Kunststoffkolloquium - 32nd Leoben-Conference on Polymer Engineering and Science 'New Materials – New Perspectives', 2024)

CircularBioMat - Schuschnigg, Stephan; Holzer, Clemens (32nd Leoben-Conference on Polymer Engineering and Science, 2024)
In the CircularBioMat project we want to minimize the environmental footprint by substitutingpetroleum-based polymers with bio-based polymers for building services engineering. Wealso want to improve the resource efficiency and bring the materials into a circular economy.To do this, we need to develop a catalogue of requirements, taking into account the currentstandards for the construction industry. First, we evaluate the existing materials and thenwe can select bio-based or recycled polymers. These are processed using standard techno-logies such as injection moulding and extrusion, but also using Additive Manufacturing viaMaterial Extrusion (MEX). During these trials, the power supply and the amount of coolingwater will be measured to provide better data for the Life Cycle Assessment (LCA). The LCAwill then show how the different materials perform in respect to the carbon footprint.As a first step, we have selected bio-based polymers that are expected to perform well com-pared to the petroleum-based polymers. All materials are characterised at the Institute ofPolymer Processing using the High Pressure Capillary Rheometer for viscosity, DifferentialScanning Calorimetry for thermal properties and pvT measurements (specific volume as afunction of pressure (p) and temperature (T)).

Feedstock Development for Material Extrusion of Aluminium: Printability and Debinding - Schuschnigg, Stephan; Momeni, Vahid; Kukla, Christian (32. Leobener Kunststoffkolloquium - 32nd Leoben-Conference on Polymer Engineering and Science 'New Materials – New Perspectives', 2024)
Metal material extrusion (MMEX) is a fabrication method that involves the progressive deposition of metallic materials in distinct layers. This process is followed by debinding and sintering, ultimately resulting in the formation of fully dense metallic structures. The sintering temperature of aluminium (Al) alloys is relatively low, which approaches the degradation temperature of the polymers employed and needs special sintering regimes. Additionally, the binder systems utilized in this rocess must fulfil several criteria, including filament flexibility, appropriate rheological properties, and satisfactory performance during the debinding process. Consequently, the development of an effective binder system that satisfies all these requirements presents significant challenges. In this study, polypropylene (PP) and polyethylene (PE) as the backbones along with thermoplastic elastomer (TPE) as the soluble part of the binder system were used in the feedstock. Filaments with a powder loading of 55 vol.% were successfully produced from the feedstocks, and their printability was assessed. Rheological analysis was performed to evaluate the flow characteristics of the feedstocks, ensuring their suitability for the printing process. Additionally, the thermal properties,including thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC), were conducted to compare the degradation behaviour of the various binder systems.

From exhaust to extraction - Funari, Valerio; Dinelli, Enrico; Gomes, H. I.; Mantovani, L.; Meisel, Thomas C.; Siciliano, A.; Vassura, I.; Vigliotti, Luigi; Vitale, L. (Journal of environmental chemical engineering, 2024)
Spent Automotive Catalytic Converters (SACC) are comprised of a support (a honeycomb ceramic structure) coated with a catalytic layer, where Platinum Group Elements (PGE), especially Pt and Pd, facilitate oxidation and reduction reactions to reduce hazardous emissions from car engines. This study provided information about various measurement procedures and principles for characterising SACC, revealing that SACC can release Potentially Toxic Elements (PTE) under environmental conditions. The SACC samples used primarily contain cordierite and moissanite, likely distinguishable upon visual inspection of waste piles. Unlike geological samples, the SACCs samples, considered as a homogeneous matrix, exhibit major elements such as Al, Si, Mg, and Ba, with minor elements including P, Na, Ca, Fe, Ti, Ce, and Zr, posing challenges for geoanalysts and environmental managers. Sequential extraction demonstrated high concentrations of PGE in the residual phase, especially Pt, Pd, and Rh. All other fractions, oxidisable, reducible and exchangeable, showed significant analytical recoveries of PTE such as Zn, Cu, and other trace elements. Watering bulk samples resulted in exceeded reference thresholds, with high Cd, Ni, and Zn, identifying SACC as a potentially hazardous materials. Toxicity tests on three aquatic species (A. fischeri, R. subcapitata, and D. magna) indicated both acute and chronic effects, further highlighting the need for proper waste management. The characterisation approach suggested here can help define the most appropriate SACC treatment demonstrating economic profit and ecological benefits.
Publisher Copyright: © 2024 The Authors
Keywords: Circular economy; Environmental impact assessment; Leaching test; Platinum group elements (PGE); Sequential extraction

Light-Driven, Reversible Spatiotemporal Control of Dynamic Covalent Polymers - Reisinger, David; Sietmann, Alexander; Das, Ankita; Plutzar, Sarah; Korotkov, Roman; Rossegger, Elisabeth; Walluch, Matthias; Holler-Stangl, Stefan; Hofer, Thomas S.; Dielmann, Fabian; Glorius, Frank; Schlögl, Sandra (Advanced materials, 2024)
Dynamic covalent polymer networks exhibit a cross-linked structure like conventional thermosets and elastomers, although their topology can be reorganized through externally triggered bond exchange reactions. This characteristic enables a unique combination of repairability, recyclability and dimensional stability, crucial for a sustainable industrial economy. Herein the application of a photoswitchable nitrogen superbase is reported for the spatially resolved and reversible control over dynamic bond exchange within a thiol-ene photopolymer. By the exposure to UV or visible light, the associative exchange between thioester links and thiol groups is successfully gained control over, and thereby the macroscopic mechanical material properties, in a locally controlled manner. Consequently, the resulting reorganization of the global network topology enables to utilize this material for previously unrealizable advanced applications such as spatially resolved, reversible reshaping as well as micro-imprinting over multiple steps. Finally, the presented concept contributes fundamentally to the evolution of dynamic polymers and provides universal applicability in covalent adaptable networks relying on a base-catalyzed exchange mechanism.
Publisher Copyright: © 2024 Wiley-VCH GmbH.
Keywords: dynamic covalent polymers; multi-step micro-imprinting; multi-step reshaping; photopolymerization; photoswitchable base catalysts; reversible photoactivation

Promoting sustainable practices through education - Murphy, Mariaelena; Obenaus-Emler, Robert (6th International Conference on Industry 4.0 & Smart Manufacturing, 2024)
This paper explores the development of a Living Lab, Sustainable Agriculture and Forestry Explained (SAFE), initiative led by the Resources Innovation Center at the Montanuniversität Leoben, designed to strengthen the university's role in the EU Missions of adaptation to climate change and healthy soil. The SAFE initiative employs the Living Lab concept to create a dynamic, real-life setting where stakeholders from academia, industry, and the community collaborate to explore develop and implement sustainable agricultural and forestry practices. The paper details the strategic implementation, educational outreach, and collaborative efforts aimed at fostering these practices. It emphasises the importance of education in building a competitive Europe, linking the initiative to broader EU policies such as Horizon Europe and the European Green Deal. By engaging various target groups through participation and research and educational activities, the SAFE initiative aims to increase societal awareness and acceptance of sustainable technologies, ultimately contributing to the EU’s goals of climate resilience and environmental sustainability.
Keywords: Living Lab; research & development; Social License to Operate

Shaping the future of mining - Murphy, Mariaelena; Bertignoll, Hanno (6th International Conference on Industry 4.0 & Smart Manufacturing, 2024)
The escalating global demand for minerals and metals, driven by rapid urbanisation and the transition to green and digital technologies, poses significant challenges for sustainable development. As the world population is projected to reach 9.7 billion by 2050, with nearly 70% residing in urban areas, the need for critical minerals such as lithium, cobalt, nickel, and rare earth elements is intensifying. These materials are essential for renewable energy technologies and electric vehicles, making them crucial for achieving global climate goals. However, the reliance on extractive activities, particularly in middle to low-income economies, exacerbates social and environmental issues, including livelihood disruptions, social conflicts, human rights violations, and occupational hazards.In response to these challenges, the EIT-funded project 'Professional Social Licence to Operate (PRO SLO)' has been launched, bringing together experts from industry, research, and academia across Europe. The project aims to equip current and future leaders in the mining sector with the skills necessary to effectively manage Social Licence to Operate (SLO) processes. Through a comprehensive PhD Summer/Winter school programme, combining advanced teaching methods such as case studies, simulations, and workshops, PRO SLO addresses critical ethical, social, and environmental concerns. The initiative aligns with European Union policies on responsible mining, fostering sustainable practices to enhance ethical standards in the industry.
Keywords: Mining; Education; Social License to Operate

A new ISO standard for the experimental characterization of in-plane permeability of fibrous reinforcements - May, David; Advani, S. G.; Duhovic, M.; Endruweit, Andreas; Fauster, Ewald; George, Andrew; Liotier, P. J.; Lira, Cristian; Lomov, S. V.; Pucci, M. F.; Schmeer, S.; Abliz, D.; et al. (Composites Part A: Applied Science and Manufacturing, 2024)
During Liquid Composite Molding, a fibrous reinforcement is impregnated with liquid resin. Process design requires knowledge of the reinforcement permeability for fluid flow, but until recently, there has been no standard available for its measurement. In 2023, following decades of benchmarking activities and a standardization project, an ISO standard for the experimental characterization of in-plane permeability of fibrous reinforcements for liquid composite molding was finally published. It focuses on the experimental characterization of unsaturated in-plane permeability and specifies the requirements for test equipment, methods and data analysis. Given the deficiency of standardized procedures within the composites industry, this paper intends to provide an example of the steps towards standardization and summarizes lessons learned. It illustrates the research milestones that led to the establishment of the standard, promotes the standard by detailing its general content and notable features and finally gives explanations and reasoning behind the developed guidelines.
Keywords: Fabrics/textiles; Permeability; Process Modeling; Resin transfer molding; Resin flow

Effect of local loading on microstructure and enhanced mechanical property of large complex castings prepared by Al–Si–Fe–Mn–Mg–Cu alloy during squeeze casting - Meng, Shuancheng; Gao, Minqiang; Liu, Yan; Yang, Li; Ma, Huan; LI, Jiehua; Wang, Jianjun; Guan, Renguo (Journal of Materials Science & Technology, 2024)
Flywheel shells with a complex structure and large wall-thickness difference, as key components in heavy trucks, serve to connect the engine and transmission. Formability and mechanical performance control of such components should be taken into consideration. In this work, an Al–Si–Fe–Mn–Mg–Cu alloy was used to manufacture the flywheel shell via squeeze casting. The role of local loading on microstructure and mechanical property at thick-walled positions was investigated. Furthermore, the effect of the squeeze casting specific pressure and heat treatment on the microstructure and mechanical property of the Al–Si–Fe–Mn–Mg–Cu alloy flywheel shells was also analyzed. The results showed that at the thick-walled positions, local loading not only helped eliminate the solidification defects, but also refined the microstructure including α-Al grains and secondary dendrite arm spacing. With increasing the squeeze casting specific pressure from 24 MPa to 32 MPa, microstructure refinement and mechanical property enhancement of squeeze casting flywheel shells were obtained. After T6 heat treatment, the yield strength and ultimate tensile strength of flywheel shells were further increased to 261.8 and 318.4 MPa, respectively, owing to the formation of spherical eutectic Si phases and nano-sized β'', Q and S precipitates.
Publisher Copyright: © 2024
Keywords: Al–Si–Fe–Mn–Mg–Cu alloy; Local loading; Refinement; Solidification defects; Squeeze casting; Strengthening mechanism

A phase-field modeling study for reaction instability and localized fluid flow in carbonate rocks - Furui, Kenji; Yoshioka, Keita (Geoenergy science and engineering, 2024)
As acidic fluids flow and dissolve minerals in carbonate formations, the reaction may localize into a dendritic pattern under certain conditions known as wormhole. Wormhole is considered to be triggered by pore-scale heterogeneity in the rock that promotes preferential flow paths. Therefore, in macroscale (Darcy scale) simulation, numerical models usually need to prescribe a certain degree of macroscopic heterogeneous permeability to promote localized dissolution (wormhole). However, experimental studies have shown that wormholes form in synthetic plasters without apparent heterogeneity, implying that macroscopic heterogeneity is not a necessary prerequisite for wormhole formation and prescribed heterogeneity may impose unnecessary biases. Here, we applied a macroscale wormhole model based on a phase-field approach to demonstrate that wormhole can form in macroscopically homogeneous media as long as the inlet velocity meets the infiltration-reaction instability condition obtained from perturbation analysis. Furthermore, we simulated wormhole growth behaviors in homogeneous and heterogeneous permeability fields with the standard variance values of 0.5, 1.0 and 2.0. The simulation results showed that the normalized injectivity decreases from 3.90 to 3.15 when the standard variance changed from 0.5 to 2.0 indicating that heterogeneity may actually suppress the wormhole growth because an increasing amount of acid infiltrates into the branched wormholes. These findings suggest that permeability heterogeneities should not be treated as a trigger for wormholes in the macroscale numerical simulation. Instead, they should be regarded as parameters that influence the nucleation and growth of wormholes because the permeability field has significant effects on post-acid wormhole geometry and resultant well productivity and injectivity.

Enhanced hydrogen gas barrier properties in highly filled acrylonitrile butadiene rubber with high aspect ratio filler - Clute, Clara; Hafner, Thomas; Balasooriya, Winoj; Kaiser, Andreas; Pinter, Gerald; Schlögl, Sandra (International Journal of Hydrogen Energy, 2024)
Acrylonitrile butadiene rubber (NBR) compounds with a hybrid filler system, containing carbon black (CB) and a surface functionalized talc filler with a platelet-like structure, were investigated. The effect of the loading of the high aspect ratio filler (0-80 phr) on mechanical, thermomechanical, morphological, and hydrogen gas barrier properties were evaluated. With increasing amount of the talc filler, the NBR grades exhibit an increase in modulus, whereas the glass transition temperature remains unaffected. The platelet-shaped fillers show a good distribution and orientation in the rubber matrix and hence create obstacles for permeating gas molecules. The coefficients related to hydrogen transport properties in the material, solubility, diffusivity, and permeability, all exhibit a decrease with increasing loading of the high aspect ratio filler, leading to overall enhanced gas barrier properties of the rubber materials.
Publisher Copyright: © 2024 Hydrogen Energy Publications LLC
Keywords: 2D filler; Acrylonitrile butadiene rubber; Gas barrier properties; Hydrogen permeation

Erosion Behavior of Coarse-Grained Alumina in Corrosive Melts: Experimental and Computational Studies with CAS and CASM Slags - Guarco, Jeronimo; Vollmann, Sandra; Harmuth, Harald; Burhanuddin, Burhanuddin (63rd Conference of Metallurgists, 2024)

KI-gestützte Verwertungs- und Aufbereitungsstrategien von Aushubmaterialien bei Großprojekten des Tiefbaus - Hauzinger, Elisabeth; Schneider, Daniel; Galler, Robert (2024)
Großprojekte prägen das Bild der europäischen Tiefbauindustrie. Einerseitswerden die TEN-T (Trans European Transport Network) Korridore für den Gütertransport aufSchiene ausgebaut, andererseits sind mit dem Future Circular Collider (FCC) und dem EinsteinTeleskop unterirdische Forschungsinfrastrukturen mit jeweils knapp 100 Tunnelkilometern geplant. Dabei fallen jeweils mehrere Millionen m3 an Ausbruchsmaterial an, die diese Projekte voreine große Herausforderung hinsichtlich Nachhaltigkeit als auch Materialbewirtschaftung stellen.Dieses Material kann sowohl aus Hartgesteins- als auch Lockergesteinsvortrieben mit unterschiedlichem Grad an anthropogener Verschmutzung je nach Vortriebsmethode stammen. Füreinige dieser Lithologien gibt es laut aktuellem Stand der Forschung noch keine Verwendungsmöglichkeit. Um aber möglichst viel des Materials wiederverwenden und so Deponieflächenschonen zu können, wird an einer modularen KI-gestützten Real-Time Analyse- als auch Aufbereitungseinheit gearbeitet, um das Material je nach Zusammensetzung einer passenden Verwendungsmöglichkeit zukommen zu lassen, ohne dabei flächenintensive Zwischendeponien aufbauen zu müssen. Langfristiges Ziel ist die Entwicklung einer allgemein gültigen EU-Richtliniezum Ende des Abfallcharakters von Aushubmaterialien, um Europas Kreislaufwirtschaft zu stärken und die Ressourcenverknappung zu entschärfen.
Keywords: Tunnelausbruchmaterial; Sensorgestützte Charakterisierung; KI; Verwendung; Deponierung

Consistent crystal orientation of core and rim pyrites indicates an epitaxial growth of rim in Carlin-type gold deposits - Xiao, Jingdan; Xie, Zhuojun; Xia, Yong; Gopon, Phillip; Tan, Qinping (Geoscience Frontiers, 2024)
The gold-bearing arsenian pyrite in Carlin-type gold deposits typically grows around the gold/arsenic-poor pyrite core, forming core–rim textured pyrite. However, the causes of rim pyrite precipitation around the early-formed core pyrite and the growth mechanisms of the rim pyrite remain unclear. Here, we combined scanning electron microscopy, electron probe micro-analysis, and nanoscale secondary ion mass spectrometry to investigate the textural and chemical characteristics of core–rim textured pyrite from the giant Shuiyindong and Lannigou gold deposits. Furthermore, we used electron backscattered diffraction and transmission electron microscopy to characterize their crystallographic structure. The results indicated that core–rim textured pyrite is the dominant pyrite type in the ore. This type of pyrite is characterized by the sharp core–rim interfaces, euhedral-subhedral morphology, and oscillating zoning. The gold/arsenic-rich rim and gold/arsenic-poor core formed during the main-ore and pre-ore stages, respectively. Crystallographically, the rim showed that a crystallographic orientation is similar to that of the core along the (0 1 0) crystal facet, indicating that the core pyrite serves as a template for the epitaxial growth of rim pyrite. Textural and chemical features indicate that the epitaxy occurs in the process of direct precipitation of main-ore pyrite over the pre-ore pyrite. As Carlin ore fluids dissolve the iron-bearing carbonates, iron concentrations in the fluids increase, thereby creating a supersaturation environment suitable for the nucleation of main-ore pyrite. Because the minimal lattice misfit would minimize the surface free energy and the (0 1 0) facet of pyrite has a lower surface energy than other facets, the nucleated pyrite would readily grow along the (0 1 0) facet of preexisting pyrite via epitaxy. Our findings highlight that the widespread preexisting pyrite facilitates late-stage pyrite precipitation. For Carlin-type gold deposits, the pre-ore pyrite is essential owing to its promoting the precipitation of gold-bearing pyrite.

Impact of Surface Microstructure and Properties of Aluminum Electrodes on the Plating/Stripping Behavior of Aluminum-Based Batteries Using Imidazolium-Based Electrolyte - Razaz, Ghadir; Weißensteiner, Irmgard; Örtegren, Jonas; Trink, Bernhard; Pogatscher, Stefan; Arshadi Rastabi, Shahrzad (ACS Applied Materials & Interfaces, 2024)
The 99.99% Al used for negative Al electrodes in aluminum-based battery studies is expensive. This is primarily due to the complex challenges associated with fabricating 99.99% Al, particularly the removal of Fe impurities from Al melts. Despite the importance of this issue for the future commercialization of Al-based batteries, it has been largely overlooked. This work accordingly studied the plating/stripping behavior of Al containing 1 wt % iron (Al 1% Fe) as an alternative electrode using conventional ([EMIm]Cl and AlCl3) electrolyte. Simultaneously, the impact of the surface microstructure of Al 1% Fe on the plating/stripping behavior was examined. The results indicate that the difference in the plating/stripping cycling of Al 1% Fe alloys and 99.99% Al is negligible. Thus, Al 1% Fe negative electrodes could serve as an efficient and commercially viable alternative to 99.99% Al for plating/stripping in Al-based batteries. This is an essential finding because facile and commercial fabrication of Al 1% Fe electrodes is absolutely feasible. The results are further discussed in terms of the impact of the Al surface microstructure (i.e., grain size, defect density, grain boundary distribution, crystal orientation, and intermetallic phases) on plating/stripping behavior. Moreover, this study provides insights into how the interphase layer formed on Al electrodes influences plating/stripping behavior.
Publisher Copyright: © 2024 The Authors. Published by American Chemical Society.
Keywords: Al 1 percent Fe; aluminum-based batteries (AIBs); interphase layer; plating/stripping; surface microstructure

Advancements in Intelligent Rock Bolt Measurement: A General Approach - Varelija, Michel; Vailhe, Pauline; Hartlieb, Philipp (The 53rd Geomechanics Colloquium, 2024)

Development of sustainable air electrode materials for solid oxide cells - Aksoy, Mehmet; Egger, Andreas; Sitte, Werner; Bucher, Edith (19th International A3PS Conference, 2024)

The development of novel materials to improve CO2 converting reactions - Schrenk, Florian; Berger, Tobias; Cotter, Thomas; Drexler, Hedda; Lindenthal, Lorenz; Michalke, Jessica; Rollenitz, Jonathan; Ruh, Thomas; Rameshan, Christoph (19th International A3PS Conference, 2024)

Analyse und Optimierung von österreichischem Polystyrol-Haushaltsabfall für die Wiederverwendung in Joghurtbecher-Lebensmittelverpackungen - Krempl, Nina; Frühwirth, Matthias; Zidar, David; Shahroodi, Zahra; Holzer, Clemens; Pinter, Elisabeth; Archodoulaki, Maria Vasiliki; Bichler, Lorenz; Jahn, Elisabeth; Gabriel, Viktoria Helene; Aschermayer, Florian (Recy & Depotech 2024, 2024)

I-STEP – A Case Study: Machine Learning powered Condition Monitoring of a Linear Motion Industrial Vibrating Screen - Krukenfellner, Philip; Flachberger, Helmut (Recy & Depotech 2024, 2024)
Vibrating Screens, crucial in mineral and waste processing industries, usually lack adequate condition monitoring to assess condition states or predict machine errors. Addressing this issue, IFE Aufbereitungstechnik GmbH and its partners are developing "i-STEP," a digitalization solution potentially integrating any market-available sensor for a customizable, plant-wide monitoring platform. Thus far, a vibration sensor, "SES" has been developed to specifically measure oscillation patterns of vibrating screens, which is the main focus of this research.
Keywords: Schwingsiebe; Schwingungsüberwachung; Zustandsüberwachung; Machine Learning; Vibration Screens; Vibration monitoring; Condition monitoring; Machine learning

Improving contact damage resistance of spinel translucent ceramics through a multi-layer design - Najafzadehkhoee, Aliasghar; Jabr, Abdullah; Talimian, Ali; Papsik, Roman; Drdlik, Daniel; Maca, Karel; Galusek, Dušan; Bermejo, Raul (Journal of the European Ceramic Society, 2024)
The brittle response of transparent spinel ceramics to contact damage is limiting their application as an alternative to glasses and single crystals. In this work, we explore a strategy to enhance the contact damage resistance of spinel ceramics by embedding alumina layers in a multi-layer architecture. Crack initiation upon Hertzian indentation was investigated in MgAl2O4 – Al2O3 laminates and compared to their corresponding monoliths. Contact stresses during loading were analyzed using finite element simulations by considering the elastic properties of the layers and contact non-linearities. Results were analyzed using Weibull statistics. It was found that the effect of in-plane residual stresses on crack formation in the laminate depends on the disposition of the compressive spinel layers, either at the surface or embedded in the structure. Embedding alumina between spinel layers increased the load-bearing capability before crack initiation by ∼70 % compared to spinel, offering a promising approach to enhance contact damage resistance.
Publisher Copyright: © 2024 The Authors
Keywords: Contact damage; Hertzian indentation; Multi-layers; Residual stresses; Transparent

Towards closed material cycles in lithium-ion batteries and PV systems: a sustainable resource approach - Gerold, Eva; Ebenauer, Klaus; Anbauer, Andreas; Shaveko, Sergei; Antrekowitsch, Helmut (Recy & Depotech 2024, 2024)

An optimization strategy for customizable global elastic deformation of unit cell-based metamaterials with variable material section discretization - Thalhamer, Andreas; Fleisch, Mathias; Schuecker, Clara; Fuchs, Peter Filipp; Schlögl, Sandra; Berer, Michael (Advances in Engineering Software, 2024)
Metamaterials with their distinctive unit cell-based periodic architecture feature a wide range of possible properties with unusual characteristics and a high potential for optimization. Due to their complex interaction between unit cell geometry and material properties, as well as their inherent multi-scale nature, suitable optimization strategies need to be developed for metamaterials. One potential approach is to optimize the distribution of unit cells within a part to achieve a predefined deformation response. However, a significant challenge lies in determining the appropriate number and distribution of areas with varying properties (material sections) to facilitate an efficient optimization. In this study, a variable material section discretization scheme is presented, which is aimed at automatically updating the discretization to enhance the efficiency of metamaterial optimizations. This scheme is implemented as an extension to a previously proposed Finite Element simulation-based optimization framework for unit cell-based metamaterials. The framework includes a numerical homogenization method and interpolation scheme for efficiently correlating unit cell parameters with homogenized material properties, coupled with a black-box optimization method. In the present study, the previously proposed framework was extended to incorporate a scheme for monitoring and adjusting the material section discretization during the optimization process. To assess the effectiveness of the implemented routine, it was tested in conjunction with a genetic algorithm for optimizing the parameter distribution of a 2D tri-anti-chiral metamaterial to match a predefined lateral deformation under load.
Publisher Copyright: © 2024 The Author(s)
Keywords: Finite Element Method; Genetic Algorithm; Homogenization; Optimization; Simulation

Synergistic Interactions in a Heterobimetallic Ce(III)–Ni(II) Diimine Complex: Enhancing the Electrocatalytic Efficiency for CO2 Reduction - Yari, Farzaneh; Aljabour, Abdalaziz; Awada, Houssein; Michalke, Jessica; Kumari, Nidhi; Coskun, Halime; Roy, Soumyajit; Krisch, Dominik; Schoefberger, Wolfgang (ACS Applied Energy Materials, 2024)
In this study, we propose a practical approach for producing a heterobimetallic Ni(II)–Ce(III) diimine complex from an extended salen-type ligand (H2L) to serve as an electrocatalyst for CO2 reduction and demonstrate an outstanding overall efficiency of 99.6% of the cerium–nickel complex and integrate it into applicable cell assemblies. We optimize not only the catalyst, but the operational conditions enabling successful CO2 electrolysis over extended periods at different current densities. A comparison of electrochemical behavior in H-cell and zero-gap cell electrolyzers suggests potential applications for industrial scale-up. In the H-cell electrolyzer configuration, the most elevated efficiency in CO production was achieved with a selectivity of 56.96% at −1.01 V vs RHE, while HCOO– formation exhibited a selectivity of 32.24% at −1.11 V vs RHE. The highest TON was determined to be 14657.0 for CO formation, followed by HCOO– with a TON of 927.8 at −1.11 V vs RHE. In the zero-gap electrolyzer configuration, the most efficient setup toward CO production was identified at a current density (CD) of 75 mA cm–2, a flow rate of 10 mL min–1, operating at 60 °C and utilizing a low KOH concentration of 0.1 M to yield a maximum faradaic efficiency (FECO) of 82.1% during 24 h of stable electrocatalysis.

High-pressure-torsion-induced segregation, precipitation and grain refinement of Al-(Si, Mg and Cu) binary alloys - Feng, Man; Wu, Qinli; Xue, Jing; Luo, Zhenjiao; Wang, Zhiping; An, Xianghai; Liao, Xiaozhou; LI, Jiehua; Jin, Shenbao; Sha, Gang (JOURNAL OF MATERIALS SCIENCE & TECHNOLOGY, 2024)
To uncover the effects of segregation and precipitation on grain refinement of metals under severe plastic deformation, high-pressure-torsion (HPT) processing is performed on three binary Al-(Si, Mg, and Cu) alloys with different stability and segregation characteristics. Atom probe tomography analysis reveals that HPT processing induces significant decomposition of Al-1 at% Si and Al-1 at% Cu alloys with coarse Si particles and fine Al 2Cu (θ) precipitates formed, but no decomposition of Al-1 at% Mg alloy, with dislocations segregated with Si, Cu, and Mg, and grain boundaries (GBs) only segregated with Cu and Mg. The GB segregation of Cu is stronger than that of Mg and Si, with Cu excess in the range of 1.5–7.0 atoms/nm 2, Mg excess in the range of 0–4.0 atoms/nm 2, but no Si excess. Interestingly, some GBs without Mg segregation develop a Mg-depletion zone along a single side. All evidences demonstrate that GB segregation and precipitation are responsible for HPT-induced grain refinement of Al-1Mg and Al-1Cu alloys but coarsening of the Al-1Si alloy. Engineering solute distribution is of significance in controlling the ultrafine grain of the Al alloys.
Publisher Copyright: © 2024
Keywords: Al alloys; Grain refinement; High pressure torsion; Precipitation; Segregation

A Comparative Analysis of Efficiency and Losses in a 5 kW Hybrid and Full-SiC Converter, for PV Applications in Austria - Chakraborty, Rupak; Eskilson, Troy; Biswas, Sumanta; Makoschitz, Markus (Energies, 2024)
Wide Bandgap (WBG) devices like SiC-MOSFETs have become quite popular in recent times due to their superior switching characteristics, high current carrying capability and temperature stability. They are being adopted for many different applications and for a wide range of power levels. For the case of PV applications, manufacturers are considering moving to SiC-based topologies due to higher converter efficiencies and improved power density. However, the present industry largely uses hybrid approaches (IGBT + SiC-diode) to optimize system cost. The aim of this paper is to present a fair comparison of an industry-grade hybrid converter with another similar counterpart where only the Si device has been replaced with the SiC device. The effects of such a direct replacement on the efficiency and losses of the converter are studied under various power ratings. Both converters consist of two stages—a boost converter and a three-phase three-level DC to AC converter. Simulation and experimental results comprehensively indicate a higher efficiency (improvements of up to 8 percent points) for the full-SiC converter, and this is more prominent at low input voltages, where the boost converter is active. However, the gains in efficiency are moderate for high input voltages (1 percent point at nominal voltage), where the boost converter is bypassed, and the losses are almost entirely attributed to the inverter. When set in the backdrop of the Austrian inverter market, the use of SiC devices in PV inverters has the potential for an estimated savings of 37.5 GWh/year in terms of loss reduction.

Understanding seismic hazard resilience in Montenegro: A qualitative analysis of community preparedness and response capabilities - Cvetković, Vladimir; Grozdanić, Goran; Milanović, Miško; Marković, Slobodan; Lukić, Tin (Open Geosciences, 2024)
Enhancing resilience against seismic hazards in earthquake-prone regions is essential for reducing the devastating impacts of disasters. Seismic resilience refers to a community’s ability to withstand and recover from earthquake impacts, while preparedness gaps are the areas where current measures are insufficient to effectively respond to or mitigate earthquake damage. This study focuses on Montenegro – a region with frequent seismic activity – aiming to assess resilience levels, identify critical gaps in preparedness, and evaluate the effectiveness of existing response strategies. Using qualitative methods, including semi-structured interviews, the research gathered insights from residents of Montenegro’s most vulnerable cities: Nikšić, Podgorica, Bar, Kotor, Cetinje, Budva, Herceg Novi, and Berane. Participants, chosen for their first-hand experience with significant earthquake impacts, provided valuable perspectives on various aspects of resilience, from local government response to individual preparedness. This research revealed significant disparities in resilience across communities: for instance, approximately 62.5% of the respondents highlighted inadequate education as a barrier to effective earthquake preparedness, and only 37.5% reported awareness of basic earthquake response procedures. Furthermore, while some communities, such as urban areas with accessible services, reported higher preparedness levels, rural areas showed deficiencies, with 50% of the respondents from these areas identifying a lack of organized drills and limited public awareness initiatives. These findings underscore the urgent need for community-specific preparedness programs and enhancements in both structural resilience and public education to bolster community readiness effectively. Also, findings highlight the need for customized preparedness programs tailored to specific community needs, alongside improvements in structural safety measures and educational outreach. The study underscores the importance of a comprehensive approach involving detailed risk assessments, community-focused preparedness training, and stronger public awareness initiatives. Furthermore, the study calls for enhanced local government capabilities to sustain proactive response measures, including rapid mobilization of emergency resources and regular disaster simulations, to build long-term resilience across communities.

Geochemical aspects on formation processes of vein-hosted pyrite in the Carboniferous-Permian rocks of the Karavanke/Karawanken tunnel, northwestern Slovenia - Soster, Ales; Bertrandsson Erlandsson, Viktor; Ravnjak, Mihael (Austrian journal of earth sciences, 2024)
The Carboniferous-Permian organic-rich shale in the Karavanke/Karawanken tunnel exhibits extensive pyrite mineralization in the form of veins and impregnations. Significant thermal alteration, induced by the overlying Mesozoic rock sequences, led to the decomposition of organic matter into methane, which subsequently acted as a sulfate-reducing agent. The primary source of sulfate were the evaporitic layers hosted within the Paleozoic strata. Reduced sulfur species necessary for pyrite formation were produced through methane-mediated thermochemical sulfate reduction, catalyzed by specific cations (Ni2+, Fe2+) and clay minerals (montmorillonite). The mineralizing fluids originated from the expulsion of interstitial water and possibly from dehydration reactions related to the gypsum-to-anhydrite phase transition. The geochemical data indicate that the metals originated from the surrounding sedimentary rocks. These mineralizing fluids were characterized by low temperatures (< 300–350 °C), moderate reducing conditions, and low chlorinity. The low permeability of Carboniferous-Permian rocks, combined with the low trace element content of the investigated pyrite, mitigates the potential risk of environmental pollution.

Product formulas for multiple stochastic integrals associated with Lévy processes - Di Tella, Paolo; Geiss, Christel; Steinicke, Alexander (Collectanea mathematica, 2024)
In the present paper, we obtain an explicit product formula for products of multiple integrals w.r.t. a random measure associated with a Lévy process. As a building block, we use a representation formula for products of martingales from a compensated-covariation stable family. This enables us to consider Lévy processes with both jump and Gaussian part. It is well known that for multiple integrals w.r.t. the Brownian motion such product formulas exist without further integrability conditions on the kernels. However, if a jump part is present, this is, in general, false. Therefore, we provide here sufficient conditions on the kernels which allow us to establish product formulas. As an application, we obtain explicit expressions for the expectation of products of iterated integrals, as well as for the moments and the cumulants for stochastic integrals w.r.t. the random measure. Based on these expressions, we show a central limit theorem for the long time behaviour of a class of stochastic integrals. Finally, we provide methods to calculate the number of summands in the product formula.
Publisher Copyright: © The Author(s) 2024.
Keywords: 60F05; 60G44; 60G51; 60H05; Central limit theorem; Lévy processes; Moment formulas; Product formulas for multiple stochastic integrals

Assessing the fracture toughness in Tungsten-based nanocomposites - Schmuck, Klemens Silvester; Burtscher, Michael; Alfreider, Markus; Kiener, Daniel (Materials and Design, 2024)
Nanocrystalline tungsten-copper composites can favorably combine the outstanding material properties of both elements. This work investigates tungsten-copper composites fabricated from elemental powders with 80 wt.% tungsten and either copper or α-brass containing 20 wt.% zinc, respectively. Moreover, high-pressure torsion is used to compact the powders, strengthen the resulting composite by grain refinement, and tailor the grain-size in the nanocrystalline regime by varying the deformation temperature between RT, 400°C and 550°C, resulting in grain-sizes of 9 nm 14 nm and 28 nm, respectively. Hardness measurements revealed a transition from normal to inverse Hall-Petch behavior for grain-sizes below 11 nm. To examine the fracture properties, micro-cantilever bending beams with a cross-section of 10x10 µm2 were fabricated. Evaluation of these experiments indicated a fracture toughness of 3 MPam. The slight decrease of fracture toughness between a grain-size of 9 nm to 14 nm indicates a reduction of the grain boundary cohesion strength. The grain-size increase to 28 nm reversed the trend in fracture toughness and raised it to 3.4 MPam, which points to activating additional deformation mechanisms, such as dislocation-accumulation and twinning. Additionally, alloying with zinc raised the composites strength and retained the composites fracture toughness, benefiting the damage tolerance.
Publisher Copyright: © 2024 The Author(s)
Keywords: High-pressure torsion; Micro-cantilever bending; Nanocrystalline microstructure; Tungsten-copper; Tungsten-α-brass

Environmental Social Governance (ESG) ... Distraction or Revolution? - Posch, Wolfgang; Feichtinger, Gerald; Kircher, Volkmar (1st SMI Online-Forum 2024, 2024)
Book-of-Abstracts with all abstracts for the 1st SMI Online-Forum 2024.
Conference code: 1
Keywords: ESG score; Finance; Risk assessment; Life Cycle Assessment (LCA); Monetization; NPV; Mining; SDG; Digital Produt Passport (DPP); Token Economy; Blockchain

Monetization of LCA-based Impacts - Feichtinger, Gerald (2024)
Keywords: LCA; Monetization; Total External Environmental Costs

ESG and Mine Plans - Haindl, Angelika (1st SMI Online-Forum 2024, 2024)
Conference code: 1
Keywords: ESG; Mine Planning; CBA

Evaluation of the Hydrogen Value Chain: Integrating Production with Distribution Networks - Fink, Justin; Azizmohammadi, Siroos; Ott, Holger; Kulhanek, Gerald (2024)
The transition to a low-carbon future necessitates the exploration of alternative energy carriers, and hydrogen has emerged as a promising solution. However, establishing a fully functional hydrogen economy is a complex undertaking full of challenges. One significant obstacle to achieving the European Union’s sustainability goals is the limited infrastructure, particularly regarding storage capacity and integration into the anticipated hydrogen network. Merely relying on underground storage is insufficient – instead, the development of hydrogen transmission and distribution networks is crucial for effective transportation and utilization of hydrogen. Thermal turbomachinery, including compressors and turbines, is a key component in hydrogen distribution networks. These components are responsible for compressing hydrogen for efficient transmission and play a critical role in maintaining the pressure and flow of hydrogen within the network, ensuring its safe and reliable transport. Therefore, investigating the performance and efficiency of integrated systems that combine underground hydrogen storage with thermal turbomachinery is essential. This study aims to address the technological challenge of designing and optimizing hydrogen distribution networks to enhance efficiency and sustainability. The research examines the integration of underground hydrogen storage and thermal turbomachinery within hydrogen networks to gain valuable insights into system performance.

Supply security beyond mines and scrap recycling - Steinlechner, Stefan; Witt, Kerrin (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences, 2024)
In the context of the European Critical Raw Materials Act, this work attempts to demonstrate the potential of residual material flows from non-ferrous metallurgy and their possible contribution to the supply security of metals by locally available new secondary resources, assuming technically and economically viable processing. Based on the aluminium, zinc, copper and lead industries, the resulting waste streams are discussed and, in particular, the complex process consisting of physical, chemical and metallurgical steps is described. Their diversity, be it slags, dusts or even sludges, has a wide variety of morphologies and compositions due to the process of generation. In the past, many concepts for reprocessing were investigated, but the goal was usually only the recovery of one target element or to avoid landfilling by using it, for example, as a building material, whereby the metals contained are completely lost. If the target is the extraction of valuables, the required interdisciplinary process development must be based on an in-depth characterization to understand the behaviour of metals and trace elements in possible extraction steps and also to develop suitable strategies for influencing the behaviour of target elements with the aim of extraction. This starts with an in-depth comprehension of the formation process, which is the subject of this article and has a direct influence on the composition and morphology of the materials, thus forming the basis for understanding the behaviour in potential recycling processes. Furthermore, typical compositions of the residual material streams, sources and, if available, quantities are shown and, in summary, an attempt is made to evaluate the materials in a SWOT analysis and to address the challenges in developing extraction steps for processing. While mine tailings are mostly found outside of Europe, the potential of the residual materials from metallurgy is local due to the processing of the concentrates in Europe. This leads to several potential advantages in a possible reprocessing, such as no or shorter transport routes, which is linked to lower quantity of emissions, defined volume and known composition, no geopolitical risk, conservation of primary resources, and increasing Europe’s sustainability through a more comprehensive use of the raw materials.
Publisher Copyright: © 2024 The Author(s).
Keywords: extractive metallurgy; industrial residues; metallurgical by-products; scarce metals

Sustainable extraction and recycling of non-ferrous metals - Gerold, Eva; Luznik, Lea Theres; Samberger, Sebastian; Antrekowitsch, Helmut (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences, 2024)
This review article provides a comprehensive examination of sustainable extraction and recycling methods for non-ferrous metals, which are critical to a wide range of industries including electronics, construction and renewable energy. Focusing on metals such as aluminium, copper and silicon, the study highlights the importance of recycling in conserving resources and minimizing environmental impact. It discusses the challenges posed by material diversity in recycling processes and the advances in recycling technologies that have emerged in response. Special emphasis is placed on the importance of a circular economy in maintaining a sustainable balance between consumption and conservation of metal resources. Through detailed analysis, it advocates innovative recycling practices and improved design for recyclability and highlights the role of policy, industry and consumer behaviour in achieving sustainability goals. The findings contribute to the discourse on strategic self-sufficiency in Europe through recycling, providing insights into how to improve efficiency and manage the complexity of the global material cycle. This work calls for a collaborative effort towards sustainable metallurgy and underlines the critical need for advances in recycling infrastructure and technology to ensure the long-term availability and environmental stewardship of non-ferrous metals. This article is part of the discussion meeting issue ‘Sustainable metals: science and systems’.
Publisher Copyright: © 2024 The Author(s). Published by the Royal Society. All rights reserved.
Keywords: circular economy; materials cycle; nonferrous metallurgy; primary production; recycling

Simulating Rolling Element Bearing Defects in Induction Machines - Floh, Florian; Makoschitz, Markus; Weiß, Helmut (Power Electronics and Drives (PEAD), 2024)
The significant occurrence of bearing faults in electrical machines necessitates continuous online monitoring of the machine’s operating data with the main objective of ensuring both high reliability and efficiency and therefore minimizing the chance of unwanted breakdowns. This work focuses on the simulation of (defective) bearings, utilizing a dedicated model with five degrees of freedom (translational motion) in conjunction with an induction motor model. The primary objective is to gain a comprehensive understanding of how faulty bearings influence both the entire bearing itself and the machine, mainly concerning vibration signals and additional frictional torque. Additionally, various shapes of spalls on the raceway(s) are being described, analyzed and compared. This work is an extended version of the conference paper “Simulating Rolling Element Bearing Defects in Induction Machines”, presenting additional information on how to simulate spalls (with different shapes and sizes) on the inner ring of the bearing. Furthermore, the so obtained vibration signal is being examined and a method is proposed aiming to verify the simulation results and to predict the location of the spall (raceway of the inner or outer ring).
Keywords: condition monitoring; induction machine; bearing faults; bearing fault detection

A unified nonlinear yield criterion for fracture and fault slip in quasi-brittle rocks - You, Tao; Zhao, Lun Yang (European Journal of Mechanics, A/Solids, 2024)
The micromechanical damage model has been developed to better describe multiscale fracture behavior in quasi-brittle rocks. While the deduced yield criterion under tension and compression has been carefully investigated in different stress spaces, it fails to capture a smooth transition from extension to shear fracture and overestimates the tensile strength of the rock. This paper introduces a unified nonlinear yield criterion based on a stress-dependent fracture energy parameter. In particular, the effect of the intermediate principal stress is encapsulated. The proposed yield criterion is then validated in the principal stress space based on a detailed parameter calibration procedure. Subsequently, four verification examples corresponding to Beishan granite, Lac du Bonnect granite, Carrara marble and Berea sandstone are carried out to show a desirable predictive capacity of the proposed yield criterion on progressive failure, extension to compressive-shear fracture transition and fault slip in quasi-brittle rocks.
Publisher Copyright: © 2024 Elsevier Masson SAS
Keywords: Fault slip; Microcracks; Micromechanics; Nonlinear yield criterion; Quasi-brittle rock; Shear fracture

Challenges in developing materials for microreactors - Tunes, Matheus Araujo; Parkison, Darren; Huang, Yuqing; Chancey, M. R.; Vogel, S. C.; Mehta, V. K.; Torrez, M. A.; Luther, E. P.; Valdez, James A.; Wang, Y.; Yu, Jianguo; Cinbiz, M. N.; et al. (Acta Materialia, 2024)
The development of microreactor technology presents an efficient solution for providing portable electricity, catering to both human space exploration needs within our solar system and supplying power to remote Earth-bound areas. The miniaturization of nuclear reactors poses immediate new challenges for materials science with respect to the capability for controlling nuclear reactions via thermalization of highly-energetic neutrons. In a microreactor, neutron moderation takes place in compact geometries, thus new moderator materials are required to exhibit high moderating power per unit of volume. This challenge is currently being addressed through the development of transition metal hydrides, known for their strong nuclear moderation capability but to date, research on their irradiation response is limited, specifically regarding phase stability, hydrogen in-lattice retention, and their dependence on irradiation temperature and dose. Herein, we present a detailed investigation on the response of yttrium dihydride (YH2) to heavy ion irradiation. The experiments indicate that YH2 is stable up to an irradiation dose of 2 dpa and below 800°C, identified herein as a critical temperature for YH2. Our study detected the nucleation and growth of voids as a function of the irradiation temperature. They were the predominant type of radiation damage present in the microstructure of YH2 that was distinguishable from pre-existing defects in the pristine YH2 samples. Below the critical temperature, no phase transformation (degassing/dehydriding) nor amorphization occurred. Experimental results with concomitant density functional theory calculations allowed us to elaborate and propose new strategies to enhance the metal hydride performance in extreme environments.
Publisher Copyright: © 2024 The Author(s)
Keywords: Metal hydrides; Microreactors; Phase stability; Radiation damage; Space materials

Evaluating refractory material performance in pyrometallurgical recycling of lithium-ion batteries under a reducing atmosphere - Wiszniewski, Lukas; Marschall, Irmtraud; Hochsteiner, Thomas; McFarlane Hoad, Thomas; Doschek-Held, Klaus; Raupenstrauch, Harald (Ceramics International, 2024)
Pyrometallurgical recycling of lithium-ion batteries (LIB) has emerged as the go-to approach in industrial recycling solutions, yet it encounters significant challenges, such as lithium (Li) slagging. This study explores a reactor for pyrometallurgical recycling, that offers the potential to overcome this bottleneck by simultaneously recovering lithium and phosphorous (P) via the gas stream, more noble elements including cobalt (Co), nickel (Ni) and copper (Cu) as an alloy and less noble elements like aluminum (Al), calcium (Ca) and silicium (Si) as a slag. However, to enhance the efficiency and performance of this reactor, a critical focus is placed on evaluating refractory materials with reduced corrosion and diffusion characteristics. Already explored refractory materials, including aluminum oxide (Al2O3) or magnesium oxide (MgO), have exhibited severe issues, such as accelerated corrosion and diffusion rates, leading to diminished performance and compromised efficiency. To evaluate a more suitable refractory material for pyrometallurgical recycling of LIB, tests using silicon carbide (SiC), chromium(III)-oxide (Cr2O3) and zirconium dioxide (ZrO2) were performed up to 1600 °C. The test results indicate that the investigated refractory materials offer distinct advantages and disadvantages. While SiC shows minimal to no wear by corrosion, Cr2O3 exhibits higher resistance to Li diffusion. Contrary, ZrO2 experienced severe corrosion and crack formation, showing unsuitability for LIB recycling. Based on these findings, a continuously operated reactor could use different refractory materials in specific zones. While the degasification zone could benefit from Cr2O3's minimal diffusion properties, areas with intense contact between the crucible and melt could utilize SiC's corrosion resistance. However, partial oxidation at the outer surface of the SiC crucible led to the formation of SiO2, another critical point to consider for scale-up plans, as it might influence the mechanical integrity long-term.
Publisher Copyright: © 2024 The Authors
Keywords: Batteries; Crucible test; InduRed; Pyrometallurgical recycling; Refractories (E); SiC (C)

GECCO2: Ein neues Christian Doppler Labor für umweltfreundliche reststoffbasierte Baumaterialien - Steindl, Florian Roman; Ratz, Bettina; Radinger, Stefanie; Zögl, Iris; Hassan, Amr Hussein Mokhtar; Raic, Sara; Rudic, Ognjen; Doschek-Held, Klaus; Sedlazeck, Klaus Philipp; Mittermayr, Florian; Vallazza-Grengg, Cyrill (Recy & Depotech 2024, 2024)

Implicit hydromechanical representation of fractures using a continuum approach - Vaezi, Iman; Parisio, Francesco; Yoshioka, Keita; Alcolea, Andres; Meier, Peter; Carrera, Jesús; Olivella, Sebastià; Vilarrasa, Víctor (International Journal of Rock Mechanics and Mining Sciences, 2024)
Fractures control fluid flow, solute transport, and mechanical deformation in crystalline media. They can be modeled numerically either explicitly or implicitly via an equivalent continuum. The implicit framework implies lower computational cost and complexity. However, upscaling heterogeneous fracture properties for its implicit representation as an equivalent fracture layer remains an open question. In this study, we propose an approach, the Equivalent Fracture Layer (EFL), for the implicit representation of fractures surrounded by low-permeability rock matrix to accurately simulate hydromechanical coupled processes. The approach assimilates fractures as equivalent continua with a manageable scale (≫1 μm) that facilitates spatial discretization, even for large-scale models including multiple fractures. Simulation results demonstrate that a relatively thick equivalent continuum layer (in the order of cm) can represent a fracture (with aperture in the order of μm) and accurately reproduce the hydromechanical behavior (i.e., fluid flow and deformation/stress behavior). There is an upper bound restriction due to the Young's modulus because the equivalent fracture layer should have a lower Young's modulus than that of the surrounding matrix. To validate the approach, we model a hydraulic stimulation carried out at the Bedretto Underground Laboratory for Geosciences and Geoenergies in Switzerland by comparing numerical results against measured data. The method further improves the ability and simplicity of continuum methods to represent fractures in fractured media.
Publisher Copyright: © 2024 The Authors
Keywords: Embedded model; Equivalent fracture layer; Fracture implicit representation; Fracture variable permeability; Hydraulic stimulation of fractures

Multiscale modeling of diffuse damage and localized cracking in quasi-brittle materials under compression with a quadratic friction law - Zhao, Lun Yang; Ren, Lu; Liu, Ling Hui; Lai, Yuan Ming; Niu, Fu Jun; You, Tao (International journal of solids and structures, 2024)
The diffuse damage and localized cracking of quasi-brittle materials (i.e., rocks and concretes) under compression can be delineated by a matrix-microcrack system, wherein a solid matrix phase is weakened by a large number of randomly oriented and distributed microcracks, and the macroscopic cracking is formed by a progressive evolution of microcracks. Several homogenization-based multiscale models have been proposed to describe this matrix-microcrack system, but most of them are based on a linear friction law on the microcrack surface, rendering a linear strength criterion. In this paper, we propose a new quadratic friction law within the local multiscale friction-damage (LMFD) model to capture the plastic distortion due to frictional sliding along the rough microcrack surface. Following that, a macroscopic Ottosen-type nonlinear strength criterion is rationally derived with up-scaling friction-damage coupling analysis. An enhanced semi-implicit return mapping (ESRM) algorithm with a substepping scheme is then developed to integrate the complex nonlinear constitutive model. The performance of LMFD model is evaluated compared to a wide range of experimental data on plain concretes, and the robustness of ESRM algorithm is assessed through a series of numerical tests. Subsequently, to effectively describe the localized cracking process, a regularization scheme is proposed by combining the phase-field model with the established LMFD model, and the discretization independent crack localization is numerically verified.
Publisher Copyright: © 2024 The Author(s)
Keywords: Homogenization-based multiscale modeling; Integration algorithm; Phase-field model; Quadratic friction law; Quasi-brittle materials

Nanoscale Characteristics of Carlin-Type Auriferous Pyrite from the Nadaleen Trend, Yukon - Holley, Elizabeth A.; Jilly-Rehak,, C; Sack, Patrick; Phillips, D.L.; Gopon, Phillip (Economic Geology (Bulletin of the Society of Economic Geologists), 2024)
Gold deposits of the Nadaleen trend in central Yukon host over 1.7 million ounces (Moz) of Au and share many characteristics in common with Nevada’s Carlin-type deposits, including similar host rock types, structural setting, alteration, and geochemistry, as well as the occurrence of gold in hydrothermal arsenian pyrite. We examined the textures, minor and trace element geochemistry, and δ34S signatures of precursor pyrite and hydrothermal pyrite overgrowths in samples grading over 35 g/t Au from the Sunrise and Conrad deposits. In the Osiris limestone at Sunrise, hydrothermal pyrite occurs as rims ranging from <1 to 5 µm overgrowing subhedral to euhedral sedimentary pyrite grains that are 20 to 100 µm in diameter; as rims (<1 to 3 µm thick) of hydrothermal pyrite that cement together the individual aggregates (measuring <1 to 5 µm) in framboidal pyrite; and as disseminated hydrothermal pyrite grains (<1 µm) that may be single stage. The hydrothermal pyrite in our Sunrise samples contains up to 45 ppm Au, 29 ppm Cu, 1,053 ppm As, and 15 ppm Ag, with δ34S compositions that are 1 to 8‰ higher than the sedimentary pyrite. The hydrothermal pyrite is zoned at the nanoscale, with the highest Au concentrations typically in the outermost portion of the rims. In the Conrad gabbroic dike, hydrothermal pyrite occurs as rims ranging from <1 to 5 µm overgrowing earlier pyrite grains that are 5 to 100 µm in diameter. The inner rims of the hydrothermal pyrite contain up to about 20 ppm Au, 900 ppm As, 60 ppm Ag, and 50 ppm Cu, whereas the outer margins of the hydrothermal pyrite contain up to about 670 ppm Au, 23,400 ppm As, 385 ppm Ag, and 115 ppm Cu. Relatively coarse hydrothermal rims (up to 5-µm) occur on the coarsest grains of precursor pyrite, suggesting that the substrate partially controls the texture of the hydrothermal pyrite, potentially due to the availability of Fe during sulfidation. The δ34S plateau values of the hydrothermal rims range from 1.2 to 11.0‰. Bayesian stable isotope modeling shows that the δ34S compositions of the hydrothermal pyrite can be generated by mixing the locally present sedimentary rocks with locally present magmatic sulfur. The modeling indicates that additional sources are not required, although they cannot be ruled out. At high Au concentrations, the modeling shows that most of the sulfur in the hydrothermal pyrite comes from a magmatic source, potentially from buried plutons visible as aeromagmetic anomalies. The modeling does not differentiate between whether (1) these magmatic rocks contributed sulfur and metals during passive leaching by an amagmatic hydrothermal fluid or (2) cooling magmas exsolved a sulfur- and metal-bearing fluid that led to magmatic-hydrothermal mineralization. We favor the latter interpretation, since the available geochronological evidence suggests that mineralization on the Nadaleen trend occurred during or shortly after Late Cretaceous emplacement of volumetrically limited, mantle-derived gabbroic dikes. Collectively, the evidence supports a Carlin-type origin for the gold deposits on the Nadaleen trend. Continued study is needed to link site-specific characteristics and processes to the regional metallogenic setting.

Herausforderungen bei der automatisierten Sortierung von Post-Consumer-Textilien mittels Standard-NIR-Spektroskopie - Stipanovic, Hana; Bäck, Tanja; Kobald, Hanna; Zirps, Sophie; Tischberger-Aldrian, Alexia (2024)
Keywords: Textilien; Textilabfälle; Textilsortierung; NIR-Spektroskopie; Herausforderungen

Recycling of Wintersport Hardgoods - The Challenges of Circularity - Zidar, David; Krempl, Nina; Pardametz, Verena; Bandl, Christine; Holzer, Clemens (2024)
Keywords: Winter sports equipment recycling; circular economy; mixed material separation; polymer processing of mixed material recyclates

Unraveling mudstone compaction at microscale - Shi, Xiangyun; Misch, David; Skerbisch, Lukas; Sachsenhofer, Reinhard F.; Žák, Stanislav; Cordill, Megan; Kiener, Daniel (Marine and petroleum geology, 2024)
Compaction processes within mudstone samples across varying depths (723.5–3213.5 m) in the Vienna Basin were investigated, focusing on porosity changes and the resulting micromechanical response in the clay-rich, fine-grained fraction (“clay matrix”). A novel approach combining nanoindentation mapping with machine learning data analysis was developed to efficiently extract representative micromechanical parameters of the clay matrix. Emphasis was put on capturing the properties of the fine-grained, clay-dominated composite rather than individual mineral phases, enabling the analysis of compaction-induced strength changes at microscale. A significant enhancement in the mechanical strength of the clay matrix with increasing burial depth was observed. Reduced elastic modulus (Er) and hardness (H) increased from 6.8 ± 3.4 to 22.6 ± 7.5 GPa and from 0.2 ± 0.2 to 0.9 ± 0.2 GPa, respectively, over the depth interval of 2490 m. Moreover, a strong correlation between depth and porosity and consequently micromechanical properties of the clay matrix exists. This highlights the substantial influence of intra-clay porosity on mechanical properties, which follow a general compaction trend with depth. Broad ion beam-scanning electron microscopy (BIB-SEM) analysis was used for textural investigations at micro-to nanoscale and indicated that the reduction in porosity predominantly resulted from mechanical compaction rather than mineral diagenesis, which would have been noticeable by signs of significant dissolution or cementation. The correlation coefficient matrix between multiscale porosity measurements and nanoindentation affirmed that the porosity loss was closely linked to the enhanced mechanical properties of the fine-grained composite clay matrix, while other compositional variables like total clay mineral content showed weak correlations. Empirical mathematical equations were derived to describe the mechanical properties as generalized functions of depth and porosity. These may be used as geomechanical input for future basin analysis and geoenergy applications (e.g., seal rock studies in a geological storage context). This study introduces a new approach to unravel compaction processes in fine-grained rocks at microscale, emphasizing the interplay between intra-clay porosity and micromechanical changes during proceeding burial.Verfasser/-in und OrganisationszugehörigkeitFügen Sie alle Verfasser (Personen, Organisationen, Autorengruppen) hinzu.Folgendes kann bei Personen geändert werden:RolleVoreingestellt ist 'Autor', aber andere Rollen (Herausgeber, Illustrator usw.) können ausgewählt werden.OrganisationszugehörigkeitFalls unrichtig bitte auf andere interne oder externe Organisation ändern.Verfasser/-in Bearbeiten Xiangyun Shi, Autor Interne Person Department Angewandte Geowissenschaften und Geophysik Organisation: Departments and Institute Lehrstuhl für Energy Geosciences (630) Organisation: Lehrstuhl Bearbeiten David Misch, Autor Interne Person Department Angewandte Geowissenschaften und Geophysik Organisation: Departments and Institute Lehrstuhl für Energy Geosciences (630) Organisation: Lehrstuhl Bearbeiten Lukas Skerbisch, Autor Interne Person Department Angewandte Geowissenschaften und Geophysik Organisation: Departments and Institute Lehrstuhl für Energy Geosciences (630) Organisation: Lehrstuhl Bearbeiten Reinhard F. Sachsenhofer, Autor Interne Person Department Angewandte Geowissenschaften und Geophysik Organisation: Departments and Institute Lehrstuhl für Energy Geosciences (630) Organisation: Lehrstuhl Bearbeiten Stanislav Zak (Stanislav Žák), Autor Externe Person Erich-Schmid-Institut für Materialwissenschaft der Österreichischen Akademie der Wissenschaften Externe Organisation: Forschungseinrichtung Bearbeiten Megan Cordill, Autor Interne Person Erich-Schmid-Institut für Materialwissenschaft der Österreichischen Akademie der Wissenschaften Externe Organisation: Forschungseinrichtung Bearbeiten Daniel Kiener, Autor Interne Person Department Werkstoffwissenschaft Organisation: Departments and Institute Lehrstuhl für Materialphysik (430) Organisation: LehrstuhlPerson hinzufügen...Organisation hinzufügen...Autorenkooperation hinzufügen...Gesamtanzahl der Autoren7Betreuende OrganisationDie Redakteure/Redakteurinnen der betreuenden Organisationseinheit sind zuständig für die Bearbeitung dieses Beitrags.Betreuende OrganisationseinheitLehrstuhl für Materialphysik (430)Organisation: LehrstuhlOrganisation ändern...FachzeitschriftFachzeitschriftMarine and petroleum geology0264-8172Web of Science (2022): Protokoll-Einflussfaktor 5,361 2161 , Scopus-Bewertung (2023): CiteScore 8,8 SJR 1,365 SNIP 1,367Fachzeitschrift ändernJahrgangAusgabenummerOpen-Access-AnleitungRichtlinienempfehlungen von Sherpa Romeo Submitted version Accepted version Published version Publisher policies Datum der letzten Aktualisierung: 20/08/24Zugang zur elektronischen Version (Volltext)Hochladen / Verlinken der elektronischen Versionen dieses ForschungsoutputsOpen access-Status: Diese Arbeit ist frei verfügbar!- frei zugänglichZugang zur elektronischen Version (Volltext) Endgültige, publizierte Fassung AnzeigenBearbeiten 10.1016/j.marpetgeo.2024.107083 Endgültige, publizierte Fassung frei AnzeigenBearbeiten X. Shi, D. Misch, L. Skerbisch, R.F. Sachsenhofer, S. Zak, M. Cordill, D. Kiener 2024 (JMPG 169,107083) Endgültige, publizierte Fassung CC BY frei 20,8 MB | p1094375 | 10 Sept. 2024 15:36Zugang zur elektronischen Version (Volltext)...Andere Links AnzeigenBearbeiten http://www.scopus.com/inward/record.url?scp=85202867501&partnerID=8YFLogxK Scopus Publikation Verknüpfung zur Publikation in ScopusAnderen Link hinzufügen...Zusätzliche DateienDatei hinzufügenSchlagwörterGeben Sie Schlagwörter an, um den Inhalt des Projekts zu charakterisieren.ÖFOS 2012verwenden Sie ÖFOS 2012 Sachgebiete für alle Datensätze ab 01.01.2014 1 NATURAL SCIENCES › 105 Geosciences › 1051 Geology, Mineralogy › 105126 Applied geophysics 2 TECHNICAL SCIENCES › 205 Materials Engineering › 2050 Materials Engineering › 205019 Material sciencesÖFOS 2012 hinzufügen ...SchlagwörterÖFOS 2002verwendet bis 31.12.2013Keine VerknüpfungenÖFOS 2002 hinzufügen ...Ziele für nachhaltige EntwicklungDie Ziele für nachhaltige Entwicklung gelten als Blaupause, um eine bessere und nachhaltigere Zukunft für alle zu schaffen. Dabei werden unsere globalen Herausforderungen angesprochen, darunter Armut, Ungleichheit, Klimawandel, Umweltzerstörung, Frieden und Gerechtigkeit. SDG 7 - Affordable and Clean Energy SDG 12 - Responsible Consumption and ProductionZiele für nachhaltige Entwicklung hinzufügen ...FördermittelDokumentierter Fördermittel-TextEinzelheiten zu Fördermitteln Bearbeiten Austrian Science Fund Akronym: FWF Fördernummern: P 33883 Bearbeiten Austrian Science Fund Akronym: FWFDetails zu Fördermitteln hinzufügenBibliographische NotizTragen Sie hier, wenn vorhanden, Anmerkungen über spezielle Bedingungen oder andere relevante Gegebenheiten hinsichtlich der Einreichung dieses Beitrags ein.Bibliographische NotizPublisher Copyright:© 2024 The AuthorsVeranstaltungVeranstaltungVeranstaltung hinzufügen...VerknüpfungenFügen Sie Verknüpfungen zu relevanten Inhalten hinzu.PublikationenAktivitätenAuszeichnungenProjekteDatensätzeAusrüstungSichtbarkeitWie ein Inhalt sichtbar ist (siehe Vorschau)Öffentlich zugänglich- z.B. auf Webseiten/-portalenCampus (IP-Adressen)- Nur von zugelassenen IP-Adressen aus sichtbarDatenbank (Pure-Nutzer/-innen)- Nur für angemeldete Pure-Nutzer/-innen sichtbar.Vertraulich- auf eingeloggte zugeordnete Nutzer und Redakteure begrenzt​D​a​t​e​n​b​a​n​k (​P​u​r​e-​N​u​t​z​e​r/-​i​n​n​e​n)Externe Publikations-IDsPublikationsimport-IDScopus: 85202867501Zusätzliche Quellen-IDsZusätzliche Quelle hinzufügen...
Publisher Copyright: © 2024 The Authors
Keywords: BIB-SEM; Geoenergy; Machine learning; Mudstone compaction; Nanoindentation; Seal analysis; Vienna basin

Austrian Mineral Waste Streams for Alkali-Activation: A Comprehensive Suitability Evaluation Approach - Hassan, Amr; Radinger, Stefanie; Rudic, Ognjen; Ratz, Bettina; Steindl, Florian Roman; Mittermayr, Florian; Zögl, Iris; Raic, Sara; Dietzel, Martin; Grengg, Cyrill (2024)

Contact damage response of alumina-based layered architectures under different loading configurations - Schlacher, Josef Christian; Stücklberger, Fabian; Jabr, Abdullah; Bermejo, Raul (Journal of the European Ceramic Society, 2024)
Hertzian contact damage upon spherical indentation is investigated in alumina-based ceramics designed with embedded textured compressive layers. The effect of the location of the embedded layer and the testing configuration (parallel or normal to the layer orientation) on the sub-surface damage evolution is explored. An acoustic emission system for crack detection and post-mortem cross sectioning are employed to evaluate the onset and extension of damage in the different samples. Distinct acoustic signals detected at different contact loads are correlated with the onset of the ring crack, cone crack propagation and quasi-plastic deformation within the textured layer. The distinct damage mechanisms are influenced by the location of the embedded textured compressive layer and the loading orientation with respect to the layers. The design of layered ceramics for contact applications should consider the loading orientation as well as the contact stress field with respect to the “protective” layer to enhance damage tolerance.

On the Prediction of Strength and Optimum Mix-Designs of Mineral-Waste-Based Alkali-Activated Materials - Zögl, Iris; Rudic, Ognjen; Ratz, Bettina; Hassan, Amr; Radinger, Stefanie; Steindl, Florian Roman; Vallazza-Grengg, Cyrill; Dietzel, Martin; Raic, Sara (2024)

Von Erdgas zu Wasserstoff, Teil I - Tichy, Stefan; Büchner, Karl; Pucher, Philip; Prillhofer, Bernd; Wibner, Stefan; Antrekowitsch, Helmut (International aluminium journal, 2024)

A renormalization scheme for semi-regular continued fractions - Langeveld, Niels; Ralston, David (Monatshefte für Mathematik, 2024)
In this article we study a renormalization scheme with which we find all semi-regular continued fractions of a number in a natural way. We define two maps, T^ slow and T^ fast: these maps are defined for (x,y)∈[0,1], where x is the number for which a semi- regular continued fraction representation is developed by T^ slow according to the parameter y. The set of all possible semi-regular continued fraction representations of x are bijectively constructed as the parameter y varies. The map T^ fast is a “sped up" version of the map T^ slow, and we show that T^ fast is ergodic with respect to a probability measure which is mutually absolutely continuous with Lebesgue measure. In contrast, T^ slow preserves no such measure, but does preserve an infinite, σ-finite measure mutually absolutely continuous with Lebesgue measure. Furthermore, we generate a sequence of substitutions which generate a symbolic coding of the orbit of y under rotation by x modulo one. In the last section we highlight how our scheme can be used to generate semi-regular continued fractions explicitly for specific continued fraction algorithms such as Nakada’s α-continued fractions.
Publisher Copyright: © The Author(s) 2024.
Keywords: 11A55; 11J70; 37A44; 37B10; 37E05; Approximating sequences; Circle rotations; Renormalization; Semi-regular continued fractions; Symbolic encodings

Biodegradable plastics – Where to throw? A life cycle assessment of waste collection and management pathways in Austria - Mhaddolkar, Namrata; Lodato, Concetta; Tischberger-Aldrian, Alexia; Vollprecht, Daniel; Fruergaard Astrup, Thomas (Waste management, 2024)
The current waste management systems are struggling to optimally handle biodegradable plastics (BDPs) and are facing numerous challenges; one of which is the consumer confusion about how to best source-segregate BDPs. Based on an environmental life-cycle assessment, this study investigated the consequences of collecting BDPs in one of three waste streams (packaging waste, biowaste, and residual waste) in Austria. Collecting BDPs as (i) packaging waste resulted in incineration (SP1) or mechanical recycling (SP2), (ii) biowaste resulted in composting (SB1) or anaerobic digestion (AD) (SB2), and (iii) residual waste in incineration (SR1). SP2 performed best in most of the 16 investigated impact categories (ICs). Three scenario analyses demonstrated that (i) utilisation of BDPs as an alternative fuel for process heat substitution yielded more environmental benefits than incineration in SP1 and SP2, (ii) adding a material recovery facility (MRF) with AD increased the environmental load for SB2, while (iii) the energy scenario with zero electricity imports plus heat from biomass performed best for most alternative pathways across the 16 ICs. Eight technology parameters (out of 97) were identified as most relevant for the results based on data quality, sensitivity ratio, and analytical uncertainty; they were related to waste incineration, MRF, recycling facility, compost- and AD processes. Overall, mechanical recycling emerged as the most favourable option which is aligned with the waste-hierarchy mentioned in the European Union Waste Framework Directive. However, effective mechanical recycling of BDPs requires (i) a ‘sufficient’ waste amount, (ii) a market for recyclates, and (iii) relevant mechanical recycling infrastructure.
Publisher Copyright: © 2024 The Author(s)
Keywords: Biodegradable plastic waste management; Life cycle assessment; Packaging waste; Recycling; Waste collection & sorting

Design of photocurable thiol-epoxy resins for the processing of vitrimers with vat photopolymerisation 3D printing - Gaca, Szymon; Dietliker, Kurt; Rossegger, Elisabeth; Schlögl, Sandra (Reactive and Functional Polymers, 2024)
Vat photopolymerisation 3D printing is a convenient approach to fabricating complex polymeric objects based on the localised photocuring of a liquid resin. Advancing from free-radical mediated curing mechanisms, the current study focuses on the vat photopolymerisation 3D printing of photopolymers formed by an ionic click reaction between thiol and epoxy monomers. In this process, selected epoxy monomers are mixed with a tetra-functional thiol crosslinker and a photobase generator, which releases 1,5-diazabicyclo[4.3.0]non-5-ene (DBN) upon light exposure to initiate the anionic ring-opening reaction. FTIR, photo-DSC and rheology studies reveal a slow cure rate of the thiol-epoxy resins at room temperature, which is significantly accelerated by increasing the temperature to 50 °C during light irradiation. By optimising the resin composition, shelf life and viscosity, printing of objects via digital light processing 3D printing is enabled by using a vat heated to 50 °C. The printed thiol-epoxy networks contain ample -OH and ester moieties, which undergo thermo-activated bond exchange reactions. Here, the photochemically liberated DBN molecules act as catalysts to accelerate the transesterification reaction at elevated temperatures (150–180 °C). Rheological measurements demonstrate the efficient and Arrhenius-like behaviour of the networks' stress relaxation, giving rise to the dynamic nature of the printed photopolymers, which is further confirmed by reshaping experiments.
Publisher Copyright: © 2024 The Authors
Keywords: Anionic photocuring; Digital light processing 3D printing; Photobase generator; Thiol-epoxy resins; Vitrimers

Industrial Disasters and Hazards: From Causes to Consequences—A Holistic View - Cvetković, Vladimir M.; Renner, Renate; Jakovljević, Vladimir (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Starting from accelerated industrial development, industrial disasters (chemical spills, explosions, nuclear accidents, etc.), which fall under man-made (technological) disasters, increasingly threaten human lives, the environment, and property. Their complexity and far-reaching consequences, both at the local and global levels, require effective management of industrial risks and the disasters themselves (preparedness, mitigation, response, and recovery). For these reasons, the review paper aims to provide a holistic description of the diverse causes, dynamics, and multidimensional consequences of disasters. Additionally, it highlights and explains the key factors that directly or indirectly contribute to their occurrence. Furthermore, it could be said that the paper analyzes existing strategies for managing risks from industrial disasters and systematizes recommendations for improving preventive and reactive measures in high-risk industries. On the other side, the paper utilizes a comprehensive literature review, which involves the systematic identification, review, analysis, and critical evaluation of existing scientific papers, studies, reports, and regulatory documents on industrial disasters. Besides that, it also includes a detailed analysis of well-known industrial disaster cases such as Seveso (Italy, 1976), Bhopal (India, 1984), Chernobyl (Ukraine, then USSR, 1986), and Fukushima (Japan, 2011). The paper emphasizes that industrial disasters are often the result of the combined influence and interaction of technical failures, human errors, and inadequately developed safety procedures. Moreover, it can be highlighted that the design and implementation of preventive measures, such as regular maintenance of technical systems and systematic training and education of employees, are crucial for reducing the likelihood of such catastrophic events. The implications of this review paper are multifaceted and point to the following: the need to reassess current safety practices in industries; reconsider the potential for introducing innovations in preventive technical-technological solutions; examine the thorough implementation of innovative early warning systems, safety procedures, and modern equipment in facilities; improve cooperation between engineers, safety managers, and regulatory workers; reassess the need for additional updates and tightening of regulations regarding the storage, transport, and use of hazardous materials in industry; and improve the management of risks from industrial disasters.

Lebenszyklusanalysen als Fundament für Umweltproduktdeklarationen - Feichtinger, Gerald; Posch, Wolfgang (TripleN Magazin über Nachhaltigkeit, 2024)
Umweltproduktdeklarationen bieten eine wichtige Möglichkeit, um qualitative Informationen zu Umweltauswirkungen von Produkten und Dienstleistungen unter Einbeziehung von ISO 14040/44 konformen Lebenszyklusbetrachtungen transparent und wertfrei zu veröffentlichen.
Keywords: Lebenszyklusanalysen; LCA; Umweltproduktdeklarationen; EPD; ISO 14040; EN 15805

Recy & DepoTech 2024 - Pomberger, Roland; Trieb, Tanja; Adam, Josef; Kandlbauer, Lisa; Nigl, Thomas; Sarc, Renato; Bouvier-Schwarz, Therese; Khodier, Karim; Koinig, Gerald; Kuhn, Nikolai Emanuel; Lasch, Tatjana; Rutrecht, Bettina; et al. (Recy & Depotech 2024, 2024)
Conference proceedings of the 17th Recy & DepoTech conference
Keywords: Recycling; Abfallverwertung; Abfallwirtschaft; Ressourcenmanagement; Deponietechnik; Altlasten; Internationale Abfallwirtschaft

Recy & DepoTech 2024 - Pomberger, Roland; Trieb, Tanja; Adam, Josef; Kandlbauer, Lisa; Nigl, Thomas; Sarc, Renato; Bouvier-Schwarz, Therese; Khodier, Karim; Koinig, Gerald; Kuhn, Nikolai Emanuel; Lasch, Tatjana; Rutrecht, Bettina; et al. (Recy & Depotech 2024, 2024)
Conference proceedings of the 17th Recy & DepoTech conference
Keywords: Recycling; Abfallverwertung; Abfallwirtschaft; Ressourcenmanagement; Deponietechnik; Altlasten; Internationale Abfallwirtschaft

Remote hydraulic fracturing at weak interfaces - You, Tao; Yoshioka, Keita (Computers and geotechnics, 2024)
Many hydraulic fracturing experiments suggest that low-viscosity fluid tends to generate a complex fracture network, which may be beneficial for geo-energy production. However, the precise impacts of low-viscosity fluid on the fracture nucleation and propagation are unknown. This study focuses on the stress jump at weak interfaces (e.g., grain boundaries or natural fractures) caused by the contrast in Biot’s coefficient, which is prevalent in hard rocks, and how failure may develop. We found that fracture nucleation at weak interfaces becomes favorable under certain Biot’s coefficient contrast and fluid viscosity. Our numerical simulations of fluid injection through a borehole demonstrate that low-viscosity fluid injection can nucleate isolated fractures at remote interfaces without connecting to the main propagating fracture. These findings imply the necessity to consider Biot’s coefficient variations within a rock mass in applications such as hydraulic fracturing or induced seismicity, especially when a diffused pressure gradient persists due to the low-viscosity fluid.

Spotmarkt-getriebene vs. netzdienliche Ladeinfrastruktur - Vopava-Wrienz, Julia; Rock, Maximilian; Fayyaz Bakhsh, Ahmad; Kienberger, Thomas (Elektrotechnik und Informationstechnik : e & i, 2024)

Thermisch behandelte Stahlschlacken und künstliche Mineralfasern als neuartige reaktive Bindemittel für die Baustoffindustrie - Steiner, Sarah; Steindl, Florian; Bendler, Clemens; Weisser, Katharina; Doschek-Held, Klaus; Krammer, Anna; Sedlazeck, Klaus Philipp; Mittermayr, Florian; Juhart, Joachim (Recy & Depotech 2024, 2024)

DC-Wallbox Pre-Scoping Study - Makoschitz, Markus; Chakraborty, Rupak; Passler, Manuel; MacHtinger, Katharina; Ledinger, Stephan (2024)

Enhancing Recycled Polymers: The Impact of Reused Glass Fiber Composites on Rheological Properties and Processing Performance - Shahroodi, Zahra; Krempl, Nina; Duretek, Ivica; Holzer, Clemens (2024)

Insights Into LAOS Analysis of Liquid Silicone Rubber for Viscosity Determination - Azevedo, Maurício; Kerschbaumer, Roman Christopher; Holzer, Clemens (3rd Annual Conference of the Austrian Society for Rheology, 2024)

Rheological Characterisation of Powder Injection Moulding Feedstocks - Duretek, Ivica; Lucyshyn, Thomas; Holzer, Clemens (3rd Annual Conference of the Austrian Society for Rheology, 2024)

A Survey on Drivers, Obstacles and Economic Effects of Digitalization in the Energy-Intensive Industry - Schlar, Daniel; Grogger, Daniel; Posch, Wolfgang (NEFI-Konferenz 2024, 2024)
In today's rapidly evolving technological landscape, the energy-intensive industry is at a critical point of innovation and change. Technologies like artificial intelligence, the Internet of Things, and advanced data analytics are transforming industrial processes and resource use. This research explores the key drivers, obstacles, and economic impacts of digitalization and energy efficiency in the energy-intensive industry. It offers a detailed understanding of its journey toward digitalization by highlighting current efforts, challenges, and future directions for improving energy efficiency and sustainable practices. Further, it aims to uncover the forces behind digital transformation in the energy-intensive industry, identifying important drivers and examining barriers to digital technology adoption. A survey of industry professionals provides insights into the current state of digitalization, its effects on energy demand, primary drivers, obstacles, and future trends. Results show a strong push towards digitalization, especially in the steel and manufacturing sectors, driven by internal strategies and external support. Key drivers include better productivity, cost reduction, and increased competitiveness. Major obstacles are high initial costs, the need for skilled workers, leadership gaps, and outdated machinery. There is a clear link between digitalization and energy efficiency, with companies reporting financial savings and expecting more improvements through innovation.
Keywords: Digitalization; Energy Efficiency; Energy-Intensive Industry; Technological Transformation; Industrial Innovation; Digitalisierung; Energieeffizienz; Energieintensive Industrie; Technologischer Wandel

Deep learning approaches for classification of copper-containing metal scrap in recycling processes - Koinig, Gerald; Kuhn, Nikolai Emanuel; Fink, Thomas; Lorber, Bojan; Radmann, Y.; Martinelli, Walter; Tischberger-Aldrian, Alexia (Waste management, 2024)
Separating copper from iron scrap is a critical operation in metal recycling and achieving this with low cost sensoric equipment like RGB cameras instead of XRF/XRT is becoming increasingly attractive. In this article, the groundwork for creating an image classification model to separate copper from iron scrap has been performed. Twenty of the most common and most easily available CNN architectures were trained on 2200 metal scrap specimens and evaluated inline on a sensor-based sorting rig for their prediction accuracy and their inference latency to mimic real circumstances in an industrial setting. Out of these evaluated architectures, DenseNet-201 with 98% accuracy in inline tests is recommended if potent hardware is available. Otherwise AlexNet with 92% accuracy or MobileNet-V2 with 90% accuracy are recommended for further investigation and model creation if hardware restrictions apply. Based on the presented results in this article, the initial cumbersome surveyance of the most suitable network architecture can be substantially reduced and the creation of a sorting model can be streamlined. This article thus provides the basis for creating an inline applicable sorting method for scrap metal that uses low cost sensorics equipment and can provide reasonably high accuracy in its prediction.
Publisher Copyright: © 2024 The Author(s)
Keywords: Circular economy; Computer vision; Deep learning; Machine learning; Metal recycling; Sensor based sorting

EXAMINATION OF THE SUITABILITY OF INDUSTRIES FOR THE INTEGRATION OF GEOTHERMAL ENERGY AND CASCADING UTILISATION OF HEAT USING THE EXAMPLE OF GMUNDEN NEFI CONFERENCE 2024 - Hammer, Andreas; Riha, Gregor; Kienberger, Thomas; Riedl, Johannes; Haslinger, Edith; Stein, Stefan (NEFI-Konferenz 2024, 2024)
The energy demand of industry accounts in Austria for around 30 % of final energy demand, with process heat demand being the largest share of industrial energy consumption. In order to successfully decarbonise the industry, geothermal energy with its diverse possibilities such as heating, cooling, power generation and storage must also be integrated into industrial processes. As part of the CASCADE project, industrial plants in the Gmunden region are being analysed for their suitability for the potential supply for geothermal energy. The Gmunden dairy is the main focus of the investigations. Analyses of measurement data from the various processes will provide information on necessary temperature levels, energy quantities and changes in energy requirements over time. The work also focuses on the excess heat potential of industrial and trade companies. At the Gmunden dairy, all relevant excess heat flows are analysed in order to assess the potential for further cascading use in the district heating network or in other companies. For all other companies the top-down approach via specific key numbers is applied to determine the excess heat streams.
Keywords: Industry; excess heat; geothermal energy; cascading energy use

Self-healable epoxy/graphene oxide vitrimers and their recyclable glass fiber reinforced composites - Sharma, Harsh; Bijalwan, Viranchika; Mourad, Abdel Hamid I.; Kumar, Ajay; Schlögl, Sandra; Rana, Sravendra (Journal of Reinforced Plastics and Composites, 2024)
Glass fiber-reinforced polymers (GFRPs) made from thermoset polymers have been widely used across various industries. However, these composites have significant drawbacks, including poor interfacial adhesion between the fiber and matrix, as well as a substantial contribution to waste and environmental pollution due to the challenges in recycling, reprocessing, and reuse. Herein, firstly graphene oxide (GO) was incorporated in vitrimer matrix to fabricate recyclable vitrimer nanocomposites with improved interfacial interaction, high thermal stability, low dielectric constant, fast stress relaxation as well as rapid self-healing ability. The nanocomposite with 0.2 wt% GO is optimized to achieve excellent remoulding (89% of flexural strength) and self-healing (60 min for a 48 μm scratch) properties due to dynamic disulfide bond exchange mechanism. Furthermore, epoxy/GO matrix was used to develop glass fiber reinforced composites via vacuum assisted resin infusion molding process (VARIM). The developed composites demonstrate tremendous mechanical strength (250 MPa), shape-memory, weldability, and degradable properties. Due to the rapid chemical degradation of epoxy vitrimer under mild conditions in the thiol (2-mercaptoethanol and 1-otanethiol), facilitated by thiol disulfide exchange reaction, glass fibers (GFs) can be effectively recycled. The performance of recycled glass fibers closely matches that of original fibers, exhibiting nearly identical woven structure and mechanical properties. The single yarn of recycled glass fibers can achieve tensile strength of 85% (1-octanethiol) and 72% (2-mercaptoethanol) of the original glass fibers, thus, the recycling of glass fibers would be highly advantageous in terms of achieving the sustainability goals.
Publisher Copyright: © The Author(s) 2024.
Keywords: Glass fiber; graphene oxide; recycling; self-healing; vitrimers

The Impact of a Novel Heat Pricing Method on a Supra-Regional District Heating Network - Steinegger, Josef; Kienberger, Thomas (2024)

Challenges and Opportunities in Carbon Fiber-Reinforced Polymer Composites Circularity: A Prospective LCA Case Study - Miao, Zoe Chunyu; Kirschnick, Ulrike; Chen, Hao; Carbajales-Dale, Mik (2024)

In Vivo Assessment on Freeze-Cast Calcium Phosphate-Based Scaffolds with a Selective Cell/Tissue Ingrowth - Pejchalová, Lucie; Pejchal, Jaroslav; Roleček, Jakub; Vojníková, Michaela; Chlup, Zdeněk; Mařák, Vojtěch; González-Sánchez, Manuela; Čížková, Jana; Salamon, David (ACS Applied Materials and Interfaces, 2024)
Highly porous bioceramic scaffolds are widely used as bone substitutes in many applications. However, the use of bioceramics is often limited to hard tissues due to the risk of potential soft tissue calcification. A further limitation of highly porous bioceramic scaffolds is their poor mechanical stability, manifested by their tendency to break under stress. In our study, highly porous CaP-based scaffolds were prepared via freeze-casting with longitudinal and oriented pores ranging from 10 to 20 μm and a relative porosity of ∼70%. The resulting scaffolds achieved a flexural strength of 10.6 ± 2.7 MPa, which, in conjunction with their favorable bioactivity, made them suitable for in vivo testing. The prepared scaffolds were subcutaneously implanted in rats for two distinct periods: 6 weeks and 6 months, respectively. The subsequent development of fibrous tissue and involvement of myofibroblasts, newly formed vessels, and macrophages were observed, with notable changes in spatial and temporal distributions within the implantation. The absence of calcification in the surrounding soft tissue, as a result of the narrow pore geometry, indicates the opportunity to tailor the scaffold behavior for soft tissue regeneration.
Publisher Copyright: © 2024 The Authors. Published by American Chemical Society.
Keywords: bioceramics; calcium phosphates; freeze-casting; in vivo; scaffolds; tissue engineering

Perspective on pathways towards responsible surface engineering - Hans, Marcus; Schneider, Jochen M.; Matthews, Allan; Mitterer, Christian (Surface & coatings technology, 2024)
In this perspective sustainability-relevant aspects of modern surface engineering technologies, which enableimproved structural and functional surface properties, are critically evaluated. Although plasma-assisted physicalvapour deposition (PVD) is increasingly employed to address global challenges, such as energy efficiency andreduction of CO2 emissions, their inherently resource-intensive nature is often not considered.Surface engineering research should thus embrace sustainability-relevant aspects from a processes and materialsdesign point of view. While we are convinced that sustainability-relevant surface engineering has to bebased on synchronised process and materials solutions, we will discuss processes and materials separately.In terms of processes, we are going to describe the challenges of state-of-the-art technology, including energyand mass balances as well as product cycles. With respect to materials, the coating and process purity as well aschemical and microstructural complexity are discussed.Such approaches are fully in line with the United Nations Sustainable Development Goal 12 ResponsibleConsumption and Production. We expect that the here discussed urgently needed pathways towards responsiblesurface engineering will become important for the surface engineering community and adopted within the nearfuture. Responsible surface engineering includes the human behaviour and necessitates a change in mindset ofmaterials scientists and process engineers. Hence, two main questions are critically evaluated in this perspective:

Revealing the embrittlement phenomena after post-weld heat treatment of high-strength weld metal using high-resolution microscopy - Schrittwieser, Daniel; Pahr, Hannes; Musi, Michael; Landefeld, Andreas; Glushko, Oleksandr; Schnitzer, Ronald (Journal of Materials Research and Technology, 2024)
High strength combined with sufficient toughness is a fundamental prerequisite for steel in the field of lightweight construction. Joining high-strength steels by means of welding requires the use of highly advanced filler metals and a stress-relief post-weld heat treatment (PWHT) for optimum performance of the joint. However, such a heat treatment can lead to embrittlement in the weld metal. In this context, the present work deals with the influence of different PWHT holding temperatures on the microstructure and mechanical properties of a high-strength multipass all-weld metal to reveal the embrittlement phenomena. The all-weld metal was fabricated via gas metal arc welding using a metal cored wire with a minimum yield strength of 690 MPa. Charpy V-notch impact testing and tensile testing were carried out to characterize the strength and toughness of the all-weld metal in the as-welded condition and after a 2 h stress-relief PWHT at 520 °C, 580 °C, and 620 °C. The microstructure was characterized utilizing high-resolution techniques such as atom probe tomography and high-energy X-ray diffraction. The strength and toughness of the all-weld metal both decrease after PWHT with different holding temperatures. The cause for the observed embrittlement was found to be the formation of Mn-rich cementite precipitates. These carbides increase in size and phase fraction with increasing holding temperature and lead to a brittle transcrystalline cleavage fracture. Consequently, it was concluded that a gas metal arc welded joint with the investigated filler metal should not be exposed to stress-relief PWHT at temperatures higher than 580 °C.

Modelling freckles and spurious grain formation in directionally solidified superalloy castings - Zhang, Haijie; Zhao, Yunxing; Xiong, Wei; Ma, Dexin; Ludwig, Andreas; Kharicha, Abdellah; Wu, Menghuai (Communications materials, 2024)
Segregation channels with misoriented spurious grains, known as freckles, are an unacceptable casting defect in superalloy turbine blades. A digital-twin method to predict segregation channels was proposed in our previous studies; however, the formation of spurious grains was ignored. Here, we extend the digital twin methodology by incorporating dendrite fragmentation, which is recognized as the predominant mechanism in the formation of spurious grains. The flow-induced fragmentation process has been refined to account for the timing of dendrite pinch-off. A three-phase mixed columnar-equiaxed solidification model was used to track the motion of the crystal fragments. Directional solidification experiments for superalloy casting were conducted in an industrial-scale Bridgman furnace, and the distribution of spurious grains in the freckles was metallographically analysed. Excellent simulation-experiment-agreement was achieved. Based on this study, the formation of spurious grains within the segregation channels is mainly caused by the flow-driven fragmentation mechanism. Experimentally measured freckles can be reproduced only if the timing of the dendrite pinch-off is considered.
Publisher Copyright: © The Author(s) 2024.

BNE4SDG12 - Doschek-Held, Klaus (Abschlussveranstaltung - Zertifikat für Hochschullehrende Bildung für Nachhaltige Entwicklung, 2024)

Efficient surface defect detection in industrial screen printing with minimized labeling effort - Krassnig, Paul Josef; Haselmann, Matthias; Kremnitzer, Michael; Gruber, Dieter Paul (Integrated computer-aided engineering, 2024)
As part of the evolving Industry 4.0 landscape, machine learning-based visual inspection plays a key role in enhancing production efficiency. Screen printing, a versatile and cost-effective manufacturing technique, is widely applied in industries like electronics, textiles, and automotive. However, the production of complex multilayered designs is error-prone, resulting in a variety of defect appearances and classes. These defects can be characterized as small in relation to large sample areas and weakly pronounced. Sufficient defect visualization and robust defect detection methods are essential to address these challenges, especially considering the permitted design variability. In this work, we present a novel automatic visual inspection system for surface defect detection on decorated foil plates. Customized optical modalities, integrated into a sequential inspection procedure, enable defect visualization of production-related defect classes. The introduced patch-wise defect detection methods, designed to leverage less labeled data, prove effective for industrial defect detection, meeting the given process requirements. In this context, we propose an industry-applicable and scalable data preprocessing workflow that minimizes the overall labeling effort while maintaining high detection performance, as known in supervised settings. Moreover, the presented methods, not relying on any labeled defective training data, outperformed a state-of-the-art unsupervised anomaly detection method in terms of defect detection performance and inference speed.

Microstructural and mechanical properties of TiN/CrN and TiSiN/CrN multilayer coatings deposited in an industrial-scale HiPIMS system: Effect of the Si incorporation - Sala, Neus; Rebelo de Figueiredo, Marisa; Franz, Robert; Kainz, Christina; Sánchez-López, J.C.; Rojas, T.C.; Fernández de los Reyes, D.; Colominas, Carles; Abdad, M.D. (Surface & coatings technology, 2024)
Surface engineering through the deposition of advanced coatings, particularly multilayer coatings has gained significant interest for enhancing the performance of coated parts. The incorporation of Si into TiN coatings has shown promise for improving hardness, oxidation resistance, and thermal stability, while high-power impulse magnetron sputtering (HiPIMS) has emerged as a technique to deposit coatings with exceptional properties. However, TiN/CrN and TiSiN/CrN coatings deposited by HiPIMS remain relatively unexplored. In this study, different TiN/CrN and TiSiN/CrN multilayer coatings with different bilayer periods from 5 to 85 nm were deposited using an industrial-scale HiPIMS reactor, and their microstructure and mechanical properties were investigated using advanced characterization techniques. Results revealed successful deposition of smooth and compact coatings with controlled bilayer periods. X-ray diffraction analysis showed separate crystalline phases for coatings with high bilayer periods, while those with smaller bilayer periods exhibited peak-overlapping and superlattice overtones, especially for the TiN/CrN coatings. Epitaxial grain growth was confirmed by high-resolution transmission electron microscopy (HRTEM). HRTEM and electron energy-loss spectroscopy measurements confirmed Si incorporation into the TiN crystal lattice of TiSiN/CrN coatings reducing the crystallinity, especially for coatings with smaller bilayer periods. Nanoindentation tests revealed that coatings with a bilayer period of 15–20 nm displayed the highest hardness values regardless of the composition. The mechanical properties of the TiSiN/CrN coatings showed no improvement over those of the TiN/CrN coatings, attributed to the Si induced amorphization of the Ti(Si)N phase and the absence of SiN x phase segregation within the TiN nanocrystals in these coatings. These findings provide valuable insights into the microstructure and mechanical properties of TiN/CrN and TiSiN/CrN multilayer coatings deposited by HiPIMS in an industrial scale reactor, paving the way for their application in various industrial sectors.
Publisher Copyright: © 2024 Elsevier B.V.
Keywords: Hardness; Industrial HiPIMS deposition system; Multilayer coatings; Superlattice; TiN/CrN; TiSiN/CrN

Strong high-density composites from wheat straw - Neudecker, Felix; Veigel, Stefan; Bodner, Sabine; Keckes, Jozef; Duchoslav, Jiri; Stifter, David; Gindl-Altmutter, Wolfgang (Composites Part A: Applied Science and Manufacturing, 2024)
Wheat straw represents a promising resource for structural materials due to its inherent strength and availability as an underutilized agricultural by-product. However, structural features such as small diameters and a hollow, low-density design, as well as a hydrophobic, waxy surface layer, hinder conventional processing. We present an approach to overcome these hindrances by engineering delignified and densified straw strands into a mechanically strong unidirectional composite material. Wheat straw split into strands along the fiber direction was subjected to water-based and mild alkaline pre-treatments and subsequently densified. As a result, the average tensile strength and modulus of elasticity of straw strands improved to impressive 466 MPa and 26 GPa, respectively. Simultaneously, chemical changes to the surface enabled better adhesive bonding. The resulting unidirectional straw composites exhibited a flexural strength of 190 MPa and an elastic modulus of 20 GPa, well within the range of established wood and bamboo-based materials.
Publisher Copyright: © 2024 The Author(s)
Keywords: Biocomposite; Mechanical properties; Strand; Surface analysis

Hydrocarbon potential and depositional environment of the Middle Miocene Balikpapan Formation, lower Kutai Basin, Indonesia - Jamaluddin, null; Wagreich, Michael; Schöpfer, Kateřina; Sachsenhofer, Reinhard F.; Maria, Jon Paul; Rahmawati, Diana (International journal of coal geology, 2024)
The Middle Miocene Balikpapan Formation is exposed in the Samarinda Anticlinorium, which forms part of the Lower Kutai Basin situated on East Kalimantan, Indonesia. The Balikpapan Formation is considered the main source rock for oil and gas fields in Lower Kutai Basin. This study integrates sedimentology, organic geochemistry, organic petrography and calcareous nannofossil analysis to characterize the depositional environment, to determine the source of the organic matter, and to assess the hydrocarbon potential of the Balikpapan Formation. The studied sections contain at one locality calcareous nannofossil assemblages with low diversity including Sphenolithus heteromorphus, suggesting nannofossil zones NN4 – NN5 (upper Burdigalian - Langhian-lower Serravallian) are restricted to the Air Putih section in the northeastern part of the study area. Six facies associations were identified in the study area, comprising eleven lithofacies, interpreted as fluvial-deltaic to shallow marine in origin. The fine-grained lithofacies include shale, coaly shale and coal while the coarse-grained facies include sandstone and sandy conglomerates. The geochemical results (TOC) indicate that the analyzed samples have strongly varying total organic carbon (TOC) contents. The organic matter is composed of type III (gas-prone) and type II-III (mixed oil and gas prone) kerogen, with HI values ranging from 32 to 252 mg HC/g TOC. The Rock-Eval parameter Tmax 409–441 °C and vitrinite reflectance values (0.40–0.67 %Rr) indicate that the sediments are immature to marginal mature. The rank of coal in the Balikpapan Formation ranges from the sub-bituminous to the high-volatile bituminous B stage.
Publisher Copyright: © 2024
Keywords: Balikpapan Formation; Depositional environment; Hydrocarbon potential; Lower Kutai Basin; Middle Miocene

A bio-reactive transport model for biomethanation in hydrogen underground storage sites - Minougou, Jean Donald; Azizmohammadi, Siroos; Gholami, Raoof; Ott, Holger (Greenhouse Gases: Science and Technology, 2024)
Underground biomethanation, which relies on the subsurface microbial activity to convert hydrogen and carbon dioxide into methane, is a promising approach to support carbon capture, utilization, and storage technology. The process involves injecting hydrogen with captured CO2 into depleted oil and gas reservoirs or aquifers colonized by hydrogenotrophic methanogens that can convert these two substrates into methane. Despite the attractiveness of this technology, there are still uncertainties about the efficiency of the conversion process, particularly the impact of microbial parameters. To investigate the efficiency of the hydrogen conversion process, we relied on a bio-reactive transport model that can mimic microbial growth and decay, consumption of substrates, and transport of reactants and products. It was found that the methane concentration peaks near the injection well when the hydrogen fraction is in the range of 75% to 80% of the injected gas composition. In addition, a noticeable hydrogen sulfide concentration can be produced due to sulfide ions in the brine. Using the Kozeny-Carman relation, an attempt was made to correlate microbial growth with reduced porosity and permeability. It was then revealed that substrate consumption by microbes leads to a drastic increase in the microbial population in the subsurface, which can reduce the petrophysical properties of the reservoir, especially in the near wellbore area. The results obtained from a series of parametric analyses showed that the hydrogen concentration in the injected gas, pressure, well spacing, and injection rate are some of the most important parameters contributing to the biomethanation process.
Publisher Copyright: © 2024 The Author(s). Greenhouse Gases: Science and Technology published by Society of Chemical Industry and John Wiley & Sons Ltd.
Keywords: bio-reactive transport; carbon capture and utilization; microbial H conversion; numerical reservoir sumulation; renewable methane; underground hydrogen storage

Nanoscale stress and microstructure gradients across a buckled Mo-Cu bilayer: Cu self-annealing triggered by interface delamination - Lassnig, Alice; Todt, Juraj; Tkadletz, Michael; Žák, Stanislav; Mitterer, Christian; Medjahed, Asma Aicha; Burghammer, Manfred; Keckes, Jozef; Cordill, Megan J.; Meindlhumer, Michael (Acta Materialia, 2024)
Residual stresses in thin film structures significantly impact their mechanical properties and affect interface delamination. Highly compressively stressed thin films buckling is the predominant interfacial failure mode due to strain energy release. In the present study the effect of cross-sectional stress and microstructural gradients of thin films on the buckling behavior are explored in a model material system consisting of a thin Cu film sputtered onto glass and a highly compressively stressed 500 nm thick Mo overlayer causing buckling delamination at the Cu-glass interface. Employing synchrotron cross-sectional X-ray nano-diffraction, multiaxial X-ray elastic strain and microstructure distributions were explored across the cross-section of the adhering and buckled bilayer, respectively. In the adhering state, a gradual thickness evolution of columnar microstructure and residual stress was found for Mo, while in Cu, no microstructure changes and only minimal stress variations were detected along the film thickness. After delamination, diffraction peak broadening and changes in unstrained lattice parameters in the Cu sublayer indicated structural defect annihilation and grain coarsening. These microstructural changes were further validated via cross-sectional transmission electron microscopy. The evaluated residual stress distributions across the two sublayers of the pristine and buckled bilayer were used to quantify the released strain energy per unit area due to buckling, amounting to 0.61 J/m². Further cross-validation of experimental stress results with finite element simulations strengthened the experimental findings, providing a comprehensive understanding of the stress distribution across the buckled bilayer.
Publisher Copyright: © 2024 The Authors
Keywords: Thin films; buckle type delamination; high resolution stress gradients; transmission electron microscopy; Cross-sectional X-ray nanodiffraction; buckle type delamination; high resolution stress gradients; Thin films; transmission electron microscopy, cross-sectional X-ray nanodiffraction

The stochastic Klausmeier system and a stochastic Schauder-Tychonoff type theorem - Hausenblas, Erika; Tölle, Jonas M. (Potential analysis, 2024)
On the one hand, we investigate the existence and pathwise uniqueness of a nonnegative martingale solution to the stochastic evolution system of nonlinear advection-diffusion equations proposed by Klausmeier with Gaussian multiplicative noise. On the other hand, we present and verify a general stochastic version of the Schauder-Tychonoff fixed point theorem, as its application is an essential step for showing existence of the solution to the stochastic Klausmeier system. The analysis of the system is based both on variational and semigroup techniques. We also discuss additional regularity properties of the solution.
Publisher Copyright: © The Author(s) 2023.
Keywords: Stochastic Klausmeier evolution system; Stochastic Schauder-Tychonoff type theorem; Pattern formation in ecology; Nonlinear stochastic partial differential equation; Flows in porous media, pathwise uniqueness; 47H10; 92C15; 37N25; 76S05; 35K57; 60H15

Chalcopyrite, sphalerite, and pyrite chemistry in stratiform sediment-hosted Cu(-Co) metallogenic districts: trace element characteristics and factors controlling polymetallic mineralization - Bertrandsson Erlandsson, Viktor; Foltyn, Krzysztof; Muchez, Philippe; Rantitsch, Gerd; Ellmies, Rainer; Melcher, Frank (Mineralium deposita, 2024)
Stratiform sediment-hosted Cu deposits are significant global sources of Cu and other important metals. The Polish Kupferschiefer produces Ag, Au, Pb, Ni, Se, and Re as by-products, whereas Co is one the of most important metals in the stratiform sediment-hosted Cu-Co deposits of the Central African Copperbelt and the Namibian Dolostone Ore Formation deposit. This study combines new and published laser ablation inductively coupled plasma mass spectrometry sulfide trace element data from these stratiform sediment-hosted copper districts. All the investigated districts exhibit sulfides occurring as disseminations and within later veins. Chalcopyrite, sphalerite, and pyrite trace element contents vary significantly between the metallogenic districts as well as between different ore stages. Random Forest discriminates the stratiform sediment-hosted Cu(-Co) districts based on trace element geochemistry. High Ag and Tl in chalcopyrite is attributed to the Polish Kupferschiefer, Ga and Ge to the Katanga Copperbelt, and Zn and In to the Dolostone Ore Formation deposit. Sphalerite from the Polish Kupferschiefer and the Dolostone Ore Formation deposit can be distinguished on the basis of the Fe and Cd contents. Cobalt and As are significantly elevated in pyrite from the Katanga Copperbelt and Mn in pyrite from the Dolostone Ore Formation deposit. The trace element contents also show that the stratiform sediment-hosted Cu(-Co) deposit sulfide data cluster separately from other deposit types. The variation in sulfide trace element contents between the three investigated stratiform sediment-hosted Cu(-Co) districts suggests that sulfide chemistry is related to the geology of the host basin and the nature of the underlying basement, which includes preexisting ore occurrences.
Publisher Copyright: © The Author(s) 2024.
Keywords: Central African Copperbelt; Dolostone Ore Formation; Kupferschiefer; LA-ICP-MS; Machine learning; Random Forest classification; Sulfides; Trace elements

Development of a self-consistent CALPHAD-database for solidification simulation of advanced steel grades by combining experimental studies and computational thermodynamics - Bernhard, Michael Christian; Presoly, Peter; Littringer, Robert; Bernhard, Christian; Kang, Youn-Bae (2024)

Enhanced thermomechanical fatigue resistance in W10Re alloys: Microstructural and surface engineering approaches - Sommerauer, Michael; Seligmann, Benjamin; Gottlieb, Hannah; Hohenwarter, Anton; You, Jeong-Ha; Bostrom, Neil; Pippan, Reinhard; Siller, Maximilian; Maier-Kiener, Verena (Nuclear Materials and Energy, 2024)
Thermomechanical fatigue of refractory metals is commonly observed in high-temperature environments like first walls and divertors for proposed fusion reactors or X-ray anodes for medical imaging. Typically, alloying with rhenium or optimized microstructures are employed to counteract or delay the detrimental effects of fatigue in tungsten. Additionally, a novel concept is the utilization of surface structures to compensate cyclic thermal stresses. This work aimed to investigate the combination of these approaches, by comparing two W10Re alloys with vastly different microstructures, as well as engineered surface conditions of varying scales. Samples were subjected to thermocyclic fatigue under pulsed electron beam exposure, mimicking the surface temperatures typically encountered in a rotating X-ray anode. Analysis of several in-situ data streams, post-mortem investigations by metallography, and finite element methods revealed the interplay between microstructure and surface modifications. The columnar microstructure exhibited higher resistance to severe surface damage compared to the globular one, linked to the deflection of cracks along grain boundaries and subsequent melting. Coarse structuring was found to partly relieve the surface stresses during thermal cycling, preventing most of the damage accumulation. A full damage relief and performance equivalence between columnar and globular microstructure was achieved by engineering fine-structured surfaces, which led to a ten-fold increase in fatigue resistance over the non-structured condition.

Integrating Environmental, Social and Governance Aspects into Mine Plans - Haindl, Angelika (SME-Connecting Mining: GenZ and Beyond, 2024)
Keywords: ESG; Mine Planning

Magnetic Railway Sleeper Detector - Heindler, Lukas; Hüttmayr, Harald; Thurner, Thomas; Zagar, Bernhard (Electronics, 2024)
In an ever expanding railway network all around the world, the need for track maintenance grows steadily. Traditionally, one major part of track maintenance is ramming large vibrating steel picks into the gravel between and under railway sleepers to compress the gravel and generate a safe substructure. Even today, maintenance personnel still have to manually locate the sleepers if they cannot be detected by computer vision systems or visually by the operator. Here we developed a first of its kind magnetic sleeper detector, even able to find sleepers, buried in gravel, undetectable by vision based systems. Our approach of magnetic detection is based on a DC magnetic field excitation and a detector moving with respect to the rail system, including the sleepers and fasteners for mounting the rails. Due to railway application constraints a large air gap between the sensor and the sleeper structure is required, which significantly complicates the magnetic sensing task for robust sleeper detection. The design and optimization of the magnetic circuit was based on extensive 3D simulation studies to ensure highest possible variation in magnetic flux density at the sensor locations for absence and presence of a sleeper. Furthermore, a low noise and high sensitivity electronic circuit has been realized to cope with sensor signal offsets from unknown or changing sensor orientations with respect to the earth’s magnetic field, or magnetic interferences from other trains potentially passing by during active measurements. Since we only want to detect sleepers in close vicinity of the moving sensor system, digital signal processing of the acquired signals can easily compensate for disturbing slowly changing or static field components within real world application scenarios. We demonstrate that magnetic detection of even buried sleepers on railway tracks is possible for distances of up to 172 mm between the sensor and the sleeper. This enables an even higher level of railway maintenance automation previously impossible in certain scenarios.
Keywords: magnetic sensing; railway maintenance; Hall effect sensor; magnetic anomaly detection

How reduction temperature influences the structure of perovskite-oxide catalysts during the dry reforming of methane - Schrenk, Florian; Lindenthal, Lorenz; Drexler, Hedda; Berger, Tobias; Rameshan, Raffael; Ruh, Thomas; Föttinger, Karin; Rameshan, Christoph (RSC sustainability, 2024)
Dry reforming of methane is a promising reaction to convert CO2 and combat climate change. However, the reaction is still not feasible in large-scale industrial applications. The thermodynamic need for high temperatures and the potential of carbon deposition leads to high requirements for potential catalyst materials. As shown in previous publications, the Ni-doped perovskite-oxide Nd0.6Ca0.4Fe0.97Ni0.03O3 is a potential candidate as it can exsolve highly active Ni nanoparticles on its surface. This study focused on controlling the particle size by varying the reduction temperature. We found the optimal temperature that allows the Ni nanoparticles to exsolve while not yet enabling the formation of deactivating CaCO3. Furthermore, the exsolution process and the behaviour of the phases during the dry reforming of methane were investigated using in situ XRD measurements at the DESY beamline P02.1 at PETRA III in Hamburg. They revealed that the formed deactivated phases would, at high temperatures, form a brownmillerite phase, thus hinting at a potential self-healing mechanism of these materials.
Publisher Copyright: © 2024 RSC.

Machine learning assisted calibration of PVT simulations for SiC crystal growth - Taucher, Lorenz; Ramadan, Zaher; Hammer, René; Obermüller, Thomas; Auer, Peter; Romaner, Lorenz (CrystEngComm, 2024)
Numerical simulations are frequently utilized to investigate and optimize the complex and hardly in situ examinable Physical Vapor Transport (PVT) method for SiC single crystal growth. Since various process and quality-related aspects, including growth rate and defect formation, are strongly influenced by the thermal field, accurately incorporating temperature-influencing factors is essential for developing a reliable simulation model. Particularly, the physical material properties of the furnace components are critical, yet they are often poorly characterized or even unknown. Furthermore, these properties can be different for each furnace run due to production-related variations, degradation at high process temperatures and exposure to SiC gas species. To address this issue, the present study introduces a framework for efficient investigation and calibration of the material properties of the PVT simulation by leveraging machine learning algorithms to create a surrogate model, able to substitute the computationally expensive simulation. The applied framework includes active learning, sensitivity analysis, material parameter calibration, and uncertainty analysis.

Process intensification of the rWGS reaction by a perovskite-based catalyst - Markowitsch, Christoph; Andritz, Marion; Lindenthal, Lorenz; Cotter, Thomas; Drexler, Hedda; Rameshan, Christoph; Lehner, Markus (Chemical Engineering Journal, 2024)
The reverse water gas shift (rWGS) reaction represents a key technology for the utilization of CO2. This study presents experimental results which compare the performance of a commercially available nickel catalyst, two novel perovskite catalysts and Al2O3. In addition to the variations of the input gas composition, the operating conditions have been adjusted between 550 and 950 °C and 1 to 8 bara. The results reveal, on the one hand, that the nickel catalyst achieves thermodynamic equilibrium, resulting in high selectivity toward CO formation at elevated temperatures (950 °C) and pressures up to 6 bara. Higher catalyst loads suppress methane formation at certain operating points. On the other hand, the perovskite catalyst prevents methane formation even at low temperature (550 °C) and higher pressures up to 8 bara favor the CO formation. In consequence, methane formation is limited to less than 2 vol-% at 650 °C and 8 bara and the CO content in the product gas is significantly higher compared with the nickel catalyst. Al2O3 also shows catalytic activity and approaches to thermodynamic equilibrium at high temperature (950 °C) and 6 bara. The investigated novel perovskite catalysts have the potential to intensify the rWGS reaction towards a simpler reactor design and a highly efficient operation, also on a large-scale basis.
Keywords: Reverse water gas shift (rWGS); Catalyst performance; Nickel catalyst; Perovskite catalysts; rWGS process intensification

A 2D – finite volume solidification software for real-time simulation of continuous slab casting - Kavic, Daniel; Bernhard, Michael Christian; Wieser, Gerhard; Taferner, Matthias; Ilie, Sergiu; Bernhard, Christian (2024)

Neue Ansätze zur Berücksichtigung des Korrosionseinflusses auf die Schwingfestigkeit von Aluminium-Bauteilen - Schönowitz, Markus; Oberreiter, Peter; Maier, Bernd; Grun, Florian (50. DVM Tagung: Betriebsfestigkeit nicht mehr relevant? - oder der Schlüssel für eine sichere und nachhaltige Zukunft!, 2024)

Editorial - Williams, Edward A.; Meisel, Thomas C. (Geostandards and Geoanalytical Research, 2024)

Experimental and numerical study on MnS stability and its influence on the solidification progress in continuous slab casting of steel - Littringer, Robert; Bernhard, Michael Christian; Presoly, Peter; Kang, Youn-Bae; Ilie, Viorel-Sergiu; Bernhard, Christian (2024)

Impact of surface oxidation on the role of tramp elements for surface quality in slab casting and endless strip production processes - Presoly, Peter; Gaiser, Georg; Littringer, Robert; Bernhard, Christian; Baumgartner, Kerstin; Grosseiber, Simon; Ilie, Sergiu (2024)
Oxidation processes, which are unavoidable in continuous casting and further hot processing of steel may have a negative impact on the surface quality. In view of the changes in the mix of input materials associated with the decarbonization of steel production, understanding the mechanisms behind high-temperature oxidation is of great importance: The interaction between external oxidation and internal oxidation, decarburization and liquid metal infiltration of grain boundaries will become essential for the retention of product quality under new operating conditions. These effects are influenced by parameters such as oxidation time, temperature, atmosphere and the chemical composition of the steel. Due to higher recycling rates of steel and the associated downscaling of scrap qualities, the issue of rising levels of tramp elements in steel is becoming a key topic, as elements such as Cu, Sn and Ni do not oxidize but accumulate at the bulk/scale interface or along grain boundaries which may lead to additional quality problems.To address these newly arising research questions a lab test setup was established: Utilizing Simultaneous-Thermal-Analysis in combination with various gas atmospheres (CO2, up to 100 vol.% H2O, N2, O2, Ar) a precise simulation of surface oxidation in a wide variety of metallurgical processes became possible. The present paper addresses results on the behavior of different carbon steel grades with varying content of tramp elements (Cu, Sn, Ni) under the conditions of slab casting (CC), thin slab casting and direct rolling (TSCR) in batch and endless mode as well as the reheating in pusher type and tunnel furnaces. Combustion atmospheres of natural gas and hydrogen were tested.The results provide a view on the potential quality problems arising with the forthcoming dynamic changes of steel composition and the need for an adoption of process routes and process conditions.
Keywords: Oxidation; tramp elements; Simultaneous thermal analysis

The role of Cu, Sn, and Ni on surface crack formation in continuous casting - Gaiser, Georg; Bernhard, Christian; Winkler, Johann; Lex, Christoph; Ilie, Sergiu; Hahn, Susanne; Burzic, Denijel (10th European Continuous Casting Conference 2024, 2024)
The decarbonization of steel production processes will lead to the increased use of scrap - including low-grade scrap - in the future. In addition to the more difficult control of some residuals in electric arc furnace steelmaking, tramp elements could also lead to problems in the manufacturing processes. In continuous casting, tramp elements such as Cu and Sn may cause network cracking and the so-called Cueq is still the most common indicator for surface defect susceptibility. This study addresses the experimental simulation of surface defect formation and the role of Cu, Sn, and Ni for the temperatures 900 and 1100 °C. Its goal is to define an optimized operational window for continuous casting. Experiments were conducted utilizing the in-situ material characterization by bending (IMC-B) test which characterizes the crack sensitivity of steel after controlled solidification and subsequent cooling under an adjustable water vapor atmosphere. The tests were performed on medium carbon steel with varying but moderate concentrations of Cu, Sn, and Ni. Results indicate that the simultaneous presence of Cu and Sn leads to a notable increase in the occurrence of surface cracks. This is attributable to the formation of partially liquid phases in the area of the grain boundaries due to selective oxidation. However, the introduction of Ni into the alloy composition demonstrates a substantial improvement in crack mitigation. This finding emphasizes the importance of carefully managed tramp element content, particularly Cu and Sn in the continuous casting process to minimize crack formation during straightening but also indicates a strong influence of thermal history and bending temperatures.

Dispersoid evolution in Al–Zn–Mg alloys by combined addition of Hf and Zr - Wessely, V.; Töpfer, U.; Basu, I.; Schäublin, Robin E.; Pogatscher, Stefan; Uggowitzer, Peter; Löffler, J. F. (Materials and Design, 2024)
Coherent Al3X-type L12-structured dispersoids have the potential of effectively stabilizing the grain structure and increasing strength. This concept has been successfully demonstrated for non-hardenable and rapidly solidified Al alloys. In precipitation-hardened Al alloys, effective dispersoid addition requires both controlling their high-temperature stability and minimizing their impact on precipitation hardening. The current study focuses on dispersoid-modified AlZn5.0Mg1.2 alloys, which exhibit MgZn precipitation upon age-hardening and include less than 1 wt% of Zr and Hf for dispersoid formation. Heat treatments between 350 °C and 500 °C for varying times were applied to evaluate dispersoid formation, thermal stability and the related strengthening potential. The microstructure was assessed using transmission electron microscopy (TEM) and atom probe tomography (APT), and the mechanical response was evaluated by hardness testing. TEM after heating at 500 °C reveals Ostwald ripening for the dispersoids. APT results on the dispersoids reveal a core–shell structure development upon longer annealing times. The Zr–Hf-modified alloy exhibits a higher initial strength than the Zr-modified alloy but the latter displays greater strength retention even after prolonged exposure to 500 °C. This effect is attributed to a destabilization of the mixed Zr–Hf dispersoids that arises from lower enthalpic benefits of Al3Hf formation over Al3Zr.
Publisher Copyright: © 2024 The Authors
Keywords: Aluminum alloys; Atom probe tomography; Image analysis; L1 precipitates; Strengthening mechanisms; Transmission electron microscopy

Fatigue Life Assessment of Corroded AlSi10MgMn Specimens - Schönowitz, Markus; Fladischer, Stefan; Oberreiter, Peter; Maier, Bernd; Grün, Florian; Bauer-Troßmann, Kathrin (Metals : open access journal, 2024)
This study investigates the influence of pre-corrosion damage on the fatigue behaviorof AlSi10MgMn high-pressure die-cast specimens, using the statistical distribution of corrosiondepths. The analysis is conducted on two different surface conditions: an unmachined roughsurface (Ra = 5.05 μm) and a machined, polished surface (Ra = 0.25 μm). For the unmachinedspecimens, the corrosive damage manifests as homogeneously spread localized corrosion, whereasthe polished specimens exhibit less uniform but deeper corrosion. The average corrosion depth of thepolished specimens is found to be slightly higher (313 μm compared to 267 μm) with a broader depthdistribution. Specimens are tested under a constant bending load amplitude in laboratory conditionsat a stress ratio of R = 0 until fracture. A fracture mechanics-based methodology is developedto assess the remaining fatigue life of corroded specimens, utilizing short and long crack fracturemechanical parameters derived from SENB specimens. This model incorporates a thickness reductionof the critical specimen cross-section based on the corrosion depth distribution and combines it witha small initial crack of the intrinsic defect size (ae f f = 14 μm). Regardless of the surface condition,using the most frequent corrosion depth for thickness reduction provides a good estimate of thelong-life fatigue strength, while using the 90th percentile depth allows for a conservative assessment.

Ins Blaue hinein - Melcher, Frank (2024)

Effect of Epoxy Chain Extender and Multiple Processing on Poly-(R)-3-Hydroxybutyrate’s Properties - Hinterberger, Klaus; Main, Priyanka; Waly, Christoph; Lucyshyn, Thomas (Journal of polymers and the environment, 2024)
The semi-crystalline poly-(R)-3-hydroxybutyrate (PHB) is a biobased and biodegradable polymer. This makes it a promising alternative to polypropylene (PP), especially for packaging applications. PHB has excellent barrier properties to O2, CO2, and H2O, but is susceptible to degradation from heat and hydrolysis. The epoxy chain extender Joncryl® was added to PHB in a simulated recycling process to reverse the degradation due to processing. The effects of the chain extender and the degradation due to processing were investigated with thermal gravimetric analysis (TGA), differential scanning calorimetry (DSC), small strain oscillatory plate-plate rheometry, tensile tests, and notched Charpy impact tests. With the addition of the chain extender, a decrease in peak crystallization temperature and tensile modulus, and an increase in zero-shear viscosity and elongation at break were observed. For each additional processing step the zero-shear viscosity, the elongation at break, and the notched impact strength decreased, while the tensile modulus increased. The effect of the thermal load during processing on the material properties is significantly higher compared to the effect of the addition of the chain extender. Therefore, the practical application of the investigated chain extender alone in a multi-stage recycling process seems limited. This is due to the low processing temperature of PHB, which seems to limit the full potential of Joncryl® due to the slow reaction speed at this temperature.
Publisher Copyright: © The Author(s) 2024.
Keywords: Biobased biodegradable polymer; Circular economy; Epoxy chain extender; Mechanical recycling; PHB

Predicting condition states, based on displacement data, generated by acceleration sensors on industrial linear vibrating screens through neural networks - Krukenfellner, Philip; Rückert, Elmar; Flachberger, Helmut (IEEE sensors journal, 2024)
Vibrating screens are crucial in the waste and mineral processing industries. However, they often lack comprehensive digital monitoring, which necessitates subjective condition assessments. This study introduces a system developed in cooperation with IFE Aufbereitungstechnik GmbH that provides an objective machine state evaluation using permanently installed acceleration sensors, developed by eSensial Data Science GmbH. Unlike previous research, data for this project were collected from a linear vibrating screen, which is operating in a waste processing plant, introducing uncertainties and occasionally missing data due to sensor damage to the analysis. The study focuses on applying supervised machine learning algorithms to predict the machine's operating condition. In particular, decision trees, multilayer perceptron (MLP) networks, and long-short-term memory (LSTM) networks that were evaluated using classical performance metrics such the MSE and the R2-Score. The models were also tested with respect to missing input data. The MLP network achieved a prediction accuracy of over 90%. Further, it displayed the ability to determine previously unlabeled intermediate states. Additionally, the main cause of prediction errors was identified and a method of handling missing input data was developed.
Publisher Copyright: © 2001-2012 IEEE.
Keywords: Machine Learning; Aufbereitung; Sensoren; Schwingsiebe; Schwingungsüberwachung; Abfallaufbereitung; Machine learning; Mineral Processing; Sensors; Vibrating Screens; Vibratoin Monitoring; Waste processing; Vibration monitoring; Vibrating screens; Mineral processing

Unveiling the Effect of Grain Size on Biodegradation of Magnesium - Medeiros, Mariana P.; Lopes, Debora R.; Carvalho, Amanda P.; Hohenwarter, Anton; Kawasaki, Megumi; Cupertino-Malheiros, Livia; Figueiredo, Roberto Braga (Advanced Engineering Materials, 2024)
It is known that the grain size plays a major role in the mechanical properties of magnesium. The aim of the present study is to evaluate its role in long-term corrosion rate. Samples of pure magnesium with grain sizes in the range of 0.9–82 μm are produced through severe plastic deformation and annealing treatments. The mechanical properties are evaluated using tensile tests and the corrosion behavior is evaluated using immersion tests in Hank's solution. A maximum yield stress of ≈150 MPa is observed in the sample with 1.8 μm of grain size and an elongation larger than 25% is observed in the ultrafine-grained sample. Ultrafine- and fine-grained magnesium display uniform corrosion with a decreasing corrosion rate while coarse-grained magnesium displays localized corrosion with an accelerated corrosion rate. A corrosion rate of ≈0.2 mm year−1 is observed in the ultrafine- and fine-grained magnesium. The corrosion product layer of the fine-grained magnesium contains elements absorbed from the media. An analysis of the data in the literature suggests that grain refinement changes the corrosion type from localized to uniform corrosion. The exact relationship between grain size and the corrosion rate remains elusive.
Publisher Copyright: © 2024 Wiley-VCH GmbH.
Keywords: biodegradations; corrosion; grain sizes; magnesium

Hydrogen induced changes in the phase composition and micro-structure of downhole cements - Sammer, Thomas; Kostoglou, Nikolaos; Ravi, Krishna; Raith, Johann G. (International Journal of Hydrogen Energy, 2024)
Underground hydrogen storage (UHS) promises great storing potential for energy produced from renewables. To make UHS a feasible and safe process, fundamental research investigating the integrity of the cement sheath applied in boreholes against hydrogen exposure is essential. In this study, hydrothermal autoclave experiments are conducted to evaluate hydrogen induced changes in the mineralogical phase composition and the microstructure of a class G cement. X-ray diffraction and scanning electron microscopy combined with nitrogen adsorption/desorption experiments are carried out. Only minor mineralogical changes are observed such as the decomposition of monosulphate and the formation of ettringite. Nitrogen adsorption/desorption experiments reveal comparable pore size distributions with minor differences in porosity and surface area. The findings of this study suggest that hydrogen does not substantially affect the phase composition and microstructure of the investigated low permeable class G cement sheath emphasizing the relatively unreactive nature of downhole cements of this type against hydrogen.
Publisher Copyright: © 2024 The Authors
Keywords: Cement sheath integrity; Cement-hydrogen interaction; Mineralogical phase analysis; Underground hydrogen storage

Optimized Integration of Medium-Voltage Multimegawatt DC Charging Stations - Biswas, Sumanta; Gerald, Cham Kpu; Herndler, Barbara; Stahleder, Daniel; Wimmer, Yannick; Makoschitz, Markus (World electric vehicle journal, 2024)
The integration of multimegawatt fast chargers into local distribution grids is becoming increasingly relevant due to recent initiatives to push for higher charging power, especially for applications like heavy-duty vehicles. However, the high-power capacity of these chargers, especially when multiple units operate simultaneously at specific locations, raises several important considerations for the optimal design and integration of multimegawatt fast chargers. These include, for example, power electronics architectures and dedicated designs, grid stability, and the incorporation of renewable energy systems. Thus, this paper provides a comprehensive analysis of the key factors influencing the optimal integration of these ultra-high-power chargers, looking into impacts on medium-voltage (MV) networks, the design considerations for medium-voltage power electronics in DC chargers, and the potential of renewable energy systems to offset grid demand. Additionally, this paper explores the potential high-level communication requirements necessary for efficient and reliable charger operation, including a proposal for a robust communication interface layer stack. This investigation aims to provide a holistic understanding of the challenges and opportunities associated with integrating multimegawatt fast chargers into existing power systems, offering insights into the enhancement of both performance and sustainability.
Publisher Copyright: © 2024 by the authors.
Keywords: battery storage systems; communication strategies; distribution grid; medium-voltage megawatt charging stations; power electronics; renewable energy systems

Synthesis and Characterization of Rebondable Polyurethane Adhesives Relying on Thermo-Activated Transcarbamoylation - Bautista-Anguís, Daniel; Reiner, Lisbeth; Röper, Florian; Maar, Sebastian; Wolfahrt, Markus; Wolfberger, Archim; Schlögl, Sandra (Polymers, 2024)
Dynamic polymer networks combine the noteworthy (thermo)mechanical features of thermosets with the processability of thermoplastics. They rely on externally triggered bond exchange reactions, which induce topological rearrangements and, at a sufficiently high rate, a macroscopic reflow of the polymer network. Due to this controlled change in viscosity, dynamic polymers are repairable, malleable, and reprocessable. Herein, several dynamic polyurethane networks were synthetized as model compounds, which were able to undergo thermo-activated transcarbamoylation for the use in rebondable adhesives. Ethylenediamine-N,N,N′,N′-tetra-2-propanol (EDTP) was applied as a transcarbamoylation catalyst, which participates in the curing reaction across its four -OH groups and thus, is covalently attached within the polyurethane network. Both bond exchange rate and (thermo)mechanical properties of the dynamic networks were readily adjusted by the crosslink density and availability of -OH groups. In a last step, the most promising model compound was optimized to prepare an adhesive formulation more suitable for a real case application. Single-lap shear tests were carried out to evaluate the bond strength of this final formulation in adhesively bonded carbon fiber reinforced polymers (CFRP). Exploiting the dynamic nature of the adhesive layer, the debonded CFRP test specimens were rebonded at elevated temperature. The results clearly show that thermally triggered rebonding was feasible by recovering up to 79% of the original bond strength.
Publisher Copyright: © 2024 by the authors.
Keywords: adhesives; dynamic polymers; rebonding; thermo-activated transcarbamoylation; vitrimers

Direct aqueous mineral carbonation of secondary materials for carbon dioxide storage - Schinnerl, Florian; Sattler, Theresa Magdalena; Noori Khadjavi, Giv; Lehner, Markus (Journal of CO2 utilization, 2024)
Mineral carbonation of secondary materials offers an innovative way of storing carbon dioxide in materials that instead would mostly go to waste. This study investigates the carbonation efficiency (CE) of 11 different secondaries from refractory production, waste incineration, and the paper industry compared to untreated and thermally activated serpentinite. To determine the chemical and mineralogical composition of the materials, various analytical methods, like X-ray fluorescence, X-ray diffraction, scanning electron microscopy, Brunauer-Emmet-Teller and thermogravimetric analysis have been employed, both before and after the direct aqueous carbonation process. Each material was examined over reaction times of 6 & 10 hours at 180 ◦C and a starting pressure of 20 bar in a 0.6 L stainless steel batch reactor. The received results were then compared to the theoretical CO2 uptake, defined as the maximum carbon dioxide storage potential achievable if all Ca, Fe and Mg ions were converted to carbonates. The findings indicate carbonation efficiencies of 14–65 % for secondary materials, compared to 0.7–14 % observed in the serpentinite samples. The highest uptakes were achieved by the refractory materials, primarily due to their high metal oxide content. However, a negative impact was observed from graphite-based carbon binders in the refractories, with increased leaching of these binders leading to a decrease in carbonation efficiency. Materials with higher SiO2 content showed reduced performance, suggesting a passivation layer buildup during carbonation.
Publisher Copyright: © 2024 The Authors
Keywords: Direct mineral carbonation; secondary materials; industrial wastes; mineralogical analysis; carbonation efficiency; Mineralogical analysis; Industrial wastes; Direct aqueous carbonation; Secondary materials; Carbonation efficiency

A comparative analysis of the economic feasibility of reversible hydrogen systems based on time-resolved operation optimisation - Banasiak, David; Kienberger, Thomas (Applied energy, 2024)
The expansion of fluctuating renewable energy production, such as wind and PV, increases the mismatch to consumption. Power-to-Hydrogen-to-Power (PtHtP) systems are believed to be a key for balancing under and overproductions. PtHtP systems can provide temporal and spatial flexibilities and among them reversible solid oxide cells (rSOC) are a promising technology. They combine production of hydrogen and power in the same electrochemical stack. This generates a financial and environmental benefit since less resources are necessary for enabling both Power-to-Hydrogen and Hydrogen-to-Power. This work investigates the application of rSOC systems in comparison to reversible PEM systems consisting of electrolysis and fuel cell unit. In the present studies time-resolved optimization is employed for simulation of the optimal operation of the PtHtP technologies in different market price conditions for electricity, hydrogen and natural gas and with coupling to industry and district heat. Both systems have a zone of market prices, that allows for a positive economic performance over lifetime. The electricity‑hydrogen price difference in this zone is in the range from −83 €/MWh to 133 €/MWh depending on the scenario. Furthermore, the electricity price fluctuations are found to have the major impact on the profitability. By studying the influence of gas grid fees, one finds that local compressed hydrogen storages can be used only for very short storage timescales up to a few hours. Finally, the derivation of application conditions, that are suitable for the two different spatial kinds of reversible hydrogen systems – spatially concentrated and delocalized and the two technologies – rSOC and PEM, is made.
Publisher Copyright: © 2024
Keywords: rSOC; PEM electrolysis; power-to-gas-to-power; sector coupling; Energy Efficiency; techno-economic assessment; Sector coupling; PEM; Energy efficiency; Power-to-gas-to-power; Techno-economic

Characterisation of the Mechanical Properties of Natural Fibre Polypropylene Composites Manufactured with Automated Tape Placement - Legenstein, Alexander; Haiden, Lukas; Feuchter, Michael; Fauster, Ewald (Journal of composites science, 2024)
The integration of natural fibre thermoplastic composites, particularly those combining flax fibres with polypropylene, offers a promising alternative to traditional synthetic composites, emphasising sustainability in composite materials. This study investigates the mechanical properties of flax/polypropylene composites manufactured using flashlamp automated tape placement and press consolidation, individually and in combination. Tensile, compression, three-point bending, and double cantilever beam tests are utilised for comparing these manufacturing processes and the mechanical performance of the resulting composites. The microstructure of the tapes is investigated using cross-sectional microscopy, and the thermophysical behaviour is analysed utilising thermogravimetric analysis and differential scanning calorimetry. The temperature during placement is monitored using an infrared camera, and the pressure is mapped with pressure-sensitive films. The natural fibre tapes show a good aptitude for being manufactured with automated tape placement. The tensile performance of tapes manufactured with automated tape placement is close to that of press consolidated samples. Compression, flexural properties, and the mode I fracture toughness critical energy release rate all benefit from a second consolidation step.

Comprehensive Risk Analysis of Emergency Medical Response Systems in Serbian Healthcare - Cvetković, Vladimir; Tanasic, Jasmina; Renner, Renate; Rokvić, Vanja; Beriša, Hatidža (Healthcare, 2024)
Background/Objectives: Emergency Medical Response Systems (EMRSs) play a vital role in delivering medical aid during natural and man-made disasters. This quantitative research delves into the analysis of risk and effectiveness within Serbia’s Emergency Medical Services (EMS), with a special emphasis on how work organization, resource distribution, and preparedness for mass casualty events contribute to overall disaster preparedness. Methods: The study was conducted using a questionnaire consisting of 7 sections and a total of 88 variables, distributed to and collected from 172 healthcare institutions (Public Health Centers and Hospitals). Statistical methods, including Pearson’s correlation, multivariate regression analysis, and chi-square tests, were rigorously applied to analyze and interpret the data. Results: The results from the multivariate regression analysis revealed that the organization of working hours (β = 0.035) and shift work (β = 0.042) were significant predictors of EMS organization, explaining 1.9% of the variance (R2 = 0.019). Furthermore, shift work (β = −0.045) and working hours (β = −0.037) accounted for 2.0% of the variance in the number of EMS points performed (R2 = 0.020). Also, the availability of ambulance vehicles (β = 0.075) and financial resources (β = 0.033) explained 4.1% of the variance in mass casualty preparedness (R2 = 0.041). When it comes to service area coverage, the regression results suggest that none of the predictors were statistically significant. Based on Pearson’s correlation results, there is a statistically significant correlation between the EMS organization and several key variables such as the number of EMS doctors (p = 0.000), emergency medicine specialists (p = 0.000), etc. Moreover, the Chi-square test results reveal statistically significant correlations between EMS organization and how EMS activities are conducted (p = 0.001), the number of activity locations (p = 0.005), and the structure of working hours (p = 0.001). Conclusions: Additionally, the results underscore the necessity for increased financial support, standardized protocols, and enhanced intersectoral collaboration to strengthen Serbia’s EMRS and improve overall disaster response effectiveness. Based on these findings, a clear roadmap is provided for policymakers, healthcare administrators, and EMS personnel to prioritize strategic interventions and build a robust emergency medical response system.
Keywords: risk; Serbian healthcare; vulnerabilities; emergency medical response systems; effectiveness; emergency preparedness; disaster

Overview on aluminium alloys as sinks for end-of-life vehicle scrap - Pogatscher, Stefan; Samberger, Sebastian (IOP Conference Series: Materials Science and Engineering, 2024)
A fundamental principle in metallurgy is that the higher the purity of metals and alloys, the more favourable their properties will be. However, as the recycling of materials in production becomes increasingly significant, the levels of impurities are also on the rise. In the case of aluminium, the consequences can be detrimental due to the low solubility of most elements in this metal, which leads to the formation of brittle intermetallic phases (IMPs). Moreover, once impurities have entered aluminium, it is difficult to remove them. In 2017, almost 100 million cars were produced worldwide. Historically, vehicle design prioritised performance, resulting in a multi-material mix to utilise the best materials for each application. This included over 40 different wrought and cast aluminium alloys, Cu-based materials for electrics, and steels for high-strength applications. In the recycling of end-of-life vehicles (ELVs), high purity wrought Al alloys are today down-cycled to low purity cast engine blocks. However, recent advancements show that the drawback of increase IMP-fractions can be turned into benefits through the strategic design of heterostructured alloys. A first successful alloy example from this approach enables interesting forming properties, previously only found in 5xxx series wrought aluminium alloys, in combination with a matrix composition and age-hardening potential known from 6xxx series wrought aluminium alloys. A second examples reviews compositions directly resulting from ELV scrap. By manipulating IMPs it is feasible to create heterostructures with an interesting balance of strength and ductility. These approaches challenge traditional views, allowing for a greater volume fraction of intermetallic phases. Understanding the formation and role of intermetallic particles is crucial. This work gives an overview to the current problem and the state of the art and addressed the potential of upcycled aluminium alloys that tolerate high impurity levels by using intermetallic phases as impurity sinks.

Auf dem Weg in eine CO2-neutrale Zukunft - Waldl, Wolfram; Flachberger, Helmut (Zement Beton, 2024)
Keywords: Aufbereitung und Veredlung; Zementindustrie

Backside metallization affects residual stress and bending strength of the recast layer in laser-diced Si - Ziegelwanger, T.; Reisinger, M.; Matoy, K.; Medjahed, A. A.; Zalesak, J.; Gruber, Manuel; Meindlhumer, M.; Keckes, J. (Materials Science in Semiconductor Processing, 2024)
Publisher Copyright: © 2024
Keywords: Die bending strength; Local residual stresses; Nanosecond laser dicing; Ultra-thin Si dies; X-ray nanodiffraction

Beurteilung von temporären Böschungen im Festgesteinstagebau - Heiss, Christian; Sammer, Georg (Geomechanics and tunnelling = Geomechanik und Tunnelbau, 2024)
lm österreichischen Festgesteinstagebau muss gemäß den aktuellen Arbeitnehmerschutzvorschriften von der fachkundigen Leitung eine Evaluierung temporärer Böschungen hinsichtlich geogener Gefahren und somit ihrer Standsicherheit durchgeführt werden. Basierend auf dieser Evaluierung ist an der Böschungsober- und -unterkante ein ausreichend großer Gefahrenbereich zu definieren und auszuweisen. Durch das neu entwickelte Böschungsbeurteilungs-System-Tagebau (B2ST) kann dies anhand eines standardisierten und nachvollziehbaren Verfahrens von Geologen, Geotechnikern, aber speziell auch von täglich im Betrieb aktiven fachkundigen Personen durchgeführt werden. Allgemein ist anzumerken, dass die Beurteilung mit B2ST das Systemverhalten des Gebirges unter Berücksichtigung interner aber auch externer Einflüsse wie Sprengungen oder Frost-Tau-Wechsel beschreibt. Die Methode liefert somit das Gefährdungspotenzial einer Böschung unter Berücksichtigung interner und externen Einflüsse und berücksichtigt bei langlebigeren Böschungen auch zeitliche Komponenten. Nach Vorbereitung und Kalibrierung des Systems für die vorherrschenden Gebirgsverhältnisse können so auch konkrete Werte für geogene Gefahrenbereiche ausgewiesen werden.
Keywords: Beurteilung von Felsböschungen; Festgesteinsgewinnung; Tagebau; Standsicherheit; geogene Gefahrenbereiche; Arbeitnehmerschutz

Editorial for the Special Issue on the Occasion of Reinhard Pippan's 70th Birthday - Kiener, Daniel; Hohenwarter, Anton (Advanced Engineering Materials, 2024)

Editorial zum 73. Geomechanik Kolloquium 2024 in Salzburg - Galler, Robert (Geomechanics and tunnelling = Geomechanik und Tunnelbau, 2024)
Stability of rock slopesGeothermal energyAssessment and repair of infrastructureClimate change related natural hazards

Effects of gradual substitution of coke breeze with charcoal on the sinter process - Eisbacher-Lubensky, Jan; Kittinger, Friedrich; Pichler, Sigrid; Weiß, Christian; Stocker, Hugo; Wegscheider, Stefan (9th ECIC European Coke and Ironmaking Congress, 2024)

Investigation of Phase Transformations and Ordering Mechanisms in a Pd–Cu–Ag–Ru Alloy - Lumper, Lea; Fecher, Jonas; Stark, Andreas; Maier-Kiener, Verena (Advanced engineering materials, 2024)
An in-depth analysis of phase transformations in a Pd–Cu–Ag alloy, crucial for applications in hydrogen membranes and electrical components, is presented. The investigation emphasizes the influence of the deformation rate and addition of Ag on the formation of the ordered CuPd phase. This study focuses on a specific alloy composition, 49.1% Cu–41.3% Pd–8.3% Ag–1.3% Ru, investigating its behavior under various conditions. Through comprehensive analysis, including the influence of the initial state, deformation variations, and chemical composition modifications, high-energy X-ray diffraction to unveil detailed phase evolution dynamics is used. Surprisingly, experimental findings deviate from the anticipated phase diagram, uncovering a previously unrecognized three-phase region with the formation of AgPd. Notably, the study reveals the pivotal role of the alloy's Ag content in the development of ordered CuPd and AgPd phases. The addition of Ru exhibits no involvement in the observed phase transformations, contributing to the understanding of the alloy's composition-dependent behavior. This research provides valuable insights into the intricate interplay of factors influencing phase transformations, offering a nuanced perspective beyond theoretical predictions. The newfound understanding of Ag's role and Ru's inertness refines material design considerations, enhancing the grasp of the alloy's thermodynamic stability under varying conditions.
Publisher Copyright: © 2024 The Authors. Advanced Engineering Materials published by Wiley-VCH GmbH.
Keywords: electrical conductors; high-energy X-ray diffraction; ordering transformations; palladium–copper–silver alloys; phase distributions

Challenges and opportunities in managing biodegradable plastic waste: A review - Mhaddolkar, Namrata; Astrup, Thomas Fruergaard; Tischberger-Aldrian, Alexia; Pomberger, Roland; Vollprecht, Daniel (Waste Management and Research, 2024)
Biodegradable plastics have certain challenges in a waste management perspective. The existing literature reviews fail to provide a consolidated overview of different process steps of biodegradable plastic waste management and to discuss the support provided by the existing legislation for the same. The present review provides a holistic overview of these process steps and a comprehensive relative summary of 13 existing European Union (EU) laws related to waste management and circular economy, and national legislations plus source separation guidelines of 13 countries, to ensure the optimal use of resources in the future. Following were the major findings: (i) numerous types and low volumes of biodegradable plastics pose a challenge to developing cost-effective waste management infrastructure; (ii) biodegradable plastics are promoted as food-waste collection aids, but consumers are often confused about their proper disposal and are prone to greenwashing from manufacturers; (iii) industry-level studies demonstrating mechanical recycling on a full scale are unavailable; (iv) the existing EU legislation dealt with general topics related to biodegradable plastics; however, only the new proposal on plastic packaging waste and the EU policy framework for bioplastics clearly mentioned their disposal and (v) clear disparities were observed between disposal methods suggested by national legislation and available source separation guidelines. Thus, to appropriately manage biodegradable plastic waste, it is necessary to develop waste processing and material utilization infrastructure as well as create consumer awareness. In the end, recommendations were provided for improved biodegradable plastic waste management from the perspective of systemic challenges identified from the literature review.
Publisher Copyright: © The Author(s) 2024.
Keywords: Biodegradable plastic waste management; consumer confusion; EU legislation; recycling; source separation guidelines; waste collection and sorting

Alteration zones as exploration parameter for stratiform Pb-Zn-Ag-Ba deposits in the Graz Paleozoic (Eastern Alps, Austria) - Rohrhofer, Sandro; Geringer, Annika; Melcher, Frank; Schuster, Ralf (Berg- und hüttenmännische Monatshefte : BHM, 2024)

Corporate Sustainability Due Diligence - Feichtinger, Gerald; Friedrich, Karl; Posch, Wolfgang (17th Hamburg International Conference of Logistics (HICL 2024), 2024)
Conference code: 17
Keywords: Corporate Sustainability Due Diligence; Online Survey; Interviews; Supply Chain; Decarbonisation

Hydroxylation of an ultrathin Co3O4(111) film on Ir(100) studied by in situ ambient pressure XPS and DFT - Haunold, Thomas; Anic, Kresimir; Genest, Alexander; Rameshan, Christoph; Roiaz, Matteo; Li, Hao; Wicht, Thomas; Knudsen, Jan; Rupprechter, Günther (Surface Science, 2024)
In the present work, we have studied the interaction of water with spinel cobalt oxide (Co3O4), an effect which has been considered a major cause of its catalytic deactivation. Employing a Co3O4(111) model thin film grown on Ir(100) in (ultra)high vacuum, and ambient pressure X-ray photoelectron spectroscopy (APXPS), hydroxylation in 0.5 mbar H2O vapor at room temperature was monitored in real time. The surface hydroxyl (OH) coverage was determined via two different models based (i) on the termination of a pristine and OH-covered Co3O4(111) surface as derived from density functional theory (DFT) calculations, and (ii) on a homogeneous cobalt oxyhydroxide (CoO(OH)) overlayer. Langmuir pseudo-second-order kinetics were applied to characterize the OH evolution with time, suggesting two regimes of chemisorption at the mosaic-like Co3O4(111) film: (i) plateaus, which were quickly saturated by OH, followed by (ii) slow hydroxylation in the “cracks” of the thin film. H2O dissociation and OH formation, blocking exposed Co2+ ions and additionally consuming surface lattice oxygen, respectively, may thus account for catalyst deactivation by H2O traces in reactive feeds.
Publisher Copyright: © 2024 The Author(s)
Keywords: Cobalt oxide; Density functional theory; In situ studies; Model catalysis; Photoelectron spectroscopy; Water

Crystal structure, electronic conductivity and oxygen exchange kinetics of high-entropy perovskites La0.2Pr0.2Nd0.2Sm0.2Sr0.2Co1-xFexO3-δ (x = 0, 0.5, 1) - Pretschuh, Patrick; Egger, Andreas; Bucher, Edith (Solid State Ionics, 2024)
High-entropy perovskites (HEPs) are attracting increasing attention as air electrode materials for solid oxide cells (SOCs). In this work, three different HEPs from the series La 0.2Pr 0.2Nd 0.2Sm 0.2Sr 0.2Co 1-xFe xO 3-δ (x = 0, 0.5, 1) are synthesized using the citric acid-ethylenediaminetetraacetate (EDTA) method. X-ray diffraction analysis finds crystal structures with the orthorhombic space group 62 (Pnma) at room temperature. The lattice distortion increases with increased Fe-substitution at the B-site. The electrical conductivity (σ e) is determined at temperatures from 600 to 850 °C and oxygen partial pressures (pO 2) between 0.001 and 0.15 bar. For the pure cobaltate, σ e is 1469 S cm −1 at 800 °C and 0.15 bar pO 2. The conductivity is significantly reduced with Fe-doping, reaching 87 S cm −1 for the pure ferrate at 800 °C. The chemical oxygen surface exchange coefficient (k chem) and the chemical oxygen diffusion coefficient (D chem) are determined by the electrical conductivity relaxation technique. D chem is found to be quite independent of B-site doping and pO 2, with values of approx. 5 × 10 −6 cm 2 s −1 at 800 °C. In contrast, k chem is strongly influenced by the B-site composition, which results in an increase of more than one order of magnitude from the ferrate (3.4 × 10 −5 cm s −1) to the cobaltate (7.7 × 10 −4 cm s −1) at 800 °C and 0.001 bar pO 2. This clearly demonstrates the beneficial effects of Co on the electronic conductivity as well as on the catalytic activity for the oxygen surface exchange reaction.
Publisher Copyright: © 2024 Elsevier B.V.
Keywords: Crystal structure; Electronic conductivity; High-entropy perovskite; Lattice distortion; Oxygen exchange kinetics; Solid oxide cell

Grain refinement of high-Mn wear-resistant cast steel by means of heterogeneous nucleation - Presoly, Peter; Wallner, Michael; Thiele, Kathrin; Bernhard, Christian; Mayer, Michael; Ressel, Gerald; Tize, Thomas (Liquid Metal Processing & Casting Conference 2024, 2024)
Understanding and controlling the primary solidification, particularlythe formation of first grains, is of significant relevance. Generally, high-Mn steels,such as alloy Mn13, exhibit a coarse-grained microstructure in the millimeterrange and are known for their high strain hardening ability and thus, excellentcyclic deformation resistance. To further improve the cyclic mechanicalproperties, this study aims to increase the strength of the alloy via grainrefinement. From a comprehensive literature research, the nonmetallicinclusions AlCeO3, CeO2, Ce2O3 and Ce2O2S were identified as the most promisingparticles for the heterogeneous nucleation of austenite. Based on this literaturereview, various grain refining agents were evaluated and finally the grain refiningagent from ELKEM (WearSeedTM) was selected for test melts. This resulted in asuccessful grain refinement and the grain size was reduced by over 80% (from1550μm to 285μm). However, the process window for a successful grainrefinement is only very small. For a deeper understanding, thermodynamiccalculations with FactSage on the interaction of O-S-Ce-Al in high-Mn steel meltsand particle analyses of the potential nuclei by automated SEM-EDS were carriedout. The framework conditions for a successful grain refinement weresystematically developed depending on the casting temperature, dissolved O andS, and the addition of Al and Ce. Finally, the static and cyclic mechanicalproperties of the grain refined high-Mn steel cast were determined using tensileand low cycle fatigue testing and showed very promising results.

Thermal shock resistant 3D-printed ceramic components through spatially tailored porosity - Schlacher, Josef; Bastos Mateus, Luisa; Nohut, Serkan; Schwentenwein, Martin; Bermejo Moratinos, Raul (Additive Manufacturing, 2024)
Planar layered ceramics designed with porous interlayers or weak interfaces have proved effective against the catastrophic failure associated with crack deflection mechanisms triggered by porosity. In this work, we explore the capabilities of spatially tailoring porosity in 3D-printing ceramic components, using the layer-by-layer vat photopolymerization process, to enhance damage tolerance. Porous interlayers or porous gradient regions are introduced in the structures by using a polymeric pore forming agent, which is removed after the debinding process. Multi-layered designs featuring varying porosity content are fabricated with both discrete and gradient interfaces. These designs are then subjected to biaxial bending tests, both before and after thermal shock testing, to assess the retained bending strength as a function of porosity. An optimized design is applied onto a welding nozzle to demonstrate the potential of combining dense and porous regions in complex 3D-printed ceramic parts to enhance their thermal shock resistance, opening a new pathway in designing structural ceramics with higher specific strength.
Publisher Copyright: © 2024 The Authors
Keywords: Alumina; Lightweight design; Porosity; Thermal shock; Vat photopolymerization

Amanita Muscaria for Heterogeneous Redox Transformations - Michalke, Jessica (Chemietage 2024, 2024)

Development of Selective Skin Patches based on Diffusive Gradients in Thin Films (DGTs) for Elemental and Isotopic Analysis at (Ultra-)Trace Levels in Sweat - Wagner, Stefan; Siebenbrunner, Antonia; Irrgeher, Johanna; Prohaska, Thomas (Chemietage 2024, 2024)

Development of sustainable air electrode materials for solid oxide cells - Aksoy, Mehmet; Egger, Andreas; Sitte, Werner; Bucher, Edith (Chemietage 2024, 2024)

High-temperature processing technology - Doschek-Held, Klaus (Science 4 Technology @MUL, 2024)
Keywords: sustainable circular economy; valorisation; recycling; residues; high-temperature processes

ReMFra - Doschek-Held, Klaus; Wolfgang, Reiter (Science 4 Technology @MUL, 2024)
Keywords: steelmaking residues; recycling; zero-waste; RecoDust process

The Effect of Homogenization and Hot Deformation on the Recrystallization Behavior in Aluminum Alloy AA8079 - Santora, Erik; Pachnek, Florian; Falkinger, Georg; Pogatscher, Stefan; Hirsch, Jürgen (Metallurgical and Materials Transactions A: Physical Metallurgy and Materials Science, 2024)
For Al–Fe–Si foil stock alloys, the recrystallization behavior is one of the key features for the design of the thermo-mechanical process route, which is highly dependent on the content of the elements in solute solution, especially Fe. Consequently, the combined effects of homogenization and hot deformation on the recrystallization behavior are of great interest. The focus of this work is on the resulting recrystallization behavior during hot deformation caused by different homogenization annealings prior to hot deformation. AA8079 samples were homogenized at two different temperatures and then used for uniaxial hot-compression tests at temperatures between 320 °C and 440 °C. The resulting hot deformation and recrystallization behavior were investigated by means of flow curves, optical microscopy, and microhardness measurements. A finite element method (FEM)-based simulation model was used to compute local temperatures and strain rates. The experimental investigation revealed a significant influence of the homogenization treatment on the hot deformation flow stress and subsequent recrystallization behavior.
Publisher Copyright: © The Minerals, Metals & Materials Society and ASM International 2024.

Varied phase ratio effects on composite air electrodes for solid oxide cells - Buxbaum, Barbara; Egger, Andreas; Kramer-Schöggl, Johanna; Brunner, Roland; Bucher, Edith (Chemietage 2024, 2024)

Comparative Study of Sulfides from Porphyry, Skarn, and Carbonate-Replacement Mineralization at the Recsk Porphyry-Mineralized Complex, Hungary - Biró, Mate; Raith, Johann G.; Feichter, Monika; Hencz, Máté; Kiss, Gabriella B.; Virág, Attila; Molnàr, Ferenc (Minerals, 2024)
Acalc–alkaline dioritic–andesitic–dacitic intrusive–volcanic complex of Early Oligocene (30 Ma) age and its Mesozoic sedimentary basement at Recsk host a well-preserved porphyry–skarn–polymetallic carbonate-replacement–epithermal mineral system. The unique occurrence offers an exceptional possibility to study these related mineralization types at a single locality. This study presents the textural–paragenetic, compositional characteristics, and systematics of sulfide mineral assemblages for the porphyry, skarn, and carbonate-replacement ore types, which are currently situated at a depth of 500–1200 m below the present surface. Detailed petrography combined with EPMA analyses of molybdenite, galena, sphalerite, tetrahedrite-group minerals and Bi-bearing sulfosalts allows for the establishment of characteristic mineral and chemical fingerprints for each mineralization type. Rhenium concentration in molybdenite, occurring as rare disseminations and quartz–carbonate veinlets in altered host rocks in all three mineralization types, shows a decreasing trend towards the more distal mineralization types. High Re contents ((Formula presented.) = 1.04 wt.%, max. up to 4.47 wt%) are typical for molybdenite from the porphyry mineralization, but Re is not homogeneously distributed, neither within individual molybdenite crystals nor on a mineralization scale. Copper and Se show opposite behavior in molybdenite, both becoming enriched in the more distal mineralization types. Silver, Bi, and Se concentrations increase in galena and tetrahedrite-group minerals, both towards the country rocks, making them the best candidates for vectoring within the whole hydrothermal system. For tetrahedrite-group minerals, Ag, Bi, Se, together with Sb and Zn, are the suitable elements for fingerprinting; all these are significantly enriched in the distal carbonate-replacement mineralization compared to the other, more proximal ore types. Additionally, further trends can be traced within the composition of sulfosalts. Lead-bearing Bi sulfosalts preferentially occur in the polymetallic carbonate-replacement veins, while being under-represented in the skarn and porphyry mineralization. Porphyry mineralization hosts Cu-bearing Bi sulfosalts dominantly, while skarn is characterized by Bi-dominated sulfosalts. Sphalerite, although present in all mineralization types, cannot be used for fingerprinting, vectoring, or thermobarometry based on EPMA measurements only. Trace element contents of sphalerite are low, often below the detection limits of the analyses. This is further complicated by the intense “chalcopyrite disease” occurring throughout the distal mineralization types. All the above-listed major, minor, and trace element ore mineral characteristics enable the characterization of the Recsk ores by mineral geochemical fingerprints, providing a possible vectoring tool in porphyry Cu–(Mo)–Au-mineralized systems.
Publisher Copyright: © 2024 by the authors.
Keywords: carbonate replacement; EPMA; fingerprinting; porphyry; skarn; sulfide; vectoring

Innovative Pathways for the use of Excavation Materials in the Frame of the Future Cirular Colllider Project - Galler, Robert; Hauzinger, Elisabeth; Schneider, Daniel (Springer, 2024)
Based on a recommendation of the European strategy of particle physics of 2020 due to the great research success of the last decade, CERN is planning a new circular collider with a circumference of approximately 91km.
Keywords: Tunneling; Molasse; Reuse; Recycling; Circular economy Landfiling

Single-stack multilayer infrared mirrors with selectable higher-order interference peaks - Meisels, Ronald; Kuchar, Friedemar; Manara, J.; Arduini, M.; Schulz, Uwe; Peters, J. O.; Gartner, T. M.; Mitterer, Christian; Paris, Oskar (Applied Optics, 2024)
A concept for the design of single-stack multilayer mirrors with multiple reflection peaks is presented. Its realization in the infrared is demonstrated by the sputter deposition of TiO2/Al2O3 bilayers on sapphire and HastelloyX substrates and corresponding reflection measurements. Even or odd higher-order interference peaks are selected by adjusting the optical thicknesses of the individual layers. The peak positions are very well reproduced by multiple scattering calculations. With the HastelloyX substrate, a potential application for high temperatures and aggressive atmospheres, e.g., in aircraft turbines, is addressed. A design for matching up to three turbine gas emission bands (CO2, H2O) is proposed.
Publisher Copyright: © 2024 Optica Publishing Group. All rights, including for text and data mining (TDM), Artificial Intelligence (AI) training, and similar technologies, are reserved.

Digitale Exzellenz im Unternehmen - Biedermann, Hubert (Digital Excellence in der Instandhaltung, 2024)

Qualitative Insights into Cultural Heritage Protection in Serbia: Evaluating Legal and Institutional Gaps - Cvetković, Vladimir M.; Gole, Stefan; Renner, Renate; Lukić, Tin (Preprints, 2024)
This research is dedicated to a comprehensive examination of the strengths and weaknesses inherent in the legal and institutional measures designed to protect cultural heritage in the Republic of Serbia from the adverse effects of natural disasters, including earthquakes, landslides, rockfalls, floods, torrents, storms, hail, and forest fires. The study aims to identify the primary challenges and shortcomings within the existing legal and institutional framework, while also pinpointing and analyzing best practices and potential improvements for the protection system. This research posits a preliminary hypothesis suggesting that challenges may exist within the legal and institutional framework for the protection of cultural heritage in the Republic of Serbia, potentially limiting effective response and recovery following natural disasters. This hypothesis will be further developed and adapted based on the analysis of available data. Data collection for this research was conducted through semi-structured interviews with experts and an in-depth analysis of existing documentation. By conducting interviews with experts in the field, the research seeks to gather critical data and insights that will enhance the understanding of these issues and contribute to formulating viable solutions. The analysis and processing of data were carried out using ATLAS.ti software, which facilitated a comprehensive and systematic examination of the collected qualitative information. Furthermore, an assessment of the current capacity of institutions to respond rapidly and effectively to natural disasters that pose a threat to cultural heritage is a key component of the study. The ultimate goal is to develop recommendations that will fortify the legal and institutional framework, thereby bolstering the resilience of cultural heritage sites in Serbia against future natural disasters. The results of the research, highlight significant deficiencies in the legal framework, inadequate institutional capacities and resources, as well as a lack of proper training for crisis response. The need for improved inter-institutional cooperation and the development of technical-logistical resources is emphasized. This paper represents a significant contribution to the understanding and enhancement of the cultural heritage protection system, providing a foundation for further research and strategy development in this area.
Cvetković, V. M., Gole, S., Renner, R., & Lukić, T. (2024). Qualitative Insights into Cultural Heritage Protection in Serbia: Evaluating Legal and Institutional Gaps. Preprints. https://doi.org/10.20944/preprints202409.1291.v1
Keywords: disasters; hazards; cultural heritage; protecting; qualitative research; interview; Serbia

Digitale Excellenz im Unternehmen - Biedermann, Hubert (Grundlagen, Strategie und Change, 2024)
Innovative Geschäftsmodelle der Instandhaltung zur Weiterentwicklung derselben zu ei-nem wertschöpfenden, ressourceneffizienten Asset-Management sind ein wesentlicher Erfolgsfaktor für Unternehmen in der Hochtechnologiegesellschaft. Die echtzeitfähige, intelligente, horizontale und vertikale Vernetzung von Menschen, Maschinen, Objekten und IKT-Systemen bietet der Instandhaltung die Chance einen hohen Reifegrad im strate-gisch-operativen Management zu erreichen. Weitere Technologien im Megatrend Digita-lisierung wie Datenanalytik, Internet der Dinge und Dienste sowie Künstliche Intelligenz bieten Möglichkeiten die weit über den Rahmen der klassischen Instandhaltung hinaus-reichen. Sie gilt es proaktiv zu nutzen, um durch digitale Transformation Exzellenz zu erreichen.

Sputter deposited silver niobate thin films: Pathway towards phase purity - Kölbl, Lukas; Kobald, Alexander; Griesser, Thomas; Munnik, Frans; Mitterer, Christian (Thin solid films, 2024)
The quest for environmentally sustainable alternatives to lead-based dielectric materials in dielectric capacitors has led research to the exploration of options such as silver niobate (AgNbO 3), which has been found to display excellent energy storage properties. Homogeneity and phase-purity of the used thin films are vital for optimal performance of these devices. In this study, a systematic variation of oxygen partial pressure and bias voltage during reactive d.c. magnetron co-sputtering from metallic targets is employed to synthesise AgNbO 3 thin films. Structural and chemical composition of the films are investigated using X-ray diffraction, Raman spectroscopy, X-ray photoelectron spectroscopy, energy dispersive X-ray spectroscopy, elastic recoil detection analysis, and Rutherford backscattering spectrometry. The findings emphasise the necessity of precise parameter control during deposition to avoid the presence of undesirable secondary phases like Ag and Ag 2Nb 4O 11 and to ensure the formation of homogeneous and phase-pure AgNbO 3 thin films. The gained insights demonstrate the potential of reactive d.c. magnetron sputtering for the deposition of lead-free AgNbO 3 thin films, offering pathways for enhanced environmental compatibility of future dielectric capacitors.
Publisher Copyright: © 2024 The Author(s)
Keywords: Energy storage; Magnetron sputtering; Silver niobate; Thin film

Supportless lattice structure of 316L stainless steel fabricated by material extrusion additive manufacturing - Parsompech, Natthaphat; Suwanpreecha, Chanun; Noraphaiphipaksa, Nitikorn; Hararak, Bongkot; Songkuea, Sukrit; Schuschnigg, Stephan; Kukla, Christian; Kanchanomai, Chaosuan; Manonukul, Anchalee (Materials Science and Engineering: A, 2024)
Studies on lattice structures fabricated by material extrusion additive manufacturing for metal, leveraging the advantages of additive manufacturing, are limited. In this work, by varying the number of unit cells, the effects of density on the macro- and microstructure, and on the physical and mechanical properties of 316L stainless steel fabricated by our in-house developed 316L metal-filled filament were investigated. Utilising our in-house developed 316L metal-filled filament, supportless octet-truss lattice specimens with relative density ranging from 16 % to 55 % were successfully fabricated. The relative density increased with the number of unit cells, compressive strength, Young's modulus, and energy absorption, consistent with the Gibson-Ashby's porous material model. Stretch-dominated behaviour was observed in the 2 × 2 × 2 and 3 × 3 × 3 unit cells, while the 4 × 4 × 4 and 5 × 5 × 5 units exhibited bending-dominated behaviour. The deformation behaviour was well simulated by finite element analysis with the core-shell structure. The successful fabrication of supportless lattice structures highlights their potential for manufacturing lightweight materials and their future application.
Publisher Copyright: © 2024 Elsevier B.V.
Keywords: 316L stainless steel: octet-truss structure; Compressive property; Finite element analysis; Material extrusion additive manufacturing

Vom schädlichen Abgas zur Ressource: CO2 als Rohstoff – Ein Sparkling Science Projekt - Rameshan, Christoph; Bartl, Patrizia; Ruh, Thomas; Messner, Martina; Lorenz, Harald (OIS zam: Forum 2024, 2024)

Green Digital Twin for Organizations as Enabler for Carbon Management - Feichtinger, Gerald; Mark, Daniel; Schlar, Daniel; Posch, Wolfgang (19th Conference on Sustainable Development of Energy, Water and Environment Systems, 2024)
Conference code: 19
Keywords: Twin Green and Digital Transition; Green Digital Twin; Life Cycle Assessment; Carbon Management; Staged Development Path; Carbon Management Maturity Assessment

Integrating Flexibility in a High-Resolution Energy System Model of Austria - Wallner, Stefan; Kienberger, Thomas (2024)

On the Role of Tramp Elements for Surface Defect Formation in Continuous Casting of Steel - Bernhard, Christian; Gaiser, Georg; Bernhard, Michael Christian; Winkler, Johann; Kern, Maximilian; Presoly, Peter; Kang, Youn-Bae (Steel research international, 2024)
In the course of the decarbonization of steel production, electric steel production will continue to gain importance. The processing of low-quality scrap will also play an important role, which may lead to an increase in the content of so-called tramp elements in steel production and further processing. This article examines the effect of the elements Cu, Sn, and Ni on the formation of surface cracks under the conditions of the continuous casting process. Results of an in situ bending test are compared with the results of the experimental simulation of high-temperature oxidation and thermodynamic analysis based on the CALculation of PHase Diagrams (CALPHAD) approach. For a temperature of 900 °C, an equivalent Cu content of 0.20 wt% must be considered as the critical upper limit. The presumable reason is the existence of Cu- and Sn-rich liquid phases at the austenite grain boundaries. The results clearly show the effect of the investigated elements but also point to the importance of the gas atmosphere and cooling conditions on the results. This can be a groundbreaking result for extending the process window for casting steels with increased tramp element contents.
Publisher Copyright: © 2024 The Author(s). Steel Research International published by Wiley-VCH GmbH.

Key considerations for the determination of metal contents in e-waste highlighted through inter-laboratory comparison - Lancaster, Shaun; Eberhard, Melissa; Feiner, Laura; Trimmel, Simone; Rachetti, Alessandra; Irrgeher, Johanna (21st Biennial National Atomic Spectroscopy Symposium, 2024)

Enhance hydrogen storage in lightweight solid-state systems based on Poly (vinylnaphthalene) - Sharifian, Mohammadhossein; Kern, Wolfgang; Rieß, Gisbert; Kostoglou, Nikolaos (International Journal of Hydrogen Energy, 2024)
This article highlights the potential of poly(2-vinylnaphthalene) (PVN) as a novel light-weight solid-state hydrogen storage system for various applications. With an impressive theoretical gravimetric hydrogen capacity of 5.2 wt.-%, PVN stands out for its attractiveness as a hydrogen carrier. The material possesses advantageous characteristics, including moldability, low toxicity, and ease of storage, making it a promising candidate for both stationary and mobile hydrogen storage applications. Experimental findings demonstrate that PVN can be hydrogenated by up to 76 % utilizing an Ru/Al 2O 3 catalyst at 250 °C for 24 h. Confirmation of the hydrogenation reaction, which results in poly(2-vinyldecalin), was achieved through characterization techniques such as FTIR, 1H NMR, and spectroscopic ellipsometry. The study of the effects of hydrogen pressure and reaction time identified moderate conditions as favorable, though a further exploration of different catalysts is suggested for optimal conversion. A palladium-based catalyst was employed to release hydrogen from the hydrogenated polymer, demonstrating almost complete reversibility of the hydrogenation of poly(2-vinylnaphthalene) with a dehydrogenation yield of 90 %.
Publisher Copyright: © 2024 The Authors
Keywords: Green energy; Hydrogen storage; Poly(2-vinylnaphthalene); Renewable energy; Solid-state hydrogen carrier

Geospatial and Temporal Patterns of Natural and Man-Made (Technological) Disasters (1900–2024) - Cvetković, Vladimir; Renner, Renate; Aleksova, Bojana; Lukić, Tin (Applied Sciences : open access journal, 2024)
This pioneering study explores the geospatial and temporal patterns of natural and human-induced disasters from 1900 to 2024, providing essential insights into their global distribution and impacts. Significant trends and disparities in disaster occurrences and their widespread consequences are revealed through the utilization of the comprehensive international EM-DAT database. The results showed a dramatic escalation in both natural and man-made (technological) disasters over the decades, with notable surges in the 1991–2000 and 2001–2010 periods. A total of 25,836 disasters were recorded worldwide, of which 69.41% were natural disasters (16,567) and 30.59% were man-made (technological) disasters (9269). The most significant increase in natural disasters occurred from 1961–1970, while man-made (technological) disasters surged substantially from 1981–1990. Seasonal trends reveal that floods peak in January and July, while storms are most frequent in June and October. Droughts and floods are the most devastating in terms of human lives, while storms and earthquakes cause the highest economic losses. The most substantial economic losses were reported during the 2001–2010 period, driven by catastrophic natural disasters in Asia and North America. Also, Asia was highlighted by our research as the most disaster-prone continent, accounting for 41.75% of global events, with 61.89% of these events being natural disasters. Oceania, despite experiencing fewer total disasters, shows a remarkable 91.51% of these as natural disasters. Africa is notable for its high incidence of man-made (technological) disasters, which constitute 43.79% of the continent’s disaster events. Europe, representing 11.96% of total disasters, exhibits a balanced distribution but tends towards natural disasters at 64.54%. Examining specific countries, China, India, and the United States emerged as the countries most frequently affected by both types of disasters. The impact of these disasters has been immense, with economic losses reaching their highest during the decade of 2010–2020, largely due to natural disasters. The human toll has been equally significant, with Asia recording the most fatalities and Africa the most injuries. Pearson’s correlation analysis identified statistically significant links between socioeconomic factors and the effects of disasters. It shows that nations with higher GDP per capita and better governance quality tend to experience fewer disasters and less severe negative consequences. These insights highlight the urgent need for tailored disaster risk management strategies that address the distinct challenges and impacts in various regions. By understanding historical disaster patterns, policymakers and stakeholders can better anticipate and manage future risks, ultimately safeguarding lives and economies.
Keywords: hazards; emergencies; natural disasters; man-made (technological) disasters; disaster risk management; socio-economic and human impact; EM-DAT database; geospatial; temporal analysis

Produktionsfaktoren - Biedermann, Hubert (2024)
Dieser Artikel erläutert, wie Unternehmen Produktionsfaktoren wie Arbeitskräfte,Maschinen und Rohstoffe einsetzen, um Güter zu produzieren. Dabei wirdzwischen elementaren Faktoren wie Rohstoffen und Maschinen und dispositivenFaktoren wie Planung und Organisation unterschieden. Die Materialwirtschaft spielteine zentrale Rolle bei der Beschaffung und dem effizienten Einsatz dieserMaterialien. Darüber hinaus werden wichtige Themen wie Kosten, Effizienz undNachhaltigkeit behandelt und Wege aufgezeigt, wie Ressourcen optimal genutztwerden können. Sie erhalten einen umfassenden Einblick in die Gestaltung undVerbesserung von Produktionsprozessen

Ressourcen- und CO2-optimierte Herstellung innovativer Zementklinker - Waldl, Wolfram (Stein & Kies (Mitgliederzeitung - Forum mineralische Rohstoffe), 2024)
Keywords: CO2 Emission; Zement; Klinkerproduktion; alternative raw materials

Status und Potenziale von Carbon Capture - Wolf-Zöllner, Philipp; Lehner, Markus (2024)
Keywords: Carbon Capture

A New Pricing Model for Supra-Regional District Heating Networks - Steinegger, Josef; Kienberger, Thomas (2024)

An Investigation into the Optimal Dimple Geometry in a Single-Dimple Sliding Contact - Scharf, Raphael; Pusterhofer, Michael; Gussmagg, Jakob; Grün, Florian (Machines : open access journal, 2024)
This study analyzes the influence of nine distinct texture geometries on a convergent oilfilm gap using a simulation model. The geometrical dimensions of the textures are characterizedby the texture area density, Stex.,A and the ratio of the textured-to-untextured area (Atex./A0). Theresults show that different texture geometries optimize the tribological performance depending onthe value of Stex.,A. Rectangular textures with variable widths (85% of the texture length atex.) significantlyenhance lifting and the drag force across a broad range of Stex.,A. Furthermore, rectangulartextures with a constant width (85% of the global width b0) show the best improvement withinthis study. The investigation also reveals that a small texture pitch angle, αtex, further enhancestribological performance.

Perovskite-Type Oxides for Methanol Steam Reforming: Advancements in Oxide Synthesis Techniques - Berger, Tobias (16th Pannonian International Symposium on Catalysis, 2024)

Three-dimensional mechanical metamaterial with tunable engineering constants in a broad range - Fleisch, Mathias; Pinter, Gerald; Schlögl, Sandra; Berer, Michael (Results in Engineering, 2024)
Keywords: Cellular material; Finite element analysis; Mechanical metamaterial; Poisson's ratio; Shear modulus; Young's modulus

High-Performance Titanium Nitride Structural Coatings for Corrosion Protection of Aluminum-Based Proton Exchange Membrane Fuel Cells - Silva, Felipe C.; Ramirez, Oscar M. Prada; Sagás, Julio C.; Fontana, Luis Cesar; Melo, Hercilio G. de; Schön, Cláudio Geraldo; Tunes, Matheus Araujo (ACS materials letters, 2024)
Electrification of vehicles is the key to reduce greenhouse gas emissions to meet new energy policies. New energy sources such as proton exchange membrane fuel cells (PEMFCs) have arisen as one of the most sustainable solutions. Their performance depends on the choice of materials, such as bipolar plates (BPPs). Reduction in weight, volume, and costs are of paramount importance to enable commercialization and popularization of PEMFCs. In this context, aluminum emerges as a promising candidate for BPPs, although its corrosion resistance is inadequate for the harsh environment of PEMFCs. Recently, titanium nitride (TiN) coatings have shown potential to increase the corrosion resistance of aluminum BPPs. Herein, we discovered that the performance of the aluminum-TiN functional system in a simulated PEMFC environment can be tailored by synthesis parameters. Electrochemical tests in combination with transmission electron microscopy indicate that optimal deposition settings can significantly improve the corrosion resistance by creating denser and defect-free film microstructures.
Publisher Copyright: © 2024 American Chemical Society

How A-site cations influence the in-situ formation of metallic nanoparticles in perovskite oxide catalysts - Schrenk, Florian; Rameshan, Christoph; Ruh, Thomas; Drexler, Hedda; Lindenthal, Lorenz; Berger, Tobias; Rollenitz, Jonathan; Rameshan, Raffael; Sanchez-Sanchez, Maria Cruz (16th Pannonian International Symposium on Catalysis, 2024)

Microscale manipulation of bond exchange reactions in photocurable vitrimers with a covalently attachable photoacid generator - Korotkov, Roman; Alabiso, Walter; Jelinek, Alexander; Schmallegger, Max; Li, Yang; Schlögl, Sandra; Rossegger, Elisabeth (Chemical science, 2024)
Vitrimers are polymer networks with covalent bonds that undergo reversible exchange reactions and rearrange their topology in response to an external stimulus. The temperature-dependent change in viscoelastic properties is conveniently adjusted by selected catalysts. In these thermo-activated systems, the lack in spatial control can be overcome by using photolatent catalysts. Herein, we advance this concept to locally manipulate bond exchange reactions on a single digit microscale level. For this, we synthetize a linkable non-ionic photoacid generator, which is covalently attached to a thiol-click photopolymer. UV induced deprotection of the photoacid yields a strong immobilized sulfonic acid species, which is able to efficiently catalyze transesterification reactions. Covalent attachment of the formed acid prevents migration/leaching processes and enables a precise tuning of material properties. As proof of concept, positive toned microstructures with a resolution of 5 μm are inscribed in thin films using direct two-photon absorption laser writing and subsequent depolymerization. In addition, the possibility to locally reprogram bulk material properties is demonstrated by performing a post-modification reaction with ethylene glycol and carboxylic acids. The Young's modulus is varied between 3.3 MPa and 11.9 MPa giving rise to the versatility of the newly introduced catalysts for creating light processable and transformable materials.
Publisher Copyright: © 2024 The Royal Society of Chemistry.

Modified Pechini Synthesis of Perovskite-type oxide Catalyst - Rollenitz, Jonathan; Drexler, Hedda; Lindenthal, Lorenz; Schrenk, Florian; Schröder, Christian; Sanchez-Sanchez, Maricruz; Rameshan, Christoph (16th Pannonian International Symposium on Catalysis, 2024)

Active seismic surveys for drilling target characterization in Ossola Valley: International Continental Scientific Drilling Program (ICDP) project Drilling the Ivrea–Verbano zonE (DIVE) phase I - Greenwood, Andrew; Hetényi, György; Baron, Ludovic; Zanetti, Alberto; Müntener, Othmar; MOS field team (Scientific Drilling, 2024)
Drilling target locations of the International Continental Scientific Drilling Program (ICDP) project Drilling the Ivrea–Verbano zonE (DIVE) have been initially proposed based on geological knowledge of surface outcrops and the structural context of the Ivrea–Verbano zone (IVZ) and of the Insubric Line. For the determination of the exact locations of drilling sites as well as for drilling geometry planning, we have carried out a series of active seismic experiments to image the subsurface at high resolution. The two drilling sites of project DIVEin Ossola Valley, one near Ornavasso and the other in Megolo di Mezzo, in the central part of the Ivrea–Verbano zone have been surveyed with site-specific velocity models and a seismic data processing chain. The findings have been interpreted in relation with the outcropping structures. These suggest a reasonable continuity from the surface. They also guide the planned borehole orientations: near-vertical at DT-1B (Ornavasso) into the tightly folded Massone Antiform and at 15–20° from the vertical in Megolo across a flank of the broad Proman Anticline. The seismic surveys indicate that the sedimentary overburden is up to 50m deep at the specific drill sites and can be minimized by relocating the proposed locations. The seismic surveys also indicate that the center of the Ossola Valley contains about 550m of sedimentary infill, defining the interface of bedrock and Quaternary glacial sediments at about 300m below sea level.
Publisher Copyright: © 2024 Andrew Greenwood et al.

Conclusions on austenite grain growth kinetics from in situ experiments and application to the continuous casting process - Bernhard, Michael Christian; Kern, Maximilian; Littringer, Robert; Bernhard, Christian (2024)

A phase-field fracture model in thermo-poro-elastic media with micromechanical strain energy degradation - Liu, Yuhao; Yoshioka, Keita; You, Tao; Li, Hanzhang; Zhang, Fengshou (Computer methods in applied mechanics and engineering, 2024)
This work extends the hydro-mechanical phase-field fracture model to non-isothermal conditions with micromechanics based poroelasticity, which degrades Biot's coefficient not only with the phase-field variable (damage) but also with the energy decomposition scheme. Furthermore, we propose a new approach to update porosity solely determined by the strain change rather than damage evolution as in the existing models. As such, these poroelastic behaviors of Biot's coefficient and the porosity dictate Biot's modulus and the thermal expansion coefficient. For numerical implementation, we employ an isotropic diffusion method to stabilize the advection-dominated heat flux and adapt the fixed stress split method to account for the thermal stress. We verify our model against a series of analytical solutions such as Terzaghi's consolidation, thermal consolidation, and the plane strain hydraulic fracture propagation, known as the KGD fracture. Finally, numerical experiments demonstrate the effectiveness of the stabilization method and intricate thermo-hydro-mechanical interactions during hydraulic fracturing with and without a pre-existing weak interface.
Publisher Copyright: © 2024 Elsevier B.V.
Keywords: Fixed stress split; Hydraulic fracturing; Isotropic diffusion method; Phase-field; Thermo-hydro-mechanical coupling; Thermo-poroelasticity

Biaxial bending strength testing of uniaxially curved thin plates using a modified ball on three balls test - Supancic, Peter; Maurer, Florian; Danzer, Robert (Journal of non-crystalline solids, 2024)
Publisher Copyright: © 2024
Keywords: Ring-on-ring test, Ball-on-three-balls test; Uniaxially curved glass plates

How A-site cations influence the in-situ formation of metallic nanoparticles in perovskite oxide catalysts - Rameshan, Christoph; Schrenk, Florian; Ruh, Thomas; Drexler, Hedda; Lindenthal, Lorenz; Berger, Tobias; Rollenitz, Jonathan; Rameshan, Raffael; Sanchez-Sanchez, Maricruz (2024)

Investigating the exciting world of high-temperature dry reforming of methane with in-situ spectroscopy - Schrenk, Florian; Lindenthal, Lorenz; Rameshan, Raffael; Drexler, Hedda; Berger, Tobias; Rollenitz, Jonathan; Rameshan, Christoph (2024)

Process Simulations for Membrane Capture of CO2: CO2 Conversion with Citizen Scientists - Ruh, Thomas; Bartl, Patrizia; Messner, Martina; Jantscher, Andreas; Lorenz, Harald; Erlebach, Christian; Stangl, Horst; Rameshan, Christoph (2024)

Spritzgießcompoundieren im Recycling von Post-Consumer PP Abfällen - Zidar, David; Krempl, Nina; Shahroodi, Zahra; Kirschnick, Ulrike; Holzer, Clemens (Jahresmagazin Kunststofftechnik : Ingenieurwissenschaften ... : im Fokus, 2024)

Unraveling the orientation-dependent mechanics of dental enamel in the red-necked wallaby - Wilmers, Jana; Wurmshuber, Michael; Gescher, Christoph; Graupp, Celine Michele; Kiener, Daniel; Bargmann, Swantje (Acta biomaterialia, 2024)
Dental enamels of different species exhibit a wide variety of microstructural patterns that are attractive to mimic in bioinspired composites to simultaneously achieve high stiffness and superior toughness. Non-human enamel types, however, have not yet received the deserved attention and their mechanical behaviour is largely unknown. Using nanoindentation tests and finite element modelling, we investigate the mechanical behaviour of Macropus rufogriseus enamel, revealing a dominating influence of the microstructure on the effective mechanical behaviour and allowing insight into structural dependencies. We find a shallow gradient in stiffness and low degree of anisotropy over the enamel thickness that is attributed to the orientation and size of microstructural features. Most notably, M. rufogriseus's modified radial enamel has a far simpler structural pattern than other species’, but achieves great property amplification. It is therefore a very promising template for biomimetic design. Statement of significance: The diversity of dental enamel structures in different species is well documented, but the mechanical behaviour of non-human enamel types is largely unknown. In this work, we investigate the microstructure and structure-dependent mechanical properties of marsupial enamel by nanoindentation and finite element simulations. Combining these methods gives valuable insights into the performance of modified radial enamel structures. Their stiffness and toughness stems from a unique structural design that is far less complex than well-studied human enamel types, which makes it a uniquely suitable template for biomimetic design.
Publisher Copyright: © 2024 The Author(s)
Keywords: Biomechanics; Finite element simulations; Hierarchical structure; Micromechanics; Microstructure; Nanoindentation

Austrian Scientists of Mass Spectrometry: A Comparison of the Biographies of Hugo Bondy and Richard Herzog – the Influence of Politics on Scientific Careers - Schober, Michael; Erker, Linda; Irrgeher, Johanna; Prohaska, Thomas (20th Austrian Chemistry Days 2024, 2024)

Coupled CFD-DEM Simulation of Flow-Induced Erosion in Cohesive Materials - Vollmann, Sandra; Rahimilarki, Mohsen; Jin, Shengli (5th Aspherix(R) & CFDEM(R) Conference, 2024)
Keywords: simulation CFD DEM; Erosion modelling

Determination and improvement of the quality of separately collected bio-waste from households - Adam, Josef; Wellacher, Martin; Azizi, Ferozan; Loidl, Alexandra; Zöscher, Andreas; Poschacher, Franz; Pomberger, Roland; Tischberger-Aldrian, Alexia (Waste management & research, 2024)
The recycling of bio-waste from households is an essential factor in achieving the recycling quotas for municipal waste laid down by the EU. A major problem is posed by impurities in the bio-waste collected, such as plastics, metals and glass. It is virtually impossible for compost producers to produce quality-assured compost from bio-waste with an impurity content of more than 3 wt%OS. The draft of the new Austrian Compost Ordinance stipulates a limit of 2 wt%OS of interfering substances in accepted bio-waste. A rapid measurement method has been developed and comprehensively validated for the immediate on-site checking of contaminant content at the bio-waste bin or in a vehicles. Data on the type and amount of impurities collected in the course of sorting analyses carried out over several years in 10 selected areas in Styria, Austria showed an average impurity content of 2.1 wt%OS. This impurity content can be considered representative for rural and urban communities in Austria. Among the interfering substances, plastics predominate, at 53%, of which pre-collection bags made of plastics form the highest proportion. A more detailed examination of pre-collection bags shows a higher proportion of use of biodegradable plastic bags, which have become more numerous in recent years in the more rural communities. In order to reduce mis-sorting, the effect of a wide variety of measures on citizens was tested in selected areas. Here, the distribution of paper bags as well as the threat of a cost increase due to special collections in combination with distribution of these bags were the methods with the greatest effect. Motivational letters and the threat of special collections, however, showed no significant result.
Publisher Copyright: © The Author(s) 2024.
Keywords: Biogene Abfälle; Störstoffe; Kunststoffe; Sammlung; Vorsammelhilfen; Bio-waste; collection; compost; impurities; pre-collection bag; quality

Interdisziplinarität im Sparkling Science Projekt „CO2-Umwandlung“ - Bartl, Patrizia; Ruh, Thomas (HAUPtsache, 2024)

Linear volumetric additive manufacturing of zirconia from a transparent photopolymerizable ceramic slurry via Xolography - Sänger, J. C.; König, N. F.; De Marzi, A.; Zocca, A.; Franchin, G.; Bermejo, R.; Colombo, P.; Günster, J. (Open ceramics, 2024)
Publisher Copyright: © 2024
Keywords: Additive manufacturing; Xolography; Zirconia

Ongoing Efforts and Challenges in Achieving Carbon-neutral Steel Production - Schenk, Johannes; Michelic, Susanne Katharina (9th Asia Steel Conference 2024, 2024)

Recycling of mineral wool waste as supplementary cementitious material through thermochemical treatment - Doschek-Held, Klaus; Krammer, Anna; Steindl, Florian Roman; Sattler, Theresa Magdalena; Juhart, Joachim (Waste Management and Research, 2024)
Mineral wool is commonly used in construction as thermal insulation material. After the product’s lifetime, it is classified as hazardous waste if no trademark of the European Certification Board for Mineral Wool Products (EUCEB) or the German Institute for Quality Assurance and Labelling (RAL) exists. Mineral Wool Waste (MWW) is typically landfilled in Europe, which is challenging due to its low bulk density and dimensional stability. This circumstance highlights the need for alternative recycling methods that increase the recycling rate of construction and demolition (C&D) waste. This article outlines the recycling opportunities of MWW and focuses on the use of thermochemical treatment of different mixtures of input materials to produce a supplementary cementitious material (SCM). The material characterisation results and investigations on the binder suitability demonstrate that the slag fractions after the thermochemical treatment are well-qualified to be used as reactive binder components. Additionally, a material flow analysis was conducted to estimate the substitution potential of MWW as SCM in the Austrian cement industry.
Publisher Copyright: © The Author(s) 2024.
Keywords: glass wool; mineral wool waste; Recycling; stone wool; supplementary cementitious material; thermochemical treatment

Sand screens for controlling sand production from hydrocarbon wells - Kumar, Sunil; Kumar, Gopal; Krishna, Shwetank; Kumar, Atul; Gupta, Tanmay; Goel, Prem Narayan; Kumari, Shashikala (Geoenergy science and engineering, 2024)
Worldwide seventy percent of the oil and gas production wells face hindrances owing to unpredictable production of sand. Predominantly, sand production along with the hydrocarbons is one of the main issues for the production wells. It tends to increase the separation cost and decrease the production rate of the hydrocarbons as it blocks the production perforation. There are four major types of sand control: one uses artificial cement to complete the well and the other uses filters in the downhole to prevent sand. Performance-wise chemical method is the most efficient but it is only applicable when the injection pressure is low. This paper presents a detailed study of the different types of sand screens with their sand-controlling efficiency and selection criteria as per the varying types of reservoir conditions. This paper also discussed the recent advancement in the development of innovative sand screens. The selection criteria for the sand screen is comprised of four stages which are also mentioned in detail. Furthermore, there are experimental studies that are used for the selection of sand screens according to the requirement and the selected screen performance is determined using two factors namely; screen plugging and particle size distribution (PSD). The study aims to comprehensively analyze the various sand screens currently available in the market. This analysis will aid in selecting the most suitable screen for a particular formation and the quantity of sand being produced.
Publisher Copyright: © 2024
Keywords: Optimization; Particle size distribution (PSD); Production wells; Sand production; Sand screen

PICS 2024 - 16th Pannonian International Symposium on Catalysis - Ruh, Thomas; Rameshan, Christoph (PICS 2024 - 16th Pannonian International Symposium on Catalysis, 2024)

Assessing risk-prone areas in the Kratovska Reka catchment (North Macedonia) by integrating advanced geospatial analytics and flash flood potential index - Aleksov, Bojana; Milevski, Ivica; Mijalov, Risto; Slobodan, Marković; Cvetković, Vladimir; Lukić, Tin (Open Geosciences, 2024)
This study presents a comprehensive analysis of flash flood susceptibility in the Kratovska Reka catchment area of Northeastern North Macedonia, integrating Geographic Information System, remote sensing, and field survey data. Key factors influencing flash flood dynamics, including Slope, Lithology, Land use, and Vegetation index, were investigated to develop the Flash Flood Potential Index (FFPI). Mapping slope variation using a 5-m Digital Elevation Model (DEM) revealed higher slopes in eastern tributaries compared to western counterparts. Lithological units were classified based on susceptibility to erosion processes, with clastic sediments identified as most prone to flash floods. Land use analysis highlighted non-irrigated agricultural surfaces and areas with sparse vegetation as highly susceptible. Integration of these factors into the FFPI model provided insights into flash flood susceptibility, with results indicating a medium risk across the catchment. The average value of the FFPI is 1.9, considering that the values range from 1 to 5. Also, terrains susceptible to flash floods were found to be 49.34%, classified as medium risk. Field survey data validated the model, revealing a significant overlap between hotspot areas for flash floods and high-risk regions identified by the FFPI. An average FFPI coefficient was calculated for each tributary (sub-catchment) of the Kratovska Reka. According to the model, Latišnica had the highest average coefficient of susceptibility to potential flash floods, with a value of 2.16. These findings offer valuable insights for spatial planning and flood risk management, with implications for both local and national-scale applications. Future research directions include incorporating machine learning techniques to enhance modeling accuracy and reduce subjectivity in assigning weighting factors.
Publisher Copyright: © 2024 the author(s), published by De Gruyter.
Keywords: FFPI; flash floods risk; geospatial analytics; GIS; Kratovska Reka; natural hazards; Remote Sensing

Innovationen in der Instandhaltung als Treiber für Wertschöpfung in Österreich - Biedermann, Hubert (Fachkolloquium Industrial Maintenance, 2024)

A multi-level IIOT platform for boosting mines digitalization - Minon, Raul; Lopez-de-Armentia, Juan; Bonilla, Lander; Brazaola, Aitor; Lana, Ibai; Palacios, M. Carmen; Mueller, Szymon; Blaszczak, Michal; Zeiner, Herwig; Tschuden, Julia; Quadri, Mohmammad Jusuf; Garcia-Mila, Ignasi; et al. (Future generation computer systems, 2024)
This paper presents an innovative IIoT multi-level platform tailored to address the specific needs of the mining domain. The platform has been conceptualized and built in the context of the illuMINEation European project. For this purpose, mining specific use cases have been designed such as promoting underground safe areas, performing efficient mining operations or boosting predictive maintenance approaches. Then, specific requirements have been identified and, as a result, the platform has been developed. It consists of four-level layered platform: (1) edge devices layer to manage several sensors deployed in the mines; (2) edge box layer to provide in-mine operations such as filtering, streaming and processing; (3) fog layer which offers an overall perspective of each mine; and (4) cloud layer to centralize the data of all the mines and to provide powerful processing capabilities. In addition, the platform is robustly secured in terms of protecting communications confidentiality and access control and also provides a toolbox aimed at manipulating 3D complex images to obtain operable mine-domain novel user interfaces. Finally, a platform validation is proposed where three different use cases are explained to better show and demonstrate the capabilities of the platform.
Publisher Copyright: © 2024
Keywords: Big data; Cloud continuum; Edge; Fog; Mine digitalization

Flow-induced erosion modelling of cohesive material with coupled CFD-DEM approach - Rahimilarki, Mohsen; Vollmann, Sandra; Jin, Shengli (Minerals engineering, 2024)
Erosion is one of the continuous wear mechanisms in cohesive materials caused by the shear stress applied by the fluid flow at the liquid–solid interface. The erosion resistance of cohesive materials is significantly influenced by the strength of the cohesive bonds that hold the particles together, increasing the complexity of the mechanism. The erosion rate of cohesive materials depends on the critical shear stress (CSS) and the erodibility coefficient at the surface. The current understanding of the relationship among the inter-particle bond strength, CSS, erodibility coefficient, and their respective contributions to the flow-induced erosion process is still lacking; therefore, it cannot be adequately described mathematically. The present research offers a coupled computational fluid dynamics (CFD)–discrete element method (DEM) approach to visualize and quantitatively analyze the flow-induced erosion in cohesive materials. The capability and accuracy of the developed model were validated using experimental data available in the literature. A cohesion model was then employed to describe the strength of the cohesive bond, and the effects of the cohesion energy density (CED) on the CSS and erodibility coefficient were investigated. The analysis indicated that for cohesive materials, the non-dimensional CSS not only is affected by the particle Reynolds number but also strongly depends on CED. The simulation results indicated that by increasing the CED value from 500 to 900kJ/m 3, the CSS increased by 25 %, and the erodibility coefficient decreased by 62 %. The proposed CFD–DEM approach can effectively estimate the erosion initiation and erosion rate of cohesive materials in different applications and geometries.
Publisher Copyright: © 2024 The Authors
Keywords: CFD–DEM modeling; Cohesion energy density; Cohesive material; Critical shear stress; Erodibility coefficient

Reprocessable carbon fiber vitrimer composites - Sharma, Harsh; Bender, Marcel; Kim, Geonwoo; Lee, Dongkwan; Caglayan, Cigdem; Schlögl, Sandra; Yun, Gun Jin; Kumar, Ajay; Rana, Svarendra (Journal of Applied Polymer Science, 2024)
Carbon fibers (CFs) are experiencing a growing demand owing to their lowspecific weight, exceptional mechanical properties, superior temperature, andcorrosion resistance, however, their sustainability and energy consumptionduring manufacturing is still a challenge. Therefore, reclamation of waste CFsand their reformatting has gained significant attention. Herein, we synthesizeda chemically degradable vitrimer matrix by curing bisphenol-A diglycidyl ether(BADGE) with 2-aminophenyl disulfide (2-AFD) and further utilized thematrix for the development of CF reinforced composites (CFRCs) through vac-uum-assisted resin infusion molding (VARIM) process. The obtained vitrimericsystem and its composites show excellent mechanical, self-adhering, shape-memory, and reprocessing properties. Meanwhile, the developed CFRP vitri-mer composites can be rapidly dissolved in thiol solvent (1-octanethiol), result-ing in the efficient recycling of CFs. X-ray diffraction, scanning electronmicroscopy, and Raman spectroscopy validate that the chemical structure ofthe recycled fibers closely resembles the structure of the original CFs. Therecycled CFs were further used to prepare second generation composite mate-rials with excellent thermal, dynamic, and mechanical properties for nonstruc-tural applications (e.g., sports, automotive, etc.). Thus, with an effective CFrecycling method, this study can assist in preparing reliable, long-term func-tional, recyclable, and high-performance composites.
Publisher Copyright: © 2024 Wiley Periodicals LLC.
Keywords: Crosslinking; Recycling; Thermosets; thermosets; recycling; crosslinking

Microstructure evolution and mechanical properties of a lamellar AlCoCrFeNi2.1 eutectic high-entropy alloy processed by high-pressure torsion - Zhang, Zequn; Fellner, Simon; Hohenwarter, Anton; Renk, Oliver; Huang, Yong; Chen, Zhuo; Song, Kaikai; Li, Caiju; Gammer, Christoph; Eckert, Jürgen (Materials science and engineering: A, Structural materials: properties, microstructure and processing, 2024)
High-pressure torsion (HPT) was applied to a lamellar eutectic high-entropy alloy (EHEA) to study the effect of severe plastic deformation (SPD) on the composite structure and mechanical properties. We found that the existence of multiple phases affects defect distribution and the fragmentation process during HPT. Structural evolution shows orientation dependence with respect to the shear plane, which finally leads to a refined multiphase structure with nanograins and vortex clusters after a shear strain γ of 24. In nanograins, dislocation-mediated deformation prevails. The high density of grain boundaries, forest dislocations, and the generation of deformation twins restrict dislocation movement. As a result, an EHEA with a yield strength of 1.75 GPa, an excellent tensile strength of 2.20 GPa, and an appreciable failure strain of 5 % is realized. Our results demonstrate that the HPT deformation process of the lamellar EHEA is significantly affected by the structure. SPD on the multiphase structure is a suitable route for designing high-strength yet ductile alloys.
Publisher Copyright: © 2024 The Authors
Keywords: Eutectic high-entropy alloys; Grain refinement; Mechanical properties; Severe plastic deformation; Structure evolution

Community-Based Disaster Risk Reduction - Cvetković, Vladimir M. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Community-Based Disaster Risk Reduction (CBDRR) plays a vital role in strengthening the resilience of local communities against both natural and man-made disasters. This paper seeks to examine the role of CBDRR in enhancing the resilience of local communities to both natural and man-made disasters. It underscores the critical importance of active community involvement across all stages of disaster management, from preparedness and mitigation to response and recovery. The paper also explores the key factors that contribute to the successful implementation of CBDRR, including institutional backing, capacity development, inclusive strategies, and the use of modern technologies. Additionally, it discusses the challenges and opportunities in building strong partnerships between local communities and external stakeholders, which are crucial for ensuring the sustainability of these efforts. Finally, the paper offers recommendations aimed at improving the effectiveness of CBDRR initiatives, drawing on insights gained from past disaster experiences. The findings of this study point to the importance of continuous monitoring and evaluation of CBDRR programs to maintain their relevance and ensure their effectiveness as risks evolve. Incorporating lessons learned from past disasters into future planning also plays a crucial role in helping communities enhance their resilience over time. Ultimately, by encouraging collaboration between communities, governments, and various organizations, CBDRR lays the foundation for a comprehensive disaster management framework that is equipped to meet future challenges and supports long-term sustainable development.

Tactical Approaches to Protection and Rescue in Traffic Accident-Induced Disasters - Cvetković, Vladimir M. (Conference Title: "Firefighting and Emergency Rescue Operations in Addressing the Consequences of Traffic Accidents Involving Electric Vehicles" Organizer: The conference is organized by the Serbian-Russian Humanitarian Center (SRHC) with the support of the International Civil Defense Organization (ICDO). Date and Venue: The event will take place from September 25 to 26, 2024, at the Serbian-Russian Humanitarian Center in Niš, Republic of Serbia. Details: This international scientific-practical conference aims to address the challenges and strategies associated with firefighting and emergency rescue operations specifically related to traffic accidents involving electric vehicles. The event will bring together experts, professionals, and researchers in the field of fire safety, emergency management, and electric vehicle technology to share knowledge, experiences, and best practices., 2024)
This study delves into the complex challenges that arise when managing rescue operations in the aftermath of traffic accidents spanning various forms of transportation, including roads, railways, aviation, and waterways. Given the inherent complexity of traffic-related disasters, these events typically necessitate well-coordinated rescue strategies, involving the collaboration of multiple emergency services and the use of specialized equipment. The legal framework set forth by the Republic of Serbia plays a pivotal role in shaping the procedures and responsibilities within these rescue efforts, guiding the allocation of resources, enforcing safety protocols, and ensuring effective coordination between different agencies. Moreover, the incorporation of innovative technical solutions is critical in successfully extricating victims from perilous situations. This paper also underscores the vital importance of preventive measures, particularly in road traffic, which are mandated by national legislation. The establishment of specialized investigative bodies, such as the Traffic Accident Investigation Center, has greatly enhanced the systematic approach to preventing future incidents. By examining the various components of rescue operations, this research highlights the essential role of timely and efficient interventions in minimizing casualties and mitigating the broader impacts of traffic disasters.

Comprehensive Risk and Efficacy Analysis of Emergency Medical Response Systems in Serbian Healthcare: Assessing Systemic Vulnerabilities in Disaster Preparedness and Response - Cvetković, Vladimir M.; Tanasić, Jasmina; Renner, Renate; Raupenstrauch, Harald; Rokvić, Vanja; Beriša, Hatidža (2024)

Novel Fe-Mo intermetallic composite synthesized via diffusional-displacive mixed-mode transformation - Varanasi, Rama Sirnivas; Srikakulapu, Kiranbabu; Utsumi, Reina; Saitoh, Hiroyuki; Schnitzer, Ronald; Akiyama, Eiji; Koyama, Motomichi (Materials characterization, 2024)
Transition metal-based intermetallic materials are candidates for high-temperature structural applications. However, they are limited by their low fracture toughness at ambient temperature. Given Fe is a low-cost metal with a low environmental impact, it is necessary to design tough Fe-based intermetallic alloys. We report a novel ferrite-Fe 2Mo intermetallic synthesized through arc melting and quenching of Fe 0.78Mo 0.22 alloy. Diffusional-displacive mixed-mode transformation of the parent ferrite phase resulted in the formation of nanocomposite microstructure. Two distinct microstructure morphologies of the product μ phase were observed: (i) allotriomorphic phase formation at the parent ferrite grain boundaries and (ii) formation of basket-weave Widmanstätten structures at the parent grain interior. Electron probe microanalysis (EPMA) revealed Mo partitioning across ∼800 nm wide Widmanstätten laths, establishing that it is a diffusional-displacive mixed-mode transformation. We performed atom probe tomography (APT) investigations to ascertain the nanoscale Mo solute partitioning. Based on the chemistry of the retained parent ferrite, the Mo partitioning temperature was estimated to be ∼865 °C. Mo partitioned Widmanstätten lath formation is clarified using a shear-assisted diffusional transformation model. APT studies further revealed that the composition of the product μ phase corresponds to stoichiometric Fe 2Mo. It is an anomaly since stoichiometric Fe 2Mo typically corresponds to λ C14 Laves phase. We explain the mechanism of μ phase formation with Fe 2Mo stoichiometry. The nanocomposite exhibits a high hardness (HV 2) of 7.54 GPa and excellent toughness (evidenced by resistance to indentation cracking).
Publisher Copyright: © 2024 The Authors
Keywords: Displacive transformation; Fe–Mo alloy; Intermetallic composite; Mixed-mode transformation; Widmanstätten lath

Reactive binder components for building materials by thermochemical upcycling of mineral wastes and by-products - Steindl, Florian Roman; Vallazza-Grengg, Cyrill; Rudic, Ognjen; Radinger, Stefanie; Hassan, Amr Hussein Mokhtar; Weisser, Katharina Maria; Krammer, Anna; Doschek-Held, Klaus; Ratz, Bettina; Steiner, Sarah; Gatschlhofer, Christoph; Mittermayr, Florian (2024)
European Mineralogical Conference, EMC 2024, EMC 2024 ; Conference date: 18-08-2024 Through 23-08-2024

Coupling structural, chemical composition and stress fluctuations with relaxation dynamics in metallic glasses - Şopu, Daniel; Yuan, Xudong; Spieckermann, Florian; Eckert, Jürgen (Acta Materialia, 2024)
Understanding the atomistic mechanisms of relaxation dynamics in metallic glasses remains a longstanding challenge. Here, using microsecond time scale molecular dynamics simulations, three main relaxation stages in metallic glasses are identified. At about 0.6T, chemical composition plays a dominant role in the relaxation, manifested by stress accumulation and only minimal variations in structure. As T approaches, the confluence of structural heterogeneity and chemical composition leads to the decoupling of relaxation mechanisms. At this temperature, the relaxation results in a structure with a lower energy state and a lower level of stress. In the supercooled liquid regime, an extensive increase in the number of closed-packed icosahedral clusters is responsible for accelerated structural relaxation while their packing frustration leads to the accumulation of intrinsic residual stresses in the glass. The atomistic origin of these dynamic relaxation modes is discussed in terms of structural, chemical composition and stress variations.
Publisher Copyright: © 2024 Acta Materialia Inc.
Keywords: Dynamics relaxation; Metallic glasses; Molecular dynamics simulations

Fertilization efficiency of thirty marketed and experimental recycled phosphorus fertilizers - Hernandez-Mora, Alicia; Duboc, Olivier; Lombi, Enzo; Bünemann, Else K.; Ylivainio, Kari; Symanczik, Sarah; Delgado, Antonio; Abu Zahra, Nadine; Nikama , Johanna; Zuin, Lucia; Doolette, Casey L.; Eigner, Herbert; et al. (Journal of Cleaner Production, 2024)
Recycling phosphorus (P) from waste streams like sewage sludge, animal manures or food industry by-products is required to sustain soil fertility without depleting non-renewable P resources. Several technologies are available for P recovery, leading to fertilizers differing in P solubility and bioavailability. In this study, thirty fertilizers obtained through different technologies were tested to assess if their fertilization efficiency was equivalent to mineral soluble fertilizer applied as triple superphosphate (TSP). The main selection criteria were (1) ensuring a wide chemical diversity, and (2) choosing products already on the market or at a late stage of development, to encompass a representative selection of current and future recycled fertilizers. The products were classified according to their organic carbon content and neutral ammonium citrate (NAC), and the main P species of each fertilizer was determined through K-edge and L2,3-edge X-ray absorption near edge structure spectroscopy (XANES). Three pot experiments with wheat, barley and ryegrass were conducted in three growing substrates with contrasting properties, all within a pH range of 5.8–6.9. Fertilizers containing ammonium magnesium phosphate, monoammonium phosphate, monocalcium phosphate, and dicalcium phosphate type species as dominant P species showed a similar fertilization efficiency to TSP, while fertilizers with hydroxyapatite, tricalcium phosphate, phytic acid or iron phosphates as their main P species had lower fertilization efficiencies. We conclude that while the trend towards high-efficiency, refined inorganic recycled P fertilizers is positive, lower-performing, mostly unrefined fertilizers must be assessed in light of their long-term P supply potential and additional benefits to soil health owing to their content of organic matter and other nutrients.
Publisher Copyright: © 2024 The Authors
Keywords: Industrial by-product; Manure; Mineral replacement value; Sewage sludge; Struvite; XANES speciation

Mapping the composite nature of clay matrix in mudstones: integrated micromechanics profiling by high-throughput nanoindentation and data analysis - Shi, Xiangyun; Misch, David; Žák, Stanislav; Cordill, Megan; Kiener, Daniel (Geomechanics and geophysics for geo-energy and geo-resources, 2024)
Mudstones and shales serve as natural barrier rocks in various geoenergy applications. Although many studies have investigated their mechanical properties, characterizing these parameters at the microscale remains challenging due to their fine-grained nature and susceptibility to microstructural damage introduced during sample preparation. This study aims to investigate the micromechanical properties of clay matrix composite in mudstones by combining high-speed nanoindentation mapping and machine learning data analysis. The nanoindentation approach effectively captured the heterogeneity in high-resolution mechanical property maps. Utilizing machine learning-based k-means clustering, the mechanical characteristics of matrix clay, brittle minerals, as well as measurements on grain boundaries and structural discontinuities (e.g., cracks) were successfully distinguished. The classification results were validated through correlation with broad ion beam-scanning electron microscopy images. The resulting average reduced elastic modulus (Er) and hardness (H) values for the clay matrix were determined to be 16.2 ± 6.2 and 0.5 ± 0.5 GPa, respectively, showing consistency across different test settings and indenter tips. Furthermore, the sensitivity of indentation measurements to various factors was investigated, revealing limited sensitivity to indentation depth and tip geometry (when comparing Cube corner and Berkovich tip in a small range of indentation depth variations), but decreased stability at lower loading rates. Box counting and bootstrapping methods were applied to assess the representativeness of parameters determined for the clay matrix. A relatively small dataset (indentation number = 60) is needed to achieve representativeness, while the main challenges is to cover a representative mapping area for clay matrix characterization. Overall, this study demonstrates the feasibility of high-speed nanoindentation mapping combined with data analysis for micromechanical characterization of the clay matrix in mudstones, paving the way for efficient analysis of similar fine-grained sedimentary rocks.
Publisher Copyright: © The Author(s) 2024.
Keywords: BIB-SEM; Bootstrapping; Geoenergy; k-means; Mudstone; Nanoindentation; REA; Shale

Phase-Field Modeling of Hydraulic Fracture in Porous Media with In Situ Stresses - You, Tao (Processes, 2024)
While the variational phase-field model has been widely used in modeling fracturing in porous media, it poses a challenge when applying high confining pressures on a model because the relatively large deformation induced by the confining pressures might cause undesired crack nucleation when the strain decomposition scheme are used, which is not consistent with engineering observations. This study proposes a two-step strategy to incorporate in situ stresses into phase-field modeling of hydraulic fractures, addressing the limitations of previous approaches in capturing realistic fracture initiation and propagation under high confinement. A micromechanics-based hydromechanical phase-field model is presented first, and the proposed two-step strategy is investigated with different strain decomposition schemes: isotropic, volumetric–deviatoric, and no-tension models. Two numerical examples show that the two-step strategy effectively achieves a desired initial state with geostatic stresses and zero strain, allowing for accurate simulations even in the presence of complex natural fractures. The efficiency of the proposed two-step strategy for incorporating in situ stresses is highlighted, and the challenges associated with capturing stiffness recovery and shear fracture nucleation under high confinement using strain-based models are discussed.
Publisher Copyright: © 2024 by the author.
Keywords: crack growth; hydraulic fracture; in situ stress; natural fractures; phase-field method

Insight into Carbon Black and Silica Fume as Cement Additives for Geoenergy Wells: Linking Mineralogy to Mechanical and Physical Properties - Sammer, Thomas; Nasiri, Arash; Kostoglou, Nikolaos; Ravi, Krishna; Raith, Johann (C – journal of carbon research, 2024)
The geoenergy industry has challenging demands on cements used as downhole materials. Once placed in the annular space, the cement sheath must be very low permeability and mechanically durable. Its characteristics are strongly influenced by its microstructure. A holistic approach, including combined mineralogical, physical, and mechanical investigations, provides a better understanding of how these characteristics interplay. Class G cement was investigated and compared to cement formulations containing carbon black or silica fu me, trying to tailor its performance. The addition of carbon black and silica fume has some effect on the modal and chemical phase composition and results in a much denser microstructure. Furthermore, porosity is reduced while the pore size distribution remains similar. Samples containing carbon black have a reduced Young’s modulus, indicating a more plastic behavior. The addition of silica fume increased both mechanical strength and permeability. However, comparable results can also be achieved by carefully tuning the water/cement ratio of the initial slurry.
Publisher Copyright: © 2024 by the authors.
Keywords: carbon black; geoenergy well cement; mechanical properties; microstructure; mineralogy; physical properties; silica fume

Selecting the suitable thermoplastic elastomer as the main component in the feedstock for metal material extrusion of aluminium - Momeni, Vahid; Shahroodi, Zahra; Hufnagl, Margarete; Gonzalez-Gutierrez, Joamin; Duretek, Ivica; Schuschnigg, Stephan; Kukla, Christian; Holzer, Clemens (Results in Engineering, 2024)
Metal material extrusion (MMEX) involves the systematic deposition of material layer by layer, followed by debinding and sintering to produce fully dense metallic parts. The feedstocks, initially comprising metal powder and a binder system, are pivotal in determining processability and final properties. This study utilized polylactic acid (PLA) as the backbone and a thermoplastic elastomer (TPE) as the primary, solvent-debindable component in the binder system, with a 50 and 55 vol% aluminium (Al) powder content. PLA was selected due to its lower degradation temperature and to try to increase the sustainability of the MMEX process. An initial experimentation with various TPEs, employing thermal analysis (TGA and DSC), rheological behavior assessment, mechanical property testing, contact angle measurement, and solvent debinding processes, aimed to identify the most suitable TPE for this study. The results demonstrated that a very low interfacial tension between PLA and TPE is not desirable, as it may result in the removal of some powder particles during the solvent-debinding process. The TPE type with lower viscosity, optimum interfacial tension with PLA, low residue after degradation, adequate rigidity, and flexibility is proper for use as the soluble part of the binder system. After selecting of the appropriate TPE, the printability at a nozzle temperature of 270 °C was undertaken. The solvent debinding process for printed samples was conducted at room temperature. The results indicated that 90 wt% of the TPE was removed successfully from the samples printed with 30 vol% PLA in binder formulation without any defects during solvent debinding.
Publisher Copyright: © 2024 The Authors
Keywords: Aluminium feedstock; Contact angle; Fused filament fabrication (FFF); MMEX; Polylactic acid (PLA)

Computer-Aided Engineering (CAE) in Raw Material Processing & Particulate Media Industries - Fimbinger, Eric (Berg- und hüttenmännische Monatshefte : BHM, 2024)
Keywords: CAE; Computer-aided engineering; Particle simulation; particle mechanics; virtual prototyping; Editorial

Waste-to-Value Feasibility Study - Shahroodi, Zahra; Krempl, Nina; Zidar, David; Mayrhofer, Tina; Kirschnick, Ulrike; Arbeiter, Florian; Duretek, Ivica; Holzer, Clemens (ACS Sustainable Chemistry and Engineering, 2024)
The reinforcement of recycled polypropylene with virgin glass fibers is a widely adopted practice to enhance the mechanical properties of recycled materials. Substituting virgin glass fibers with recycled ones from authentic waste streams poses multiple challenges. This article shows a possible solution for reusing two waste fractions that count as outstandingly challenging when trying to reach a high degree of circularity. Composites consisting of a recycled polypropylene matrix derived from Austrian household waste as well as 10, 30, and 50 wt % of two different postindustrial chopped polypropylene-glass fibers (GF-PP) were produced by extrusion in a twin-screw extruder, followed by injection molding. Fiber length measurements were conducted to characterize the quality and heterogeneity of the two input GF-PP waste composites. Subsequently, the performance of these compounds was assessed by investigating their thermal, rheological, morphological, and mechanical properties. The study revealed that the initial formulation and manufacturing method of the chopped GF-PP composite exerted a significant influence on the extent of reinforcement achieved in the recycled polypropylene composites. Despite the same processing principles and parameters, the different types of GF-PP waste composites exhibited significant differences in terms of their rheological and mechanical properties. The trend was also visible when comparing the results across various compound ratios. These compounds also demonstrated acceptable flow behavior and processability. Despite substantial fiber breakage during the compounding and injection molding processes, resulting in an 87-90% reduction in the average fiber length, the produced composites displayed appropriate mechanical properties, which are mostly comparable to virgin glass-fiber-reinforced polypropylene. The findings indicate that by optimizing both the type of postindustrial GF-/PP composites added to recycled polypropylene and the blend ratio, chopped GF-PP can be effectively enhanced and converted into short-fiber-reinforced recycled polypropylene. This process serves as a model for improved recycling practices.
Publisher Copyright: © 2024 The Authors. Published by American Chemical Society.
Keywords: fiber length; mechanical properties; polypropylene-glass fiber composite; recycled polypropylene

Effect of Surface Contamination on Near-Infrared Spectra of Biodegradable Plastics - Mhaddolkar, Namrata; Koinig, Gerald; Vollprecht, Daniel; Astrup, Thomas Fruergaard; Tischberger-Aldrian, Alexia (Polymers, 2024)
Proper waste sorting is crucial for biodegradable plastics (BDPs) recycling, whose global production is increasing dynamically. BDPs can be sorted using near-infrared (NIR) sorting, but little research is available about the effect of surface contamination on their NIR spectrum, which affects their sortability. As BDPs are often heavily contaminated with food waste, understanding the effect of surface contamination is necessary. This paper reports on a study on the influence of artificially induced surface contamination using food waste and contamination from packaging waste, biowaste, and residual waste on the BDP spectra. In artificially contaminated samples, the absorption bands (ADs) changed due to the presence of moisture (1352–1424 nm) and fatty acids (1223 nm). In real-world contaminated samples, biowaste samples were most affected by contamination followed by residual waste, both having altered ADs at 1352–1424 nm (moisture). The packaging waste-contaminated sample spectra closely followed those of clean and washed samples, with a change in the intensity of ADs. Accordingly, two approaches could be followed in sorting: (i) affected wavelength ranges could be omitted, or (ii) contaminated samples could be used for optimizing the NIR database. Thus, surface contamination affected the spectra, and knowing the wavelength ranges containing this effect could be used to optimize the NIR database and improve BDP sorting.
Publisher Copyright: © 2024 by the authors.
Keywords: Biologisch abbaubare Kunststoffe,; PLA; Oberflächenkontamination; NIR-Sortierung; biodegradable plastics waste management; effect on NIR spectrum; near-infrared sorting; polylactic acid; surface contamination; thermoplastic starch

Fatigue Crack Propagation Across the Multiple Length Scales of Technically Relevant Metallic Materials - Hohenwarter, Anton; Leitner, Thomas; Pippan, Reinhard (Annual review of materials research, 2024)
The fundamentals of our understanding of fatigue crack propagation were formed more than 60 years ago by Paul C. Paris. Since then, the run toward new metallic materials and alloys with ever finer-grained microstructures has had a large impact on research. Along with enormous variation of the microstructural length scales (i.e., grain size), the essential parameters for the description of fatigue crack growth, such as the crack propagation rate and plastic zone size, also exhibit an immense change from the subnanometer to the micrometer regime. These enormous variations in the fatigue crack growth behavior’s controlling parameters motivate this contribution. This article presents an overview of the effect of grain size, from the millimeter to the nanometer grain-size regime, on fatigue crack propagation of mainly ductile metals and alloys with an attempt to summarize the most important findings and underlying physical phenomena, including with respect to selected materials such as pure iron, nickel, and austenitic and pearlitic steel.
Publisher Copyright: © 2024 by the author(s).
Keywords: crack closure; fatigue crack propagation; fracture; nanocrystalline; severe plastic deformation; ultrafine-grained

Forearc magmatism in the Pannonian basin recorded by metasomatised skarnoid xenoliths in Pliocene basalt (Novohrad-Gemer Volcanic Field, Slovakia) - Reato, Luca; Huraiová, Monika; Ackerman, Lukáš; Ďurišová, Jana; Horschinegg, Monika; Konečný, Patrik; Meisel, Thomas C.; Hurai, Vratislav (Lithos, 2024)
Anorthite-diopside-spinel-forsterite xenoliths occur in basaltic lava flow in northern part of the Pannonian basin in the Novohrad-Gemer Volcanic Field (NGVF). Several lines of geochemical evidence suggest that the typical skarn assemblage originated by multiple carbonatitic and alkaline silicate metasomatism of pristine basalt to picrobasalt protolith rather than by the modification of crustal carbonates around shallow magma chambers. Interaction with mantle-derived magnesite or dolomite carbonatite melt triggered the crystallization of neoformed forsterite at the expense of primary clinopyroxene. The alkaline silicate metasomatism resulted in the replacement of primary diopside and augite by neoformed aegirine and aegirine-augite accompanied by amphiboles (richterite, katophorite, arfvedsonite). Weakly metasomatised Group 1 xenoliths retained their fore-arc magmatic geochemical signatures: flat REE patterns, low concentrations of high-field strength elements (Ti, P, Zr) and Ni compared to MORB, low ratios of highly-to-less incompatible elements (Ti/V, Zr/Y) relative to MORB, low Na2O, low total REE, and supra-subduction affinity of primary clinopyroxenes, being thus analogues to fore-arc basalts (FAB). In contrast, strongly metasomatised Group 2 xenoliths exhibit LREE-enriched patterns sub-parallel with those of host trachybasalts. Some Group 1 xenoliths also exhibit large positive Eu anomalies and strongly depleted signatures diagnostic of low-pressure plagioclase-pyroxene cumulates. One xenolith with complementary negative Eu, Sr and positive Rb anomalies has been identified as high-Mg basaltic andesite melt residuum. Sr and Nd isotopes plot along the OIB-MORB array. The Group 1 converges at initial 87Sr/86Sr and 143Nd/144Nd ratios of 0.7038–0.7041 and 0.5127–0.5128, respectively, thus recording a 140–190 Ma old mantle source. Thermobarometry data on metasomatically unmodified pyroxenes have been arranged along decompression cooling trend, propagating from ∼1230 °C and ∼ 1 GPa and ending at ∼1160 °C around atmospheric pressure. The maximum pressure indicates the melt generation zone ∼35 km deep, reflecting thin lithospheric mantle. The FABs identified for the first time in the AlCaPa megaunit corroborate the affinity of the NGVF lithospheric segment to Dinarides.

Geospatial and Temporal Patterns of Natural and Man-made (Technological) Disasters (1900-2024): Insights from Different Perspectives - Cvetković, Vladimir M.; Renner, Renate; Lukić, Tin; Aleksova, Bojana (2024)

Virtual Prototyping of the RM Active Grid®: a DEM-MBD Study - Falkner, Philipp; Fimbinger, Eric; Flachberger, Helmut (Berg- und hüttenmännische Monatshefte : BHM, 2024)
Numerical simulation is an established tool to improve knowledge of complex systems and to accelerate the development of new prototypes. In this contribution, the patented Active Grid® made by the company RM RUBBLE MASTER HMH GmbH is examined.In an initial step, representative system parameters (spring properties) are found via a multibody dynamic simulation; at this point, without particles acting on the system components. After that, the virtually defined Active Grid® system is loaded with particles in order to include the interaction effects of various bulk materials acting on the system’s mechanical components. For this purpose, a DEM-MBD co-simulation, extending the discrete element method (DEM) towards multibody dynamics (MBD) simulation, is performed, accounting for the bulk materials via DEM and the interacting system components via MBD. This bi-directional co-simulation enables the consideration of interactions between the bulk materials (the particles) and the driven spring-damper system (the moving system components).With this virtual prototype of the Active Grid®, performance benefits and characteristics in terms of screening efficiency for different material types and varying drive speeds are analysed. The overall aim is to achieve a scalable DEM-MBD model that allows virtual prototyping and, especially, optimisation for future system developments.
Keywords: Discrete element method; DEM; multibody dynamics; MBD; multiphysics; virtual prototyping; Active Grid

FFG-Endbericht: Innovationsscheck mit Selbstbehalt, Desoxidation von Stahlschmelzen mit Al-haltigen Vorstoffen - Wibner, Stefan; Antrekowitsch, Helmut (2024)

Glass and nanocrystalline phase formation in CuZrAg alloys - Putz, B.; Milkovič, O.; Mohanty, G.; Ipach, R.; Pethö, L.; Milkovičová, J.; Saksl, K.; Michler, J. (Materials and Design, 2024)
Publisher Copyright: © 2024 The Author(s)
Keywords: Combinatorial materials science; Magnetron sputtering; Polymer substrate; Structure analysis; Thin film metallic glass; X-ray diffraction

On matching and periodicity for (N,α)-expansions - Kraaikamp, Cor; Langeveld, Niels (The Ramanujan Journal, 2024)
Recently a new class of continued fraction algorithms, the (N,α)-expansions, was introduced in Kraaikamp and Langeveld (J Math Anal Appl 454(1):106–126, 2017) for each N∈N, N≥2 and α∈(0,N-1]. Each of these continued fraction algorithms has only finitely many possible digits. These (N,α)-expansions ‘behave’ very different from many other (classical) continued fraction algorithms; see also Chen and Kraaikamp (Matching of orbits of certain n-expansions with a finite set of digits (2022). To appear in Tohoku Math. J arXiv:2209.08882), de Jonge and Kraaikamp (Integers 23:17, 2023), de Jonge et al. (Monatsh Math 198(1):79–119, 2022), Nakada (Tokyo J Math 4(2):399–426, 1981) for examples and results. In this paper we will show that when all digits in the digit set are co-prime with N, which occurs in specified intervals of the parameter space, something extraordinary happens. Rational numbers and certain quadratic irrationals will not have a periodic expansion. Furthermore, there are no matching intervals in these regions. This contrasts sharply with the regular continued fraction and more classical parameterised continued fraction algorithms, for which often matching is shown to hold for almost every parameter. On the other hand, for α small enough, all rationals have an eventually periodic expansion with period 1. This happens for all α when N=2. We also find infinitely many matching intervals for N=2, as well as rationals that are not contained in any matching interval.
Publisher Copyright: © The Author(s) 2024.
Keywords: N-continued fractions; quadratic irrationals; matching; periodicity; Matching; 37A45; Quadratic irrationals; Periodicity; 37E15; 37E05; (N,α)-continued fractions

The Optical Spectra of Hydrogen Plasma Smelting Reduction of Iron Ore - Pauna, Henri; Ernst, Daniel; Zarl, Michael Andreas; Souza Filho, Isnaldi Rodrigues de; Kulse, Michael; Büyükuslu, Ömer; Jovičević-Klug, Matic; Springer, Hauke; Huttula, Marko; Schenk, Johannes; Fabritius, Timo; Raabe, Dierk (Steel research international, 2024)
Due to the ever-increasing demand for high-quality steel and the need to reduce CO2 emissions, research and development of sustainable steelmaking processes have gained a lot of interest in the past decade. One of these processes is the hydrogen plasma smelting reduction (HPSR), which has proven to be a promising solution for iron ore reduction where water vapor is formed instead of CO2. However, due to the highly dynamic and sometimes unpredictable behavior of plasmas and their nonlinear interaction with the liquid oxides, the monitoring and control of the underlying processes must be improved. This article explores the usage of optical emission spectroscopy (OES) and image analysis for HPSR process monitoring at laboratory and pilot scale. The results cover the time evolution of the OES and camera data with the focus on the most interesting radiating species, such as atomic hydrogen, iron, and oxygen together with the FeO molecule. In addition, the advantages, disadvantages, and requirements of these methods for HPSR process monitoring are discussed.
Publisher Copyright: © 2024 The Authors. Steel Research International published by Wiley-VCH GmbH.
Keywords: color analysis; hydrogen plasma smelting reduction; iron ore; optical emission spectroscopy; process monitoring

On the fatigue crack growth behavior of nanocrystalline CrMnFeCoNi - Pillmeier, Simon; Burtscher, Michael; Laplanche, Guillaume; Pippan, Reinhard; Eckert, Jürgen; Hohenwarter, Anton (International Journal of Fatigue, 2024)
The fatigue crack growth (FCG) behavior of the equimolar CrMnFeCoNi Cantor-alloy in the nanocrystalline grain size regime has been explored with special focus on the influence of specimen orientation and the effect of additional heat-treatments. For the synthesis severe plastic deformation using high-pressure torsion (HPT) was used. The results were critically discussed regarding the impact of grain size on the FCG-behavior and compared to a conventional 316L stainless steel in the nanocrystalline state: The reduction of grain size in the Cantor alloy from the micrometer to the nanometer regime invokes crack growth rates being about one order of magnitude higher paired with significantly lower threshold values. Furthermore, the sensitivity of thresholds and crack growth rates in the Paris regime on the applied load ratio in the NC material state is also profoundly reduced. This can be explained based on a diminishing contribution of crack closure effects, especially roughness induced closure. Even though the chemical composition differs distinctively, the crack growth rates and fatigue threshold values of the nanocrystalline Cantor alloy and the stainless steel are comparable with the latter being slightly lower for the CrMnFeCoNi alloy. Moreover, the extent of anisotropy is more pronounced than for 316L. Heat-treatment leading in the NC-Cantor alloy to an increasing hardness, has also an effect on the FCG-rate and depends on the specimen orientation. In addition, an unusual self-annealing behavior affecting the FCG behavior of the Cantor alloy was found.
Publisher Copyright: © 2024 The Author(s)
Keywords: Fatigue crack growth; High entropy alloy; Nanocrystalline materials; Severe plastic deformation

Evaluation of the Effectiveness of Search and Rescue Dogs in Finding Survivors During Disasters: The Case of Serbia, Croatia, And Slovenia - Vladimir, Cvetković M.; Miljković, Nemanja (2024)
Disasters, whether natural or human-induced, pose significant threats to human lives, property, and infrastructure. This study examines the effectiveness of search and rescue (SAR) dogs in locating survivors during disasters, with a focus on the experiences in Serbia, Croatia, and Slovenia. The primary goals are to evaluate training protocols, operational challenges, success rates, and the overall impact of SAR dogs in disaster scenarios. The findings indicate that SAR dogs greatly enhance the efficiency of disaster response operations. Their superior sense of smell, agility, and ability to manoeuvre through complex terrains make them crucial for quickly locating survivors. However, the performance of SAR dogs is affected by various factors, including the quality of their training, environmental conditions, and the coordination between handlers and dogs. The research highlights several challenges encountered by SAR dogs, such as extreme weather conditions, hazardous terrains, fatigue, and psychological stress. Additionally, limited resources and inconsistent training standards can hinder their effectiveness. The study underscores the importance of standardized training protocols, increased resource allocation, and better coordination among SAR teams. By addressing these challenges, the efficiency of SAR dogs can be further optimized, resulting in more effective disaster responses and higher survival rates. SAR dogs play an essential role in disaster management in Serbia, Croatia, and Slovenia. Ongoing investment in their training and welfare, along with improved operational protocols, will ensure their crucial contribution to saving lives during disasters. This study contributes to a broader understanding of the effectiveness of SAR dogs and provides practical recommendations for enhancing disaster response strategies.

Legal and Organizational Framework for the Use of Search and Rescue Dogs in Disasters: A Comparative Analysis between Serbia, Croatia, and Slovenia - Vladimir, Cvetković M.; Miljković, Nemanja (International European Congress on Advanced Studies in Basic Sciences, 26-28 July 2024, pp. 1254-1268.At: Amsterdam, Netherlands, 2024)
This study critically explores the legislative frameworks and national regulations of Serbia, Croatia, and Slovenia concerning the engagement, training, and responsibilities of search and rescue dogs and their handlers. The goal is to offer a thorough understanding of how these dogs and their handlers are engaged, trained, and managed in each country. By carefully analyzing the legal foundations, the study aims to clarify the rights, duties, and responsibilities of all parties involved, ensuring that search and rescue dog deployments are conducted within a structured and lawful framework. Such an understanding is crucial for improving disaster management and ensuring a coordinated response to various emergencies. The findings reveal that although each country has strong legal provisions for deploying search and rescue dogs, there are significant differences in the detail and scope of these regulations. Slovenia is notable for its detailed guidelines, regular evaluations, and licensing processes, setting a high standard. Croatia benefits from strong institutional support and active international collaboration, which greatly enhances its disaster response capabilities. On the other hand, Serbia, despite having a solid foundational framework, could improve by better coordinating with non-governmental organizations and aligning more closely with international standards. Key areas for improvement include harmonizing standards, enhancing training programs, increasing public awareness, better resource allocation, and adopting new technologies. By addressing these issues, Serbia, Croatia, and Slovenia can further strengthen their legal and institutional frameworks, ensuring their search and rescue teams are better prepared for disasters. This study emphasizes the need for continuous improvement through collaboration, standardization, and innovation to maximize the effectiveness of search and rescue operations involving dogs.

Fatigue and residual strain monitoring for thermoplastic composite using embedded FBG inscribed in highly-birefringent side-hole elliptical core optical fiber - Wachtarczyk, Karol; Yadav, Neha; Błachut, Aleksander; Gąsior, Paweł; Schledjewski, Ralf; Kaleta, Jerzy (Measurement, 2024)
Monitoring of thermoplastic carbon reinforced composites is critical for the safe operation and optimization of composite structures. Strain measurement during their manufacturing and operation is often achieved with embedded Fiber Bragg Gratings (FBG). However, conventional FBGs can only measure axial strain. To measure multiaxial strain in thermoplastic composites, FBGs inscribed in highly-birefringent side-hole elliptical core optical fiber (SH2 FBG) are proposed. SH2 FBG were used to monitor composite produced by automated tape laying process, first − to measure residual in-plane and out-of-plane strain during the manufacturing stage, second − in plane transverse strain during cyclic loading. It was demonstrated that the sensors can be used to measure multiaxial residual strain, observe changes in material stiffness, and calculate the area of the mechanical hysteresis loop. As a result − it was shown that embedding SH2 FBG can be an effective and robust method for monitoring the carbon fiber reinforced thermoplastic composite.
Publisher Copyright: © 2024 The Author(s)
Keywords: Fatigue; FBG sensor; Polymer-matrix composites; Process monitoring; Strain measurement

The Need for Properly Designed Synthesized Micro- and Nanoplastics with Core–Shell Structure - Galakhova, Anastasiia; Meisel, Thomas C.; Rieß, Gisbert (Microplastics, 2024)
While there are a number of available reference and testing materials for micro- and nanoplastic (MNP) studies in toxicology, they are not well-characterized and do not cover all major polymer types that may potentially pollute the environment. This review article will address the question of why we need properly designed synthesized micro- and nanoplastics with a core–shell structure (with organic–inorganic units) and provide researchers with a scientific basis for the design of synthesized MNP particles. It will include a list of commercially available MNPs, an overview of the theoretical background to polymer particle synthesis, and an analysis of the advantages and disadvantages of MNP preparation methods, namely, fragmentation and synthesis, along with examples of synthesized MNP particles. The current study will demonstrate that polystyrene is one of the most prevalent MNP particle types among reference materials from certification bodies and among testing particles synthesized by chemical scientists. Nevertheless, the global industrial production of polystyrene represents approximately 5% of the total, and it is not a dominant plastic type in the textile or packaging industries. In contrast to mechanically fragmented MNP particles, the synthesis approach offers the potential to control the physico-chemical properties, enabling the more selective detection and quantification, as well as a greater comparability of the results amongst toxicological studies.

Grain boundary segregation for the Fe-P system - Reichmann, Alexander; Tuchinda, Nutth; Dösinger, Christoph Alexander; Scheiber, Daniel; Razumovskiy, Vsevolod I.; Peil, Oleg E.; Matson, Thomas P.; Schuh, Christopher A.; Romaner, Lorenz (Acta materialia, 2024)
In this work we re-assess experimental data for grain boundary (GB) segregation of P in bcc Fe with thermodynamic and statistical methods. The data are based on Auger-Electron-Spectroscopy (AES) measurements which have provided P GB concentrations for various bulk contents and temperatures for ferrite. While in the previous investigations of this system a single-site McLean equation was used to extract segregation enthalpy and entropy, we employ multi-site segregation models as suggested by atomistic simulations. We use a recently introduced methodology based on inter-atomic potentials to calculate the segregation energy spectrum, as well as vibrational entropy and solute-solute interactions of P in polycrystalline Fe, thereby obtaining a three-dimensional distribution of energy, entropy and interactions. Using this trivariate distribution we predict P GB concentrations and compare them to the experimental measurements. Furthermore, we calibrate the parameters of physical models of increasing complexity to the experimental data with an inverse modeling approach based on Bayesian inference. While it is not possible to seamlessly link the results from AES to atomistic modeling, our investigation provides significant new insights for thermodynamic modeling of GB segregation. The vibrational entropy deduced from experiment differs from physics based atomistic simulations even when taking the spectral nature of energy, entropy and interactions into account. However, the correlations of the quantities are in good agreement when considering the trivariate model. Our investigation highlights the need for new and more accurate experimental datasets of GB segregation.
Publisher Copyright: © 2024 The Author(s)
Keywords: Atomistic simulations; Auger-Electron-Spectroscopy (AES); Bayesian inference; Grain boundary segregation; Thermodynamics

Smart predictions of petrophysical formation pore pressure via robust data-driven intelligent models - Krishna, Shwetank; Irfan, Sayed Ameenuddin; Keshavarz, Sahar; Thonhauser, Gerhard; Umer Ilyas, Suhaib (Multiscale and multidisciplinary modeling, experiments and design, 2024)
Predicting pore pressure in the formation is crucial for assessing reservoir geomechanical characteristics, designing drilling schemes/mud programs, and strategies to enhance oil recovery. Accurate predictions are vital for safe and cost-effective exploration and development. Recent research has seen the emergence of intelligent models utilizing machine learning (ML) and deep learning (DL) algorithms, offering promising outcomes. However, there remains a need to identify the most accurate and dependable model among these. This study aims to address this gap by comparing the performance of various ML and DL models, as reported in existing literature, to determine the optimal approach for pore pressure prediction. The sorted machine learning (ML) and deep learning (DL) regression algorithms used for the comparative analysis are decision tree (DT), extreme gradient boosting (XGBoost), random forest (RF), recurrent neural network (RNN), and convolutional neural network (CNN). A total dataset of 22,539 is gathered from five wells (15/9-F-1 A, 15/9-F-1 B, 15/9-F-11 A, 15/9-F-11 T2, and 15/9-F-14) drilled at North-sea Volve oil field, Norway. The first four wells are used to train and test the ML and DL algorithm, and the remaining well (15/9-F-14) is used to evaluate the best-performing algorithm’s universality in predicting pore pressure at the field of study. Seven different petrophysical parameters are used as input parameters to develop the predictive models. Statistical performance metrics are carried out to analyze the applied ML and DL performance. Based on performance indicators, the RF algorithm showed superior results compared to other predictive models with R 2 and RMSE values of 0.97 and 2.70 MPa, respectively. Furthermore, the best-performing predictive model with low prediction error RMSE value is applied to the other well dataset from the field of study to access the universality of the RF algorithm to predict pore pressure in the field of study. The results of the universality analysis show a satisfactory prediction accuracy with R 2 and RMSE values of 0.905 and 6.48 MPa, respectively.
Publisher Copyright: © The Author(s) 2024.
Keywords: Deep learning; Machine learning; Petrophysical properties; Pore pressure; Prediction

State-of-the-art and future directions of fs-laser assisted specimen preparation techniques for atom probe tomography measurements - Tkadletz, Michael; Schiester, Maximilian; Renk, Oliver; Schalk, Nina (Microscopy and microanalysis, 2024)

Unraveling the potential of Cu addition and cluster hardening in Al-Mg-Si alloys - Aster, Philip; Dumitraschkewitz, Phillip; Uggowitzer, Peter; Tunes, Matheus Araujo; Schmid, Florian; Stemper, Lukas; Pogatscher, Stefan (Materialia, 2024)
With the aim of further exploiting the trade-off between formability and strength in Al alloys, this study addresses the influence of Cu in Al-Mg-Si alloys that achieve simultaneously high strength and high ductility via cluster hardening. The study carefully examines the mechanical properties and strain hardening behavior of various Mg/Si ratios with and without Cu and compares the effects of pre-aging and atypical long-term low-temperature aging treatments at 100°C to conventional heat treatments. Interestingly, in all cases adding Cu improved ductility. In the extremal case cluster hardening plus the addition of Cu quadruples elongation, while keeping yield strength similar to the classical T6 state. The results of the study are discussed with a focus on the dense distribution of clusters and partial hardening phases based on atom probe tomography data. Most importantly, the cluster-hardened alloys exhibit pronounced strain-hardening properties, which we evaluate using a Kocks-Mecking approach in combination with a microstructural analysis in the pre-aging and long-term aging condition. The key finding of the study involves the role of Cu in refining clusters/precipitates, where it causes a substantial increase in number density and volume fraction. This refinement, in combination with strain-induced clustering, contributes significantly to improving the alloys’ overall mechanical performance and underlines the central role of Cu in tailoring microstructural features, especially in alloys primarily strengthened by clusters.
Publisher Copyright: © 2024 The Author(s)
Keywords: Aluminum alloys; APT; Cluster hardening; Dynamic recovery; Mechanical testing; Microstructure evolution

Hydrogen penetration into the NiTi superelastic alloy investigated in-situ by synchrotron diffraction experiments - Weiser, Adam; Todt, Juraj; Holcova, Jitka; Zalezak, Tomas; Paulik, Anna; Holec, David; Jary, Milan; Zobac, Ondrej; Mrazek, Jan; Frenzel, Jan; Keckes, Jozef; Dlouhý, Antonin (Acta materialia, 2024)
Microstructural changes induced by a hydrogen permeation into the NiTi superelastic alloy were investigated in-situ using the X-ray synchrotron diffraction. A new design of an electrochemical cell enabled to uncover time and position dependent processes under a flat alloy surface exposed to the cathodic hydrogen. The diffraction data supported by thermo-elastic FEM calculations helped to quantify an evolution of compressive stresses in the B2 austenitic phase hosting hydrogen atoms. The compressive stress state initiates a formation of martensitic phases starting from the exposed surface layer and advancing into the alloy volume with increasing time of hydrogen charging. We have performed the ab-initio DFT study in order to rationalize volumetric changes associated with variations in the B2 austenite and B19′ martensite lattice parameters. The numerical results also contributed to the identification of a new hydride phase with orthorhombic crystal structure and lattice parameters a = 0.8505 nm, b = 0.7366 nm and c = 0.4722 nm.

Carbon Management für ein klimaneutrales Österreich - Hochmeister, Susanne; Kühberger, Lisa; Kulich, Jakob; Ott, Holger; Kienberger, Thomas (Elektrotechnik und Informationstechnik : e & i, 2024)
Die Erfüllung der globalen Klimaziele gemäß des Pariser Abkommens stellt eine entscheidende Herausforderung der kommenden Jahrzehnte dar. Gewisse Emissionen der Industrie, Energieerzeugung sowie diffuse Emissionen aus der Landwirtschaft, der Deponierung von Abfällen und fluorierte Gase (F-Gase) können jedoch nicht vollständig vermieden werden. Carbon Capture and Utilization (CCU) und Carbon Capture and Storage (CCS) werden daher als wesentliche Komponenten zur Erreichung der Klimaziele angesehen. Um das Potenzial von CCU- und CCS-Aktivitäten für die langfristigen Klimaziele zu beurteilen und geeignete Carbon Management-Strategien zu identifizieren, ist eine Bewertung dieser Technologien insbesondere in Österreich erforderlich, wo bisher kaum umfassende Studien dazu durchgeführt worden sind.Diese Arbeit umfasst eine ganzheitliche Analyse relevanter CO2-Punktquellen in Österreich und deren prognostizierte Entwicklung bis 2050 anhand technologiebasierter Szenarien. Die geologische Speicherung von CO2 ist vorwiegend in ehemaligen Kohlenwasser-Stofflagerstätten möglich. Bedarfe für CO2 als Rohstoff werden zukünftig in der chemischen sowie petrochemischen Industrie bestehen.Bis 2050 wird Österreichs Industrie jährlich etwa vier Millionen Tonnen (Mt) an unvermeidbarem CO2 emittieren. Diese Emissionen müssen langfristig gespeichert werden und entsprechen somit dem Mindestbedarf an Carbon Capture and Storage (CCS). Diffuse Restemissionen aus der Landwirtschaft, der Deponierung von Abfällen und fluorierte Treibhausgase sind nicht für CCU/S-Maßnahmen geeignet. Zur Erreichung der Klimaziele sind daher negative Emissionen notwendig.
Publisher Copyright: © The Author(s) 2024.
Keywords: Bioenergy Carbon Capture and Storage (BECCS); Carbon Capture and Storage (CCS); Carbon Capture and Utilization (CCU); Direct Air Carbon Capture and Storage (DACCS)

Synthesis and Characterization of Alkali Metal Hypersilyl Borates - Lainer, Thomas; Walkner, Christoph; Tasch, Nina M.; Fischer, Roland C.; Torvisco, Ana; Stueger, Harald; Haas, Michael (Zeitschrift für anorganische und allgemeine Chemie, 2024)
This study focuses on the synthesis of H- and MeO- functionalized alkali metal hypersilyl borates. Consequently, two distinct silanides were used as polysilane frameworks for our chemical manipulations. Tris(silyl)silanide (1) and tris(trimethoxysilyl)silanide (2) react in the same manner with the BH3 ⋅ SMe2 complex to obtain two new alkali metal hypersilyl borates [(R3Si)3SiBH3M (M=alkali metal; R=H, (3), R=MeO, (4 a–c))] in good to excellent yields. NMR spectroscopy for all compounds and single-crystal X-ray crystallography for 3 and 4 a, b enabled a clear structural characterization. Single crystal X-ray analysis of 3 showed a dimeric structure, where two THF-molecules and three hydrides from the BH3-group contribute to the coordination sphere of the lithium atom. Interestingly, crystals suitable for X-ray analysis of 4 a and 4 b showed a solvent-free cluster formation, due to the coordination of the MeO groups. Both species form coordination polymers with different coordination modes depending on the nature of the alkali metal. Attempted hydride abstraction reactions of 3 and 4 with various reagents under the formation of the free boranes proceeded unselectively.
Publisher Copyright: © 2024 The Author(s). Zeitschrift für anorganische und allgemeine Chemie published by Wiley-VCH GmbH.
Keywords: boron; hydrosilanes; methoxysilanes; silicon; silylborate

EHD simulation study on the influence of measured ICE compression piston ring profiles on the lubrication film formation - Gussmagg, Jakob; Maier, Michael; Pusterhofer, Michael; Grün, Florian (Tribology International, 2024)
In this simulation-based research, the authors investigate the influence of the contacting profile and its tilting orientation of original compression piston rings on their hydrodynamic properties in internal combustion engines (ICEs). They employ a systematic approach, detailing the computational framework and simulation parameters. Three different original piston rings belonged to the same engine are used for the simulation and corresponding experimental validation in this publication. Results and discussions highlight the directional dependence of hydrodynamic conditions, with distinct differences for individual rings. Original smoothed profiles are compared with substitute geometries like quadratic parabola and circular arc fits. The research contributes insights into the complex dynamics of compression rings in ICEs, providing a foundation for optimizing ring profiles for enhanced hydrodynamic properties.
Publisher Copyright: © 2024 The Authors
Keywords: Elastohydrodynamic; Mixed friction; Ring-on-Liner

Manufacturing bio-based fiber-reinforced polymer composites: Process performance in RTM and VARI processes - Kirschnick, Ulrike; Feuchter, Michael; Ravindran, Bharath; Salzmann, Moritz; Duretek, Ivica; Fauster, Ewald; Schledjewski, Ralf (Advanced Manufacturing: Polymer and Composites Science, 2024)
The utilization of bio-based materials for the manufacturing of fiber-reinforced polymer composites is gaining importance under the sustainability paradigm. The identification of suitable process parameters and limited process reproducibility remain among the major challenges to enhance the industrial application potential of bio-based composites. This is especially relevant, as the manufacturing process influences composite quality, economic performance and environmental impacts. This study compares Resin Transfer Molding and Vacuum Assisted Resin Infusion for two sets of process parameters in order to manufacture a composite plate consisting of a flax-fiber textile impregnated with a partially bio-based epoxy matrix. Process quality is described through statistical analysis of processing and composite properties, and performance in terms of process replicability and reliability using performance estimates. Processing parameters were selected to depict a range of manufacturing scenarios that were suitable for the selected bio-based material system from curing for 180 min at 60 °C to curing for 30 min at 100 °C. For an identical set of process conditions, Resin Transfer Molding outperforms Vacuum Assisted Resin Infusion in terms of tensile and flexural characteristics. Conversely, the latter shows the strongest fiber-matrix adhesion and the most homogeneous impregnation. Whereas manufacturing at lower temperature leads to positive effects on composite quality, higher processing temperature with shorter curing cycles achieve highest process performance in terms of Pp and Ppk indices. An additional annealing at 120 °C neither increases composite quality nor reduces manufacturing-induced variability. Results depend on processing differences and indicators to determine process performance, as well as methodological choices.
Publisher Copyright: © 2024 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: annealing; bio-based materials; composite manufacturing; Performance measures; resin transfer molding; vacuum assisted resin infusion

Theoretical and experimental approaches to determine the mass transfer coefficient in the steel/slag/refractory system - Schickbichler, Manuel; Karimi Sibaki, Ebrahim; Kharicha, Abdellah; Michelic, Susanne Katharina (2024)

Optimization Strategy for Process Design in Rubber Injection Molding - Traintinger, Martin; Azevedo, Maurício; Kerschbaumer, Roman Christopher; Lechner, Bernhard; Lucyshyn, Thomas (Polymers, 2024)
Selecting the optimal settings for the production of rubber goods can be a very time-consuming and resource-intensive process. A promising method for optimizing rubber processing in a short period of time is the use of simulation routines. However, process simulations have only recently enabled meaningful predictions of not only the part’s state of cure but also its mechanical characteristics. As a first approach, second-order polynomials were considered suitable for describing the properties of compression-molded parts. However, more precision is required for injection molding due to the narrower distribution of mechanical characteristics of parts produced at different vulcanization temperatures. This became evident when the approximation of mechanical data with second order models partly revealed significant failures of part behavior prediction. To tackle this issue, a combined approach for approximation is proposed in this contribution by means of logistic growth function in addition to second order polynomials. To feed the model, an experimental plan was designed for producing injection-molded parts from an SBR compound at various temperatures and to different degrees of cure. The parts obtained were then characterized mechanically, and the results were opposed to varying degrees of cure and extents of reaction to calculate the model coefficients. Once available, a simulation-based calculation of the mechanical part quality is possible. The comparison of test results from the simulation and the real process has shown a reliable prediction, as simulation results were found within the natural deviation of the real measurements.
Publisher Copyright: © 2024 by the authors.
Keywords: injection molding; logistic growth; mechanical characterization; optimization; rubber part quality; simulation; sustainability

Text mining on mining Investigating a sustainability report corpus through the lens of climate change - Meyer, Anna (2024)
Climate change is associated with human activities, which contribute to global warming.In recent years, publishing sustainability reports to account for operational impacts hasbecome a trend. This can also be observed in the mining sector, which is naturally impactintensive in its operations. Significant greenhouse gas emissions stem fromenergyintensive mining and the processing. This paper makes a contribution to the fieldof public corporate discourse in relation to environmental impacts and investigates“corporate discourse and the outside world” (Jaworska 2020) using annual sustainability reports.
Keywords: discourse analysis, corporate discourse, collocation networks, mining companies, sustainability reporting

Challenges and Obstacles in the Use of Search and Rescue Dogs During Disaster Operations: A Case Study of the Earthquake in Turkey - Cvetković, Vladimir M.; Miljković, Nemanja (2024)

Electronic structure, phase formation, and defect distribution in the Ba(Ce,Fe,Acc)O3-δ system investigated by density functional theory calculations - Merkle, Rotraut; Chesnokov, Andrei; Hoedl, Maximilian Felix; Gryaznov, Denis; Nader, Christina; Egger, Andreas; Bucher, Edith; Kotomin, Eugene A.; Maier, Joachim; Sitte, Werner (24th International Conference on Solid State Ionics (SSI24), 2024)

Geomechanical characterization and mineralogical correlation of compositionally diverse world-class Kazakhstani source rocks - Nurbekova, Riza; Shi, Xiangyun; Hazlett, Randy; Misch, David; Fustic, Milovan; Sachsenhofer, Reinhard (International journal of coal geology, 2024)
Extensive nanoindentation testing over a range of deflection depths of up to 4 μm yielded a large dataset, providing a viable framework for the statistical assessment of the mechanical properties, specifically elastic modulus (E) and hardness (H), of compositionally diverse organic-rich mudstone samples. The data from indentations as shallow as 300–400 nm were clustered using the k-means algorithm to identify three mechanical categories in the samples: a soft pseudophase (e.g., organic matter, gypsum, and clay minerals), a stiff pseudophase (e.g., quartz and feldspar), and a transitional composite-like pseudophase bridging the soft and hard minerals. The initially diverse values of E and H for the mechanical pseudophases were observed to converge to a constant value at indentations beyond 2–2.5 μm (varying between different samples), implying the existence of a minimal probing depth for assessing the bulk E and H of heterogeneous mudstone samples. The obtained bulk E and H values (8–21 GPa and 0.3–0.9 GPa, respectively) demonstrated a strong correlation with the mineralogical composition of the indented samples. Despite containing a notable proportion of mechanically stiff components (>45 vol%), the bulk mechanical parameters determined in this study were significantly lower than those reported for major shale formations such as the Barnett and Longmaxi Shale. This discrepancy is primarily due to the presence of organic matter with low thermal maturity (Ro < 0.6%), which constitutes <36 vol% of the samples, and a significant gypsum content, accounting for <15 vol%.The employed approach not only demonstrated the importance of choosing the proper indentation depths for investigating the mechanical properties of highly heterogeneous mudstone rocks and their constituent minerals, but it also illustrated the capability of examining various volumes of investigation using nanoindentation, approaching macroscopic values, and identifying a representative element volume (REV). The findings also provided crucial insights into the fracability and overall producibility of the investigated formations, thereby enhancing our understanding of their extraction potential.
Publisher Copyright: © 2024 Elsevier B.V.
Keywords: Continuous stiffness measurement; Elastic modulus; Hardness; Nanoindentation; Organic-rich mudstones

Influence of Silicon and Tramp Elements on the High-temperature Oxidation of Steel in Direct Casting and Rolling Processes - Gaiser, Georg; Presoly, Peter; Bernhard, Christian; Baumgartner, Kerstin; Grosseiber, Simon (ISIJ international, 2024)
Oxidation processes are unavoidable in continuous casting and further hot processing of steel. A deeper understanding of the occurring phenomena such as intergranular oxidation and liquid metal infiltration of grain boundaries is essential to continuously improve the quality of the products. In this study, oxidation experiments were performed with simultaneous thermal analysis for two thin slab casting and rolling applications under near-process conditions up to the point prior to the first reduction stage. The experiments were performed for two low-carbon steels contaminated with undesirable tramp elements (Cu, Sn, …). In addition, the two steels contain Silicon at different levels. The results show that for the “Endless Strip Production” process (ESP), intergranular oxidation is significantly less pronounced compared to a “Thin Slab Casting and Rolling process” with a gas-fired tunnel furnace (TSCR TF). Due to the short process time at high temperatures in the ESP process, hardly any liquid metal infiltration by copper appears. In low silicon steel, intergranular oxidation results from various oxides, and liquid metal infiltration appears simultaneously in the TSCR TF process. Furthermore, the yield loss from oxidation is significantly higher in the TSCR TF process. The change from a natural gas combustion atmosphere to a hydrogen combustion atmosphere further increases the oxidation rate and results in a higher mass loss.
Publisher Copyright: © 2024 The Iron and Steel Institute of Japan.
Keywords: fayalite; intergranular oxidation; liquid metal infiltration; low carbon steel; rolling process; thin slab casting; tramp elements

Optimizing methane plasma pyrolysis for instant hydrogen and high-quality carbon production - Daghagheleh, Oday; Schenk, Johannes; Zheng, Heng; Zarl, Michael Andreas; Farkas, Manuel; Ernst, Daniel; Kieush, Lina; Lehner, Markus; Kostoglou, Nikolaos; Obenaus-Emler, Robert (International Journal of Hydrogen Energy, 2024)
The European Green Deal has set a target for Europe to achieve net-zero greenhouse gas emissions by 2050, necessitating a transition to more sustainable energy sources. Hydrogen gas (H 2) has emerged as a promising solution, with methane pyrolysis presenting a viable method for its production. This study explores the optimization of methane plasma pyrolysis for hydrogen and high-quality carbon production. Employing a statistical approach by a design of experiment software, critical process parameters are systematically analyzed to predict their impact within a defined range. Additionally, the paper conducts comprehensive characterization of the solid carbon produced during pyrolysis using imaging, spectroscopic and elemental analysis, and gas sorption analysis methods. The experimental investigation was conducted using a thermal plasma reactor with several settings of influential parameters including methane gas (CH 4) content in the plasma gas, electric current, and arc length. The DC-transferred plasma arc is formed using a variable gas mixture of argon gas (Ar) and CH 4, with a constant flow rate of 5 Nl/min. Thirteen tests were designed, evaluating responses such as power input, process stability, and H 2 yield. The H 2 yield indicates the hydrogen produced from CH 4, with 100% representing total conversion. While the process exhibited inconstancy, attributed to reactor design constraints, a high H 2 yield of 67%–100% was achieved. The results indicate that a higher CH 4 content in the plasma gas and extended arc lengths disturb the plasma arc, hence reducing the H 2 yield. Increased power input, achieved through higher amperage levels, and a wider reaction zone eased by extending the arc length both led to an improved H 2 yield. Scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) revealed microstructural differences, with carbon samples from the filter exhibiting finer textures and carbon samples from the reactor larger sizes and dendritic particles. Raman spectroscopy confirmed crystalline graphitic-like structures with low defect concentrations, a finding supported by X-ray diffraction (XRD) analysis. Inductively coupled plasma mass spectroscopy (ICP-MS) analysis confirmed high-purity carbon with slight impurities from initial filter contamination. Brunauer-Emmett-Teller (BET) specific surface area calculations based on gas sorption analysis showed significant variations, with filter-collected samples exhibiting 40–170 m 2/g and reactor-collected ones showing 7–30 m 2/g.
Publisher Copyright: © 2024 The Author(s)
Keywords: Carbon; Green energy; Hydrogen production; Methane pyrolysis; Natural gas pyrolysis; Sustainability; Thermal plasma; Turquoise hydrogen

Comparative analysis of experimental techniques for microstructural characterization of novel nanostructured aluminium alloys - Willenshofer, Patrick; Santa Rosa Coradini, Diego; Renk, Oliver; Uggowitzer, Peter; Tunes, Matheus Araujo; Pogatscher, Stefan (Materials characterization, 2024)
Precipitation holds a pivotal role in comprehending the intrinsic behavior of materials. In the design of nanostructured metallic alloys, precipitates have found to increase the alloys' stability and response under extreme environmental conditions. Studies on precipitation often rely on conventional and ex situ electron-microscopy methods, but a systematic investigation that compares different sample conditions during heat treatment and its microstructural implications are rarely available. In this context, we employed a novel ultrafine-grained AlMgZnCuAg crossover alloy to compare three distinct conditions for investigating the precipitation sequence: (i) ex situ transmission electron microscopy (TEM) from bulk heating, (ii) ex situ TEM from TEM foil heating, and (iii) in situ TEM with microelectromechanical-system (MEMS) heating. Although the heat treatment procedure was consistent across all cases studied, the application of these three different experimental conditions in the same alloy system resulted in significant and non-negligible differences in the final precipitation behavior. Ultimately, it resulted in observable microstructural variations and precipitates with distinctively different shape and sizes and, as a result, we outline herein the major similarities and differences among these techniques to achieve comparable results. This knowledge will help to compare and assess results of precipitation sequences obtained in different conditions.
Publisher Copyright: © 2024 The Author(s)
Keywords: (in situ) Transmission Electron Microscopy; Aluminium crossover alloys; Heat treatment; Precipitation analysis; STEM-EDX analysis

Exploring environmental awareness, knowledge, and safety - Cvetković, Vladimir; Sudar, Srna; Ivanov, Aleksandar; Lukić, Tin; Grozdanić, Goran (Open Geosciences, 2024)
This comparative study aims to investigate environmental awareness, knowledge, and safety among students in Montenegro and North Macedonia, considering the unique socio-cultural and environmental contexts of both countries. A mixed-methods approach involving surveys and interviews was employed to gather data from students in educational institutions across Montenegro and North Macedonia. The study assessed various factors, including students’ awareness of environmental issues, their perceived level of knowledge, and their attitudes towards safety measures. A comprehensive series of 400 face-to-face interviews was carried out, and these interviews encompassed 200 students from Montenegro and an equal number from North Macedonia, taking place at two esteemed academic institutions: The University of Montenegro in Podgorica and The University of St. Clement of Ohrid, Bitola, Republic of North Macedonia. Our hypothetical conceptual framework proposes that a combination of variables, including gender (H1), age (H2), year of study (H3), and rate of study (H4), significantly influences the attitudes of students from Montenegro and North Macedonia towards environmental awareness, safety, and knowledge. Research findings indicate significant variations in environmental awareness and knowledge perception among students in the two countries. While both Montenegro and North Macedonia face environmental challenges, differences in educational systems and socio-economic factors contribute to distinct attitudes and behaviours towards environmental issues and safety practices. This study sheds light on the importance of understanding regional differences in environmental awareness and knowledge perception among students. By identifying areas of strength and areas needing improvement, policymakers and educators can develop targeted interventions to enhance environmental education and foster a culture of sustainability in both Montenegro and North Macedonia.
Publisher Copyright: © 2024 the author(s).
Keywords: awareness; comparative study; environment; knowledge; Montenegro; North Macedonia; perception; safety; students; survey

Legal and Organizational Framework for the Use of Search and Rescue Dogs in Disasters: A Comparative Analysis between Serbia, Croatia, and Slovenia - Cvetković, Vladimir M.; Miljković, Nemanja (2024)

Seismic structure of the Balmuccia Peridotite from a high-resolution refraction and reflection survey - Pasiecznik, Damian; Greenwood, Andrew; Bleibinhaus, Florian; Hetényi, György (Geophysical journal international, 2024)
In anticipation of a forthcoming scientific deep drilling initiative within the Western Alps near Balmuccia, Italy, a high-resolution seismic survey is performed at the proposed drill site. This site is situated within the Ivrea Verbano Zone (IVZ), characterized by lower crustal materials and fragments of upper-mantle rocks exposed adjacent to the Insubric Line. The 2-km-long seismic survey crosses an isolated km-scale outcrop of peridotite near the town of Balmuccia. Applying P-wave traveltime tomography, a substantial contrast in seismic velocities is identified, with velocities in the range of 1–8 km s−1. The peridotite displays velocities ranging from 6 to 8 km s−1. The higher velocities near 8 km s−1 are consistent with laboratory measurements on small-scale samples, while the low-velocity areas within the peridotite body reflect the influence of fractures and faults. The mean velocity derived for the peridotite body is ca. 7 km s−1. The reflection seismic analysis reveals subvertical reflectors positioned at the peridotite boundaries mapped at the surface, converging at a depth of ca. 0.175 km b.s.l. which images a lens-like structure for the peridotite body. However, the area beneath the imaged lens and the deeper Ivrea Geophysical Body (IGB) suggested by earlier studies is not well imaged, which leaves room for other interpretations regarding the relationship of these two bodies. Prior geophysical investigations provide only approximate depth estimates for the top of the IGB, spanning between 1–3 km depth b.s.l. Although the reflection data do not exhibit a series of continuous reflectors beneath the peridotite, a prominent reflection at ca. 1.3 km depth may indicate the top of the IGB.
Keywords: Europe; Controlled source seismology; Seismic tomography; Crustal structure

Digitalisation and technological innovations towards energy-efficient quarries - Sánchez, Felipe; Kopeinig, Hanspeter; Lee, Christina; Hartlieb, Philipp (SDIMI 2024: Sustainable Development in the Minerals Industry 11th International Conference, 2024)

Dissolution of Oxide Particles in Multi-component Slags Governed by Diffusive and Convective Fluxes - Ogris, Daniel Marian; Michelic, Susanne Katharina; Gamsjäger, Ernst (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2024)
The kinetics of the dissolution of oxide particles in metallurgical slags is simulated by means of a sharp-interface finite difference model where multi-component diffusion is considered. The effect of convective fluxes on the dissolution kinetics is being considered by a constrained boundary layer thickness. The thickness of this boundary layer can be estimated from theory and is used together with the interdiffusivity matrix to predict the dissolution kinetics of spherical alumina particles in various CaO–SiO 2–Al 2O 3 slags. The numerical results are compared to experimental observations using High-Temperature Confocal Scanning Laser Microscopy (HT-CSLM).
Publisher Copyright: © The Minerals, Metals & Materials Society and ASM International 2024.

Evaluation of the Effectiveness of Search and Rescue Dogs in Finding Survivors During Disasters: The Case of Serbia, Croatia, and Slovenia - Cvetković, Vladimir M.; Miljković, Nemanja (2024)

A novel approach to the realisation of a rail specimen with defined surface cracks in work-hardening manganese steel for the calibration of inductive thermographic measurements - Tuschl, Christoph; Oswald-Tranta, Beata; Künstner, David; Eck, Sven; Dornig, Peter (17th Quantitative InfraRed Thermography Conference, 2024)
Induction thermography is a well-established method for the detection of surface defects in magnetic steel. Furthermore, static inductive measurements are used to estimate the depths and penetration angles of surface cracks. This work presents a new approach to creating crack-like, but defined surface defects in a manganese steel rail specimen. Cuts with different penetration depths and angles are introduced into the head of the rail via wire erosion. The work-hardening behaviour of manganese steel allows for the cuts being closed by subsequent roll-overs performed on a full-scale wheel-rail test rig. This improves the calibration of the parameters used for the specification of crack depth and penetration angle during measurements of rolling contact fatigue damage in track.

INFLUENCE OF FLUID PROPERTIES ON TRANSVERSE FABRIC COMPRESSIBILITY DURING IN-SITU IMPREGNATION - Bender, Marcel; Fauster, Ewald (2024)
In this study, the influence of different fluids on the transverse compressibility behaviour of technical reinforcing fabrics was investigated. Specifically, a glass fibre woven and a non-crimp fabric with comparable fibre areal weight, were studied in a novel test-rig with in-situ impregnation of the samples under transverse load. Four test fluids with varying viscosity and polarity, respectively, were chosen to analyse the influence of fluid viscosity and polarity on the relaxation behaviour. In addition, silicone oil with four different levels of viscosity across three orders of magnitude was used to isolate the influence of fluid viscosity, as no significant difference in polarity was observed. A qualitative analysis showed that the fabrics reacted significantly different to the impregnation, as with lower flexibility and increasing viscosity, hydrostatic effects in the compressed area counteracted a lubricating effect. However, only in the fabric with lower fibre bundle flexibility a slight to significant relative pressure relaxation was measured only as a result of fluid polarity. In addition, the viscosity of the fluid had no significant effect on the relative relaxation at the same polarity, but with increasing viscosity the time to reach pressure equilibrium increased significantly.
Keywords: Composites; Compression test; Processing of Composite Materials

In situ mapping of elemental dissolution at ultra-trace levels during aqueous corrosion of Al alloys - Wagner, Stefan; Mukhametzianova, Gulnaz; Eskinja, Magdalena; Moshtaghi, Masoud; Mori, Gregor; Prohaska, Thomas (European Workshop on Laser Ablation 2024, 2024)

Electro-tuned catalysts - Summerer, Harald; Rath, Kirsten; Nenning, Andreas; Schachinger, Thomas; Stöger-Pollach, Michael; Rameshan, Christoph; Opitz, Alexander Karl (Journal of Materials Chemistry A, 2024)
In this work, we show how the activity states of bimetallic Ni0-Fe0 catalysts exsolved from Nd0.6Ca0.4Fe0.97Ni0.03O3−δ (NCFNi) can be influenced electrochemically. The NCFNi parent oxide was employed in the form of thin film mixed conducting model electrodes, which were operated in a humid hydrogen atmosphere. By precisely controlling the oxygen chemical potential in the parent oxide electrode via applying an electrochemical polarisation, we managed to selectively exsolve Ni nanoparticles from the perovskite lattice and study their catalytic activity switching characteristics. To be able to track the surface chemical changes during the switching process, electrochemical polarisation experiments were combined with near ambient pressure X-ray photoelectron spectroscopy (NAP-XPS) measurements. This in situ analytical approach allowed relating the difference we observed in the switching behaviour of Ni particles here and of Fe particles in a recent study, to a different kinetic interplay between electrochemical driving force and atmosphere. We propose that slow oxygen transport through nickel oxide, located at the particle/perovskite interface, is mainly responsible for the observed difference to iron exsolutions, which becomes especially evident for larger nickel particles. In addition, in the case of bimetallic exsolutions and with applied bias voltage as a control parameter, we are able to reversibly switch between three different activity states, namely bimetallic Ni0-Fe0 (medium activity), pure Ni0 (high activity), and the inactive oxides.
Publisher Copyright: © 2024 The Royal Society of Chemistry.

How to catch a shear band and explain plasticity of metallic glasses with continuum mechanics - Glushko, Oleksandr; Pippan, Reinhard; Şopu, Daniel; Mitterer, Christian; Eckert, Jürgen (Nature Communications, 2024)
Capturing a shear band in a metallic glass during its propagation experimentally is very challenging. Shear bands are very narrow but extend rapidly over macroscopic distances, therefore, characterization of large areas at high magnification and high speed is required. Here we show how to control the shear bands in a pre-structured thin film metallic glass in order to directly measure local strains during initiation, propagation, or arrest events. Based on the experimental observations, a model describing the shear banding phenomenon purely within the frameworks of continuum mechanics is formulated. We claim that metallic glasses exhibit an elastic limit of about 5% which must be exceeded locally either at a stress concentrator to initiate a shear banding event, or at the tip of a shear band during its propagation. The model can successfully connect micro- and macroscopic plasticity of metallic glasses and suggests an alternative interpretation of controversial experimental observations.
Publisher Copyright: © The Author(s) 2024.

Possible charge ordering and anomalous transport in graphene/graphene quantum dot heterostructure - Roy, Rajarshi; Holec, David; Michal, Lukas; Hemzal, Dusan; Sarkar, Saikat; Kumar, Gundam Sandeep; Nečas, David; Dhankhar, Meena; Kaushik, Preeti; Gómez, I. Jénnifer; Zajíčková, Lenka (Journal of physics (Condensed matter), 2024)
Observations of superconductivity and charge density waves (CDW) in graphene have been elusive thus far due to weak electron-phonon coupling (EPC) interactions. Here, we report a unique observation of anomalous transport and multiple charge ordering phases at high temperatures ( T 1 ∼ 213 K , T 2 ∼ 325 K ) in a 0D−2D van der Waals (vdW) heterostructure comprising of single layer graphene (SLG) and functionalized (amine) graphene quantum dots (GQD). The presence of functionalized GQD contributed to charge transfer with shifting of the Dirac point ∼ 0.05 eV above the Fermi level (ab initio simulations) and carrier density n ∼ − 0.3 × 10 12 cm − 2 confirming p-doping in SLG and two-fold increase in EPC interaction was achieved. Moreover, we elucidate the interplay between electron-electron and electron-phonon interactions to substantiate high temperature EPC driven charge ordering in the heterostructure through analyses of magnetotransport and weak anti-localization (WAL) framework. Our results provide impetus to investigate strongly correlated phenomena such as CDW and superconducting phase transitions in novel graphene based heterostructures.
Publisher Copyright: © 2024 The Author(s). Published by IOP Publishing Ltd.
Keywords: ab initio simulation; charge ordering; graphene; graphene quantum dots; heterostructure; low temperature transport; Raman spectroscopy

High-entropy perovskite La0.2Pr0.2Nd0.2Sm0.2Sr0.2FeO3-δ as SOEC air electrode with enhanced performance - Pretschuh, Patrick; Egger, Andreas; Brunner, Roland; Kramer-Schöggl, Johanna; Bucher, Edith (16th European SOFC & SOE Forum, 2024)

Microstructure effects in high entropy perovskite air electrodes investigated with advanced 3D imaging - Egger, Andreas; Pretschuh, Patrick; Paulachan, Priya; Schöggl, Johanna; Brunner, Roland; Bucher, Edith (16th European SOFC & SOE Forum, 2024)

Additive Manufacturing of Bone Implants - Holzer, Clemens (Biomaterials International (BMI) Confernce 2024, 2024)

Achieving Superior Strength-ductility-conductivity Combination in TiB2p 6201 Composites via Particle Rotation and Sub-grain Refinement - Zhao, Kai; Li, Xinchen; Liu, Xiangting; Shi, Shuyan; Guo, Enyu; Kang, Huijun; Hao, Zhigang; LI, Jiehua; Zhang, Yubo; Chen, Zongning; Wang, Tongmin (Advanced engineering materials, 2024)
The key factor in the material design of overhead power transmission lines is to obtain a desired balance among strength, ductility, and electrical conductivity. Herein, TiB2 particulate-reinforced aluminum matrix composites are prepared to find a way out of the intrinsic dilemma behind this balance by tailoring the subgrain refinement. The interaction in the form of inhomogeneous deformation induced by the flexibility discrepancy between the rigid particles and soft matrix is studied. On the one hand, the hexagonal plate-like TiB2 particles rotate with the inhomogeneous deformation, forcing the biggest exposed plane ((0001) basal plane) parallel to the plastic flow direction, which is beneficial for the dislocation multiplication and hindrance of dislocation slipping. On the other hand, inhomogeneous deformation generates plentiful geometry necessary dislocations and divides the microstructure into two types: in the particle-rich region ultrafine grains are formed and in the particle-free region significant subgrains refinement is observed. The subgrains with 3 wt% TiB2 are refined from ≈897 to ≈248 nm. Thanks to these microstructural benefits, the composites achieve the following strength–ductility–conductivity combination: ultimate tensile strength is 370 MPa, elongation after fracture is 11.2%, and electrical conductivity is 51.79% IACS. Besides, the elastic modulus reaches 75.43 GPa.

Advancements in metal additive manufacturing - Schimbäck, David; Kaserer, Lukas; Mair, Philipp; Mohebbi, M.S.; Staron, Peter; Maier-Kiener, Verena; Letofsky-Papst, Ilse; Kremmer, Thomas; Palm, Frank; Montes, I.; Höppel, Heinz Werner; Leichtfried, Gerhard J.; et al. (Materials science and engineering: A, Structural materials: properties, microstructure and processing, 2024)
The high design freedom of laser powder bed fusion (LPBF) additive manufacturing enables new integrated structures, which in turn demand advances in the process conditions and material design to exploit the full potential of this process. A computational multi-scale thermal simulation and metallurgical analysis of the aluminium alloy Scalmalloy® were used to develop and present a specific process window to enable an in-situ heat treatment during LPBF. High resolution analysis and synchrotron experiments on specimens manufactured in this process window revealed a major proportion of nano-sized Al 3(Sc xZr 1−x) solute-clusters were already present in the as-built state, as predicted by simulation. Supported by this experimental research, the new processing concept of in-situ heat treatment yielded the highest recorded strength values combined with high ductility directly after LPBF for Scalmalloy®. This advancement in LPBF enables highly complex, thin-walled structures directly made from a high-strength, lightweight material, which is not possible with conventional processes that require a subsequent heat treatment cycle.
Publisher Copyright: © 2024 The Authors

Automatic and time-resolved determination of fracture characteristics from in situ experiments - Schmuck, Klemens Silvester; Antenreiter, Martin; Alfreider, Markus; Kiener, Daniel (Materials & design, 2024)
The characterization of materials in ever smaller dimensions is crucial for the growing demand for miniaturized devices. Hence, in situ fracture experiments are frequently performed at the micron to sub-micron scale. To evaluate fracture process of these experiments, knowledge of the crack length or the crack tip opening displacement is required. Acquired in situ frames provide a direct measurement of the crack length, crack tip opening displacement and -angle. An algorithm was developed to extract these parameters from the in situ frame sequences automatically. To verify the performance of the algorithm, fracture characteristics were measured manually for several frames of the available in situ experiments. The fracture behavior of these samples ranged from brittle over semi-brittle to ductile. The comparison between algorithmic results and manual measurements demonstrated the applicability of the algorithm to different fracture behaviors. Additionally, the fracture characteristics determined by the algorithm are in accordance with the fracture toughness data reported in literature. The crack tip opening displacement measurement gives thorough insight into the plastic deformation during fracture. The automatic extraction of the fracture characteristics allows a more detailed analysis of small-scale fracture processes and enables a reproducible, continuous evaluation of the fracture characteristics of all frames.
Publisher Copyright: © 2024 The Author(s)
Keywords: Crack propagation; Image processing techniques; In-situ microcantilever testing; Small scale fracture experiments

Binder System Composition on the Rheological and Magnetic Properties of Nd-Fe-B Feedstocks for Metal Injection Molding - Momeni, Vahid; Luca, Sorana; Gonzalez-Gutierrez, Joamin; Cano, Santiago; Sueur, Emilie; Shahroodi, Zahra; Schuschnigg, Stephan; Kukla, Christian; Holzer, Clemens (Applied Sciences (Switzerland), 2024)
The applications of Nd-Fe-B-based magnets are experiencing significant diversification to achieve efficiency and miniaturization in different technologies. Metal injection molding (MIM) provides new opportunities to manufacture Nd-Fe-B magnets with high geometrical complexity efficiently. In this study, the impacts of the binder system composition and powder loading on the rheological behavior, contamination, and magnetic properties of the Nd-Fe-B MIM parts were investigated. A high-pressure capillary rheometer was used to measure the apparent viscosity and pressure drops for feedstocks with different binder formulations and powder contents. Also, oxygen and carbon contamination, density, and magnetic properties were measured for different feedstock formulations and powder loadings. From the rheological, density, and magnetic properties points of view, the binder system consisting of 45 vol.% LLDPE as backbone was selected as the optimum formulation. The findings indicated that the sample with this binder system and 55 vol.% powder content had a high density (6.83 g/cm3), remanence (0.591 T), and coercivity (744.6 kA/m) compared to other binder compositions. By using 58 vol.% powder loading, the values of density (7.54 g/cm3), remanence (0.618 T), and carbon residue (982 ppm) improved, and a suitable rheological behavior was still observed. Thus, a suitable feedstock formulation was developed.
Publisher Copyright: © 2024 by the authors.
Keywords: binder system; carbon residue; magnetic properties; metal injection molding; rheological behavior

CO2 Conversion with Citizen Scientists – A Sparkling Science 2.0 Project - Ruh, Thomas; Bartl, Patrizia; Messner, Martina; Jantscher, Andreas; Lorenz, Harald; Erlebach, Christian; Rameshan, Christoph (18th International Congress on Catalysis (ICC), 2024)

CO2 Conversion with Citizen Scientists – A Sparkling Science 2.0 Project - Ruh, Thomas; Bartl, Patrizia; Messner, Martina; Jantscher, Andreas; Lorenz, Harald; Erlebach, Christian; Rameshan, Christoph (18th International Congress on Catalysis (ICC), 2024)

Metal impact and vaporization on the Moon’s surface - Gopon, Phillip; Douglas, James; Gardner, Hazel; Moody, Michael; Wood, Bernard; Halliday, Alexander; Wade, Jon (Meteoritics and planetary science, 2024)
Millimeter-to-nanometer-sized iron- and nickel-rich metals are ubiquitous on the lunar surface. The proposed origin of these metals falls into two broad classes which should have distinct geochemical signatures—(1) the reduction of iron-bearing minerals or (2) the addition of metals from meteoritic sources. The metals measured here from the Apollo 16 regolith possess low Ni (2–6 wt%) and elevated Ge (80–350 ppm) suggesting a meteoritic origin. However, the measured Ni is lower, and the Ge higher than currently known iron meteorites. In comparison to the low Ni iron meteorites, the even lower Ni and higher Ge contents exhibited by these lunar metals are best explained by impact-driven volatilization and condensation of Ni-poor meteoritic metal during their impact and addition to the lunar surface. The presence of similar, low Ni-bearing metals in Apollo return samples from geographically distant sites suggests that this geochemical signature might not be restricted to just the Apollo 16 locality and that volatility-driven modification of meteoritic metals are a common feature of lunar regolith formation. The possibility of a significant low Ni/high Ge meteoritic component in the lunar regolith, and the observation of chemical fractionation during emplacement, has implications for the interpretation of both lunar remote-sensing data and bulk geochemical data derived from sample return material. Additionally, our observation of predominantly meteoritic sourced metals has implications for the prevalence of meteoritic addition on airless planetary bodies.
Publisher Copyright: © 2024 The Authors. Meteoritics & Planetary Science published by Wiley Periodicals LLC on behalf of The Meteoritical Society.

Harmonization of Soft Power and Institutional Skills: Montenegro’s Path to Accession to the European Union in the Environmental Sector - Sudar, Srna; Cvetković, Vladimir; Ivanov, Aleksandar (International journal of disaster risk management, 2024)
This research investigates the alignment of soft power and institutional skills in Montenegro's journey towards accession to the European Union (EU), with a particular focus on the environmental sector. An online survey targeting individuals employed in state institutions directly engaged in negotiation processes, notably the Ministry of Sustainable Development and Tourism and the Agency for Nature and Environmental Protection, was conducted. The research conducted an online survey, distributed before and after the summer recess to accommodate the transition of power following parliamentary elections, aimed at assessing the effectiveness of current personnel and identifying areas for improvement in staffing and negotiation strategies within Montenegro's environmental sector. Employing diverse methodologies, the survey's analysis delved into the demographic, social, and professional backgrounds of respondents. It explored their roles within institutions, involvement in environmental negotiations, and possession of relevant skills and expertise. Furthermore, respondents' knowledge of environmental issues, legislation, and challenges facing the country was assessed to gauge institutional capacity for environmental governance. Demographic data, including gender, age, education and regional origin, were collected to understand gender-specific attitudes and regional disparities in environmental perspectives. The sample of 84 individuals, comprising executives and employees from both institutions, provided insights into the age structure and regional diversity of personnel involved in negotiation tasks for Chapter 27. The selection of the Ministry of Sustainable Development and Tourism and the Agency for Nature and Environmental Protection reflects their pivotal roles in shaping Montenegro's environmental policies and addressing climate change challenges. This study aims to illuminate the dynamics of environmental governance within Montenegro's state administration, contributing to the country's path towards EU accession. The research findings highlight the critical need for Montenegro to prioritize strategic initiatives in personnel management, skill development, and institutional capacity-building within its environmental sector. The implications of this research extend beyond academia to inform policymaking and societal action, emphasizing the urgency for Montenegro to bolster its environmental sector capabilities, fostering both EU alignment and sustainable governance practices for the benefit of present and future generations.
Sudar, S., Cvetković, V. M., & Ivanov, A. (2024). Harmonization of Soft Power and Institutional Skills: Montenegro’s Path to Accession to the European Union in the Environmental Sector . International Journal of Disaster Risk Management, 6(1), 41–74.

Experimental, analytical, and numerical quantification of the Marangoni effect in static refractory finger test - Vollmann, Sandra; Guarco, Jeronimo; Burhanuddin, Burhanuddin (Ceramics International : CI, 2024)
This study investigated the local corrosion of alumina and magnesia refractory in CaO–Al2O3–SiO2–MgO slag due to the Marangoni effect, which is a key factor for localized wear in different industrial processes, using experimental, analytical, and numerical approaches. The objective is to explore the Marangoni effect using computational fluid dynamics simulation aiming to provide insights into the dominant slag flow patterns influencing refractory corrosion and to determine whether the observed corrosion groove can be attributed solely to the Marangoni effect. Static finger tests were conducted at temperatures of 1500 and 1550 °C employing a continuous wear testing device. A two-dimensional axisymmetrical section model of the test assembly was created, incorporating concentration-dependent surface tension gradients and surface tension forces to replicate the Marangoni flow. As the surface-tension simulation required time steps in the order of 10−5 s, modeling up to the experimental time scale cannot be realized. Consequently, the simulation outcomes were extrapolated to anticipate the groove radii of the experimental corrosion steps. Corrosion rates were derived from measurements and analytical methodologies. Established analytical equations for corrosion under surface-tension-flows were adapted to enhance the accuracy of corrosion rate estimation. However, the analytical considerations yielded poor estimates. Meanwhile, the employed simulation model successfully generated plausible predictions of the Marangoni flow. Drawing from the extrapolated simulation outcomes, the projected groove radii exhibited a close correspondence to the measured values, demonstrating a relative error of approximately 3 %, 11 %, and 15 % for the magnesia system at 1500 °C and alumina systems at 1500 and 1550 °C, respectively. Taking into account the uncertainties inherent in the methodological approach, the disparities in the alumina values suggest the involvement of mechanisms beyond the Marangoni effect in the localized wear. Consequently, this study effectively clarifies the impact of the Marangoni effect on the local wear of the examined material systems.
Publisher Copyright: © 2024 The Authors
Keywords: C. Corrosion; D. Al O MgO; E. Refractories

Cobalt-free high-entropy perovskite La0.2Pr0.2Nd0.2Sm0.2Sr0.2FeO3-δ solid oxide cell air electrode with enhanced performance - Pretschuh, Patrick; Egger, Andreas; Paulachan, Priya; Schöggl, Johanna; Brunner, Roland; Bucher, Edith (Fuel Cells, 2024)
This study investigates the novel cobalt-free high-entropy perovskite, La 0.2Pr 0.2Nd 0.2Sm 0.2Sr 0.2FeO 3–δ (LPNSSF), as an air electrode material for solid oxide cells (SOCs). When testing a button cell with a single-phase LPNSSF electrode, a current density of 0.55 A cm −2 is obtained at 0.7 V in fuel cell mode at 800°C. In order to mitigate the moderate electronic conductivity of LPNSSF, two approaches are explored. Incorporating a Co-free highly conductive perovskite, LaNi 0.6Fe 0.4O 3–δ (LNF), either as an LPNSSF–LNF composite electrode or as a current collector layer (CCL), enhances the performance to 0.61 and 0.66 A cm −2, respectively, under the same conditions. Microstructural features are studied by electron microscopy and show a rather dense structure of the CCL. Optimization of the current collector increases the current density further to 0.96 A cm −2 at 0.7 V in a 5 × 5 cm 2 anode-supported cell at 800°C. This cell exhibits good long-term stability in electrolysis mode in H 2-H 2O with 80% humidification. Continuous polarization of −0.69 A cm −2 is sustained for 1000 h, with an average degradation rate of 10 mV kh −1 after an initial run-in phase. These findings demonstrate the promising performance and durability of LPNSSF as cobalt-free SOC air electrode.
Publisher Copyright: © 2024 The Author(s). Fuel Cells published by Wiley-VCH GmbH.
Keywords: cobalt-free air electrode; current collector layer; electrochemical impedance spectroscopy; high-entropy perovskite; long-term stability; solid oxide electrolyzer cell; solid oxide fuel cell

Inverter for an alternating current grid - Makoschitz, Markus (2024)

Plasma-Treated Cobalt-Doped Nanoporous Graphene for Advanced Electrochemical Applications - Knabl, Florian; Kostoglou, Nikolaos; Gupta, Ram K.; Tarat, Afshin; Hinder, Steven J.; Baker, Mark; Rebholz, Claus; Mitterer, Christian (C – journal of carbon research, 2024)
Metal–carbon nanocomposites are identified as key contenders for enhancing water splitting through the oxygen evolution reaction and boosting supercapacitor energy storage capacitances. This study utilizes plasma treatment to transform natural graphite into nanoporous few-layer graphene, followed by additional milling and plasma steps to synthesize a cobalt–graphene nanocomposite. Comprehensive structural characterization was conducted using scanning and transmission electron microscopy, X-ray diffraction, Raman spectroscopy, gas sorption analysis and X-ray photoelectron spectroscopy. Electrochemical evaluations further assessed the materials’ oxygen evolution reaction and supercapacitor performance. Although the specific surface area of the nanoporous carbon decreases from 780 to 480 m 2/g in the transition to the resulting nanocomposite, it maintains its nanoporous structure and delivers a competitive electrochemical performance, as evidenced by an overpotential of 290 mV and a Tafel slope of 110 mV/dec. This demonstrates the efficacy of plasma treatment in the surface functionalization of carbon-based materials, highlighting its potential for large-scale chemical-free application due to its environmental friendliness and scalability, paving the way toward future applications.
Publisher Copyright: © 2024 by the authors.
Keywords: cobalt; graphene; nanocomposites; nanoporous powders; oxygen evolution reaction; plasma; supercapacitor; water splitting

Influence of Tramp Elements on Surface Properties of Liquid Medium-Carbon Steels - Cejka, Julian; Sammer, Bernhard; Gruber, Isabell; Michelic, Susanne Katharina (Steel research international, 2024)
The transformation of the steel industry is inevitably linked to increased recycling rates of steel. However, end-of-life scrap is often contaminated with tramp elements like copper, molybdenum, and tin and while their influence on mechanical properties of steels is well described, their effect on nonmetallic inclusions remains largely unknown. Therefore, herein, two medium-carbon steels are alloyed with up to 1 wt% of the listed tramp elements. The influence these elements have on the inclusion behavior in liquid steel is investigated using the sessile drop method in contact with alumina and zirconia as well as in steel/slag melting experiments to evaluate the formation and separation of new inclusions. Additionally, a semiempirical approach using CALPHAD to model the surface tension of steels with tramp elements is done. Copper and tin decrease the surface tension, while molybdenum increases the surface tension. It is demonstrated that most investigated alloys lead to a decrease of wetting angle as compared to the nonalloyed steels. The shown trends in the sessile drop experiments are lower contact angles with increased surface tension while a higher number of inclusions occurs with a decrease in surface tension. Thus, this study demonstrates that tramp elements affect the oxidic cleanness of steels.
Publisher Copyright: © 2024 The Author(s). Steel Research International published by Wiley-VCH GmbH.
Keywords: medium-carbon steels; nonmetallic inclusions; steel cleanness; surface behavior; tramp elements; wetting

Limitations of Hydrogen Detection After 150 Years of Research on Hydrogen Embrittlement - Tunes, Matheus Araujo; Uggowitzer, Peter; Dumitraschkewitz, Phillip; Willenshofer, Patrick; Samberger, Sebastian; da Silva, Felipe; Schön, Cláudio Geraldo; Kremmer, Thomas; Antrekowitsch, Helmut; Djukic, Milos; Pogatscher, Stefan (Advanced Engineering Materials, 2024)
Hydrogen's significance in contemporary society lies in its remarkable energy density, yet its integration into the worldwide energy grid presents a substantial challenge. Exposing materials to hydrogen environments leads to degradation of mechanical properties, damage, and failure. While the current approach for assessing hydrogen's impact on materials involves mainly multiscale modeling and mechanical testing, there exists a significant deficiency in detecting the intricate interactions between hydrogen and materials at the nanoatomic scales and under in situ conditions. This perspective review highlights the experimental endeavors aimed at bridging this gap, pointing toward the imminent need for new experimental techniques that can detect and map hydrogen in materials’ microstructures and their site-specific dependencies.
Publisher Copyright: © 2024 The Author(s). Advanced Engineering Materials published by Wiley-VCH GmbH.

Revolutionizing heat distribution: A method for harnessing industrial waste heat with supra-regional district heating networks - Steinegger, Josef; Hammer, Andreas; Wallner, Stefan; Kienberger, Thomas (Applied energy, 2024)
In both practice and literature, there is a lack of a concept for a supra-regional district heating network that efficiently transports heat from renewable and industrial waste heat sources to multiple heat sinks and regional district heating networks, like the high-voltage electricity transmission network in the electricity sector. This paper addresses this gap by presenting a novel method for the basic design of a supra-regional district heating network and its evaluation, along with key performance indicators for assessment. The method highlights essential data requirements and the derivation process necessary to enable the integration of such a heating network. Additionally, it describes how a basic design of such a network can be made feasible and evaluated. This method is then applied to a case study to demonstrate its implementation for a real-world application. Furthermore, this case study aims to either demonstrate or provisionally disprove the general feasibility of a supra-regional district heating network. The results indicate that the implementation of such a network has a positive impact on the CO2 balance and primary energy demand. The case study further demonstrates the technical feasibility of such a network, showing that a high linear heat density can be achieved through integration and that temperature levels within the network can be maintained adequately. This study confirmed that the developed method can effectively assess whether further investigations into implementing a supra-regional district heating network in a specific region are warranted. Additionally, the method offers a guideline on how to initially design such a network.

Characterization of atmospheric pressure plasma deposited (APPD) coatings to improve the friction behavior of thermoplastic surfaces - Gleirscher, Milena; Kopp, Dietmar; Hausberger, Andreas; Angerer, Paul; Lackner, Jürgen; Schlögl, Sandra (Surface and Coatings Technology, 2024)
Achieving a significant friction reduction is crucial for using thermoplastic materials as substrates in tribological applications and presents an eligible alternative to the use of light metals. In this study, previously developed MoS2/graphite/zinc composite coatings, applied by an atmospheric pressure plasma deposition (APPD) process, were investigated to extend the understanding of their characteristics and the influence of the process and environmental parameters on friction behavior. Tribological tests were conducted in ambient conditions and at elevated temperatures (110 °C) to study the friction behavior under application-oriented conditions. The presence of atmospheric oxygen during the deposition process was shown to influence the durability of the coatings, which motivated the application of an inert gas atmosphere for the coating deposition. A novel shrouding plasma nozzle was introduced, which further lowered the friction coefficients. The oxidizing effect of the plasma spray deposition was studied with X-ray photoelectron spectroscopy to investigate the strong impact of the deposition current on the friction behavior and durability of the deposited coatings. Coating composition, morphology, and the effects of the tribological testing were evaluated using optical microscopy, 3D surface measurements, scanning electron microscopy, X-ray diffraction, and nanoindentation. The fabricated coatings with thicknesses in the 10 μm range and good adhesion on the polyamide substrate were stable under extended testing durations and at elevated temperatures and accomplished a significant friction reduction compared to the uncoated polyamide. Thus, APPD-fabricated MoS2/graphite/zinc coatings represent an excellent candidate for low-friction applications of thermoplastic substrates.
Publisher Copyright: © 2024 Elsevier B.V.
Keywords: Atmospheric pressure plasma deposition; Ball-on-disc tribometer; Coating characterization; Dry lubricants; Low-friction coating

Designing Intelligent Rock Support Systems to Detect Gravity-Driven Wedges - Varelija, Michel; Hartlieb, Philipp (Rock mechanics and rock engineering, 2024)
Intelligent rock bolts can be used in mining operations to acquire information on the bolt's status and movements of the rock mass. The future value of this technology resides in optimizing the support layout and increasing safety. The primary goal of this research is to investigate the sensor spatial distribution necessary for efficiently identifying roof wedges in mines. Roof wedges occur when three joints intersect over the roof, forming a triangular shape. They present a hazard by falling and causing damage. Sensor density refers to the number of sensors on a single rock bolt and the number of intelligent rock bolts in the mine or one section. Too many sensors drive costs up, and too few sensors compromise measurement quality. This research visualizes and investigates the results of the simulated models of intelligent rock bolts depending on the number of installed sensors and intelligent bolts to get a better understanding of the problem and describe the technique used, including numerical simulations and the considered parameters. Furthermore, it offers insight into the findings' possible implications, providing knowledge about the viability of using intelligent rock bolts.
Publisher Copyright: © The Author(s) 2024.
Keywords: Intelligent rock bolt; Sensor density; Numerical Modelling; Measurement; Numerical modelling; Roof wedge

Polymetallic tungsten skarn mineralisation related to the Periadriatic intrusion at Lienzer Schlossberg, East Tyrol, Austria - Raith, Johann; Hutter, Florian; Altenberger, Florian; Weilbold, Julia; Auer, Christian; Krause, Joachim; Berndt, Jasper; Neinavaie, Hassan (Austrian journal of earth sciences, 2024)
A regional tungsten anomaly was discovered and explored in the Lienzer Schlossberg area that is part of the crystalline Austroalpine nappe complex of the Eastern Alps in the 1970/80-ties. Tungsten is present as scheelite, which occurs in steeply SSW dipping WNW-ENE oriented quartz veinlets and joints within the porphyritic dioritic to tonalitic/granodioritic host rocks of the Oligocene Lienz/Edenwald intrusion and in the exoskarn, which developed at the contact of the intrusion with Ca-rich lithologies. The skarn system is characterised by two stages: (1) a primary high-temperature calc-silicate stage characterised by grossular, diopside-hedenbergite, vesuvianite, wollastonite and Ca-plagioclase and (2) a retrograde skarn stage including scheelite-bearing massive sulphide ores (pyrrhotite, chalcopyrite, tremolite-actinolite, diopside-hedenbergite) and scheelite-rich fault rocks with calcite, sericite and chlorite. The two ore stages, the mineral paragenesis and composition is like that of a reduced tungsten skarn; i.e., garnet is grossular-rich, clinopyroxene is diopside-hedenbergite. Vesuvianite contains up to 1.8 mass % fluorine. Scheelite has been studied by cathodoluminescence (CL), electron probe microanalysis and laser ablation-inductively coupled plasma-mass spectrometry. Three types of scheelite (Scheelite 1–3) are distinguished. In short-wave UV light, all types show blue fluorescence but CL revealed internal micro-textures in scheelite grains which are dominated by oscillatory zoning. Prolonged hydrothermal activity is indicated by dissolution-replacement and overgrowth textures affecting the primary zonation and trace element composition of scheelite. The distribution of rare earth elements (REE) in Scheelite 1 in tonalite-hosted quartz veinlets shows a convex (i.e., middle REE-enriched), heavy REE-depleted pattern with negative Eu anomalies (EuA). The evolution of REE patterns from skarn-hosted Scheelite 2 and 3 illustrates a gradation of convex REE patterns with high ΣREE and distinct negative Eu anomalies to relatively flat REE patterns with small to no EuA. Scheelite at Lienzer Schlossberg has one of the highest ΣREE+Y contents of all scheelite-bearing ore settings in the Eastern Alps but incorporates minor Mo and the least Sr. High Na and Nb contents together with the positive correlation of REE+Y vs. Na+Nb+Ta suggests that the main exchange vectors for REE incorporation in scheelite is via a combined coupled substitution mechanism. Results of this study confirm the genetic similarity with reduced tungsten skarns and highlight the tungsten potential of this area.
Publisher Copyright: © 2023 Johann G. Raith et al., published by Sciendo.
Keywords: Eastern Alps; scheelite; tungsten skarn; Periadriatic intrusion; trace elements; LA-ICP-MS

Dual cross-linking of XNBR latex with epoxy-functional calcium silicate particles for the production of accelerator-free medical gloves - Grabmayer, Theresa; Manhart, Jakob; Fleischmann, Darya; Kaiser, Simon; Schaller, Raimund; Holzner, Armin; Schlögl, Sandra (Journal of applied polymer science, 2024)
In this work, an innovative dual cross-linking strategy for carboxylated nitrile butadiene rubber (XNBR) latex using epoxy-modified calcium silicate particles is presented. In their role as dual cross-linker, the particles are able to form covalent bonds (nucleophilic ring opening of epoxy moieties) as well as ionic cross-links (calcium ions of the inorganic core) across the carboxylic acid groups of the rubber. To characterize the curing efficiency, thin elastomer films are prepared by using a conventional coagulant dipping process and their cross-link densities, curing kinetics, and tensile properties are investigated as a function of the concentration of the cross-linker and curing time. The results show that latex films containing 5 phr of epoxy-functional particles give the highest tensile strength, which is further improved by pre-vulcanizing the liquid latex compound at 60°C for 30 min. The latex formulations are stable over 3 days and the pre-cured films exhibit a high resistance against gamma sterilization and subsequent accelerated aging. Moreover, sterile films do not cause any skin irritation or skin sensitization reactions, showing the high potential of epoxy-functional particles in the production of accelerator-free hypoallergenic gloves.
Publisher Copyright: © 2024 Wiley Periodicals LLC.
Keywords: applications; elastomers; films; rubber

A methodology for the determination of future Carbon Management Strategies - Hochmeister, Susanne; Kühberger, Lisa; Kulich, Jakob; Ott, Holger; Kienberger, Thomas (International Journal of Sustainable Energy Planning and Management, 2024)
The achievement of global climate targets outlined in the Paris Agreement represents a critical challenge in the coming decades. Certain industry sectors cannot completely avoid all emissions from their processes. In this context, the term unavoidable or Hard-to-abate emissions is used. Carbon Capture and Utilization (CCU) and Carbon Capture and Storage (CCS) are recognized as essential components for addressing those emissions to achieve Net Zero Emissions. To identify effective Carbon Management Strategies, balancing future CO2 sources and possible sinks for achieving long-term climate targets is essential. Especially in Austria hardly any comprehensive studies have been carried out.This work presents a comprehensive analysis of Austria’s CO2 point sources as well as their projected development until 2050 based on technology-based scenarios. Geological CO2 storage in Austria is primarily feasible in former hydrocarbon reservoirs and saline aquifers. Future demands for CO2 as CCU feedstock will arise in the chemical industry. By 2050, industry will emit approximately 4 Million tons (Mt) of unavoidable CO2 annually. These emissions must be stored in the long term and correspond to the minimum demand for CCS. Fugitive emissions from agriculture, for example, cannot be captured. Thus, they are not subject of CCU/S measures. Negative emissions are therefore necessary to achieve the climate targets. These negative emissions and the possible use of CO2 as feedstock are covered by biogenic CO2
Publisher Copyright: © 2024, Aalborg University Press. All rights reserved.
Keywords: Bioenergy Carbon Capture and Storage (BECCS); Bioenergy Carbon Capture and Utilization (BECCU); Carbon Capture and Storage (CCS); Carbon Capture and Utilization (CCU); Net Zero Emissions

Comparative study of oxide dissolution modelling in secondary steelmaking slags - Preisser, Nikolaus; Michelic, Susanne Katharina (2024)

A Facile Synthesis of Photocatalytic Fe(OH)3 Nanoparticles for Degradation of Phenol - Kayhan, Mehmet; Aksoy, Mehmet; Kayhan, Emine (ChemistrySelect, 2024)
Iron hydroxide (Fe(OH)3) nanoparticles have garnered considerable attention for their effectiveness in water treatment. This paper reviews recent studies on the photocatalytic degradation of phenol using Fe(OH)3, detailing the synthesis procedure, photocatalytic reaction conditions under UV-C and catalyst amount optimization. Iron hydroxide was synthesized using a facile precipitation method, and the produced catalyst was thoroughly characterized using XRD, FTIR, UV-DRS, DTA/TGA and SEM. Characterization results indicated that the catalyst exhibited very low crystallinity, a 1.84 eV band gap, and very small particle sizes. The study investigated the degradation performance of phenol for different amounts of iron hydroxide, ranging from 0.1 g to 1 g, and determined the optimum catalyst amount to be 0.7 g. The catalyst demonstrated a degradation efficiency for phenol exceeding 90 % at the end of a 180 minute photocatalytic reaction. The paper offers a comprehensive analysis of Fe(OH)3 as a photocatalyst for phenol degradation, highlighting its potential for future applications in water treatment.

Hydrogen diffusivity, uptake and embrittlement of solution annealed and cold deformed austenitic stainless steel 1.4435 at hydrogen pressures up to 1000 bar and 200 °C - Eichinger, Matthias; Pengg, Johann; Zwittnig, Dino; Mori, Gregor Karl (Corrosion science, 2024)
Austenitic stainless steel 1.4435, a candidate material for high-pressure tubing for hydrogen applications, was investigated in two different stages of cold deformation (0 and 27 %) regarding its hydrogen embrittlement tendency. The determination of effective diffusion coefficients revealed slightly increased diffusion kinetics at 60°C for the cold-reduced material (8.0 · 10−15 m²/s) compared to the solution annealed one (5.0 · 10−15 m²/s). High-pressure gaseous hydrogen charging shows no differences regarding the degree of cold deformation with a maximum hydrogen concentration of 112 wt.-ppm. Furthermore, a significant ductility loss expressed by the ratio of the reduction of area was observed.
Publisher Copyright: © 2024 The Author(s)
Keywords: austenitic stainless steel; high-pressure charging; hydrogen embrittlement; Hydrogen uptake

Capacity of hydrogen traps affects H-assisted crack initiation and propagation mechanisms in martensitic steels - Safyari, Mahdieh; Bhosale, Saurabh; Moshtaghi, Masoud (Engineering Failure Analysis, 2024)
Low-carbon martensitic steels are candidate materials for different hydrogen applications. Hydrogen embrittlement (HE) of the steels can be mitigated by designing trap site characteristics. In this study, the different capacities of hydrogen trapping, and reversibility of the trap sites are studied to reveal the extent of HE susceptibility of the steels and H-assisted crack initiation and propagation mechanisms. The trap sites in Ti-contained and Mo-contained martensitic steels were identified and discussed. The trap sites in Ti-contained martensitic steel include basic martensitic microstructure, the interface of the TiC/matrix interface and carbon vacancies inside the TiC carbides. The trap sites in Mo-contained martensitic steel including basic martensitic microstructure and interface of the Mo 2C/matrix interface. Ti-contained steel indicates a mitigated HE susceptibility, controlled by carbon vacancies inside TiC acting as strong hydrogen trap sites, and a higher possibility of building up a critical hydrogen content at Mo 2C carbide due to lower hydrogen capacity. These results prove that hydrogen trapping capacity at the designated hydrogen trap sites is a determinant factor for H-assisted crack initiation and propagation in martensitic steels. A critical local hydrogen amount should be built up at the trap site to assist the crack to develop. It was also revealed that crack initiation originated from Mo 2C carbides accompanied by interfacial decohesion at the interface of martensitic matrix/Mo 2C carbides and propagated in quasi-cleavage patterns along {0 1 1} planes.
Publisher Copyright: © 2024 The Author(s)
Keywords: Crack initiation; Crack propagation; Hydrogen embrittlement; Hydrogen trapping capacity; Martensitic steels

Effect of Slag Basicity on Alumina Dissolution and Diffusivity - Burhanuddin, Burhanuddin; Harmuth, Harald (China's refractories, 2024)
Alumina is one of the crucial and extensively utilized refractory components. As the refractory wear due to dissolution at elevated temperatures during operation is a major threat to refractory lifespan, quantifying dissolution is important for developing cost-effective and resource-efficient refractories. This study investigated the dissolution of alumina particles intwo silicate and one calcium aluminate slags at 1 450, 1 500, and 1 550 °C using high-temperature confocal laser scanning microscopy (HT-CLSM). Dissolution was quantified in terms of diffusivity, with all influencing factors, including Stefan flow and bath movement, incorporated into the determination process. The trends observed in total dissolution time and diffusivity in three slags at three experimental temperatures could not be explained solely on the basis of slag basicity. Two parameters, considering the influencing factors, were introduced to explain these trends. Furthermore, the linear trend observed in Arrhenius plots of diffusivities supports the diffusivity results. Additionally, good agreement between the diffusivities of alumina in one silicate slag obtained via CLSM and rotating finger test investigations verified the reliability of the results.
Publisher Copyright: © 2024 Editorial Board of China's Refractories. All rights reserved.
Keywords: Alumina; Dissolution; Diffusivity; Corrosion; Refractory; refractory; alumina; corrosion; dissolution; diffusivity

Kontinuierliches Trennen eines Kunststoffgemisches - Franz, Grassegger; Michael, Feuchter; Nadine, Wild (2024)
Es wird eine Vorrichtung (100) beschrieben zum Trennen eines Kunststoffgemisches (111), die Vorrichtung (100) aufweisend: i) einen Zufuhrbereich (110), welcher eingerichtet ist zum Zuführen Kunststoffgemisches (111) in zumindest teilweise geschmolzenem Zustand; ii) einen Zentrifugierbereich (120), welcher an den Zufuhrbereich (110) gekoppelt ist, und welcher eingerichtet ist, das zumindest teilweise geschmolzene Kunststoffgemisch (111) mittels Zentrifugierens in eine erste Kunststofffraktion (112) und eine zweite Kunststofffraktion (113) zu trennen, wobei die erste Kunststofffraktion (112) von der zweiten Kunststofffraktion (113) verschieden ist; und iii) einen Ausfuhrbereich (130), welcher an den Zentrifugierbereich (120) gekoppelt ist, und welcher eingerichtet ist zum Bereitstellen der abgetrennten ersten Kunststofffraktion (112) und der abgetrennten zweiten Kunststofffraktion (113). Die Vorrichtung (100) ist eingerichtet in einem kontinuierlichen Betrieb zu operieren.

Modellbasierte Rohmehlkonzeptsteuerung für eine CO2-optimierte Klinkerproduktion - Pöllabauer, Florian; Gröll, Christine; Köck, Wolfgang; Flachberger, Helmut (Berg- und hüttenmännische Monatshefte : BHM, 2024)
Die Zementindustrie steht vor der Herausforderung, ihren CO2-Fußabdruck zu reduzieren. Eine Möglichkeit dazu besteht im verstärkten Einsatz von CO2-armen Ersatzrohstoffen in der Klinkerproduktion. Dieser Artikel beschreibt die Entwicklung einer innovativen Prozesssteuerung zur Optimierung der Rohmehlproduktion im Zementwerk Wietersdorf der Alpacem Zement Austria GmbH. Durch den Einsatz von Inline-Analysetechnologien und einem Optimierungsalgorithmus können verschiedene Qualitäten von Ersatzrohstoffen gleichzeitig eingesetzt werden, um die CO2-Emissionen nachhaltig zu minimieren. Das Tool befindet sich derzeit in der Testphase und hat das Potenzial, die Produktgleichmäßigkeit bei gleichzeitiger Erhöhung der Ersatzrohstoffrate zu optimieren und dadurch den CO2-Fußabdruck zu reduzieren.

A new approach for in situ electrochemical nanoindentation: Side charging as a promising alternative - Zeiler, Stefan; Jelinek, Anna; Terziyska, Velislava; Schwaiger, Ruth; Mitterer, Christian; Brinckmann, Steffen; Maier-Kiener, Verena (Acta materialia, 2024)
Understanding hydrogen embrittlement in metals is an essential task for the energy transition, where hydrogen plays a key role. Besides the economic consequences of embrittlement, safety aspects are a very important factor to consider. Therefore, materials need to be screened in order to evaluate their mechanical response under hydrogen influence. Besides macroscopic mechanical testing, in situ electrochemical nanoindentation and micromechanical testing —in general— represent promising methods as they allow to characterize individual microstructural features. In the established “front-side” charging approach, hydrogen enters the sample at the same surface on which indentation tests are performed. An alternative is “back-side” charging, where hydrogen is introduced at the opposite side of the indentation location. In the present study, a novel “side” charging cell was designed and the results were compared to those obtained by “front-side” charging. For this purpose, a ferritic steel with high chromium content (X6Cr17) underwent a grain coarsening heat treatment to ensure that multiple nanoindentation experiments can be performed within a single grain. A similar grain orientation was tested with both charging approaches. The novel “side” charging cell design outperforms the stiffness of the reference front-side charging cell by 60 %. Both cell designs yielded constant Young's moduli before, during and several hours after charging. The hardness increased during charging due to hydrogen uptake, whereas the hardness settled several hours after charging to the values before charging started. The presence of hydrogen at the indentation side was confirmed by in situ X-ray diffraction using a self-reporting titanium film.

Emergence of Coated Piston Ring Scuffing Behavior on an Application-Oriented Tribological Model Test System - Markut, Thomas; Summer, Florian; Pusterhofer, Michael; Grün, Florian (Lubricants, 2024)
A major problem in lubricated piston ring/cylinder liner contact sliding systems is the tribological failure mechanisms known as scuffing. In order to evaluate and better understand this damage phenomenon in these tribological systems, a tilted linear tribometer (TE77) for application-oriented reciprocating model tests was developed and validated with scuffed field engine parts. With precise oil lubrication, original engine parts, such as CKS-coated piston rings (chromium-based coating with included aluminum oxides), original liners and fully formulated lubrications, were tested under conditions similar to the most critical part of the internal combustion engines (ICEs), known as fired top dead center (FTDC). Various in situ measurements during the tests allowed for a detailed investigation of the damage processes (crack transformation) on the tribological components. For the coated piston ring, vertical cracks were attributed to residual stresses, while horizontal cracks resulted from shear stresses. The crack transformation and wear results from other studies were confirmed for the liner. The results from FIB (Focused Ion Beam) cuts, along with EDS and SEM analyses, revealed that Fe (deriving from material transfer) acts as a catalyst on the CKS layer for the tribopads and that zinc sulfides are not present everywhere.
Publisher Copyright: © 2024 by the authors.
Keywords: application-oriented model test; coated piston ring; grey cast iron; scuffing phenomena

Influence of Mo carbides and two-stage tempering methodology on the susceptibility of medium carbon martensitic steel to hydrogen embrittlement - Eskinja, Magdalena; Winter, Gerald; Schnideritsch, Holger; Klarner, Jürgen; Razumovskiy, Vsevolod I.; Moshtaghi, Masoud; Mori, Gregor Karl (Engineering Failure Analysis, 2024)
The objective of the present study was to enhance the hydrogen embrittlement (HE) resistance of the quenched and tempered martensitic steel via the interplay of heat treatment variance and precipitation of nanosized carbides. For this purpose, one-stage tempering and two-stage tempering methodologies were implemented, and steel was alloyed with Mo to instigate the precipitation of Mo carbides. The results revealed that two-stage tempered steel exhibited superior resistance to HE, as a result of reduced dislocation density and higher quantity of Mo2C. To discern the role and trapping behaviour of Mo2C carbides, Thermal Desorption Spectroscopy (TDS) combined with electrochemical hydrogen charging was utilized. Precipitated nanosized Mo2C exhibited the ability to trap hydrogen. On the contrary, an increase of dislocations and higher diffusible hydrogen content in one-stage tempered steel promoted deterioration of mechanical properties which was investigated by Slow Strain Rate Test (SSRT) and fracture surface morphology analysis. In addition, the effective diffusion coefficient for one-stage tempered steel was lower, as dislocations served as additional trap sites.
Publisher Copyright: © 2024 The Author(s)
Keywords: Hydrogen embrittlement; Martensitic steels; Mo carbides; Tempering

Saturation of grain fragmentation upon severe plastic Deformation: Fact or fiction? - Renk, Oliver; Hohenwarter, Anton; Edalati, Kaveh; Kapp, Marlene W. (Advanced engineering materials, 2024)
There has been general agreement that grain refinement upon severe plastic deformation (SPD) saturates at equivalent strains of 10–20, as a dynamic equilibrium between refinement and coarsening is established. Meanwhile, few reports question such steady state, but suggest another strain hardening regime might be entered for strains >1000. So far, neither an in-depth analysis nor a general theory for such ultra-SPD strain hardening has been established. The present work provides clear evidence for additional strain hardening at ultra-severe strains. Although at this stage the strain hardening rate is awfully weak (≈0.03 MPa), it manifests in noticeable grain refinement and hardness increase. Texture and the existence of subgrains still support dislocation-based plasticity. Specimens deformed to ultra-severe strains possess improved thermal stability. Although an unambiguous conclusion regarding the origin of the ultra-SPD strain hardening is currently not possible, the potential mechanisms are being discussed. While continuous impurity uptake from the anvils could explain the hardening and improved thermal stability, estimation of grain boundary migration rates suggests that a slight but continuous net refinement is also plausible. Together with structural transformations of grain boundaries, this offers an alternative, intrinsic source for ultra-SPD hardening. It is hoped that this thought-provoking conclusion stimulates further research into this subject.

Understanding the Continuous Casting Process with CFD Modelling: The Impact of Microscopic Dynamics on Macroscopic Scales - Gruber, Christine; Barati, Hadi; Holzinger, Gerhard; Javurek, Mirko; Zhang, Xiaomeng; Ilie, Sergiu; Michelic, Susanne Katharina; Saeedipour, Mahdi; Wu, Menghuai (2024)

Mapping electro-vortex flow patterns from tornado to inverted tornado in a hemispherical container - Abdi, Mehran; Karimi Sibaki, Ebrahim; Sommitsch, Christof; Barati, Hadi; Al Nasser, Mohamad; Wu, Menghuai; Teplyakov, I.; Kharicha, Abdellah (International Journal of Thermofluids, 2024)
This study aims to investigate the intricate interaction between fluid flow and magnetic fields, known as magnetohydrodynamic (MHD) phenomena, within a hemispherical container filled with conducting gallium–indium–tin (Ga-In-Sn) liquid. The primary objective is to explain the influence of the external magnetic field and electric current intensities on the flow structure. Novel insights into the emergence of Lorentz forces that drive the flow dynamics are pursued by varying these parameters. The motivation for this investigation is rooted in the desire to deepen our understanding and uncover new insights into magnetohydrodynamic (MHD) phenomena within a specific experimental setup. Specifically, we aim to understand how swirl velocity is generated and altered by fluctuations in magnetic field strength and electric current intensity within the system. Our investigation reveals a transformation in the flow pattern in a hemispherical pool as the magnetic field strength increases while maintaining a constant electric current intensity. Sequential transformations from a rope tornado to a tornado, cyclone, and finally an inverted tornado are observed, shedding light on the complex behavior of the system. On the other hand, under fixed external magnetic field conditions, it is observed that, as the electric current intensifies, the flow pattern evolves from a tornado to a rope tornado or from a cyclone to a tornado. Furthermore, once the electric current intensity exceeds a specific threshold, the flow pattern remains unchanged, providing valuable insights for process optimization and control. This study contributes to a deeper understanding of MHD phenomena and offers practical implications for optimizing processes such as electroslag remelting (ESR) and vacuum arc remelting (VAR) that involve a similar hemispherical pool of conductive liquid. The simulation results are validated against experimental measurements, ensuring the reliability and accuracy of our findings.

Mechanical processing and thermal stability of the equiatomic high entropy alloy TiVZrNbHf under vacuum and hydrogen pressure - Schweiger, Lukas; Römer, Felix; Gizer, Gökhan; Burtscher, Michael; Kiener, Daniel; Pistidda, Claudio; Schökel, Alexander; Spieckermann, Florian; Eckert, Jürgen (Applied physics letters, 2024)
Publisher Copyright: © 2024 Author(s).

Rock joint filling breakage under three different instant loading conditions; physical test and PFC simulation - Zhou, Lei; Sarfarazi, Vahab; Haeri, Hadi; Shahbazian, Armin; Moayedi Far, Arsham; Fatehi Marji, Mohammed (Computational particle mechanics, 2024)
In this investigation, the influences of filling shapes on the failure mechanisms of rock masses under uniaxial compressive tests were analyzed using experimental and numerical simulation methods. For this purpose, a gypsum filling slab with three different shapes (isosceles trapezoid shape, triangle shape, and square shape) was inserted between the two granite specimens. In this regard, three different gypsum conditions were prepared; (1) gypsum containing a hole, (2) intact gypsum, and (3) gypsum containing the grout. Nine models were subjected to compression load with an axial load rate of 0.05 mm/min. Moreover, PFC2D was also employed to conduct numerical simulations of the models containing gypsum filling. In this matter, eight distinct types of soft gypsum filling were created; (1) concave shape, (2) semi-concave shape, (3) isosceles trapezoid shape, (4) triangle shape, (5) square shape, (6) bit shape, (7) lozenge shape, and (8) trapezoid. In addition, three different conditions were considered, i.e., gypsum containing a hole, intact gypsum, and gypsum containing the grout. The Brazilian tensile strength of gypsum and grout was 0.4 and 1 MPa, respectively. According to the results obtained, the failure process was predominantly controlled by the filling shape and filling conditions. With regard to the compressive strength, the fracture pattern and the failure mechanisms associated with the filling were found to play the main role. It was concluded that the compressive behavior of the filling is highly affected by the number of generated tensile cracks. As for hits of the acoustic emission (AE), a few AE hits were captured in the preliminary phase of loading, followed by a rapid growth in AE hits when the applied load reached its highest value. Furthermore, a large number of AE hits were observed during the stress drop.
Publisher Copyright: © The Author(s) under exclusive licence to OWZ 2024.
Keywords: Acoustic emission; Filling shape; PFC2D; Physical test

Effect of cold rolling route and annealing on the microstructure and mechanical properties of AISI 316 L stainless steel - Mohammadzehi, Sara; Roostaei, Milad; Mirzadeh, Hamed; Mahmudi, Reza; Weißensteiner, Irmgard (Materials characterization, 2024)
Since cross rolling promotes the transformation of austenite to deformation-induced α΄-martensite and increases the dislocation density in the retained austenite, the reversion/recrystallization annealing after cross rolling might be more effective to achieve finer grain sizes in metastable austenitic stainless steels. Accordingly, the effect of cold rolling route and annealing for grain refinement and improvement of mechanical properties of AISI 316 L stainless steel was systematically investigated in the present work. It was found and formulated that by increasing strain, the grain refinement efficiency during annealing is improved, the effect being more pronounced if the cold rolling step is applied by cross rolling instead of unidirectional rolling. The evaluation of tensile properties revealed that all cold rolling and annealing routes lead to significant improvements of mechanical properties in terms of strength and plasticity, the influence of cross rolling being more prominent again. Moreover, the cross rolling and annealing route led to a remarkable strength-ductility balance, which revealed the opportunities that this route can offer for the improvement of mechanical properties of austenitic stainless steels. Accordingly, the results of the present work may shed light on the further utilization of cold rolling route and annealing treatment.
Publisher Copyright: © 2023
Keywords: Austenitic stainless steels; Cross rolling; Grain refinement; Mechanical behavior; Recrystallization

Exploring Refinement Characteristics in FeTi–Cux Composites - Schweiger, Lukas; Spieckermann, Florian; Buchebner, Nadine; Keckes, Julius F.; Kiener, Daniel; Eckert, Jürgen (Advanced Engineering Materials, 2024)
FeTi–Cu composites with varying Cu contents are subjected to high-pressure torsion, and their deformation behavior is explored systematically using scanning electron microscopy, microhardness, and nanoindentation. The study identifies the limiting factors influencing the refinement during severe plastic deformation. The pronounced strength differences between phases lead to fragmentation primarily through hard–hard (FeTi–FeTi) contact points, promoted by homogeneous, i.e., nonlocalized, and possibly turbulent material flow. These conditions are prevalent in Cu-rich composites and during high-temperature deformation. Conversely, Cu-lean composites exhibit deformation localization, hindering the fragmentation process. Abrasion becomes an efficient refinement mechanism at the submicron-/nanoscale, particularly for composites containing higher concentrations of nanocrystalline FeTi and exhibiting homogeneous plastic deformation. Consequently, deformation localization in Cu-lean composites inhibits both refinement mechanisms, while Cu-rich compositions and higher temperatures result in efficient refinement but at the risk of coarsening at the nanoscale. Refinement is localization-limited in the former case and abrasion-limited in the latter. Optimized processing conditions can overcome these constraints, yielding a uniform nanocomposite. This study sheds light on the intricate interplay of the mechanical properties of the respective phases in a composite, emphasizing the importance of tailored compositions and deformation conditions to optimize nanocomposites, particularly when dealing with challenging material pairings.
Publisher Copyright: © 2024 The Author(s). Advanced Engineering Materials published by Wiley-VCH GmbH.
Keywords: deformation localization; high-pressure torsion; mechanical properties; nanocomposites; refinement

Multiphase evolution of fluids in the Rudnik hydrothermal-skarn deposit (Serbia) - Petrovic, Stefan; Bakker, Ronald Jack; Cvetkovic, Vladica; Jelenkovic, Rade (Mineralogy and Petrology, 2024)
This study presents and discusses first detailed petrographic, microthermometric and Raman spectroscopic data from quartz-hosted fluid inclusions at Rudnik Zn-Pb-Cu-Ag skarn deposit (Serbia) and combines them with the information on skarn- and ore paragenesis. Three periods in the metamorphic-hydrothermal history of the deposit are recognized: 1) the pre-ore prograde skarn period when garnet-clinopyroxene skarns formed, 2) the syn-ore period that encompasses a retrograde stage marked by epidote and zoisite and a quartz-sulfide stage characterized by quartz, pyrrhotite, sphalerite, galena and chalcopyrite, and 3) the post-ore period associated with precipitation of calcite and quartz. The hydrothermal evolution is inferred from studying six groups of quartz-hosted fluid inclusions (FI). Two-phase FI of high- (Group A) and moderate salinity (Group B) are found in quartz cores and homogenized at 380–390 °C (mode) and 370–380 °C (mode), respectively. Group A FI consists of H 2O-NaCl liquids and CO 2-CH 4 gas mixtures and likely represents the original fluid composition, whereas Group B FI records dilution of the original fluid at constant temperature, with a slight increase in CH 4 contents. The quartz cores also contain Group C as volatile-rich FI (mostly CO 2 with up to 10 mol% CH 4 and H 2S) of a moderately low salinity and liquid-rich Group D FI composed of pure water with homogenization temperatures of 180–200 °C (mode). The transitional zones of quartz crystals show overgrowth textures and host Group E FI with low salinity that homogenized at 235–401 °C, which vapour phase is a CO 2-CH 4 mixture with up to 17 mol% CH 4. Group F comprises FI found within the rim zones of quartz crystals and they exhibit a low salinity and homogenization temperatures between 259–365 °C. Accordingly, the hydrothermal history at Rudnik involved: a) mixing of different salinity fluids at high temperatures (Groups A and B—retrograde stage), b) introduction of fluids with high volatile contents (Group C) and cooling of fluids with constant salinity (between Groups E and F), which likely correspond to the quartz-sulfide stage, and c) inflow of meteoric water (Group D—the post-ore quartz-calcite stage).
Publisher Copyright: © The Author(s), under exclusive licence to Springer-Verlag GmbH Austria, part of Springer Nature 2024.
Keywords: Fluid inclusions; Rudnik; Serbian Cenozoic Magmatic Province; Skarn deposit; Western Tethyan Metallogenetic Belt

Reshapable bio-based thiol-ene vitrimers for nanoimprint lithography - Sölle, Bernhard; Reisinger, David; Heupl, Sarah; Jelinek, Alexander; Schlögl, Sandra; Rossegger, Elisabeth (Reactive & functional polymers, 2024)
Taking inspiration from natural surfaces known for their ability to adaptively remodel their shape, we fabricated stimuli-responsive microstructures by using UV-induced nanoimprint lithography. For this, a fully bio-based dynamic thiol-ene photopolymer was synthetized by the radical mediated addition of a trifunctional eugenol-based thiol (SH3E) crosslinker across an allylated linseed oil (ALELO). To catalyze the bond exchange reactions between the hydroxyl and ester groups within the network, a bio-based eugenol phosphate ester was introduced as a transesterification catalyst. Pure eugenol was further added as a reactive diluent to increase the number of hydroxyl groups and thus, accelerate the thermo-activated bond exchange reactions. Once cured by UV exposure, the dynamic photopolymer is thermally stable up to 250 °C and is able to relax 63% of the original stress within 62 min at 160 °C. Subsequently, films with micropillars, having an aspect ratio of 1:2.5 were prepared by using nanoimprint lithography. The macroscopic reflow capability of the dynamic network enabled a reorientation of the imprinted structures during a thermal reshaping step. The imprints were characterized by 2D/3D optical microscopy, μCT imaging and static water contact angle measurements. Based on the orientation of the micropillars, the water contact angle was varied between 118° and 95°, giving rise to a possible application in microfluidic devices.
Publisher Copyright: © 2024
Keywords: Biobased thiol-ene networks; Nanoimprint lithography; Photopolymerization; Switchable surfaces; Vitrimers

Crack characterization in manganese steel using a µ-bolometer camera and an air-cooled inductor - Tuschl, Christoph; Oswald-Tranta, Beata; Dornig, Peter; Künstner, David; Pötz, Melanie; Eck, Sven (SPIE Defense + Commercial Sensing 2024, 2024)
Due to beneficial mechanical properties, cast manganese (Mn13) steel is used for premium grade railway turnout frogs worldwide. However, its coarse-grain structure makes common non-destructive testing (NDT) methods for defect detection used in this industry very difficult to apply. Inductive thermography is a NDT method well suited for this problem.Scanning inductive thermography is used to localise surface defects on the running surfaces of turnout frogs. Once localised, we propose additional static measurements to characterise the detected surface defects with respect to crack length, depth and penetration angle. Simulations with ANSYS Multiphysics are conducted to study the influence of different crack geometries as well as the influence of different excitation parameters. Validation measurements on samples with defined crack geometries are conducted. The results of both, simulation and measurements on samples, are used to characterize surface defects on actual manganese turnout frogs.
Conference code: 13047
Keywords: inductive thermography; crack detection; crack characterization; scanning inspection; manganese stee; railway inspection

Energy Absorption and Beam Damage during Microfocus Synchrotron X-ray Diffraction - Stanko, Štefan T.; Schawe, Jürgen E. K.; Spieckermann, Florian; Eckert, Jürgen; Löffler, Jörg F. (The journal of physical chemistry letters, 2024)
In this study, we combine in situ fast differential scanning calorimetry (FDSC) with synchrotron X-ray measurements to study simultaneously the structure and thermophysical properties of materials. Using the example of the organic compound BCH-52, we show that the X-ray beam can heat the sample and induce a shift of the heat-flow signal. The aim of this paper is to investigate the influence of radiation on sample behavior. The calorimetric data is used to quantify the absorbed beam energy and, together with the diffraction data, reveal an irreversible damage of the sample. The results are especially important for materials with high absorption coefficients and for high-energy X-ray and electron beams. Our findings illustrate that FDSC combined with X-ray diffraction is a suitable characterization method when beam damage must be minimized.
Publisher Copyright: © 2024 The Authors. Published by American Chemical Society.

Rohgutcharakterisierung und aufbereitungstechnische Untersuchungen an Roherzen aus der Grube Clara der Firma Sachtleben Bergbau GmbH & Co. KG - Prem, Dominic; Petersen, Thies Olaf; Rieger, Ana; Mauerlechner, Robert; Flachberger, Helmut (Berg- und hüttenmännische Monatshefte : BHM, 2024)
Mit Fortschreiten des Abbaus in tiefere Bereiche der Grube Clara der Firma Sachtleben Bergbau GmbH & Co. KG am Standort Wolfach ist nach derzeitigem Wissenstand mit einem vermehrten Auftreten von kupfer- und silberhaltigen Vererzungen zu rechnen. Bisher wurden diese vor allem im südlichen Teil der Lagerstätte angetroffen und gesondert hereingewonnen sowie aufbereitet. Durch das vermehrte Auftreten dieser Vererzungen ist der bisherige Anlagenbetrieb zur Sulfid-Flotation unter Nutzung der bestehenden Aufbereitungsanlage kritisch zu hinterfragen, was im Zuge eines mehrjährigen Forschungsprojektes gemeinsam mit dem Lehrstuhl für Aufbereitung und Veredlung der Montanuniversität Leoben geschah.Als Grundlage für die Forschungsaktivitäten dienten Roherze aus unterschiedlichen Lagerstättenbereichen, die im Zuge einer als umfangreich zu bezeichnenden Probenahmekampagne hereingewonnen wurden. Diese wurden nach der Leobener Schule der Aufbereitungstechnischen Merkmalsklassenanalyse hinsichtlich ihrer Mineralogie, Verwachsung und Aufbereitbarkeit untersucht. Darauf aufbauend wurden umfangreiche Zerkleinerungs- und Flotationsversuche durchgeführt. Die forschungsrelevanten Teile der diesbezüglichen Aktivitäten erfolgten im Rahmen der Dissertation des erstgenannten Autors.Dieser Beitrag gibt Einblicke in die komplexen gleichwie intensiven Verwachsungsverhältnisse der aufgefundenen Kupfer- und Silberträger und zeigt, dass trotz der unterschiedlichen Zerkleinerungswiderstände der Wertminerale, Flotationskonzentrate mit mehr als 90 % Inhaltsausbringen und hoher Selektivität erzeugt werden können.

KIRAMET - Neubauer, Melanie; Rückert, Elmar (Integrated Computational Materials, Process and Product Engineering 2024, 2024)

Semi-analytical and experimental heat input study of additively manufactured Zr-based bulk metallic glass - Hadibeik Neishaboori, Sepide; Gingl, Emanuel; Schretter, Lukas; Bochtler, Benedikt; LI, Jiehua; Gammer, Christoph; Hohenwarter, Anton; Spieckermann, Florian; Eckert, Jürgen (Additive Manufacturing, 2024)
Laser powder bed fusion (LPBF) of Zr-based bulk metallic glasses (BMGs) has recently attracted attention due to its capacity for microstructure control, the potential for custom-tailored properties, and its versatile applicability across various industries. It is crucial to strike a balance between relative density, relaxation, and crystallinity tailored to a specific application when 3D printing amorphous components. However, prior findings have not revealed an exclusive study concerning low fractions of crystallinity (<5 vol%) and atomic-scale effects during the LPBF process, e.g. the relaxation degree of the amorphous structure. This study employs a systematic experimental approach, complemented by semi-analytical modeling, to comprehensively recognize the nano- and macro-scale amorphous structure and the associated mechanical behavior. Differential scanning calorimetry (DSC) along with flexural stress-strain measurements disclose that the highest relaxation and crystallization enthalpies, which are obtained for samples printed with lower heat input, are not in correlation with the desired mechanical properties. On the contrary, samples printed with a heat input of ΔH=44 reveal the maximum density range (up to 99.97 %) and showcase laboratory-XRD amorphous structure. This results in the highest flexural strength (up to 2080 MPa) and elastic deformation range (up to 2.6 %), along with the lowest Young's modulus span (60–70 GPa). In this case, the crystallinity (0.02–0.2 vol%) associated with the desired mechanical properties is calculated from the modeling results. The outcomes indicate increased heating/ cooling rates corresponding to the amplified heat input, with cooling rates reaching up to 5×104 °C/s and heating rates up to 6×105 °C/s. However, underlying layers are subjected to reduced heating and cooling rates. This observation not only validates the intricate thermal dynamics in LPBF but also elucidates the crystalline formation in heat-affected zones (HAZs) with associated lower heating and cooling rates.
Publisher Copyright: © 2024 The Authors
Keywords: Bulk metallic glass (BMG); Crystallization; Laser powder bed fusion (LPBF); Relaxation; Semi-analytical simulation

Comparing the properties of cellulose nanofibrils from wood and bark of Norway spruce (Picea abies KARST.) and silver poplar (Populus alba L.) - Supriyadi, Didik; Bodner, Sabine; Keckes, Jozef; Gindl-Altmutter, Wolfgang; Veigel, Stefan (Carbohydrate polymer technologies and applications, 2024)
Bark, an underutilized biomass resource, is a promising raw material for cellulose nanofibrils (CNF) production due to its renewability, abundance, and low cost. Because data on the physical and chemical properties of bark-based CNF is scarce, we investigated the feasibility of CNF production from two different bark species (Norway spruce and silver poplar) using a combination of sequential extraction, delignification, and mechanical fibrillation. The chemical composition, crystallinity index, morphology, fibril diameter, thermal stability, and mechanical properties of the CNF were evaluated and compared with those of wood-based CNF from the same species. The results showed that spruce bark yielded CNF virtually undistinguishable from spruce wood-derived CNF in terms of structure and mechanical properties of nanopapers made thereof. Nanopapers prepared from spruce wood and bark showed comparable tensile strength and Young's modulus of around 130 MPa and 15 GPa, respectively. Contrarily, CNF derived from poplar bark were different in structure compared to poplar wood CNF, and nanopapers produced from poplar bark CNF showed only modest mechanical performance. In summary, the extensive characterization carried out demonstrated the general feasibility of CNF production from tree bark but also revealed the need for further optimization, like in the case of poplar bark.
Publisher Copyright: © 2024 The Author(s)
Keywords: Bark; Nanocellulose; Nanopaper; Poplar; Spruce

Influence of broad ion beam polishing on the surface roughness of hydrated cement paste and its implications on microstructural analysis - Sammer, Thomas; Shi, Xiangyun; Khan, Muhammad Zubair; Matkovic, Aleksandar; Teichert, Christian; Raith, Johann (Cement and concrete research, 2024)
In recent years, the technical capabilities of high-resolution Scanning Electron Microscopes (SEM) improved significantly. To fully utilise their potential, it is crucial that also the preparation techniques are advanced to obtain a high-quality surface which preserves even nanometre sized microstructural features. In this study, state-of-the-art resin-embedded polishing, and novel Broad Ion Beam (BIB) milling of hydrated cement paste are compared. SEM microstructural investigations are aided by image processing to determine porosity and pore geometry factors. Additionally, a comprehensive quantitative surface roughness analysis based on Atomic Force Microscopy scans is carried out. BIB-milling enabled the study of nanoscale features such as gel porosity or the acicular morphology of calcium-silicate-hydrates. Pores exhibit increased aspect ratios whereas resin-embedded polishing results in higher circularity. However, a superior vertical surface roughness was achieved by the resin-embedded polishing approach. The research highlights the advantages and drawbacks of BIB-milling as a polishing method for hydrated cement pastes.
Publisher Copyright: © 2024 The Authors
Keywords: Atomic force microscopy; Broad ion beam milling; Hydrated cement paste; Image processing; Surface roughness analysis

Ab initio study of oxygen vacancy filament formation at Ta/HfO2 interface - Zhang, Donglan; Wang, Jiong; Wu, Qing; Du, Yong; Holec, David (Surfaces and Interfaces, 2024)
The resistive switching (RS) behavior of resistive random access memory (RRAM) based on oxygen vacancy (V O) conduction is significantly affected by the interface properties between metal electrode and oxide layer, yet the modulation between the RS behavior and the physico-chemical properties of the interface is still not very clear. In this study, the correlative role of Ta/HfO 2 interface with the RS behavior in HfO 2-based RRAM is explored at atomic level. First-principles thermodynamic calculations show that the strong interaction between three-fold oxygen vacancies (V O3) leads to a formation of V O3-based conductive filament (CF) along direction perpendicular to the interface. Four-fold oxygen vacancies (V O4) make a major contribution to the re-formation and growth of CFs during the set process by diffusing into the residual filaments. The results of electronic properties further indicate that as the number of V Os perpendicular to the interface increases, the charge redistribution between O and Ta atoms at the interface is significantly increased, and more electron clouds are gathered around V Os. This is the underlying mechanism of forming a conductive channel. This study reveals the important regulation mechanism of the interface characteristics between metal electrode and oxide layer in RRAM on the formation and growth of V O-based CFs.
Publisher Copyright: © 2024
Keywords: Conductive filaments; Interface; Oxygen vacancy; Resistive switching; RRAM

Asymmetric supercapacitors based on biomass-derived porous activated carbon (PAC)/1D manganese oxide (MnO2) electrodes with high power and energy densities - Lee, Young-Seok; Selvaraj, Aravindha Raja; Kostoglou, Nikolaos; Rebholz, Claus; Rajendiran, Rajmohan; Raman, Vivekanandan; Kim, Heeje; Rajesh, John Anthuvan; Nagulapati, Vijay Mohan; Oh, Tae Hwan; Jerome, Peter; Kim, Sung-Shin (Materials science and engineering B (Solid-state materials for advanced technology), 2024)
In this study, we present the electrochemical performance of an asymmetric supercapacitor (ASC) composed of one-dimensional manganese oxide (MnO 2) nanorods embedded in porous activated carbon sheets (MnO 2/PAC) as the positive electrode (positrode), and renewable porous activated carbon (PAC) as the negative electrode (negatrode). This configuration facilitates a high rate of charge/discharge while maintaining substantial specific capacity. The MnO 2/PAC composite was successfully synthesized using a hydrothermal technique, while the PAC material was produced through pyrolysis reaction. The MnO 2/PAC composite exhibited a maximum specific capacitance of 208.75F g −1 at 0.5 A/g and demonstrated a cyclic stability of 87.43 % in neutral aqueous electrolytes. This notable electrochemical performance is attributed to the significant contribution of the high pseudo-capacitance offered by dense MnO 2 nanorods, in addition to the expansive surface area of the activated carbon sheets with closely packed structures. The ASC constructed as PAC//MnO 2/PAC displayed a high energy density of 23.3 Wh kg −1 and a power density of 350.4 W kg −1 at a current density of 0.5 A/g. Furthermore, the device showcased exceptional cycling stability, retaining 90.3 % at a current density of 4 A/g. These results underscore the substantial untapped potential of ASC devices for innovative applications in advanced energy storage.
Publisher Copyright: © 2024 Elsevier B.V.
Keywords: 1D β-MnO nanorods; Asymmetric capacitors; Biomass derived hierarchically porous carbon; Pseudo capacitance

Characterization of mineral waste as potential precursors for alkali-activated materials - Ratz, Bettina; Sedlazeck, Klaus Philipp; Raic, Sara; Steindl, Florian Roman; Rudic, Ognjen; Grengg, Cyrill (2024)

Detachment of a Soluble Particle at the Slag-Argon Interface - Zhang, Xiaomeng; Michelic, Susanne Katharina; Pirker, Stefan; Saeedipour, Mahdi (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2024)
The behavior of non-metallic inclusions at interfaces of high-temperature melt and molten slag affects the removal of inclusions and the consequent melt cleanness. This study presents real-time in situ observations on the behavior of an oxide particle in the vicinity of the slag-argon interface by means of high-temperature confocal scanning laser microscopy (HT-CSLM). On top of that, CFD simulations are conducted to investigate the underlying mechanisms of particle-interface interactions. In addition to revealing the particle motion process from the argon phase toward the slag, a significant particle morphology alteration associated with its dissolution in the slag is experimentally observed. Particularly, upon detachment from the slag-argon interface, the particle exhibits more dissolution at the near-interface area. By combining with numerical simulations, this study indicates that particle separation at the interface can be characterized as two stages. First, a short-term capillary force-driven motion stage happens until the particle initially settles at the interface. The settling position estimated by simulation shows good consistency with experimental measurement. Second, the particle takes a relatively long time to eventually detach from the interface, and this period is accompanied by particle dissolution. Investigations suggest that the concentration variation near the interface arising from particle dissolution triggers a Marangoni flow. This flow, in turn, enhances the local dissolution rate, consequently causing a significant particle morphology change that influences the detachment. This study provides new insight into the mechanism of inclusion removal through slag absorption in metallurgical processes. Both particle dynamics and dissolution kinetics, especially the effect of solutal Marangoni convection, are highlighted in detaching a small-scale particle from the fluid-fluid interface.
Publisher Copyright: © The Author(s) 2024.

Fördersystem des ROBOMINERS-Prototyps - Berner, Michael; Pinkse, Tobias; Riaz, Sadia (Mining Report, 2024)

Near-infrared spectroscopy in resin transfer molding—determination of the degree of cure - Salzmann, Moritz; Märzinger, Wolfgang; Teuchtmann, Michael; Ravindran, Bharath; Kirschnick, Ulrike; Fauster, Ewald (International Journal of Advanced Manufacturing Technology, 2024)
Near-infrared (NIR) spectroscopy is employed to directly monitor the degree of cure of composite material during the curing phase in the resin transfer molding (RTM) process. The composite material consists of natural fibers and an epoxy-amine resin system. The quantitative determination of the degree of cure, α, from the NIR spectra is realized by partial least square (PLS) regression in conjunction with various pre-treatments of the spectral data. As a reference, the degree of cure is determined by isothermal differential scanning calorimetry (DSC) experiments. The best PLS model that could be obtained for α is characterized by a determination coefficient of prediction (R²P) of 0.980 and root mean square error of prediction (RMSEP) of 4.4 %. While the spectra change during curing according to the literature for each RTM trial, significant differences can be observed between the spectra of different RTM trials. The reasons for this are discussed in detail. The findings show the potential of inline NIR spectroscopy for monitoring α in the RTM process.
Publisher Copyright: © The Author(s) 2024.
Keywords: Bio-composite; Degree of cure; Near-infrared spectroscopy; Resin transfer molding

Oxygen Distribution at the Hot Spot in BOF Steelmaking - Mitas, Bernhard; Schenk, Johannes (Metallurgical and Materials Transactions B: Process Metallurgy and Materials Processing Science, 2024)
The distribution of oxygen between the gaseous and liquid oxidation products at the hot spot is modeled. The simplified model accurately describes the interaction of the gas jet exiting the lance nozzles with the gaseous surrounding of the jet. This interaction changes the chemical composition of the gas jet influencing the subsequent interaction with the hot spot. The iterative procedure then calculates the chemical composition of the gas exiting the cavity. The characterization of the exiting gas flowing past the lance head as well as the generation rate of FeO is attained by combining the modeled gas composition exiting the cavity with an oxygen mass balance based on a quasi-stationary BOF operation.
Publisher Copyright: © The Author(s) 2024.

Probing local adhesion: A miniaturized multi-photon lithography design demonstrated on silanized vs. Untreated surfaces - Jelinek, Alexander; Rossegger, Elisabeth; Schlögl, Sandra; Kiener, Daniel; Alfreider, Markus (Materials and Design, 2024)
As multi-photon lithography technology matures, advanced integrated device design concepts become possible, positioned onto small surfaces, such as optical fibres. Only local adhesion anchors the printed object on the surface and ensure proper print-development without structure loss and long-term usability. Although surface treatments such as silanization are well known to considerably increase adhesion strength, quantification of adhesion is not straightforward and commonly assessed indirectly by surface characteristics and technological methods. The present work aims to quantify adhesion on a micrometer scale through SEM in situ tension experiments, that utilize a newly developed specimen geometry. Multiple specimens, with various footprints, were manufactured on both silanized and untreated fused silica substrates, allowing the comparable quantification of adhesion stresses between different surface conditions. Specimens on an untreated substrate failed with a high scatter in detaching force, whereas specimens on a silanized substrate tend to fail within the photoresist, either at the gauge section or just above the substrate, rather than at the interface itself. Thus, the adhesion stress was increased at least by a factor of 1.4 by the silanization treatment. Generally, a novel approach was developed, that can quantify local adhesions properties in realistic packaging or integrated circuits.
Publisher Copyright: © 2024
Keywords: Multi-photon lithography; Adhesion; Tensile specimen; Micromechanics; Photoresist

fs-laser preparation of half grid specimens for atom probe tomography and transmission electron microscopy - Tkadletz, Michael; Schiester, Maximilian; Waldl, Helene; Schusser, Georg; Krause, Michael; Schalk, Nina (Materials Today Communications, 2024)
For atom probe tomography (APT) and transmission electron microscopy (TEM) half grids are commonly applied as specimen carriers, serving as mount for focused ion beam (FIB) processed lift-outs. This technical note presents an alternative way to fabricate half grids directly from the material to be investigated using femtosecond (fs)-laser ablation. After cutting ∼200 µm thin in-plane and cross-plane slices from a TiN coated cemented carbide substrate using a precision cutting saw, two different half grid geometries, one suitable for APT and the other for TEM, were cut via fs-laser processing. Freestanding posts for APT were further sharpened and the areas intended for TEM were thinned top-down using the fs-laser system followed by final annular FIB milling of the APT and thinning of the TEM specimens. For proof of concept, the TiN APT half grid specimens in in- and cross-plane direction were successfully measured in voltage and laser-assisted mode, utilizing a local electrode atom probe, while electron transparency of the in- and cross-plane TEM half grid specimens was proven using a scanning electron microscope equipped with a scanning transmission electron microscopy (STEM) detector. The herein presented method is simple, fast and omits the necessity of a lift-out, reducing the complexity of FIB operations. Additionally, a frequently considered weak point of APT lift-out specimens, the Pt weld between specimen and half grid or microtip coupon is avoided, whilst a wide range of materials can be processed and consumables consumption is reduced. Thus, this work clearly demonstrates the great potential of fs-laser processing for APT and TEM specimen preparation.
Publisher Copyright: © 2024 The Authors
Keywords: APT; Coatings; Femtosecond laser ablation; Lift-out; TEM

Exploring Students’ and Teachers’ Insights on School-Based Disaster Risk Reduction and Safety: A Case Study of Western Morava Basin, Serbia - Cvetković, Vladimir; Nikolić, Neda; Lukic, Tin (Safety : open access journal, 2024)
Integrated disaster risk reduction in schools represents a key component of safety strategies within the educational sector of every country. The aim of this study is to comprehensively explore the impact of various demographic and socio-economic factors on the perceptions of students and teachers regarding disaster risk reduction and safety in schools. This study is distinguished by its extensive empirical approach, employing a multistage random sampling method to conduct 850 face-to-face interviews (650 with students and 200 with teachers) throughout 2023 in 10 out of the total 18 municipalities in the Western Morava Basin of the Republic of Serbia. Two structured survey instruments were developed, incorporating a mix of qualitative (closed-ended) multiple-choice questions and five-point Likert scales. The research proposes two central hypotheses regarding school-based disaster risk reduction. Firstly, it suggests that gender, age, parent’s employment, academic achievement, living situation, parental education levels, and engagement with social media collectively influence students’ perspectives on this matter (H1–H8). Secondly, it posits that gender, age, marital status, parenthood, and educational background significantly impact teachers’ viewpoints on school-based disaster risk reduction (H1–H5). Multivariate linear regression was used to explore predictors of students’ and teachers’ insights on school-based disaster risk reduction. Various statistical tests, including Chi-square, t-tests, one-way ANOVA, and Pearson’s correlation, were employed to investigate the influence of demographic and socioeconomic factors on these insights. The results of multivariate regression analyses indicate that age, gender, and marital status emerge as the primary predictors across various facets of students’ and teachers’ insights on school-based disaster risk reduction, including awareness of disasters, disaster education activities, attitudes toward disaster risk reduction education, and enhancement of disaster information accessibility. The findings of this study provide comprehensive insights into the key factors influencing students’ and teachers’ perceptions of disaster risk reduction in schools. This research not only contributes to the academic discourse on disaster education but also serves as a foundational basis for improving educational programs, developing policies and strategies, refining normative educational frameworks, guiding teacher training, and informing further research in disaster education.
Publisher Copyright: © 2024 by the authors.
Keywords: disaster; education; human resources; preparedness; risk reduction; safety; schools; Serbia; students; teachers; Western Morava Basin

Improving the corrosion resistance of 7055 alloy by manipulating passivation film through trace addition of TiB2 nanoparticles - Li, Xuekai; Wang, Wei; Wu, Yihong; Kang, Huijun; Guo, Enyu; LI, Jiehua; Chen, Zongning; Xu, Yanjin; Wang, Tongmin (Applied surface science, 2024)
In this study, 7055 alloy inoculated by a minor addition of TiB 2 nanoparticles was prepared and subjected to passivation treatment. The microstructures, pitting behaviors, and electrochemical properties of the 7055-0.5TiB 2 composite were comparatively investigated with respect to the base alloy. The results show that the incorporation of 0.5 wt% TiB 2 nanoparticles refines the grain size (from 142.4 μm to 44.1 μm) and reduces the volume fractions of the residual intermediates from 0.59 % to 0.49 %, leading to an increased thickness (from 4.05 nm to 5.95 nm) and improved homogeneity of the passivation film. Both the pitting diameter and the pitting area fractions are reduced upon immersing in 3.5 % NaCl for 24 h. Electrochemical test results show that the values of passivation layer resistance, charge transfer resistance, and polarization resistance are significantly increased, while the corrosion current is reduced after the incorporation of TiB 2 nanoparticles, confirming the formation of a more effective barrier layer, i.e., the passivation film. The improved corrosion resistance of 7055 alloy with the incorporation of TiB 2 nanoparticles is attributed to the reduced active dissolution rate in the grain boundary region and a more uniform and thicker passivation film with a lower corrosion rate.
Publisher Copyright: © 2024 Elsevier B.V.
Keywords: Aluminum matrix composite; Aluminum microstructure; Corrosion; Passive film

Nanocomposite versus solid solution formation in the TiSiN system - Schalk, Nina; Moritz, Yvonne; Nayak, Ganesh Kumar; Holec, David; Hugenschmidt, C.; Burwitz, V.V.; Mathes, L.; Schiester, Maximilian; Saringer, Christian; Czettl, Christoph; Pohler, Markus; Mitterer, Christian; et al. (Acta materialia, 2024)
This work contributes to the ongoing scientific debate on the structure of TiSiN coatings. In order to illuminate the formation of a nanocomposite structure versus the formation of a Ti 1-xSi xN solid solution, a series of TiSiN coatings was synthesized and the influence of varying N 2 pressures and the addition of Ar to the deposition atmosphere on the structure of TiSiN coatings was investigated in detail. The powdered TiSiN coatings all exhibited a lower lattice parameter than reported for TiN, which further decreased with increasing N 2 pressure, at comparable elemental compositions. For all coatings the presence of a crystalline Ti 1-xSi xN solid solution as well as an amorphous SiN x phase fraction could be detected, where more Si was incorporated into the Ti 1-xSi xN solid solution at higher pressures, due to less energetic growth conditions and the additional kinetic activation stemming from Ar ions resulted in less Si incorporation. Density functional theory calculations showed that defects only play a subordinate role for the low observed lattice parameters.
Publisher Copyright: © 2024
Keywords: Atom probe tomography; Coatings; Microstructure; Nanocomposite; Solid solution; TiSiN; X-ray diffraction

Artificial thermal shock cracks in WRe – A proof of concept study - Sommerauer, Michael; Siller, Maximilian; Pippan, Reinhard; Bostrom, Neil; Maier-Kiener, Verena (Nuclear Materials and Energy, 2024)
Thermal shock cracks are frequently observed in environments where extensive thermal cycling at high amplitudes is common. Typical cases for such are first wall materials in proposed fusion reactors and rotating anodes for computed tomography scanners. The formation of these cracks is driven by significant tensile stresses during the cooldown phase, following prior plastic deformation at elevated temperatures. This work proposes an experimental approach, where artificial thermal shock-like structures are generated via femtosecond laser ablation in WRe as a model material. Following a detailed laser parameter study in a W sheet material, patterns were introduced to WRe samples and investigated by different microscopy techniques. Their morphology as well as their response to thermo-cyclic loads was investigated and compared to conventionally induced thermal shock cracks. The introduction of artificial cracks by femtosecond laser ablation that mimic the morphology and behaviour of naturally induced thermal shock cracks is feasible within certain boundaries. Cuts, comparable to thermal shock cracks in width and depth, can be ablated. The cuts show an effect on the surrounding microstructure in line with the thermal shock cracks. Therefore, comparability could be proven concerning morphological and microstructural aspects. The conducted thermo-cyclic fatigue tests revealed an analogous effect on subsequent damage accumulation between the thermal shock cracks induced by thermal loading and artificial laser ablated cuts, proving the comparability under dynamic loading conditions. The extent of the effect is adjustable by tailoring the geometry of the lasered structures. The presented work suggests the possibility of studying the influence of thermal shock cracks on further fatigue mechanisms in exceptionally demanding applications, such as first wall materials or rotating anodes, by practical experimentation. Based on the resulting in-depth understanding of underlying interactions, the lifetime of these components might be prolonged by a deliberate introduction of crack networks or laser-ablated structures.
Publisher Copyright: © 2024 The Author(s)
Keywords: Fatigue Testing; Femtosecond Laser Ablation; High-Temperature Electron Scanning Microscopy; In-situ Damage Acquisition; Thermal Expansion; Thermal Shock Cracking

Critical properties of plastic packaging waste for recycling: A case study on non-beverage plastic bottles in an urban MSW system in Austria - Gritsch, Lea; Breslmayer, Gisela; Rainer, Ricarda; Stipanovic, Hana; Tischberger-Aldrian, Alexia; Lederer, Jakob (Waste management, 2024)
The low recycling rate of post-consumer plastic packaging waste (PPW), which is partly due to insufficient separate collection, heterogeneous composition and high levels of contamination, poses a challenge in Austria, where the recycling rate must double in order to meet the target of 55 %. This study analyzes key packaging characteristics of non-beverage plastic bottles influencing recyclability, using Vienna as a case study. Additionally, a net quantity indicator and separate collection rates were calculated. 738 bottles from mixed MSW and 1,159 bottles from separate PPW collection were analyzed. The main polymer's proportion described by the net quantity indicator was higher for bottles from separate collection (69–72 %) than from mixed MSW (58 %), showing that a large share of the foreign materials are residues and dirt, with significantly higher contents in mixed MSW (20 %) than in separate collection (11 %). With a separate collection rate of 19.2 %, the great potential for recycling currently lies in mixed MSW at 4,112 t/yr. Thereof, 46 % is uncolored, 54 % is colored/white and, in terms of material grade, 30 % is food grade. The most common filling volume for PET, PP and HDPE was 0.5 < x ≤ 1.5 L (23–59 %) and the most common decoration technology was label (60–85 %). PET and PP had the highest shares of food-grade bottles (37–46 %), while PP had the highest share of colored bottles (22–31 %). The mechanical recycling potential of bottles depends largely on packaging characteristics, influencing separate collection and also automatic sorting. Harmonized design specifications are therefore crucial for this heterogeneous PPW fraction.
Publisher Copyright: © 2024 The Author(s)
Keywords: Verpackungsabfall; Getrennte Sammlung; Verpackungsdesign; Produktrückstände; Packaging design; Packaging waste; Product residues; Separate waste collection

Optimizing the tunnel ventilation design related to respirable dust in tunnelling by using CFD - Wei, Ranzhu; Galler, Robert; Weiß, Christian (World Tunnel Congress 2024, 2024)
Keywords: Optimization tunnel ventilation; Dust movement; Tunnel construction; Numerical simulation

Scalable synthesis of biomass-derived three-dimensional hierarchical porous activated carbons for electrochemical energy storage and hydrogen physisorption - Selvaraj, Aravindha Raja; Kostoglou, Nikolaos; Rajendiran, Rajmohan; Cho, Inho; Rebholz, Claus; Chakravarthi, Nagarajan Deepan; Prabakar, Kandasamy (Journal of energy storage, 2024)
Pore structure properties such as specific surface area, pore volume, and pore size distribution are important considerations when using nanoporous carbons as electrochemical energy storage and H 2 storage materials. In this work, the Quenched Solid Density Functional Theory (QSDFT) analysis is employed to study the nanopore structure of hierarchical porous carbon (HPC) materials derived from bamboo chopsticks (BCS) by adopting a few-step chemical activation method. The effect of carbonization temperature (600–800 °C) and inorganic activator ratio on the surface chemistry and properties of HPC materials are investigated along with the way this influences the energy storage and H 2 storage performances. The as-prepared materials exhibit high surface area (1439–1940 m 2 g −1) and porosity, which is achieved even with a low KOH:BCS ratio. The supercapacitor (SC) HPC material processed at 800 °C and a KOH:BCS of 2:1, showed a good capacitive performance of 360 F g −1 at a current density of 0.5 A g −1 and exhibited a superior rate characteristic along with excellent electrochemical stability. A symmetrical SC reached a specific energy of over 75.3 Wh kg −1 and a specific power of 375 W kg −1 in an organic electrolyte. Furthermore, pouch cell type SC devices are fabricated to light LEDs. The hydrogen uptake of all the HPC samples is above 2 wt% (at 77 K and 1 bar) with the highest being 2.3 wt% for the sample processed at 700 °C due to its higher micropore volume. This study proposes a feasible low-cost method to convert waste biomass and exploit the desired hierarchical porous carbon material for multifunctional storage applications.
Publisher Copyright: © 2024 Elsevier Ltd
Keywords: Hierarchical porous carbons; Hydrogen storage; Pouch cell; QSDFT gas sorption analysis; Supercapacitor energy storage

A Review of Tailings Dam Safety Monitoring Guidelines and Systems - Zare, Masoud; Nasategay, Florida; Gomez, Jose A.; Moayedi Far, Arsham; Sattarvand, Javad (Minerals, 2024)
The awareness of tailings dam safety monitoring has widened due to the recent disasters caused by failures of such structures. The failure rate of tailings dams worldwide (i.e., the percentage of failed dams out of total) is estimated at 1.2%, compared to the 0.01% rate for traditional water dams. Most of the tailings dam monitoring guidelines suggest that the owner develops a robust surveillance program to detect possible indicators of potential failures. This paper presents a thorough review of major guidelines on tailings storage facility (TSF) monitoring and surveillance, the visual parameters to be monitored, as well as good practice in the development of monitoring systems. This paper reviews the recent literature with an emphasis on the development of monitoring systems utilizing sensors, unmanned aerial vehicles (UAVs), and satellite images that may be considered as supplementary guarantees against failure events.
Publisher Copyright: © 2024 by the authors.
Keywords: monitoring system; safety; stability; tailings dam

Experimental investigation and computational thermodynamics of the quaternary system Fe-C-Mn-S - Littringer, Robert (51st International Conference on Computer Coupling of Phase Diagrams and Thermochemistry (CALPHAD LI), 2024)
During the reduction of iron ores, substantial amounts of S, originating from the coke, dissolve in the molten iron. S poses several problems during the casting and processing of steels, such as hot tearing or surface defects, respectively. Residual amounts of S are typically bound by adding Mn to the steel to avoid the formation of low-melting phases. Mn is also an important alloying element for large variety of steel grades. To track the steel quality during the casting process, online quality prediction systems are currently under development in numerous steel plants. Thermodynamic data of the steel grade are combined with solidification calculations and kinetic models to describe the casting process as a function of the casting parameters, whereby the thermodynamic information is obtained from the CALPHAD approach.In the present work, experiments in the systems Fe-Mn and Fe-Mn-S with very low amount of C (~ 150 ppm) were performed using Differential Scanning Calorimetry (DSC) and Differential Thermal Analysis (DTA). The Fe-Mn-Clow phase diagram at high temperatures was experimentally reconstructed up to 40 mass pct. Mn. [1] Previous thermodynamic assessments [2,3] showed noticeable deviation from the measured peritectic phase equilibria, which required further investigation and re-optimization of the thermodynamic database. Hence, a CALPHAD-type thermodynamic modeling of the Fe-Mn and Fe-Mn-C system using FactSage thermochemical software [4] was performed to improve the prediction of solid/liquid phase equilibrium temperatures. For the liquid phase, the Modified Quasichemical Model (MQM) was used, solid solutions were described by the Compound Energy Formalism (CEF) and several compounds with constant composition were treated as stoichiometric. In the second part, the experimental and computational approach is combined and applied to the ternary Fe-Mn-S system, as shown exemplary in Figure 1 (a). Two isopleth sections of 0.5 and 2.0 mass pct. Mn with up to 0.3 mass pct. S were studied. The DSC technique enabled also to analyze the dissolution of manganese sulfides (Mn,Fe)S, as can be seen in Figure 1 (b), which was additionally in situ by high temperature laser scanning confocal microscopy (HT-LSCM). Hence, the proper evaluation of the DSC signals could be confirmed. Though a significant improvement was obtained for calculating the Fe-C-Mn system, the previous evaluation of the Fe-Mn-S system, which in this case was selected from the studies of Kang and coworkers [2,3], already led to excellent results.References:[1] Presoly, P., private communication, Montanuniversitaet Leoben, 2023[2] Y.-B. Kang, Critical evaluations and thermodynamic optimizations of the Mn–S and the Fe–Mn–S systems. Calphad, 34 (2010), 2, pp. 232–244.[3] M.-S. Kim and Y.-B. Kang, Thermodynamic Modeling of the Fe-Mn-C and the Fe-Mn-Al Systems Using the Modified Quasichemical Model for Liquid Phase. Journal of Phase Equilibria and Diffusion, 36 (2015), 5, pp. 453–470.[4] C.W. Bale et al., FactSage thermochemical software and databases, 2010–2016. Calphad, 54 (2016), pp. 35–53.

Hybrid data-driven thermodynamically-based temperature modeling of secondary steelmaking - Kavic, Daniel; Bernhard, Michael Christian; Rössler, Roman; Bernhard, Christian (51st International Conference on Computer Coupling of Phase Diagrams and Thermochemistry (CALPHAD LI), 2024)

Interplay between alloying and tramp element effects on temper embrittlement in bcc iron: DFT and thermodynamic insights - Reiners-Sakic, Amin; Schnitzer, Ronald; Holec, David (Acta materialia, 2024)
The details of the temper embrittlement mechanism in steels caused by impurities are unknown. Especially from an atomistic point of view, there are still open questions regarding their interactions with alloying elements such as Ni, Cr, and Mo. Therefore, we used density functional theory to investigate the segregation and co-segregation behavior and the resulting influence on the cohesion of three representative tilt grain boundaries in iron. The results are implemented in a multi-site and multi-component kinetic and thermodynamic model for grain boundary segregation, to gain insights into the temporal and final grain boundary coverage. Our results show that the segregation tendency of As, Sb, and Sn is stronger than that of the alloying elements and significantly mitigates the grain boundary cohesion. Depending on the GB type, interactions between Sb and Sn vary from negligible to strongly attractive, which increases the likelihood of co-segregation. The cohesion-weakening effect is further amplified when elements such as Sb, Sn, and As co-segregate, compared to their individual segregation. In contrast, the co-segregation of Ni and Cr does not significantly increase the enrichment of impurities at grain boundaries, and their impact on cohesion is found to be negligible. The ability of Mo to mitigate reversible temper embrittlement is primarily attributed to its cohesion-enhancing effect and its capability to repel tramp elements from GBs, rather than scavenging them within the bulk, as suggested by previous literature.

Multi-Material 3D Printing of Biobased Epoxy Resins - Bergoglio, Matteo; Rossegger, Elisabeth; Schlögl, Sandra; Griesser, Thomas; Waly, Christoph; Arbeiter, Florian; Sangermano, Marco (Polymers, 2024)
Additive manufacturing (AM) has revolutionised the manufacturing industry, offering versatile capabilities for creating complex geometries directly from a digital design. Among the various 3D printing methods for polymers, vat photopolymerisation combines photochemistry and 3D printing. Despite the fact that single-epoxy 3D printing has been explored, the fabrication of multi-material bioderived epoxy thermosets remains unexplored. This study introduces the feasibility and potential of multi-material 3D printing by means of a dual-vat Digital Light Processing (DLP) technology, focusing on bioderived epoxy resins such as ELO (epoxidized linseed oil) and DGEVA (vanillin alcohol diglycidyl ether). By integrating different materials with different mechanical properties into one sample, this approach enhances sustainability and offers versatility for different applications. Through experimental characterisation, including mechanical and thermal analysis, the study demonstrates the ability to produce structures composed of different materials with tailored mechanical properties and shapes that change on demand. The findings underscore the promising technology of dual-vat DLP technology applied to sustainable bioderived epoxy monomers, allowing sustainable material production and complex structure fabrication.
Publisher Copyright: © 2024 by the authors.
Keywords: 3D printing; biobased; epoxy thermosets; multi-materials; photopolymers

Experimental and thermodynamic evaluation of the Fe-Si system and application to the processing of silicon steels - Bernhard, Michael Christian; Presoly, Peter; Kavic, Daniel; Wi, Tae-Gyu; Park, Won-Bum; Rössler, Roman; Jungreithmeier, Alfred; Ilie, Sergiu; Bernhard, Christian; Kang, Youn-Bae (2024)

How DSC measurements and CALPHAD helps to avoid breakouts during the continuous casting of peritectic steels - Presoly, Peter; Bernhard, Michael Christian; Bernhard, Christian; Hahn, Susanne; Ilie, Sergiu (2024)
Keywords: DSC; peritectic; casting

Microstructural investigation of the undercooled austenite in the Fe-C - Jacob, Aurélie; Presoly, Peter; Gürtenhofer, Richard; Kozeschnik, Ernst; Povoden-Karadeniz, Erwin (2024)

Predictive Model for Catalytic Methane Pyrolysis - Pototschnig, Ulrich; Matas, Martin; Scheiblehner, David; Neuschitzer, David; Obenaus-Emler, Robert; Antrekowitsch, Helmut; Holec, David (Journal of physical chemistry C (C, Nanomaterials and interfaces), 2024)
Methane pyrolysis provides a scalable alternative to conventional hydrogen production methods, avoiding greenhouse gas emissions. However, high operating temperatures limit economic feasibility on an industrial scale. A major scientific goal is, therefore, to find a catalyst material that lowers operating temperatures, making methane pyrolysis economically viable. In this work, we derive a model that provides a qualitative comparison of possible catalyst materials. The model is based on calculations of adsorption energies using density functional theory. Thirty different elements were considered. Adsorption energies of intermediate molecules in the methane pyrolysis reaction correlate linearly with the adsorption energy of carbon. Moreover, the adsorption energy increases in magnitude with decreasing group number in the d-block of the periodic table. For a temperature range between 600 and 1200 K and a normalized partial pressure range for H 2 between 10 -1 and 10 -5, a total of 18 different materials were found to be optimal catalysts at least once. This indicates that catalyst selection and reactor operating conditions should be well-matched. The present work establishes the foundation for future large-scale studies of surfaces, alloy compositions, and material classes using machine learning algorithms.
Publisher Copyright: © 2024 The Authors. Published by American Chemical Society.

All van der Waals Semiconducting PtSe2 Field Effect Transistors with Low Contact Resistance Graphite Electrodes - Aslam, Muhammad Awais; Leitner, Simon; Tyagi, Shubham; Provias, Alexandros; Tkachuk, Vadym; Pavlica, Egon; Dienstleder, Martina; Knez, Daniel; Watanabe, Kenji; Taniguchi, Takashi; Yan, Dayu; Shi, Youguo; et al. (Nano Letters, 2024)
Contact resistance is a multifaceted challenge faced by the 2D materials community. Large Schottky barrier heights and gap-state pinning are active obstacles that require an integrated approach to achieve the development of high-performance electronic devices based on 2D materials. In this work, we present semiconducting PtSe2 field effect transistors with all-van-der-Waals electrode and dielectric interfaces. We use graphite contacts, which enable high ION/IOFF ratios up to 109 with currents above 100 μA μm-1 and mobilities of 50 cm2 V-1 s-1 at room temperature and over 400 cm2 V-1 s-1 at 10 K. The devices exhibit high stability with a maximum hysteresis width below 36 mV nm-1. The contact resistance at the graphite-PtSe2 interface is found to be below 700 Ω μm. Our results present PtSe2 as a promising candidate for the realization of high-performance 2D circuits built solely with 2D materials.
Publisher Copyright: © 2024 The Authors. Published by American Chemical Society
Keywords: contact resistance; graphene; graphite electrodes; Platinum diselenide; transistors

Improved conditions for the distributivity of the product for σ-algebras with respect to the intersection - Steinicke, Alexander; Rao, K.P.S. Bhaskara (Mathematica Slovaca, 2024)
We present a variety of refined conditions for σ-Algebras A (on a set X), F; G (on a set U) such that the distributivity equation (Formula Presented) The article generalizes the results in an article of Steinicke (2021) and includes a positive result for-Algebras generated by at most countable partitions, which was not covered before. We also present a proof that counterexamples may be constructed whenever X is uncountable and there exist two α-Algebras on X which are both countably separated, but their intersection is not. We present examples of such structures. In the last section, we extend Theorem 2 in Steinicke (2021) from analytic to the setting of Blackwell spaces.
Publisher Copyright: © 2024 Mathematical Institute Slovak Academy of Sciences.
Keywords: sigma-algebra; intersection of sigma-algebras; product sigma-algebras; counterexample for sigma-algebras; sigma-Algebra; intersection of sigma-Algebras; product sigma-Algebras; counterexample for sigma-algebras.

An Investigation on The Effects of Post-industrial Glass Fiber Flakes on the Properties of Recycled Polypropylene - Raguz, Ivan; Shahroodi, Zahra; Krempl, Nina; Arbeiter, Florian; Friesenbichler, Walter; Holzer, Clemens (PPS 2024: 39th International Conference of the Polymer Processing Society, 2024)

Applied Life Cycle Based Environmental Analysis - Feichtinger, Gerald; Schlar, Daniel; Mark, Daniel; Grabner, Christoph (Science 4 Technology @MUL, 2024)
Keywords: Environmental Assessment; Carbon Footprint; Data Analysis Software; Applications

Compaction behaviour of textile reinforcements - Bender, Marcel (Science 4 Technology @MUL, 2024)
Keywords: Composites; RTM; Compression test

Demonstration plant for hydrogen and carbon production via methane pyrolysis - Wibner, Stefan; Sprung, Andreas (Science 4 Technology @MUL, 2024)

Hydrogen uptake and embrittlement of steels under highest pressures - Eichinger, Matthias; Mori, Gregor Karl (Science 4 Technology @MUL, 2024)

Parameter Study for the Numerical Analysis of the Wire Arc Additive Manufacturing Process - Czipin, Marcel (2024)

Recycling of Paper Machine Clothing - Duretek, Ivica (Science 4 Technology @MUL, 2024)

Recycling of red mud from the aluminium industry - Wibner, Stefan (Science 4 Technology @MUL, 2024)

Additive Manufacturing Material Extrusion @ Institute of Polymer Processing - Schuschnigg, Stephan (Science 4 Technology @MUL, 2024)

Additive Manufacturing of Aluminium by Material Extrusion MEX - Momeni, Vahid (Science 4 Technology @MUL, 2024)

Chemitecture: Dielectric Elastomer Actuator (DEA) produced by Material Extrusion (MEX) - Raguz, Ivan (Science 4 Technology @MUL, 2024)

Closing the circle of polyolefin packaging - Krempl, Nina (Science 4 Technology @ MUL, 2024)

Extrusion and Additive Manufacturing@ Institute of Polymer Processing - Schuschnigg, Stephan (Science 4 Technology @MUL, 2024)

LightCycle: Upcycling of regenerates with a new Injection Moulding Compounder (IMC) - Shahroodi, Zahra (Science 4 Technology @MUL, 2024)

Material Data Determination @ Institute of Polymer Processing - Duretek, Ivica (Science 4 Technology @MUL, 2024)

Recycling Biobased Plastics - Main, Priyanka (Science 4 Technology @MUL, 2024)

Successful Integration of Circular Economy Concepts for the Extractive Industry - Murphy, Mariaelena; Obenaus-Emler, Robert; Pacher, Corina (Springer, 2024)
This chapter delves into the area of transversal skill development within the engineering domain, with a specific focus on the Extractive Mining Industry. It commences by underlining the importance of the Sustainable Development Goals (SDGs), notably focusing on SDG12, Responsible Consumption and Production. The chapter elucidates the pivotal role SDG12 plays in fostering sustainable consumption and production patterns, offering a contextual backdrop to the subsequent exploration of transversal skills within the extractive sector. A pivotal theme within the context of this chapter is the profound impact of the extractive industry on the environment. Recognising the imperative to address environmental concerns, the chapter introduces the principles of the Circular Economy as a strategic avenue for instilling sustainability within the industry. It ventures into the conceptual landscape of circular economy principles and their potential applications in mitigating environmental impact, thereby paving the way for a more sustainable extractive sector. Central to the discourse is the integration of circular economy concepts into the extractive industry, emphasising the transformative potential it holds. The narrative underscores the need for a paradigm shift in industry practices, advocating for a holistic approach that not only meets current demands but also ensures the preservation of resources for future generations. Moving beyond environmental considerations, the chapter critically examines the concept of competence and its symbiotic relationship with transversal skills. Providing a solid theoretical foundation, it delineates the intrinsic value of cultivating competence profiles within the extractive industry. By elucidating the nexus between competence and transversal skills, the chapter advocates for a comprehensive approach to professional development that transcends traditional skill sets. In a culminating synthesis, the chapter presents a purpose-designed competence profile tailored to the extractive industry. This profile encapsulates the transversal skills imperative for professionals to navigate the dynamic landscape of the sector successfully. Through this multifaceted exploration, readers are equipped with a nuanced and comprehensive understanding of the fundamental components essential for cultivating transversal skills indispensable for success in the extractive industry. The chapter serves as a leading light for industry practitioners, educators, and policymakers alike, propelling them towards a future where sustainable practices and transversal skills converge for a resilient and competitive extractive sector.
Keywords: Circular Economy; Extractive Industry

Wintersport Ressource Efficiency and Improved Circular Economy - Krempl, Nina (Science 4 Technology @MUL, 2024)

Beyond Hot Air. - Saxinger, Gertrude; Auer, Marlene; Batterbury, Simon P.; Eyselein, Gabriel; Jensen, Ellen Marie; Kowasch, Matthias; Melcher, Frank; Wilson, Emma (Mining the connections, 2024)

Multi-proxy record of the Austrian Upper Triassic Polzberg Konservat-Lagerstätte in light of the Carnian Pluvial Episode - Lukeneder, Alexander; Lukeneder, Petra; Sachsenhofer, Reinhard; Roghi, Guido; Rigo, Manuel (Scientific Reports, 2024)
We present a multi-proxy investigation of a lower Carnian basinal succession from Polzberg in the Northern Calcareous Alps (Lower Austria). A section comprising a unique Konservat-Lagerstätte was studied based on bio- and chemostratigraphy along with geophysical methods, yielding a detailed and robust stratigraphic calibration of the Polzberg succession. The Polzberg section revealed the paleoceanographic history and helped to identify a global climatic reversal, the Carnian Pluvial Episode. The age of the Upper Triassic Reingraben formation in the Northern Calcareous Alps is refined as the Austrotrachyceras austriacum Zone within the lower Carnian (Julian 2). Ammonoids and conodonts provide a detailed biostratigraphic subdivision that serves as a basis for analyses of the faunal distribution and the paleoenvironmental evolution of the Upper Triassic Reifling Basin. The succession includes lithological and facies changes similar to those of coeval units in the Tethys. The Carnian was characterized by a weak (~ 1‰) positive δ13C trend, punctuated by a negative shift during the lower Carnian corresponding to the initiation of the Carnian Pluvial Episode, a period representing the onset of early/late Carnian transitional global greenhouse conditions. Organic maturity parameters and the conodont alteration index (CAI) show that the thermal overprint of the Polzberg section is low. Biomarker proxies suggest that the organic matter of the uppermost Göstling formation is a mixture of marine and terrestrial material deposited in a dysoxic environment. Within the overlaying Reingraben formation, the amount of marine biomass decreased gradually upwards. Oxygen-depleted conditions, probably due to water-column stratification, continued during deposition of the Reingraben formation. Bacterial sulfate reduction played a major role in organic matter degradation.
Publisher Copyright: © The Author(s) 2024.

Student perspectives on the Wolfsberg lithium project in Austria - Kowasch, Matthias; Baumann, Christoph; Batterbury, Simon P.; Melcher, Frank; Saxinger, Gertrude; Wilson, Emma (Mining the connections, 2024)

Time for green extractivism in the EU? - Kowasch, Matthias; Melcher, Frank; Auer, Marlene; Batterbury, Simon P.; Eyselein, Gabriel; Lesser, Pamela; Saxinger, Gertrude; Wilson, Emma (Mining the connections, 2024)

Green and blue infrastructure as model system for emissions of technology-critical elements - Trimmel, Simone; Spörl, Philipp; Haluza, Daniela; Lashin, Nagi; Meisel, Thomas C.; Pitha, Ulrike; Prohaska, Thomas; Puschenreiter, Markus; Rückert, Elmar; Spangl, Bernhard; Wiedenhofer, Dominik; Irrgeher, Johanna (Science of the total environment, 2024)
Over the recent decades, technological advancements have led to a rise in the use of so-called technology-critical elements (TCEs). Environmental monitoring of TCEs forms the base to assess whether this leads to increased anthropogenic release and to public health implications. This study employs an exploratory approach to investigate the distribution of the TCEs Li, Be, V, Ga, Ge, Nb, Sb, Te, Ta, Tl, Bi and the REYs (rare-earth elements including yttrium) in urban aerosol in the city of Vienna, Austria.Leaf samples (n = 292) from 8 plant species and two green facades and water samples (n = 18) from the Wienfluss river were examined using inductively coupled plasma tandem mass spectrometry (ICP-MS/MS). Surface dust contributions were assessed by washing one replicate of each leaf sample and analysing the washing water (n = 146). The impacts of sampling month, plant species and storey level on elemental distribution were assessed by statistical tools and generative deep neural network modelling. Higher TCE levels, including Li, V, Ga, Ge, Tl, Bi, and the REYs, were found in the winter months, likely due to the use of de-icing materials and fossil fuel combustion. A. millefolium and S. heufleriana displayed the highest levels of Li and Ge, respectively. In addition, increased elemental accumulation at lower storeys was observed, including Be, Sb, Bi and the REYs, indicating greater atmospheric dust deposition and recirculation closer to ground level.The results suggest a broad association of TCE levels with urban dust. This study enhances the current understanding of TCE distribution in urban settings and underscores the importance of their inclusion in pollution monitoring. It highlights the complex interplay of human activities, urban infrastructure, and environmental factors, offering valuable insights for managing urban environmental health risks and underlining the need for comprehensive urban ecosystem studies.
Publisher Copyright: © 2024 The Authors
Keywords: ICP-MS/MS; REEs; TCEs; Urban aerosol; Urban dust; Multielement analysis; Urban greening; Air pollution; Environmental monitoring; Rare-earth elements; Emerging pollutants

Small-angle neutron scattering reveals high-density adsorbed hydrogen in carbon micropores at low pressures and supercritical temperature - Stock, Sebastian; Seyffertitz, Malina; Kostoglou, Nikolaos; Rauscher, Max; Demé, Bruno; Mitterer, Christian; Paris, Oskar (9th International Workshop on Characterization of Porous Materials: From Angstroms to Millimeters, 2024)

Bio-Based Backbone for Highly Reactive Metal Alloys Feedstocks for MEX - Holzer, Clemens; Momeni, Vahid; Pöhle, Georg; Riecker, Sebastian; Schuschnigg, Stephan; Kukla, Christian (39th International Conference of Polymer Processing Society, 2024)
Keywords: Additive Manufacturing; Aluminium alloy; Material Extrusion

Magnetospheric Venus Space Explorers (MVSE) mission: A proposal for understanding the dynamics of induced magnetospheres - Albers, Roland; Andrews, Henrik; Boccacci, Gabriele; Castro Pires, Vasco Daniel; Laddha, Sunny; Lundén, Ville; Maraqten, Nadim; Matias, João; Krämer, Eva; Schulz, Leonard; Palanca, Inés Terraza; Teubenbacher, Daniel; et al. (Acta astronautica, 2024)
Induced magnetospheres form around planetary bodies with atmospheres through the interaction of the solar wind with their ionosphere. Induced magnetospheres are highly dependent on the solar wind conditions and have only been studied with single spacecraft missions in the past. Without simultaneous measurements of solar wind variations and phenomena in the magnetosphere, establishing a link between both can only be done indirectly, using statistics over a large set of measurements. This gap in knowledge could be addressed by a multi-spacecraft plasma mission, optimized for studying global spatial and temporal variations in the magnetospheric system around Venus, which hosts the most prominent example of an induced magnetosphere in our solar system. The MVSE mission comprises four satellites, of which three are identical scientific spacecraft, carrying the same suite of instruments probing different regions of the induced magnetosphere and the solar wind simultaneously. The fourth spacecraft is the transfer vehicle which acts as a relay satellite for communications at Venus. In this way, changes in the solar wind conditions and extreme solar events can be observed, and their effects can be quantified as they propagate through the Venusian induced magnetosphere. Additionally, energy transfer in the Venusian induced magnetosphere can be investigated. The scientific payload includes instrumentation to measure the magnetic field, electric field, and ion–electron velocity distributions. This study presents the scientific motivation for the mission as well as requirements and the resulting mission design. Concretely, a mission timeline along with a complete spacecraft design, including mass, power, communication, propulsion and thermal budgets are given. This mission was initially conceived at the Alpbach Summer School 2022 and refined during a week-long study at ESA’s Concurrent Design Facility in Redu, Belgium.
Publisher Copyright: © 2024 The Author(s)
Keywords: Induced magnetosphere; Mission concept; Multi-spacecraft mission; Space Plasma Physics; Venus

Simulation of the Melting Region in Additive Manufacturing Material Extrusion Dies for Highly Filled Feedstocks - Schuschnigg, Stephan; Hentschel, Lukas; Holzer, Clemens (39th International Conference of Polymer Processing Society, 2024)
Material Extrusion (MEX) is a simpler AM technology, aﬀordable also for home use. There are diﬀerent designs of the dies, and we investigated two designs (MK10 and E3D), with each two variants. We assumed that the forces of the ﬁlament are related to the melt pool and not on the friction. For the investigation we used Ansys Polyﬂow and constructed the nozzle assemblies. We used a highly ﬁlled feedstock (55 vol.% 316L steel powder in a polymeric binder) and measured the temperature and shear dependent viscosity and the other material data. The region where we assume solid ﬁlament has a temperature dependent slip condition as a boundary, to obtain a smoother transition between the solid area and the melting region. The thermal conditions are diﬀerent for each variant. The MK10 variants are an all-metal construction and a PTFE tube inside. The E3D version has a shorter or longer PTFE insert. The calculations showed interesting results, especially for the temperatures, whereas the pressures were not satisfactory as the temperature dependent viscosity model had to be adapted to calculate lower temperatures. The temperature of the all-metal design showed that, at low extrusion speeds, the melt pool was approximately 15 mm, while in the PTFE version it was only 10 mm. At higher speeds the temperature in the all-metal does not change much, but in the PTFE the desired temperature cannot be reached. In the E3D version we can see similar results between the long and short PTFE tubes. One thing is the high thermal conductivity of the feedstock at 0.98 W/(m·K), in contrast to polymers having about 0.2 W/(m·K). The MEX printer is set at increasing speeds until the gears can be heard trying to push the ﬁlament, but the solid ﬁlament is blocked in the die because there is not enough heaHng capacity. This can be heard during trials to achieve maximum prinHng speeds. The next steps are measurements with a die equipped with a load cell between the die and the gear.
Keywords: Feedstocks; Simulation Model; Additive Manufacturing

Unlocking the Potential of Recycled Polypropylene in Food Packaging - Krempl, Nina; Holzer, Clemens; Pinter, Elisabeth; Frühwirth, Matthias; Shahroodi, Zahra; Jahn, Elisabeth; Aschermayer, Florian; Gabriel, Viktoria Helene (PPS 2024: 39th International Conference of the Polymer Processing Society, 2024)

Utilization of Charcoal Obtained from Woody Biomass in Metallurgical Processes Based on Solid–Gas Reactions - Dornig, Christian; Hanke, Gustav; Antrekowitsch, Jürgen (Metals, 2024)
The high demand for carbon-based products within pyrometallurgy is placing the industry in an increasingly challenging position to meet stringent requirements. To transition away from fossil carbon carriers, biochar emerges as a sustainable and CO2-neutral alternative, presenting a viable solution without necessitating fundamental adjustments to plant technology, unlike hydrogen as an alternative reducing agent. Prior investigations have underscored the potential of woody biomass pyrolysis products for CO2-neutral metallurgy. Nonetheless, it is imperative to recognize that biochar must meet distinct requirements across various metallurgical processes. This paper conducts a comparative analysis between biochar and petroleum coke using thermogravimetric analyses, surface measurements, reactivity assessments, and scanning electron microscopy. Furthermore, the performance in a furnace for simulating the Waelz process, specifically regarding ZnO reduction, is scrutinized. The results illustrate the optical differences between petroleum coke and biochar and the significantly higher reactivity and specific surface area of biochar. When used in solid–gas reactors, it is observed that due to its high reactivity, biochar reacts more vigorously and carbon is completely consumed. However, during the reduction of ZnO, only minor differences were monitored, making biochar comparable to petroleum coke. Therefore, under certain constraints, biochar can be considered a potential substitute for metallurgical solid–gas reactions.
Keywords: Charcoal; Biomass; Secondary Meatllurgy

Empowering the Regional Network of Experts for Disaster Risk Management in the Western Balkans by the Scientific-Professional Society for Disaster Risk Management - Cvetković, Vladimir M. (2024)

Recovery of plastic packaging from mixed municipal solid waste. A case study from Austria - Blasenbauer, Dominik; Lipp, Anna-Maria; Fellner, Johann; Tischberger-Aldrian, Alexia; Stipanovic, Hana; Lederer, Jakob (Waste management, 2024)
Austria must recycle more packaging materials. Especially for plastic packaging waste, significant increases are necessary to reach the EU recycling targets for 2025 and 2030. In addition to improving separate collection and introducing a deposit system for specific fractions, the share of plastic packaging in mixed municipal solid waste (MSW) could be utilized.In Austria, about 1.8 million tonnes of mixed MSW are generated. This includes about 110,000 t/a of plastic packaging waste. Most of the mixed MSW (94 %) is sent directly or via residues from pre-treatment, such as mechanical–biological treatment or waste sorting, to waste incineration. While materials such as glass and metals can also be recovered from the bottom ash, combustible materials such as plastics must be recovered before incineration.This work aims to evaluate the recovery potential of plastic packaging waste in mixed MSW with automated waste sorting. For this purpose, two of the largest Austrian waste sorting plants, with a total annual throughput of about 280,000 t/a, were investigated. The investigation included regular sampling of selected output streams and sorting analysis.The results show that the theoretical recovery potential of plastic packaging from these two plants is 6,500 t/a on average. An extrapolation to Austria results in a potential of about 83,000 t/a. If losses due to further treatment, such as sorting and recycling, are considered, about 30,000 t/a of recyclate could be returned to plastic production. This would correspond to an increase in plastic packaging recycling rate from 25 % to 35 %.
Publisher Copyright: © 2024 The Author(s)
Keywords: Municipal solid waste; Plastic packaging waste; Recycling; Circular Economy; Material revovery facility; Automated waste sorting; Automated waste sorting; Circular economy; Material recovery facility; Municipal solid waste; Plastic packaging waste; Recycling

Increasing the melt viscosity of post-consumer recycled polypropylene via E-Beam techniques - Krämer, Johannes; Guedes de la Cruz, Gema del Carmen; Kern, Wolfgang; Roitner, Julia; Witschnigg, Andreas; Rittmannsberger, Franz; Schnetzinger, Karl (Radiation physics and chemistry, 2024)
Polypropylene from post-consumer waste (PCR-PP) was melt-mixed with a di- and trifunctional molecule and treated with E-Beam radiation, to increase its viscosity and melt strength by long-chain branching and partial crosslinking. After adding diallyl- or triallylisocyanurate to polypropylene by melt compounding, the compounds were subjected to e-beam irradiation with doses between 10 and 60 kGy. Two types of polypropylene recyclates were investigated, both differing in the content of polyethylene. The samples were investigated with respect to the formation of microgels (gel content), rheological behaviour, melt flow rate and their mechanical properties. It was found that low irradiation doses in the range from 10 to 30 kGy reduce the melt flow rate significantly, and increase the tensile properties of PCR-PP while the gel content stays low. The results are discussed with respect to the amount of polyethylene impurities, and the processing behaviour of polypropylene, aiming at technically feasible recycling strategies for polyolefin recyclates.
Publisher Copyright: © 2024 The Authors
Keywords: Electron beam techniques; Melt flow rate; Polypropylene recycling; Recyclate quality

Seismic Hazard Resilience in Montenegro: A Comprehensive Qualitative Analysis of Local Preparedness and Response Mechanisms - Cvetković, Vladimir M.; Grozdanić, Goran; Milanović, Miško; Marković, Slobodan; Lukić, Tin (2024)

In-Depth Analysis of Disaster (Risk) Management System in Serbia: A Critical Examination of Systemic Strengths and Weaknesses - Cvetković, Vladimir M. (2024)

Multimethod cross-sectional characterization approaching the limits of diamond monophase multilayers - Meindlhumer, Michael; Grau, Jakob; Sternschulte, Hadwig; Halahovets, Yuriy; Siffalovic, Peter; Burghammer, Manfred; Steinmüller-Nethl, Doris; Keckes, Jozef (Materials characterization, 2024)
Chemical vapour deposited diamond draws significant scientific interest due to its wide range of mechanical and functional properties, which can be easily tuned by the applied deposition conditions. Here, hot filament chemical vapour deposition was used to synthesize four monophase multilayer diamond thin films with individual layer thickness down to ∼ 300 nm. Extensive structural characterization by scanning electron microscopy and Raman spectroscopy on the cross-section confirmed the different diamond morphologies originating from the different applied process parameters of the individual sublayers, where Raman spectroscopy could give a clear distinction between nano- and microcrystalline diamond down to a layer thickness of ∼ 1 μm. Cross-sectional X-ray nanodiffraction identified exclusively the diamond crystal structure throughout the cross-section of the multilayered diamond thin films. Cross-sectional phase and FWHM analysis allowed to discriminate between the diamond morphologies down to ∼ 500 nm, thus identifying the limitations of monophase diamond multilayers. While the microcrystalline diamond sublayers all exhibit pronounced structural gradients expressed in (i) increasing intensity of the 111 Debye-Scherrer ring, (ii) ⟨110⟩ fibre texture, and periodic variations of (iii) grain size and (iv) residual stress, the nanocrystalline diamond sublayers showed no pronounced cross-sectional variations. In summary, the experimental results provide insights into the cross-sectional evolution of microstructure and residual stress and the limitations of monophase multilayered diamond thin films.
Keywords: Cross-sectional X-ray nanodiffraction; Hot-filament chemical vapour deposition; Raman spectroscopy; diamond multilayers

Constraining the stress field and its variability at the BedrettoLab: Elaborated hydraulic fracture trace analysis - Bröker, Kai; Ma, Xiaodong; Zhang, Shihuai; Doonechaly, Nima Gholizadeh; Hertrich, Marian; Klee, Gerd; Greenwood, Andrew; Caspari, Eva; Giardini, Domenico (International Journal of Rock Mechanics and Mining Sciences, 2024)
The measurement of the stress field and its natural heterogeneity is a common challenge in the field of geophysics and underground engineering. This study presents findings from an extensive mini-frac campaign conducted at the Bedretto Underground Laboratory (BedrettoLab) in the Swiss Alps. Six dedicated stress measurement boreholes, spanning 500 m along the Bedretto Tunnel, were utilized to prepare for meso-scale hydraulic stimulation experiments in a granitic rock volume. A detailed analysis of the induced hydraulicfracture trace morphology was carried out using acoustic televiewer logging data, with an interpretation based on the local geological context. The results show that the far field orientation of the maximum horizontal stress (𝑆Hmax) is on average N112°E and the overburden stress can be assumed to be a principal stress direction. However, the en-echelon shape of the observed hydraulic fracture traces suggests that there is a slight inclination of the greatest principal stress away from the vertical stress direction. The mini-frac testintervals along boreholes inside the enlarged niche of the BedrettoLab indicate a counterclockwise rotated horizontal stress by up to 37° and potentially stronger inclination of the greatest principal stress from the vertical stress direction. The most likely causes of this stress field rotation, along with a considerably larger scatter in stress magnitudes, appear to be the larger laboratory niche dimensions compared to the tunnel and the presence of natural fractures that are preferentially oriented for slip in the far field stress state. Althoughthe uncertainties and variability of the stress field around the BedrettoLab are not yet fully understood, our results are useful for strategic planning and design of meso-scale stimulation experiments in the rock volume. Furthermore, our detailed analysis procedure contributes to advancing the understanding of mini-frac tests in similar geological settings.
Publisher Copyright: © 2024 The Authors
Keywords: In situ stress field; Hydraulic fracture traces; Natural fractures; Underground research; laboratory; Fractured crystalline rock; Bedretto underground; laboratory for; geoenergies and; geosciences; Underground research laboratory; Bedretto underground laboratory for geoenergies and geosciences

Raman Spectroscopy of carbonaceous material thermometry in the Carnic Alps (Austria, Italy) - Rantitsch, Gerd (Austrian journal of earth sciences, 2024)
The Carnic Alps (eastern Southern Alps) provide a classical area to study polyphase very-low- to low-grade metamorphism within the Variscan belt of Europe. Temperature indicators collected during the past three decades map the general metamorphic structure of a mountain chain affected by three major tectonic events (Variscan and Alpine thrusting, Oligocene transpression). Thermometric data obtained by Raman Spectroscopy of carbonaceous material (RSCM) described in this study extend the already published database, provide a map of metamorphic isotherms, and are interpreted in the view of current tectonic concepts. The RSCM temperatures of this study describe a gradient between ca. 460 °C in the tectonically deepest segments, bordered by the Periadriatic Fault System, and temperatures of ca. 200 °C in Permian-Triassic boundary strata of the Gartnerkofel-1 core. Mapped isotherms indicate three domains with different thermal histories, characterized by Variscan imbrication of an accretionary wedge, Permo-Mesozoic burial, and Oligocene contact metamorphism.
Publisher Copyright: © 2024 Walter de Gruyter GmbH. All rights reserved.
Keywords: Carnic Alps; Metamorphism; Raman Spectroscopy of carbonaceous material; Southern Alps

Cu-doped perovskite-type oxides - Berger, Tobias; Drexler, Hedda; Ruh, Thomas; Lindenthal, Lorenz; Schrenk, Florian; Bock, Johannes; Rameshan, Raffael; Föttinger, Karin; Irrgeher, Johanna; Rameshan, Christoph (Catalysis today, 2024)
Perovskite-type oxides have gained significant attention in the scientific community due to their unique properties and potential applications. Their ability to exsolve reducible B-site cations (e.g. Co, Ni, Cu) combined with their flexibility regarding A-site and B-site composition allows for the tailoring of novel catalytic materials. This study focuses on B-site doped perovskite-type oxides with a general formula of Nd0.6Ca0.4Fe1-xCuxO3 and Pr0.6Ca0.4Fe1-xCuxO3 (x = 0.0, 0.03, 0.05, 0.10) for potential use as a catalyst for Methanol Steam Reforming via the exsolution of catalytically active Cu nanoparticles. The atomic and electronic structure, morphology, and exsolution behaviour of these materials were investigated experimentally and with density functional theory, with a specific emphasis on the impact of B-site doping with varying Cu content as well as choice of A-site element. Both parameters influenced the crystal structure, surface area, and morphology of the materials. The exsolution behaviour of the materials was observed using in-situ XRD at DESY beamline P02.1 at PETRA III, with nanoparticles forming after reductive treatments on the host oxide surface. The quantity and size of the nanoparticles were found to be adjustable by selecting the A-site ion, doping content at the B-site, and the choice of reducing agent. Materials with higher Cu content on the B-site exhibited facilitated exsolution. Furthermore, exsolution was promoted with Nd as the A-site element compared to Pr. In conclusion, the controlled exsolution of Cu nanoparticles introduces Cu-doped perovskite-type oxides as promising candidates for developing novel catalytic systems. The findings underscore the importance of fine-tuning the oxide composition (A-site element, amount of B-site dopant) to achieve tailored exsolution of nanoparticles, which is crucial for rational material design. By leveraging this knowledge, catalysts with finely tuned properties can be created for specific applications and operational environments.
Publisher Copyright: © 2024 The Authors
Keywords: DFT; Exsolution; In-situ XRD; Perovskite; Synchrotron

Effect of mechanical recycling on short glass fibre reinforced polyamide 6,6 from post-industrial waste - Salvi, A.; Lucyshyn, T.; Marano, C.; Ostrowska, M.; Vangosa, F. Briatico; Dotelli, G.; Holzer, C. (AIP Conference Proceedings, 2024)
Publisher Copyright: © 2024 American Institute of Physics Inc.. All rights reserved.

Multi-Material Implant Structures with Medical-Grade Polyurethane via Additive Manufacturing - Hentschel, Lukas; Petersmann, Sandra; Gradischar, Andreas; Lebschy, Carola; Lindenmann, Jörg; Smolle-Juettner, Freyja; Gonzalez-Gutierrez, Joamin; Dias, Aylvin; Kynast, Frank; Hammer, Niels; Schäfer, Ute; Holzer, Clemens (AIP Conference Proceedings, 2024)
Publisher Copyright: © 2024 American Institute of Physics Inc.. All rights reserved.

Thermodynamic Information and Evaporation Mechanism of Fe-M-C-S (M = As, Cu, Pb, Sb, Sn) Alloys for Controlling Tramp Elements in Steel - Park, Won-Bum; Bernhard, Michael Christian; Jung, Chanumul; Kang, Youn-Bae (2024)

Microstructure Evolution and Mechanical Properties at Ambient and Elevated Temperatures of in-situ TiB2/2219Al Matrix Composites During Cold Rolling - Li, Linwei; Zhou, Donghu; Wei, Chengbin; Han, Zhenhao; LI, Jiehua; Kang, Huijun; Guo, Enyu; Zhang, Yubo; Chen, Zongning; Wang, Tongmin (Metals and materials international, 2024)
Cold rolling is one of the feasible and effective methods for regulating the microstructure and enhancing the mechanical properties of metallic materials. However, the cold rolling of particulate-reinforced aluminum matrix composites has been rarely studied comprehensively and systematically due to their limited plasticity. In this study, in-situ TiB 2/2219Al matrix composites with a comparable ductility to 2219Al matrix were prepared and subjected to T3 treatment, which includes solution treatment, cold rolling, and natural ageing, with varying degrees of rolling reduction. The effects of cold rolling on the dislocation multiplication, grain and texture evolution, precipitation behavior, and mechanical properties were comprehensively investigated and discussed. The results reveal that both total dislocation density and geometrically necessary dislocation density increase with increasing rolling reduction. The average grain size progressively decreases under the joint influence of gradual growth of large grains and increase of small grains. Besides, rolling deformation changes the ageing behavior of composites, resulting in a decrease in precipitation temperature for both θ″ and θ′ phases. Under a large deformation, these phases precipitate at room temperature. Moreover, the types and proportions of textures undergoes a distinct evolution during deformation, with S, Copper and Brass textures being predominantly observed in the composite subjected to a 60% rolling reduction. Additionally, the increase in deformation results in an enhanced hardness and strength at both room temperature and 373 K. However, the strength initially increases but subsequently decreases at 573 K, and the composite with a 20% rolling reduction exhibits the highest strength at 573 K. Graphical Abstract: (Figure presented.).
Publisher Copyright: © The Author(s) under exclusive licence to The Korean Institute of Metals and Materials 2024.
Keywords: Cold rolling; Mechanical property; Microstructure evolution; Precipitation behavior; Texture evolution; TiB /2219Al matrix composite

Morphological structure and mechanical properties of a nucleated Polyoxymethylene (POM) homopolymer resin processed under conventional injection molding conditions - Schrank, Theresia; Ramoa, Bruno; Feuchter, Michael; Pinter, Gerald; Pantani, Roberto; Berer, Michael (Polymer Testing, 2024)
When injection molding semi-crystalline polymers, it is known that the resulting morphological and mechanical properties are strongly dependent on the processing conditions. Selectively influencing the performance of the final part as early as during processing is of great interest for industrial applications. To investigate the processing-structure-property correlation for a POM hompolymer resin, tensile specimens were manufactured under conventional injection molding conditions following a Design of Experimets (DoE). Morphological characterization was carried out by microscopy and X-ray measurements. Crystallinity was also measured by differential scanning calorimetry (DSC). Additionally, the (fracture) mechanical behaviour of the samples was assessed. Influences of the processing parameters on the crystalline structure and orientations within the material were identified. Furthermore, tensile tests were found to be sensitive to changes in morphology and processing, whereas the fracture behaviour did not change significantly despite the structural changes within the samples.
Publisher Copyright: © 2024 The Authors

Simulation of Secondary Metallurgical Processes by Using Computational Thermodynamics and Comprehensive Statistical Learning Methods - Kavic, Daniel; Bernhard, Michael Christian; Rössler, Roman; Bernhard, Christian (2024)

Corrigendum to “From abandoned mines to carbon sinks: Assessing the CO2 storage capacity of Austrian low-rank coal deposits” [International Journal of Coal Geology 286 (2024) 1–13/104495] - Safaei Farouji , Majid; Misch, David; Sachsenhofer, Reinhard F.; Rauscher, Max; Kostoglou, Nikolaos (International journal of coal geology, 2024)
This study represents the first assessment of CO 2 storage potential in Austrian coal seams. Coal samples were taken from Fohnsdorf and Leoben abandoned coal mines, with particular emphasis on the Fohnsdorf coal since Leoben coal reserves were largely mined during previous coal production. Several methods were used to compare coal characteristics, including Rock-Eval pyrolysis (RE), organic petrography, and low-pressure N 2 and CO 2 sorption measurements. Both Fohnsdorf and Leoben coal samples show low sulfur and ash yields, as well as correspondingly high total organic carbon (TOC) contents. The pyrolysis T max and vitrinite reflectance values agree with a low coal rank for both sites. According to the N 2 adsorption measurements at 77 K, low-lying mire coals from Fohnsdorf show a higher BET-specific surface area (BET-SSA) and BJH pore volume compared to raised-mire coals from Leoben. However, sapropelic shales and high-ash coals from Leoben show the highest BET-SSA and BJH pore volumes of all investigated samples and considerably exceed the N 2 adsorption volumes of pure coals from both locations (N 2 uptake up to 16 cm 3/g; avg. for all samples 5.4 cm 3/g). In contrast, the mean adsorbed CO 2 uptake measured at 273 K and ∼ 1 bar followed the order of Fohnsdorf low-lying mire coals > Leoben raised-mire coals > Leoben sapropelic coals and shales, ranging at ∼0.8 mmol/g, ∼0.7 mmol/g, and ∼ 0.2 mmol/g, respectively. This shows that BET-SSA and BJH equations did not allow for adequate estimation of CO 2 adsorption capacity trends in the investigated sample set. Furthermore, based on the existence of a hysteresis loop between CO 2 adsorption and desorption branches for all investigated samples, the occurrence of weak chemisorption phenomena during CO 2 adsorption is indicated. This effect helps to increase CO 2 uptake and storage safety since the chemisorption process is not fully reversible upon pressure decrease. Ultimately, the theoretical CO 2 sequestration potential of the remaining unmined Fohnsdorf coal reserves was estimated at 4.65 million tons, with an additional potential for enhanced coal bed methane production due to the gas-rich nature of Fohnsdorf coals with an estimated 1.2 billion m 3 of CH 4 in place.
Publisher Copyright: © 2024 The Authors
Keywords: CO adsorption; Coal; Fohnsdorf; Leoben; Nanopores; Nitrogen adsorption

High-cellulose content of in-situ Miocene fossil tree stumps and trunks from Lusatia lignite mining district, Federal Republic of Germany - Kus, Jolanta; Dolezych, M.; Schneider, Wolfgang; Hower, James C.; Hofmann, Timothy; Visiné Rajczi, E.; Bidló, A.; Bolodár-Varga, B.; Sachsenhofer, Reinhard F.; Bechtel, Achim; Stojanović, Ksenija; Životić, Dragana; et al. (International journal of coal geology, 2024)
Second Miocene Seam Complex (2nd MFK; germ.: 2. Miozäner Flözkomplex) holds many in-situ, not permineralised fossil tree stumps and trunks with high-cellulose contents. The state of preservation of a set of in-situ fossil trees (Taxodioxylon cryptomerioides, Sciadopityoxylon wettsteinii, and Quasisequoioxylon piskowitzense) collected from three open-cast mines (Welzow-Süd, Meuro, and Piskowitz) in Lusatia lignite mining district, Federal Republic of Germany was investigated using a multi-method research schema. Examination of preservation state of thermally immature fossil woods revealed: (1) well-preserved (non-deformed, non-degraded, and non-flattened) textinite, (2) a retained structural integrity represented by multilayered (multi-zoned) cells with primary, secondary cell wall, and middle lamella, (3) microfracturing restricted to secondary walls only, (4) preservation of polyphenolic parenchyma cells (PP cells), (5) excellent preservation of pits in ray tracheids, (6) presence of amorphous silica (opal-A) coating, and (7) crystalline silica (opal-CT) fillings of small-bladed crystals. Thermogravimetric analysis results showed dissimilar gelification status of fossil samples, supporting chlorite holocellulose assay results. The latter indicated anomalously high-cellulose values (15.6–37.6% holocellulose). The micro-FTIR data obtained revealed an excellent preservation of both hemicellulose (bands at 1740 and 1245 cm−1) and cellulose (bands at 1110 and 1040 cm−1). Micro-FTIR spectrometry indicated lack of preferential hydrolytic removal of polysaccharides in examined samples. Biomarker patterns in lignite revealed forested and prevailing reed-mire vegetation. The results indicated lower contribution of Cupressaceae and emergent macrophyta to precursor organic matter of Welzow-Süd in comparison to Piskowitz lignite. Piskowitz lignite formed in permanent mire with stable water table under reducing, mesotrophic conditions. In contrast, more pronounced water level fluctuations (reducing to slightly oxic settings) and/or post-depositional events are postulated for Welzow-Süd samples. Biomarker assemblages obtained from fossil wood show a distinct dominance of diterpenoids and δ13C values (−24.6 ‰ to −20.3 ‰) that clearly confirm gymnosperm sources. Distributions of diteprenoids and sesquiterpenoids, as well as fatty acids indicate the higher amount of saturated diterpenoids (pimarane, abietane) in fossil than in modern wood. This indicates reducing conditions promoting hydrogenation reactions. In addition to low Eh, preservation of cellulose in fossil wood was also favored by acidic conditions, very low degrees of aerobic fungal degradation, and protection of wood by Cupressaceae-derived resins. While δ13C values of fossil wood are generally consistent with stratigraphic trends and chemotaxonomical classification, slightly elevated δ13C values recorded in T. cryptomerioides and S. wettsteinii in Welzow-Süd and Meuro open-cast mines, respectively, compared to published δ13C data of fossil gymnosperm wood are also indicative for good cellulose preservation. Both preservation of in-situ Miocene fossil stumps and trunks and retention of high-cellulose contents are suggested to be related to high-amplitude temporal fluctuations associated with repeated eustatically-controlled wet-dry cycling inducing: (1) weathering of tuff- and rhyolite-dominated acidic volcanics and Lausitz granodiorite, (2) associated erosion of saprolites, and (3) peat-sourced circulation of humic acid- and fulvic acid-rich waters. The latter led to the formation of Middle Miocene kaolinite deposits, as well as to the release of silicic acid and its subsequent precipitation in form of opal-A. The latter influenced preservation of high-cellulose contents in fossil wood.
Publisher Copyright: © 2023
Keywords: Biomarkers; Calcofluor-stained CLSM; Carbon isotope; CLSM; Fossil and modern wood; Holocellulose; Lignite; micro-FTIR; Second Lusatian lignite seam; Xylite

Toughness enhancement in TiN/Zr0.37Al0.63N1.09 multilayer films - Lorentzon, Marcus; Meindlhumer, Michael; Palisaitis, Justinas; Greczynski, Grzegorz; Keckes, Jozef; Rosen, Johanna; Hultman, Lars; Birch, Jens; Ghafoor, Naureen (Acta Materialia, 2024)
The hardness and fracture toughness of high-temperature wear-resistant transition metal aluminum nitride multilayer films depend largely on the constituting layer's structure, compositional modulation, morphology, and interface coherency. We present a study on 1-micron thick multilayered films consisting of stacked layers of TiN and Zr0.37Al0.63N1.09, each layer being 10 nm thick. The films were grown using ion-assisted reactive magnetron sputtering on MgO(001) and Si(001) at substrate temperatures ranging from ambient to 900°C. By increasing growth temperature, we found that the ZrAlN layers transition from near amorphous to nanocrystalline wurtzite to decomposed c-ZrN and w-AlN domains. Concurrently, the TiN layers exhibit strong fiber texture, polycrystallinity, and epitaxial growth carried by the ZrN domains. Both hardness and fracture stress, evaluated by nanoindentation and micromechanical tests, increase with temperature from H=24 GPaMgO, 23 GPaSi to 36 GPaMgO, 30 GPaSi, and σFSi= 6.1-7.7 GPa, respectively. An improved fracture toughness of KIC=2.4-2.8 MPa√m is related to different toughening mechanisms for the various microstructures. The difference in hardness between the substrates is related to compressive stress due to the deposition conditions and thermal contraction. The superior fracture stress is attributed to dense multilayers, free from macroscopic defects due to ion-assisted growth. After being deposited at 200°C, the multilayers remained thermally stable when vacuum annealed for 15 hours at 900°C, with no significant change in phase composition or hardness. The improved hardness, toughness, and temperature stability of the otherwise brittle nitrides are promising for industrial applications.
Publisher Copyright: © 2024 The Authors
Keywords: Sputtering; Multilayers; STEM HAADF; Interface toughness; Micromechanics; Interface toughness; Micromechanics; Multilayers; Sputtering; STEM HAADF

Cationic UV-curing of bio-based epoxidized castor oil vitrimers with electrically conductive properties - Bergoglio, Matteo; Palazzo, Gabriele; Reisinger, David; Porcarello, Matilde; Kortaberria, Galder; Schlögl, Sandra; Sangermano, Marco (Reactive & functional polymers, 2024)
The growing appeal of carbon nanotube composites in the contemporary market derives from their exceptional thermal and chemical stability, coupled with electrical conductivity. In this study, we combined these salient features with a biobased epoxy matrix having vitrimeric properties, hence being reprocessable and resheapable, to obtain a biobased conductive coating. Epoxidised castor oil (ECO) was chosen as a monomer precursor for the straightforward synthesis. The synthesis relied on a cationic UV-curing process, embedding the conductive carbon nanotubes in the matrix. Photo DSC and transmission FTIR analysis were conducted to determine the final conversion of the epoxy rings in the cationic photocuring process. Thermo-mechanical properties were evaluated by tensile tests, and DMTA. Thermal stability was assessed by TGA. Dielectric spectroscopy confirmed increased electrical conductivity in the presence of increasing CNT content, reaching a percolation threshold at 0.5 phr of CNTs. Vitrimeric properties were proved by stress relaxation experiments, and the UV-cured composite underwent a thermo-activated transesterification reaction starting from 70 °C, catalysed by dibutyl phosphate. Overall, the ECO-CNT composite showed high thermal resistance (up to 400 °C) electrical conductivity with 0.5 phr CNT concentration, and vitrimeric properties. The study can be, therefore, considered a promising starting point to obtain sustainable biobased and electrically conductive vitrimers.
Publisher Copyright: © 2023
Keywords: Bio-based epoxy monomers; Cationic photopolymerization; Conductive films; Vitrimers

Laser-induced graphene formation on different wood species - Lengger, Sabine K.; Neumaier, Lukas; Haiden, Lukas; Feuchter, Michael; Griesser, Thomas; Kosel, Jürgen (Sustainable Materials and Technologies, 2024)
Conductive, 3D, porous graphene can be produced with a CO2 laser from a large variety of materials, including wood, at room temperature, and under inert atmosphere or after treatment for fire protection. Here, we investigated the suitability for direct conversion of 46 typical European and Asian woods into laser-induced graphene (LIG), without pre-treatment. The LIG was characterized by resistance measurements to determine if a conductive layer had formed, and via Raman spectroscopy. Here, we show, for the first time, that it is possible to produce LIG on certain woods under atmospheric conditions without additional fire protection treatment. We determined that the ability to produce LIG on untreated, natural wood under ambient atmosphere is favoured overall by a high density and a diffuse-porous xylem structure, as well as a high soluble lignin content. Some of these characteristics are similar to those required for high yields in char production. Problematic for the production of LIG-based electronics is the presence of pronounced growth rings, or other geometric wood features, with density variations, which can be reduced using specific cuts with minimized growth rings and absence of rays. This is the first time that untreated wood has been directly converted into LIG using a conventional CO2 laser and ambient atmosphere. Our results represent a further step towards the development of a new generation of sustainable electronics relying on natural materials.
Publisher Copyright: © 2023
Keywords: Laser-induced graphene; Natural materials; Supercapacitors; Sustainable electronics; Sustainable sensors; Wood

Design of Reversible Adhesives by Using a Triple Function of Ionic Liquids - Wanghofer, Florian; Kriehuber, Matthias; Reisinger, David; Floh, Florian; Wolfahrt, Markus; Schlögl, Sandra (Macromolecular materials and engineering, 2024)
Reversible adhesives are crucial for a circular economy of composites as they play a key role for rework, repair, and recycling of adhesively bonded components. Herein, electrically debondable adhesives are prepared by introducing ionic liquids in dynamic thiol–epoxy networks. The function of the ionic liquid in the networks is threefold as it accelerates the curing reaction between thiol and epoxy monomers, facilitates electrical debonding, and catalyzes thermoactivated transesterification reactions, required for rebonding at elevated temperature. A library of 1,3-dibutylimidazolium-based ionic liquids with varying anions is synthetized and it is found that 1,3-dibutyl-1H-imidazol-3-ium dicyanamide (DiButIm─N(CN)2) is superior in accelerating bond-exchange reactions between hydroxy and ester moieties at elevated temperature. Thus, a thiol–epoxy resin containing 20 wt% of DiButIm─N(CN)2 is used to impregnate glass fiber mats yielding adhesive connections for aluminum substrates with 10.2 MPa pull-off strength. The adhesive connections are successfully debonded at the metal–adhesive interface by applying 120 V. The samples are then rebonded via the thermoactivated change in the networks’ viscoelastic properties and ≈80% (8.1 MPa) of their original bond strength can be regained. By providing a simple strategy to synthetize reversible adhesives, this approach paves a way toward improved recyclability and repairability of adhesively bonded structures.
Publisher Copyright: © 2024 The Authors. Macromolecular Materials and Engineering published by Wiley-VCH GmbH.
Keywords: dynamic polymer networks; electrical debonding; ionic liquids; reversible adhesives; vitrimers

Turning of high entropy alloy into high entropy carbides by modifying carbon content during reactive sintering - Valášek, D.; Pouchlý, V.; Salamon, David (Ceramics International, 2024)
Publisher Copyright: © 2024 Elsevier Ltd and Techna Group S.r.l.
Keywords: Carbides; Hardness; High entropy; Phase transition; Spark plasma sintering

CO2 Utilization with Citizen Scientists - Ruh, Thomas; Messner, Martina; Lorenz, Harald; Rameshan, Christoph (Science 4 Technology @ MUL, 2024)

Design and characterization of novel Zr-Al-Fe-Y metallic glasses with nanoscale phase separation - Singh, Devinder; Parthiban, Ramasamy; Jelinek, Anna; Bhattacharya, Rahul; Chen, Zhuo; Fellner, Simon; Gammer, Christoph; Zhang, Zaoli; Eckert, Jürgen (Materialia, 2024)
We present a new phase-separated Zr-based metallic glass (MG) composition, free of toxic elements (Ni and Cu) prepared in a glass-forming system by alloying addition. The substitution of Y in Zr 70- xAl 12.5Fe 17.5Y x (x = 0–15 at.%) results in phase separation, giving rise to nano-amorphous domains in a glassy matrix. A homogeneous MG feature is observed for low concentrations of Y up to x = 5. Microstructure and thermal property analysis indicate that the glasses with x = 10 and 15 at.% Y exhibit a typical liquid phase separation-induced two-glassy phase (Zr-rich and Y-rich) with droplet-like microstructures (nano-amorphous domains). With increasing Y addition, the domain size increases. The microstructural evolution arising due to phase separation in these alloys is confirmed by a combination of transmission electron microscopy (TEM) and atom probe tomography (APT) analysis. The formation of nanometer-size Y-enriched clusters is confirmed by APT for x = 15.
Publisher Copyright: © 2024
Keywords: Metallic glasses; Microstructure; Nano-amorphous domain; Phase separation; Zr-alloys

Exploring Multifaceted Factors Influencing Community Resilience to Earthquake-Induced Geohazards: Insights from Montenegro - Grozdanić, Goran; Vladimir, Cvetković M. (2024)
This scientific monograph stems from a deep interest in the resilience of local communities to natural disasters, particularly earthquakes, which pose one of the greatest challenges humanity faces. In our quest to explore the multifaceted factors influencing this crucial dimension of societal preparedness, we focused on Montenegro, a country located in the seismic active zone of the Mediterranean. Through an in-depth analysis of various aspects, we aim to contribute to a better understanding of the factors shaping the resilience of local communities to earthquakes and provide guidance for the development of effective strategies and programs. Our research mission aims to identify key factors shaping the resilience of local communities to earthquakes and analyze the prerequisites for the development and implementation of various strategies and programs that would enhance the situation in this area. In doing so, we rely on an interdisciplinary approach, integrating insights from various scientific disciplines to gain a deeper understanding of the complexity of this issue. In this context, we consider demographic, socioeconomic, and psychological factors influencing the resilience of local communities to earthquakes. We understand that resilience is not only the result of technical preparations but also of deeper social, economic, and psychological dynamics. Through a systematic analysis of these factors, we strive to provide a comprehensive picture of the state of preparedness of local communities and to identify key points of intervention to improve their resilience. Research approach is based on the analysis of available data as well as on field research, including interviews with the population and relevant experts. This enables us to gain a more detailed insight into the perception and attitudes of citizens regarding preparedness for earthquakes, as well as to identify specific challenges faced by local communities. Given the complexity of the problem and the importance of an interdisciplinary approach, we aim for our monograph to be a valuable resource for various stakeholders, including government institutions, non-governmental organizations, local communities, and the scientific community. We hope that the results of our research will serve as a basis for the development of concrete action plans and policies that will enhance the preparedness of local communities for earthquakes. This monograph is not only the result of our research effort but also the product of collaboration with a wider community of experts and practitioners who have contributed their knowledge and experience to our understanding of this complex issue. We express our gratitude to all who have supported and contributed to our research. Through the following pages, we will guide you through a deep analysis of the factors shaping the resilience of local communities to earthquakes, providing insight into the complexity of this problem and identifying opportunities for improving the preparedness of local communities. We hope that this monograph will be a valuable resource for all those involved in this important field and will contribute to strengthening the resilience of local communities to earthquakes and other natural disasters. A large number of social and natural factors influence the resilience of local communities to geohazards caused by earthquakes. Understanding these factors plays a crucial role in devising and implementing strategies to enhance resilience. The results of previous research on citizen resilience to geohazards caused by earthquakes have influenced the development of hypotheses, which are grounded in the concept of resilience. The general hypothesis involves testing the assertion that there is a relationship between demographic (gender, age, education, household size), socio-economic (employment, income level, marital status), and psychological characteristics (fear, past experience, risk perception) of citizens and their level of preparedness to respond to geohazards caused by earthquakes in the Republic of Montenegro. It is assumed that this relationship is at the pre-planning level, implying that citizens recognize the problem and accept that action must be taken. Based on the general hypothesis, three specific hypotheses have been defined: The first hypothesis concerns testing the assertion that there is a correlation between demographic factors (gender, age, education, household size) of citizens in the Republic of Montenegro and their resilience levels in responding to geohazards caused by earthquakes. The second hypothesis pertains to testing the assertion that there is a correlation between socio-economic factors (employment status, income level, marital status) of citizens in the Republic of Montenegro and their resilience levels in responding to geohazards caused by earthquakes. The third hypothesis concerns testing the assertion that there is a correlation between psychological characteristics (fear, previous experience, risk perception) of citizens and their readiness levels in responding to geohazards caused by earthquakes in the Republic of Montenegro. In the methodological framework of our research, we employed a combination of quantitative and qualitative methods to gather and analyze data. Surveys and interviews were conducted to collect quantitative and qualitative data, respectively, while statistical analysis techniques were applied to test the formulated hypotheses. Additionally, a comprehensive literature review was conducted to provide a theoretical foundation for our research and to contextualize our findings within existing knowledge. Through this methodological approach, we aimed to ensure the rigor and validity of our research findings. We extend our gratitude to the reviewers who provided valuable feedback and insights during the development of this monograph. Their contributions have undoubtedly enriched the quality of our work and have helped us refine our analysis and interpretations.

GECCO2 - Recycling of mineral residues in geopolymer-materials - Ratz, Bettina (Science 4 Technology @MUL, 2024)

Hydrogen from Methane Pyrolysis in Liquid Metals - Scheiblehner, David (Science 4 Technology @MUL, 2024)

Hydrogenation/Dehydrogenation kinetics of magnesium-based metal powders originating from different process routes - Vigl, Elias; Eisbacher-Lubensky, Jan; Kittinger, Friedrich; Weiß, Christian; Dopler, Martin; Schäffler, Peter; Edinger, Stefan; Dimopoulos, Theodoros; Gneiger, Stefan (18th International Symposium on Metal-Hydrogen Systems, 2024)

Large-scale experimental research in waste management: WASTE SCANNER and DIGITAL WASTE RESEARCH LAB - Kandlbauer, Lisa (Science 4 Technology @MUL, 2024)

Method development for digital waste analysis for digital waste analysis for non-hazardous mixed commercial waste - Kandlbauer, Lisa (Science 4 Technology @ MUL, 2024)

Micro-Mechanical Fracture Investigations on Grain Size Tailored Tungsten-Copper Nanocomposites - Schmuck, Klemens Silvester; Burtscher, Michael; Alfreider, Markus; Wurmshuber, Michael; Kiener, Daniel (JOM, 2024)
Tungsten-copper composites are used in harsh environments because of their superior material properties. This work addresses a tungsten-copper composite made of 20 wt.% copper, which was subjected to grain refinement by high-pressure torsion, whereby the deformation temperature was varied between room temperature and 400 °C to tailor the grain size. Deformation was performed up to microstructural saturation and verified by hardness measurement and scanning electron microscopy. From the refined nanostructured material, micro-cantilever bending beams with cross-sections spanning from 5 × 5 to 35 × 35 µm 2 were cut to examine possible size effects and the grain size influence on the fracture behavior. Fracture experiments were performed in situ inside a scanning electron microscope by applying a quasi-static loading protocol with partial unloading steps. Inspection of the fracture surfaces showed that all cantilevers failed in an inter-crystalline fashion. Nevertheless, remaining coarser tungsten grains impacted the resultant fracture toughness and morphology. Cantilevers fabricated from the 400 °C specimen exhibited a fracture toughness of 220 ± 50 Jm2 . For the room temperature cantilevers, a fracture toughness of 410 ± 50 Jm2 was observed, which declined to 340 ± 30 Jm2 for cantilevers < 10 × 10 µm 2, confirming a size effect. The increased fracture toughness is attributed to the delamination-like structures formed in the room temperature sample.
Publisher Copyright: © 2024, The Author(s).

Neuartige Sensoren und digitale Innovationen zur kontinuierlichen Prozessüberwachung am Beispiel von Schwingsieben - Krukenfellner, Philip (Stein & Kies (Mitgliederzeitung - Forum mineralische Rohstoffe), 2024)
Keywords: Schwingsiebe; Condition Monitoring; Schwingungsanalyse; Industrie 4.0; Vibrating Screens; Condition Monitoring; Vibration Analysis; Industrie 4.0

Prediction of thermal shock induced cracking in multi-material ceramics using a stress-energy criterion - Papšík, Roman; Sevecek, Oldřich; Schlacher, Josef; Bermejo Moratinos, Raul (Engineering Fracture Mechanics, 2024)

The Efficiency of Disaster and Crisis Management Policy at the Local Level: Lessons from Serbia - Tanasic, Jasmina; Vladimir, Cvetković M. (2024)
A scientific monograph offers a comprehensive examination of crisis and disaster management policy in Serbia. Leveraging rich scientific research experience in the field of disaster studies, the authors critically assess the merits and demerits of various levels of crisis and disaster management. Crafted to address the subject matter, objectives, and methodologies employed, the monograph stands as a multidimensional, multimethod work primarily of a qualitative nature. Rooted in a qualitative approach, it scrutinizes the concept of crisis and disaster management policy across 23 cities in Serbia. Beyond enriching understanding in the intricate realm of crisis and disaster management policy at the local level, its aim extends to furnishing recommendations concerning necessary methodological and organizational shifts in the operations of local governance and decision-making bodies, legal frameworks and protocols, security strategies, decision-making processes, coordination efforts, collaborative initiatives, communication strategies, public engagement practices, educational endeavors, and information dissemination channels. In terms of the societal justification for the research, derived from empirical findings, specific conclusions and proposals have been drawn regarding the efficacy, transparency, and deficiencies in the implementation of crisis management policy concepts within Serbian cities. Concrete recommendations and proposals are presented to enhance the qualitative aspects of the concept in areas where shortcomings or inadequacies are identified. The societal justification for this research primarily lies in augmenting the capacities of local self-governments to enhance preparedness, cope with, and overcome crises and disasters, fortify safety cultures, and foster the development of "resilient local communities." Within the initial portion of the scientific monograph, the authors scrutinize and elaborate on five thematic units, each classified into corresponding chapters. The opening (first) chapter explores crises and disasters as political constructs. Delving into the concepts of crisis and disaster, the discussion navigates through theoretical distinctions among related phenomena such as disasters, emergencies, risks, accidents, and crises. Special emphasis is placed on examining the characteristics of disasters and emergencies, with reference to typologies such as classical, modern, and combined. In the second chapter of the scientific monograph, the authors delve into theoretical concepts surrounding crisis and disaster management. They explore themes such as strategic management and leadership during crises and disasters, crisis management, emergency management, and related concepts. The chapter also examines the characteristics of crisis and disaster management, models of management processes during crises and disasters, crisis and disaster management within public administration, and organizational approaches to crisis and disaster management. Moving on to the third chapter, the authors undertake a comprehensive examination of crisis and disaster management policy. Within this section, they scrutinize various issues pertaining to crisis and disaster identification, decision-making in crisis and disaster situations, interpretation of crises and disasters within the realm of political communications, risk communication regarding crises and disasters, resolution strategies for crises and disasters, as well as the assignment of blame and responsibilities. The chapter also highlights the potential for organizational learning and the implementation of reforms induced by crises and disasters. The fourth chapter of the scientific monograph focuses on community resilience in crisis and disaster situations. Here, the authors outline the characteristics of resilient communities, with particular emphasis on urban safety and the criteria for designating cities as safe. Additionally, citizen responses to crises and disasters are examined within this context. In the fifth chapter, the authors explore crisis and disaster management practices within the European Union and European countries, along with the institutional framework for such management within the EU. Special attention is given to the analysis and description of crisis and disaster management systems across European nations. In the second part of the scientific monograph, a detailed methodological framework for the conducted research is presented. This includes discussions on research subjects, objectives, and tasks, as well as the hypothetical research framework, scientific and social justifications, sources and types of data, and methodologies for data collection and processing, alongside an overview of key indicators. The third part of the scientific monograph comprehensively describes the analytical dimensions of the conducted research results. The first chapter of this section explores the cultural and historical dimensions of crisis and disaster management policy in Serbia, examining administrative-territorial frameworks, central and local levels of management and administrative structures, responsibilities and regulatory frameworks, legal reforms, and degrees of regulatory governance. In the second chapter of the third part, the authors delve into the dimensions of crisis and disaster management as public policies, discussing the socio-economic context of crisis and disaster management in Serbian cities. They explore strategic frameworks, the development of strategic and institutional frameworks for security and crisis management at the local level, intersectoral collaboration, operational frameworks for disaster management, institutional frameworks, financing, coordination between agencies, supervision, evaluation of public policies, and resource monitoring. In the third chapter, the exploration extends to partnerships and collaborative efforts in crisis and disaster management processes within Serbian municipalities. This encompasses the intricate dynamics between the state, local self-governance, and citizens concerning crisis management policies in Serbia. It further delves into the expectations that local self-governments hold towards citizens and vice versa, particularly regarding the safeguarding of their interests. Additionally, the chapter scrutinizes the typologies of crises and their perceptual reality among citizens in Serbia, as well as the identified risks delineated in national and local strategic documents. Furthermore, it examines scenarios in crisis and disaster management where volunteer engagement is integral, assessing the readiness level of citizens for such involvement within local communities. Moreover, the chapter explores collaborative initiatives with neighboring municipalities, ongoing projects concerning crisis management within Serbian local self-governments, and the scope and nature of regional or international cooperation pertaining to crisis and disaster management at the local level in Serbia. Concluding with the fourth chapter, attention shifts towards the realm of information dissemination and educational endeavors concerning crises and disasters within Serbian municipalities. This includes the specialized training programs tailored for mayoral officials in navigating crisis and disaster scenarios effectively. Moreover, it encompasses the intricacies of crisis communication strategies deployed at the local level and the pivotal role of informative and educational initiatives as integral components of proactive crisis management strategies within local communities. Join us in unraveling the complexities of crisis and disaster management policy, as we pave the way for resilient local communities and informed decision-making. Stay tuned for the release of our scientific monograph, offering invaluable lessons from Serbia's journey in crisis management.

Walk the line: Erfolgsfaktor Citizen Science - Maurer, Jakob; Längauer, Julia; Duboc, Olivier; Hascher, Cornelia; Irrgeher, Johanna; Prohaska, Thomas; Puschenreiter, Markus; Schober, Michael; Teschler-Nicola, Maria; Pieler, Franz (2024)

Developing a prediction model in a lightweight packaging waste sorting plant using sensor-based sorting data combined with data of external near-infrared and LiDAR sensors - Schlögl, Sabine; Kamleitner, Josef; Kröll, Nils; Chen, Xiaozheng; Vollprecht, Daniel; Tischberger-Aldrian, Alexia (Waste management & research, 2024)
Sensor-based material flow monitoring allows for continuously high output qualities, through quality management and process control. The implementation in the waste management sector, however, is inhibited by the heterogeneity of waste and throughput fluctuations. In this study, challenges and possibilities of using different types of sensors in a lightweight packaging waste sorting plant are investigated. Three external sensors have been mounted on different positions in an Austrian sorting plant: one Light Detection and Ranging (LiDAR) sensor for monitoring the volume flow and two near-infrared (NIR) sensors for measuring the pixel-based material composition and occupation density. Additionally, the data of an existing sensor-based sorter (SBS) were evaluated. To predict the newly introduced parameter material-specific occupation density (MSOD) of multi-coloured polyethylene terephthalate (PET) preconcentrate, different machine learning models were evaluated. The results indicate that using SBS data for both monitoring of throughput fluctuations caused by different bag opener settings as well as monitoring the material composition is feasible, if the pre-set teach-in is suitable. The ridge regression model based on SBS was comparable (RMSE = 3.59 px%, R² = 0.57) to the one based on NIR and LiDAR (RMSE = 3.1 px%, R² = 0.68). The demonstrated feasibility of the implementation at plant scale highlights the opportunities of sensor-based material flow monitoring for the waste management sector and paves the way towards a more circular plastics economy.
Publisher Copyright: © The Author(s) 2024.
Keywords: Sensor-based material flow monitoring; leightweight packaging waste; plastic; sorting plant; machine learning; prediction model; near-infrared; LiDAR; LiDAR; lightweight packaging waste; machine learning; near-infrared; plastic; prediction model; Sensor-based material flow monitoring; sorting plant

Usefulness of Lumped Kinetic Modeling - Lorbach, Sebastian-Mark; Lechleitner, Andreas; Zapf, Fabian; Lehner, Markus (Chem & bio engineering, 2024)
Chemical recycling of plastic wastes through pyrolysis, gasification, or partial oxidation is a promising alternative to landfill disposal and incineration which must be applied in a future circular economy. These technologies enable the chemical industry, which currently heavily relies on crude oil, to obtain necessary chemical feedstock from postconsumer plastic waste. Kinetic models of pyrolysis and gasification reactions are required to dimension and design these processes on an industrial scale. The creation of detailed kinetic networks is often not feasible due to their complexity in this application, which is when the lumped kinetic modeling approach is used. This work develops and compares five lumped kinetic models for the co-pyrolysis of LDPE with a heavy petroleum fraction in a tubular reactor. A priori lumping is used for four models, and the fifth is created using a posteriori principle whereby in each model the product mixture is defined by eight lumps distinguished by their boiling point. The aim of this work is to compare different approaches for modeling reaction pathways in lumped kinetic models and to identify their impact on the predictive accuracy of the model. It was shown that all of the modeling approaches and the resulting models have similar prediction accuracies and deviations but with different kinetic parameters. Each model was used for a scale-up of an industrial-sized reactor to check whether the model had an influence on the design or predicted operation of the reactor.
Keywords: Kunststoffrecycling; Chemisches Recycling; Pyrolyse; Modellierung

Effect of Flashlamp Heating System Parameters on the Wedge Peel Strength of Thermoplastic Carbon Fiber Tape in the Automated Tape Placement Process - Legenstein, Alexander; Fauster, Ewald (Journal of Manufacturing and Materials Processing, 2024)
Laser-assisted automated tape placement systems are currently the state of the art regarding thermoplastic tape placement. Flashlamp heating systems are rather new in this field of application and offer high energy density with low safety requirements and moderate costs compared to laser-assisted automated tape placement systems. In this study, the effect of processing parameters on interlaminar bonding of carbon fiber-reinforced polyamide 6 tapes is investigated using a flashlamp heating system. The temperature during placement is monitored using an infrared camera, and the bonding strength is characterized by a wedge peel test. The bonding quality of the tapes placed between 210 °C and 330 °C at a lay-up speed of 50 mm/s is investigated. Thermogravimetric analysis, differential scanning calorimetry, and micrographs are used to investigate the material properties and effects of the processing conditions on the thermophysical properties and geometric properties of the tape. No significant changes in the thermophysical or geometric properties were found. Moisture within the tapes and staining of the quartz guides of the flashlamp system have significant influence on the bonding strength. The highest wedge peel strength of dried tapes was found at around 330 °C.
Publisher Copyright: © 2024 by the authors.
Keywords: automated tape placement; bonding; material characterization; polymer matrix composites; thermoplastic resin

Investigation of probable squat growth from initial surface cracks in rails using a three-dimensional rollover simulation - Gschwandl, Timna Jakomijna; Antretter, Thomas; Künstner, David; Scheriau, Stephan; Daves, Werner (Proceedings of the Institution of Mechanical Engineers, Part F: Journal of Rail and Rapid Transit, 2024)
Squats are rather complex failure mechanisms in rails and challenge railway operators all over the world, thus calling for a detailed investigation of squats by means of finite element analysis to locate the initiation and propagating mechanisms. In this work, a cyclic three-dimensional (3D) finite element model of a wheel-rail contact including an initial penny-shaped defect is used. This work presents the implementation of the starting penny-shaped crack in the rail for a wheel-rail simulation by utilising a submodel strategy. Moreover, viable evaluation options are shown. In the future, this set-up will help to assess multiple crack positions and possible squat growth mechanisms.
Publisher Copyright: © IMechE 2023.
Keywords: configurational force; crack driving force; elasto-plastic material model; finite element analysis; penny-shaped crack; residual stresses; Squats; initial surface cracks in rails; three-dimensional rollover simulation

Peculiarity of hydrogen absorption in duplex steels - Pogrielz, Thomas; Eichinger, Matthias; Weiser, Adam; Todt, Juraj; Hohenwarter, Anton; Ascii, Atacan; Sarac, Baran; Brandl, Dominik; Ressel, Gerald; Jary, Milan; Dlouhý, Antonin; Mori, Gregor Karl; et al. (Scripta Materialia, 2024)
Electrochemical hydrogen absorption in duplex steels is not fully understood. In this work, an in-situ synchrotron cross-sectional X-ray micro-diffraction analysis is performed on steel with comparable phase fractions of ferrite and austenite, coupled with electrolytic hydrogen charging. The results reveal that charging with a constant current density of 10 mA/cm² for 5 h leads to expanding the austenitic lattice to a depth of approximately 250 µm, up to ≥0.15 %. In contrast, the lattice parameter of the ferrite phase remains unchanged during this process. As the austenite expansion progresses, it generates different amounts of equivalent in-plane compressive stresses, which amount to approximately -150 and -450 MPa in the austenite and ferrite phases at the sample surface, respectively. Using a finite element model of grain interaction, this difference is qualitatively interpreted by mutual mechanical constraints between ferrite and austenite, as well as between the hydrogen-charged surface layer and the underlying material.
Publisher Copyright: © 2024 The Author(s)
Keywords: Duplex steel; Electrochemistry; Hydrogen embrittlement; Residual stress; Synchrotron x-ray diffraction

Modeling Desiccation Cracks in Opalinus Clay at Field Scale with the Phase-Field Approach - Cajuhi, Tuanny; Ziefle, Gesa; Massmann, Jobst; Nagel, Thomas; Yoshioka, Keita (InterPore Journal, 2024)
Geological materials such as Opalinus Clay show complex coupled hydro-mechanical behavior at laboratory and field scales. In the context of radioactive waste disposal, in-situ excavations might remain open for ventilation and operation for decades and, consequently, be susceptible to environmental changes such as desaturation. The saturation changes can then lead to mechanical deformation and desiccation cracks. To account for desiccation cracking at field scale, this study proposes an unsaturated hydro-mechanical model combined with the phase-field approach. Using laboratory and in-situ experimental data as input in the numerical model, the modeling framework is applied for simulating the hydro-mechanical effects and desiccation cracks reported in the Cyclic Deformation (CD-A) experiment carried out in the Opalinus Clay formation at the Mont Terri Rock Laboratory in Switzerland. Simulations with homogeneous and heterogeneous material properties generated from experimentally obtained ranges are carried out. Crack initiation and propagation show a good correlation with the monitored relative humidity range of the experiment. Practical information is summarized to motivate the application of the proposed formulation at different setups. Finally, possibilities to improve the framework and to reason simplification of more abstract models are indicated.

The Geodynamic Significance of Continental UHP Exhumation - Bidgood, Anna; Parsons, Andrew; Roberts, Nick; Waters, David; Tapster, Simon; Gopon, Phillip (Tectonics, 2024)
The burial and exhumation of continental crust to and from ultrahigh-pressure (UHP) is an important orogenic process, often interpreted with respect to the onset and/or subduction dynamics of continent-continent collision. Here, we investigate the timing and significance of UHP metamorphism and exhumation of the Tso Morari complex, North-West Himalaya. We present new petrochronological analyses of mafic eclogites and their host-rock gneisses, combining U-Pb zircon, rutile and xenotime geochronology (high-precision CA-ID-TIMS and high-spatial resolution LA-ICP-MS), garnet element maps, and petrographic observations. Zircon from mafic eclogite have a CA-ID-TIMS age of 46.91 ± 0.07 Ma, with REE profiles indicative of growth at eclogite facies conditions. Those ages overlap with zircon rim ages (48.9 ± 1.2 Ma, LA-ICP-MS) and xenotime ages (47.4 ± 1.4 Ma; LA-ICP-MS) from the hosting Puga gneiss, which grew during breakdown of UHP garnet rims. We argue that peak zircon growth at 47–46 Ma corresponds to the onset of exhumation from UHP conditions. Subsequent exhumation through the rutile closure temperature, is constrained by new dates of 40.4 ± 1.7 and 36.3 ± 3.8 Ma (LA-ICP-MS). Overlapping ages from Kaghan imply a coeval time-frame for the onset of UHP exhumation across the NW Himalaya. Furthermore, our regional synthesis demonstrates a causative link between changes in the subduction dynamics of the India-Asia collision zone at 47–46 Ma and the resulting mid-Eocene plate network reorganization. The onset of UHP exhumation therefore provides a tightly constrained time-stamp significant geodynamic shifts within the orogen and wider plate network.

Metallographic Etching of Al–Mg–Zn–(Cu) Crossover Alloys - Samberger, Sebastian; Kremmer, Thomas; Stemper, Lukas; Tourey, Serena; Uggowitzer, Peter; Pogatscher, Stefan (Advanced engineering materials, 2024)
Various alloys demand customized etchants due to their diverse chemical compositions, particularly in the realm of aluminum alloys. Consequently, in this study, a technique is proposed for metallographic visualization of small grain structures within Al–Mg–Zn–(Cu) crossover alloys. In this method, a thermal pretreatment combined with an etching process is relied on. In the study, it is primarily sought to comprehend how grain-boundary precipitation affects etchability, addressing the complexities of characterizing these alloys. The demonstrated approach facilitates the swift assessment of grain sizes <10 μm using light optical microscopy. Exploring the etchability of Al–Mg–Zn–(Cu) crossover alloys across a standard heat-treatment pathway identifies the optimal treatment and suitable etchant for grain visualization. Through process refinement, a reduction in processing time is achieved by employing a single-step preheat treatment lasting 20 min at 180 °C post solution annealing. Transmission electron microscope analysis reveals continuous occupancy of the grain boundary with T-phase as the key factor influencing the alloy's etchability. Grain size assessment involves line intercept counting and equivalent circle diameter measurement for precise characterization.
Publisher Copyright: © 2024 The Authors. Advanced Engineering Materials published by Wiley-VCH GmbH.
Keywords: aluminum alloys; crossover alloys; etching; grain size measurements; grain-boundary precipitations; light optical microscopies; T-phase

Vitrimer Transition Phenomena from the Perspective of Thermal Volume Expansion and Shape (In)stability - Klingler, Andreas; Reisinger, David; Schlögl, Sandra; Wetzel, Bernd; Breuer, Ulf; Krüger, Jan Kristian (Macromolecules, 2024)
Vitrimers are covalently cross-linked polymers that can be reshaped and recycled, triggered by the temperature. Well above the canonical glass transition temperature Tg, they gain malleable, thermoplastic-like properties; below, they behave as thermosets. The responsible molecular mechanism is enabled by dynamic covalent bond exchange. However, the underlying physics of the transition from thermoplastic to thermoset properties is rather unclear and the subject of current scientific debate. In this work, we address the questions of what extent the temperature-dependent malleability of vitrimers is reflected in the thermal expansion behavior and, conversely, to what extent the thermal expansion behavior is suited to characterize the respective creep behavior of vitrimers. It will be shown that at least in the case of the used model vitrimer, only the canonical glass transition is able to stop the vitrimer to undergo irreversible shape changes and that the often-discussed topology freezing temperature of vitrimers Tv is purely operational.
Publisher Copyright: © 2024 The Authors. Published by American Chemical Society.

Crack characterization in manganese steel using a µ-bolometer camera and an air-cooled inductor - Tuschl, Christoph; Oswald-Tranta, Beata; Dornig, Peter; Künstner, David; Pötz, Melanie; Eck, Sven (SPIE Defense + Commercial Sensing 2024, 2024)
Due to beneficial mechanical properties, cast manganese (Mn13) steel is used for premium grade railway turnout frogs worldwide. However, its coarse-grain structure makes common non-destructive testing (NDT) methods for defect detection used in this industry very difficult to apply. Inductive thermography is a NDT method well suited for this problem. Scanning inductive thermography is used to localise surface defects on the running surfaces of turnout frogs. Once localised, we propose additional static measurements to characterise the detected surface defects with respect to crack length, depth and penetration angle. Simulations with ANSYS Multiphysics are conducted to study the influence of different crack geometries as well as the influence of different excitation parameters. Validation measurements on samples with defined crack geometries are conducted. The results of both, simulation and measurements on samples, are used to characterize surface defects on actual manganese turnout frogs.
Conference code: 13047
Keywords: Thermography; Non-destructive testing

Fracture network characterisation of the Balmuccia peridotite using drone-based photogrammetry, implications for active-seismic site survey for scientific drilling - Menegoni, Niccolò; Panara, Yuri; Greenwood, Andrew; Mariani, Davide; Zanetti, Alberto; Hetényi, György (Journal of Rock Mechanics and Geotechnical Engineering, 2024)
The presence of discontinuities (e.g. faults, fractures, veins, layering) in crystalline rocks can be challenging for seismic interpretations because the wide range of their size, orientation, and intensity, which controls the mechanical properties of the rock and elastic wave propagation, resulting in equally varying seismic responses at different scales. The geometrical characterisation of adjacent outcrop discontinuity networks allows a better understanding of the nature of the subsurface rocks and aids seismic interpretation. In this study, we characterise the discontinuity network of the Balmuccia peridotite (BP) in the Ivrea–Verbano Zone (IVZ), northwestern Italy. This geological body is the focus of the Drilling the Ivrea–Verbano zonE (DIVE), an international continental scientific drilling project, and two active seismic surveys, SEismic imaging of the Ivrea ZonE (SEIZE) and high-resolution SEIZE (Hi-SEIZE), which aim to resolve the subsurface structure of the DIVE drilling target through high-resolution seismic imaging. For fracture characterisation, we developed two drone-based digital outcrop models (DOMs) at two different resolutions (10–3–10 m and 10–1–103 m), which allowed us to quantitatively characterise the orientation, size, and intensity of the main rock discontinuities. These properties affect the seismic velocity and consequently the interpretation of the seismic data. We found that (i) the outcropping BP discontinuity network is represented by three more sets of fractures with respect to those reported in the literature; (ii) the discontinuity sizes follow a power-law distribution, indicating similarity across scales, and (iii) discontinuity intensity is not uniformly distributed along the outcrop. Our results help to explain the seismic behaviour of the BP detected by the SEIZE survey, suggesting that the low P-wave velocities observed can be related to the discontinuity network, and provide the basic topological parameters (orientation, density, distribution, and aperture) of the fracture network unique to the BP. These, in turn, can be used for interpretation of the Hi-SEIZE seismic survey and forward modelling of the seismic response.
Publisher Copyright: © 2024 Institute of Rock and Soil Mechanics, Chinese Academy of Sciences
Keywords: Remote sensing; Fracture intensity; Digital outcrop model (DOM); Rock discontinuity; Fault; SEismic imaging of the Ivrea ZonE (SEIZE); Ivrea–Verbano Zone (IVZ); Crystalline rock

Reducing part deformation of isotactic polypropylene specimens fabricated with powder bed fusion technique through controlling crystallization behaviors - Gao, Xia; Guo, Junqiang; Zhang, Daijun; Li, Jing; Su, Yunlan; Arbeiter, Florian; Li, Huayi (Journal of polymer science, 2024)
Serious shrinkage and warpage are obstacles to the development of ideal isotactic polypropylene (iPP) materials for polymer-based powder bed fusion (PBF) technique. In this work, the variations of the dimensional accuracy of the PBF-printed iPP parts were investigated with various printing parameter and nucleating agent. The iPP parts printed at a scanning speed of 700 mm/s exhibit smaller extents of shrinkage and curling than those at lower speeds, due to a lower degree of crystallinity. Interestingly, iPP blended with the α- or β-nucleating agent demonstrates more serious part deformation with respect to neat iPP. Especially, α-nucleating agent tends to trigger the most severe curling under the investigated printing parameters. Based on X-ray diffraction and differential scanning calorimetry (DSC) results, both neat iPP and α-iPP parts crystallize into α-crystal, while β-iPP parts display the coexistence of β- and α-crystals. And, the difference of the crystallinity is less than 3% in three specimens. This suggests that both crystallinity and crystalline structure are not the main reasons for the shrinkage and warpage in this case. Instead, the severe part deformation of the α-iPP parts is assigned to the narrower sintering window as well as the higher onset crystallization temperature of α-iPP, which hinder relaxation of residual stresses. This work provides insights into the part deformation mechanism for PBF-processed polymer materials.
Publisher Copyright: © 2024 Wiley Periodicals LLC.
Keywords: crystallization behavior; isotactic polypropylene; part deformation; powder bed fusion technique

recAIcle: Prototyp für experimentelle Datenakquise und Training von ML-Modellen - Aberger, Julian; Brensberger, Lena; Khodier, Karim; Sarc, Renato (Österreichische Abfallwirtschaftstagung, 2024)

Evaluating Multi-target Regression Framework for Dynamic Condition Prediction in Wellbore - Keshavarz, Sahar; Elmgerbi, Asad; Vita, Petr; Thonhauser, Gerhard (The Arabian journal for science and engineering, 2024)
In recent years, the focus has shifted towards leveraging physics-based modelling and data-driven analysis to predict drilling incidents and anomalies in real time, with the goal of reducing non-productive periods. However, much of this attention has directed at specific drilling operations like drilling and tripping, leaving other vital processes, such as wellbore conditioning, comparatively overlooked. The primary objective of this study is to employ data-driven techniques for predicting the dynamic state of the wellbore by utilising sensor data, operating parameters, and surface measurements. Accurate predictions are pivotal for automating these processes, promising significant savings in both redundant time and associated costs, ultimately elevating operational efficiency.In this research, the surface drilling parameters such as flowrate, rotation speed, block position, and drill string length are incorporated with the surface measurements such as hookload, pressure, and torque during wellbore conditioning operation to predict further surface sensor measurements. Different parameter settings are evaluated to find the best approach. Six supervised learning algorithms are used to select the best prediction method. The findings reveal that considering all surface parameters and measurements yields the most accurate predictions. Among various single and multi-target regression methods, including deep learning approaches, the Gaussian process and random forest models exhibit the lowest prediction errors.By reliably predicting and understanding wellbore behaviour, this research paves the way for more efficient and autonomous drilling operations in the future, bridging a critical gap in the industry's automation capabilities.
Publisher Copyright: © The Author(s) 2024.
Keywords: Supervised learning; Wellbore monitoring; Surface drilling parameters; Wellbore conditioning; Multi-targetregression; Multi-target regression

Morphological investigations on silica and carbon-black filled acrylonitrile butadiene rubber for sealings used in high-pressure H2 applications - Clute, Clara; Balasooriya, Winoj; Cano Murillo, Natalia; Theiler, Géraldine; Kaiser, Andreas; Fasching, Michael; Schwarz, Thomas; Hausberger, Andreas; Pinter, Gerald; Schlögl, Sandra (International Journal of Hydrogen Energy, 2024)
To understand the effects of additives on the properties of rubber grades suitable for sealing applications in high-pressure H2 gas infrastructure, five acrylonitrile butadiene rubber (NBR) vulcanizates with different fillers and curing agents are investigated. Structure-property relationships of these grades are correlated with the additives and properties required for high-pressure gas atmospheres are evaluated. Further, the influence of the exposure to high-pressure hydrogen, i.e., hydrogen uptake and morphological changes after exposure, is evaluated. With the addition of a silica filler and a coupling agent for improved filler-matrix interfaces, similar overall properties, e.g. crosslink density, tensile strength, and storage modulus are obtained, compared to a carbon black (CB) filled grade. Density reduction after hydrogen exposure is significantly higher for CB-filled NBR, indicating higher hydrogen uptake in CB-filled rubber compared to silica filled NBR grades, or slower gas desorption. However, CB-filled specimens show to be less prone to filler migration than the silica-filled samples.
Publisher Copyright: © 2024 Hydrogen Energy Publications LLC
Keywords: Acrylonitrile butadiene rubber; Filler-rubber-interaction; High-pressure hydrogen gas; Rapid gas decompression (RGD); Sealing

Community Disaster Resilience in Serbia - Vladimir, Cvetković M.; Šišović, Vanja (2024)
In the face of natural disasters, communities are often the first line of defence, bearing the brunt of devastation while also displaying remarkable resilience in their aftermath. The ability of societies to withstand, adapt to, and recover from such crises is a testament to the strength and resourcefulness inherent in human communities. This monograph, titled "Community Disaster Resilience in Serbia," represents a concerted effort to delve into the underlying dynamics that shape a community's capacity to cope with natural disasters. Fo-cusing on Serbia, a country with a rich tapestry of social, economic, and demographic complexities, this research endeavors to unravel the intricate interplay between various socio-economic and demographic factors and community resilience. The research methodology employed in this study is grounded in a comprehensive quantitative approach, leveraging rigorous statistical analyses to explore the multifaceted dimensions of community disaster resilience. Through the administration of a carefully crafted questionnaire to 321 participants in January 2024, we sought to capture diverse perspectives and experiences, enriching our understanding of the complex socio-economic and demographic landscape of Serbia. At its core, this study recognizes the critical importance of understanding how factors such as income, employment status, marital status, education, risk perception, gender, and age intersect to influence a community's ability to withstand and recover from natural disasters. By shedding light on these nuanced relationships, we aim to equip policymakers, practitioners, and community leaders with evidence-based insights to enhance disaster preparedness and response efforts. A notable aspect of our methodology is the utilization of the snowball sampling method, which facilitated the organic expansion of our participant pool. By harnessing the networks and connections within communities, we were able to access a diverse array of voices, enriching our dataset and ensuring the robustness of our findings. Central to our inquiry is the exploration of how age, education, and gender intersect with broader social structures, capital, mechanisms, equity, diversity, and beliefs to shape community disaster resilience in Serbia. By elucidating these relationships, we aim to provide insights that can inform targeted interventions and policy initiatives aimed at bolstering community resilience across the country. This monograph holds significant importance in the field of disaster resilience research and practice for several reasons. Firstly, it fills a crucial gap in the existing literature by providing comprehensive insights into the impacts of demographic and socioeconomic factors on community disaster resilience, particularly within the context of Serbia. While studies on disaster resilience abound, there is a notable scarcity of research specifically examining the influence of demographic and socioeconomic factors on resilience in this region. Secondly, the findings of this research offer practical implications for policymakers, government agencies, non-governmental organisations, and community leaders involved in disaster management and resilience-building initiatives. By identifying key predictors and factors influencing community resilience, stakeholders can tailor interventions and strategies to address specific vulnerabilities and enhance the capacity of communities to withstand, adapt to, and recover from disasters effectively. Furthermore, the utilization of robust statistical methods and the comprehensive nature of the research design enhance the reliability and validity of the findings presented in this monograph. The employment of multivariate regression analysis allows for a nuanced understanding of the relationships between various predictors and different dimensions of community disaster resilience, providing valuable insights for both academics and practitioners. Moreover, by employing an adapted version of the ‘5Ssocial resilience framework, this research contributes to the advancement of theoretical frameworks and conceptual models in the field of disaster resilience. The application of such frameworks enables researchers and practitioners to systematically assess and evaluate the complex interplay between social, economic, and environmental factors shaping community resilience, thereby facilitating more informed decision-making and resource allocation. Overall, this monograph serves as a seminal contribution to the burgeoning field of disaster resilience, offering evidence-based insights and actionable recommendations for enhancing resilience-building efforts in Serbia and beyond. Its significance lies not only in its empirical findings but also in its potential to inform policy development, guide practice, and inspire further research in the pursuit of building more resilient and adaptive communities worldwide. As we embark on this intellectual journey, we extend our gratitude to all those who have contributed to this endeavor, from the participants who generously shared their insights to the researchers and practitioners whose expertise has guided our inquiry. We hope this monograph will serve as a valuable resource for academics, policymakers, and practitioners alike, fostering dialogue and collaboration in our collective efforts to build more resilient communities in Serbia and beyond. Conclusion: The resilience of social communities to natural disasters represents an important research area in the field of disaster studies. By enhancing the level of such resilience, the fundamental prerequisites for the safe functioning of society in various unforeseen events are achieved. This scientific monograph delves into the intricate dynamics of community disaster resilience, shedding light on the interplay between demographic and socioeconomic factors. Through a rigorous quantitative study, the research investigates how variables such as age, education, employment status, and property ownership influence the resilience of communities to disasters of varying magnitudes. Utilizing multivariate regression analysis, the study identifies key predictors across different dimensions of community disaster resilience. It uncovers nuanced insights, revealing the differential impact of demographic and socioeconomic factors on various aspects of resilience. Among the findings, age, education, employment status, and property ownership emerge as significant predictors, shaping the overall resilience profile of communities. The calculated mean value of the community disaster resilience index provides a comprehensive overview, indicating a modest level of resilience across the studied communities. Notably, the analysis highlights variations in resilience across different subscales, with social beliefs garnering the highest ratings and social structure scoring the lowest. This disparity underscores the complex nature of community resilience and the need for targeted interventions to address specific vulnerabilities. Furthermore, the research offers valuable insights into the prevalence of preventive measures adopted by communities to mitigate disaster risks. Epidemics, extreme temperatures, and storms emerge as the most common focus areas for preventive measures, reflecting societal priorities in disaster preparedness. Interestingly, the study also delves into societal perceptions of disaster resilience, revealing divergent attitudes towards different types of hazards. While epidemics, extreme temperatures, and drought are perceived to have higher resilience levels, volcanic eruptions, landslides, and tsunamis are viewed with comparatively lower confidence. This discrepancy in perception underscores the importance of understanding community attitudes and beliefs in shaping disaster resilience strategies. In essence, this monograph contributes to the growing body of knowledge on community disaster resilience by providing empirical evidence and nuanced insights into the factors influencing resilience levels. By identifying predictors, assessing resilience indices, and exploring societal perceptions, the research informs evidence-based approaches for enhancing community resilience and fostering sustainable disaster risk reduction strategies.Distinct subscales underscore variations, emphasizing the importance of targeted interventions. Positive views on response services and community leadership coexist with a generally neutral stance on disaster preparedness. Social capital reflects mutual trust, with space for increased community engagement. Social mechanisms indicate positive attitudes but underscore the need for enhanced household disaster preparedness, risk perception, and citizen disaster awareness. High scores in addressing social injustices reveal positive attitudes, but lower ratings for specific programs suggest areas for improvement. Cultural aspects demonstrate positive attitudes towards traditions, faith, and cultural values, with challenges in trust during disasters and the role of religious leaders pointing to potential improvements. Correlations between education status, marital status, and various dimensions highlight nuanced relationships impacting community disaster resilience. The study offers a basis for focused interventions across a variety of criteria and sheds light on areas that might want improvement. By adding to our knowledge of Serbian community disaster resilience, this study helps practitioners and policymakers create focused interventions and promote a more just and resilient society that can withstand a variety of calamities. Aside from that, this study significantly advances our knowledge of community (social) resilience in the face of various natural disasters, with an emphasis on the effects of demographic and socioeconomic factors. The identification of key predictors such as age, education, employment, and property ownership provides researchers with a foundation for further investigations and analyses. The research results indicate the need for differentiated approaches in studying community resilience to various types of disasters, providing new insights into complex sociodemographic factors. This paper carries significant social implications that can be utilized in the development of policies and practices to enhance community (social) disaster resilience in Serbia. These results can be used as a starting point for the creation of educational initiatives, awareness-raising campaigns, and community support systems for anticipating and responding to various calamities. Results of the analysis across various dimensions of community resilience to disasters indicate a significant role of age as a predictor of social structure. These findings can be explained by the fact that older individuals, thanks to their previous life experiences, social networks, and spiritual beliefs, contribute to shaping the social structure of the community. Their prolonged exposure to disaster-related events allows them a subtler understanding of social structures and the effectiveness of responses in such situations. Further examinations also suggest a correlation between age and dimensions such as social structure, social mechanisms, social justice and diversity, as well as social beliefs. Subsequent analysis suggests that older participants have a positive association with higher ratings for social structure, while ratings for social mechanisms, social justice and diversity, as well as social beliefs, decrease as the age of participants progresses. This trend can be attributed to factors such as accumulated life experiences, historical perspectives, and deeper involvement in communal activities over time. Concurrently, education emerges as a key predictor for the sub-scale of social capital. Participants with a high school diploma consistently rate higher across dimensions including social structure, social mechanisms, and social justice and diversity compared to those with a university degree. This positive correlation can be attributed to increased social awareness, communication skills, and a broader understanding of community dynamics that come with higher education. Additionally, participants with a university education report higher ratings for social capital, preventive measures, and perception of disaster resilience compared to those with a high school diploma. These individuals with a university education likely experience higher levels of social connectedness, engagement, and support, thus being more inclined towards taking proactive measures and showing greater resilience perception in facing disasters compared to their peers with a high school diploma. Furthermore, employment has been shown as the most significant predictor for the sub-scales of social mechanisms, social justice and diversity, while property ownership is a key predictor for the sub-scale of social beliefs. Additional analysis reveals associations between employment and various variables, including social structure, social mechanisms, social justice and diversity, as well as social beliefs. Unemployed participants often give higher ratings regarding social structure, equality/diversity, and beliefs compared to employed participants. This study further demonstrates that individuals who own personal property consistently give lower ratings across various dimensions, including social capital, social beliefs, preventive measures, and resilience to disasters, compared to individuals who own property within family ownership. Detailed analysis reveals that participants with below-average income consistently assign lower ratings across various dimensions. Specifically, compared to those with average income, participants with below-average income give lower ratings for social mechanisms, social justice and diversity, and social beliefs. Additional analysis reveals that individuals residing in households with two members usually give lower ratings to social structures, while those in households with more than four members tend to give higher ratings to social mechanisms, social justice and diversity, as well as social beliefs. Furthermore, the research indicates a correlation between marital status and ratings, with single individuals consistently giving higher ratings across different dimensions compared to those who are in a relationship or divorced. This relationship between marital status and various dimensions may indicate that the existence of singles has specific attitudes or behaviors that contribute to a more positive valuation of social capital, preventive measures, and disaster resilience. The average value of the index measuring community (social) resilience to disasters, calculated on a Likert scale from 1 to 5, is in the lower range of values. This implies that the overall level of resilience to disasters in the community is relatively moderate. The proximity of values to the lower end of the scale suggests potential room for improvement in community resilience to disasters. Further analysis shows that preventive measures are most commonly taken before dangers such as epidemics, extreme temperatures, and storms. The perception of society's resilience is highest against dangers from epidemics, followed by extreme temperatures and drought. Participants express a relatively high level of confidence in society's ability to cope with epidemics, extreme temperatures, and drought. A detailed analysis of all obtained research results indicates that the general hypothesis predicting a statistically significant correlation between socio-economic factors and social resilience to disasters can be confirmed. Based on the defined hypotheses, data analyses show and confirm two specific assertions: a) the influence of sociological factors on the level of social resilience to disasters is confirmed; b) the influence of economic factors on the level of social resilience to disasters is also confirmed. These results direct our understanding of the relationship between different aspects of socio-economic factors and the ability to withstand disasters in society. On a societal level, the results of this research point to key areas where there is a need to enhance the capacity to resist and overcome the effects of disasters. From a fairness perspective, the focus should be on the older population, as a group that has been shown to be a significant factor in social resilience. Raising awareness and providing resources for the elderly can be crucial in encouraging their active participation in the community and increasing overall social resilience. Tailoring educational campaigns and programs to groups with lower levels of education can also be part of a strategy to increase awareness and preparedness in these population groups. Education about disaster prevention and response measures can significantly impact readiness and information provision, thereby raising the level of social resilience. The scientific implications of this research can enrich the field of social sciences and disaster studies. These studies can serve as a starting point for more detailed analyses of factors contributing to social resilience. New studies can explore specific aspects of older citizens or individuals with low education, contributing to a better understanding of their role in disaster preparedness and response processes. Ultimately, the applications of the results of this research can be broad and include support for the development of policies, programs, and interventions in the field of disaster management. Scientists and practitioners can use this knowledge to better direct resources and efforts towards building a more resilient and prepared society to face the challenges of disasters.

Investigation on the Duration of Action of Mg3N2 as a Grain Refiner for AZ80 Alloy - Hösele, Thomas; Neunteufl, Ernst; Li, Jiehua (Metals, 2024)
In magnesium alloys with aluminum as an alloying component, zirconium loses its grain refinement effect as a grain refiner. Instead of zirconium, Mg3N2 can be used, and promising results have already been obtained. However, the duration of action of Mg3N2 has not been elucidated yet. The aim of this work is therefore to determine the grain size of the AZ80 alloy as a function of the duration of action of Mg3N2 and thus the economically reasonable duration of use. It was found that the Mg3N2 reaches its full effect from 30 min after a complete remelting and does not lose this grain refinement effect even after 90 min. It thus proves to be a stable and reliable grain refiner. A grain size of 146.3 ± 10.3 µm was achieved. Furthermore, a minimum tensile strength of 205 MPa with a break elongation of 5.99% was achieved.
Publisher Copyright: © 2024 by the authors.
Keywords: AZ80 alloy; grain refinement; growth restriction factor; mechanical properties; MgN; thermal analysis

Imaging hydrothermal alteration with electrical resistivity tomography in La Soufrière de Guadeloupe volcano - Mendieta, Aida; Rosas-Carbajal, Marina; Bajou, Raphaël; Baud, Patrick; Deroussi, Sébastien; Esposti Ongaro, Tomaso; Komorowski, Jean-Christophe; Kushnir, Alexandra; Villeneuve, Marlene C.; Heap, M. J. (2024)
Hydrothermal alteration plays a major role in volcanic instability. Improving techniques that allow us to better understand the timescales of alteration in active volcanoes is thus paramount. Since the reactivation of the fumarolic field at the top of the dome of La Soufrière de Guadeloupe (Guadeloupe, France) in 1992 and the expansion of its surface area in recent years, the area of study is subjected to prolonged variable alteration that has promoted past flank collapses and can also influence permeability and thus shallow depth overpressurization. During a field campaign in May 2022 we performed 25 electrical resistivity tomography (ERT) profiles in the summit of La Soufrière, next to active fumaroles and acid boiling ponds. These ERT profiles were inverted using the open-source code pyGIMLi. Thanks to the ERT profiles we are able to roughly map the altered areas to a depth of about 20 m in this zone of La Soufrière. Some of the byproducts of alteration that have been identified in La Soufrière are clays, sulfates and pyrite. Thus, we infer that the low electrical resistivity zones (<20 Ωm) correspond to alteration and high electrical resistivity (>1500 Ωm) corresponds to unaltered rock. Low electrical resistivity anomalies are observed north of the Breislack fault, near the fumaroles. The explored north-most region is characterized by higher values of electrical resistivity. We take into account ground temperature and spatial variability to interpret the electrical conductivity anomalies and we use this first high-resolution resistivity model to plan a repetition of our experiment. This time-lapse experiment will allow us to estimate the evolution of hydrothermal alteration in the volcano’s summit over a 2-year period in the context of the current ongoing multiparameter unrest.

Synthesis of Bio-Based Polyester Resins for Vat Photopolymerization 3D Printing - Cazin, Ines; Ocepek, Martin; Kecelj, Janez; Stražar, Aleš Stanislav; Schlögl, Sandra (Materials, 2024)
Driven by environmental considerations, the scientific community has directed great effort towards the synthesis of new materials derived from renewable resources. However, for photocurable resins, most commercially available building blocks still rely on petroleum-based precursors. Herein, we present a simple synthesis route for bio-based acrylate-modified polyester resins, whose viscosity is sufficiently low for processing them with vat photopolymerization 3D printing. The established synthesis route enables the gradual substitution of fossil-based raw materials with bio-based alternatives. The acid number, color and viscosity of the bio-based acrylic resins are characterized and photocurable formulations are prepared by adding a radical photoinitiator. The photopolymerization kinetics, and thermomechanical and mechanical properties of the photopolymers are investigated as a function of the resin structure and benchmarked against a commercially available petroleum-based counterpart. Finally, the processability of the new bio-based resins via digital light processing 3D printing is demonstrated and test specimens are successfully 3D printed with a resolution in the millimeter range.
Publisher Copyright: © 2024 by the authors.
Keywords: additive manufacturing; bio-based polymers; photocuring; polyester resins; vat photopolymerization 3D printing

Treatment of carbon electrodes with Ti3C2Tx MXene coating and thermal method for vanadium redox flow batteries: a comparative study - Teenakul, Kavin; Alem, Sayed Ali Ahmad; Gond, Ritambhara; Thakur, Anupma; Anasori, Babak; Khataee, Amirreza (RSC Advances, 2024)
One of the significant challenges of vanadium redox flow batteries is connected to the negative electrode where the main reaction of V(II)/V(III) and the side reaction of hydrogen evolution compete. To address this issue, we used titanium carbide (Ti3C2Tx) MXene coating via drop-casting to introduce oxygen functional groups and metals on the carbon electrode surface. Characterization through scanning electron microscopy and X-ray photoelectron spectroscopy confirmed the even distribution of Ti3C2Tx MXene on the electrodes and the presence of titanium and termination groups (–O, –Cl, and –F). The cyclic voltammetry analysis of MXene-coated electrodes showed more sharp electrochemical peaks for the V(II)/V(III) reaction than thermal-treated electrodes, even at relatively high scan rates. Notably, a relatively high reaction rate of 5.61 × 10−4 cm s−1 was achieved for the V(II)/V(III) reaction on MXene-coated electrodes, which shows the competitiveness of the method compared to thermal treatment (4.17 × 10−4 cm s−1). The flow battery tests, at a current density of 130 mA cm−2, using MXene-coated electrodes showed pretty stable discharge capacity for over 100 cycles. In addition, the voltage and energy efficiency were significantly higher than those of the system using untreated electrodes. Overall, this work highlights the potential application of MXene coating in carbon electrode treatment for vanadium redox flow batteries due to remarkable electrocatalytic activity and battery performance, providing a competitive method for thermal treatment.
Publisher Copyright: © 2024 The Royal Society of Chemistry.
Keywords: Redox Flow Battery; Carbon Materials; MXene; 2D Materials; Surface Chemistry; Functionalization

Polymer Processing Bringing Together Polymers, Metals and Ceramics - Holzer, Clemens (12th EEIGM International Conference on Advanced Materials Research, 2024)

Production of Permanent Magnets from Recycled NdFeB Powder with Powder Extrusion Moulding - Rathfelder, Stefan; Schuschnigg, Stephan; Kukla, Christian; Holzer, Clemens; Burkhardt, Carlo (Journal of Manufacturing and Materials Processing, 2024)
In the last fifteen years, several groups have investigated metal injection moulding (MIM) of NdFeB powder to produce isotropic or anisotropic rare earth magnets of greater geometric complexity than that achieved by the conventional pressing and sintering approach. However, due to the powder’s high affinity for oxygen and carbon uptake, sufficient remanence and coercivity remains difficult. This article presents a novel approach to producing NdFeB magnets from recycled material using Powder Extrusion Moulding (PEM) in a continuous process. The process route uses powder obtained from recycling rare earth magnets through Hydrogen Processing of Magnetic Scrap (HPMS). This article presents the results of tailored powder processing, the production of mouldable feedstock based on a special binder system, and moulding with PEM to produce green and sintered parts. The magnetic properties and microstructures of debinded and sintered samples are presented and discussed, focusing on the influence of filling ratio and challenging processing conditions on interstitial content as well as density and magnetic properties.
Keywords: powder extrusion moulding (PEM; metal injection moulding (MIM); production of NdFeB permanent magnets; recycling of EOL-magnets

Seismic while drilling with a diamond drill bit in project DIVE DT-1B borehole in the Ivrea-Verbano Zone (Western Alps, Italy) - Trabi, Bernd; Bleibinhaus, Florian; Greenwood, Andrew (EGU General Assembly 2024, 2024)
A unique Seismic While Drilling (SWD) experiment, whereby a diamond coring drill rig as the seismic source has been conducted in the Val d’Ossola, Western Alps, Italy. For the SWD experiment 64 3C-sensors are employed in an array at the surface and the vibrational action of coring the rock acts as an active seismic source within the borehole. The maximum offset of the sensor array is 480 m with non-uniform spacing that increases with distance. The drilling operation took place from early October until mid-December 2022 and reached a depth of approximately 580 m. The seismic sensors recorded at a sampling rate of 1 ms, which is more than sufficient for an expected frequency of up to 200 Hz. The proposed SWD experiment is to evaluate the potential and limitations of the SWD method for diamond core drilling commonly utilized in scientific drilling projects with a focus on fundamental developments of the methodology and data processing techniques. Ideally the drill-bit seismic record should produce a seismic image around the bore hole and ahead of the drill bit. First it is important to determine if a signal can be detected, and to what depth, from a diamond core drill bit. In contrast to percussion or reverse circulation drilling, the diamond core drilling method produces a very weak signal. The seismic data is also heavily contaminated by coherent and random noises generated at the drill site, including rig engines, generators and mud-pumps, vehicles, and the movement of equipment. Separation of theses coherent noises using radon transform has thus far failed and other wavefield separation methods are investigated. Using seismic interferometric methods for unknown source positions, we aim to detect the weak signal at known drill bit positions. This is promising especially at drilling depths where the drill-rig and drill-bit wave-fields are spatial or temporal separated from each other, due to their different origins and velocities. Interferograms are obtained using the cross-coherence method, which is applied to the recorded passive seismic data. These are computed from 30sec time windows of the continuous recordings and then stacked into the final interferogram to increase the signal-to-noise ratio. Instead of migration summation, semblance is measured for the interferometric migration process. For the migration process, a constant velocity model is sufficient in this hard-rock environment. The major noise sources that we image are the vibrations of the drill rig and power generator, which appear to mask the weaker signal from the drill bit. In an ongoing second experiment, we utilize grid power, reducing the noise sources to the mud-pumps, rotating string, and rig.
Keywords: Seismic while drilling; interferometry; matched field processing; source location imaging; geophysics; FWF; icdp; dive

Harmonization of Soft Power and Institutional Skills: Montenegro’s Path to Accession to the European Union in the Environmental Sector - Sudar, Srna; Cvetković, Vladimir M.; Ivanov, Aleksandar (2024)

Mapping elemental solutes at sub-picogram levels during aqueous corrosion of Al alloys using diffusive gradients in thin films (DGT) with LA-ICP-MS - Mukhametzianova, Gulnaz; Wagner, Stefan; Eskinja, Magdalena; Moshtaghi, Masoud; Mori, Gregor Karl; Prohaska, Thomas (Analytical and bioanalytical chemistry, 2024)
A novel approach using diffusive gradients in thin films (DGT) with laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) for two-dimensional mapping of elemental solute release at sub-picogram levels during aqueous corrosion of Al alloys is presented. Evaluation of different DGT gels with mixed micro-sized binding phases (polyacrylamide-Chelex-Metsorb, polyurethane (PU)-Chelex-Metsorb, PU-Chelex-Zr(OH) 4) demonstrated the superior performance of PU gels due to their tear-proof handling, low shrinkage, and compliance with green chemistry. DGT devices containing PU-Chelex-Zr(OH) 4 gels, which have not been characterized for Al sampling before, showed quantitative uptake of Al, Zn, and Cu solutes over time (t = 4–48 h) with higher Al capacity (Γ DGT = 6.25 µg cm −2) than different gels. Application of PU-Chelex-Zr(OH) 4 gels on a high-strength Al-Cu alloy (Al2219) exposed to NaCl (w = 1.5%, pH = 4.5, T = 21 °C) for 15 min in a novel piston-type configuration revealed reproducible patterns of Al and Zn co-solubilization with a spatial expansion ranging between 50 and 1000 µm. This observation, together with complementary solid-state data from secondary electron microscopy with energy-dispersive X-ray spectroscopy, showed the presence of localized pitting corrosion at the material surface. Detection limits for total solute masses of Al, Zn, and Cu were ≤0.72 pg, ≤8.38 pg, and ≤0.12 pg, respectively, for an area of 0.01 mm 2, demonstrating the method’s unique capability to localize and quantify corrosion processes at ultra-trace levels and high resolution. Our study advances the assessment of Al alloy degradation in aqueous environments, supporting the design of corrosion-resistant materials for fostering technological safety and sustainability. Graphical Abstract: (Figure presented.)
Publisher Copyright: © The Author(s) 2024.
Keywords: Aluminium; Chemical imaging; Corrosion; Diffusion; Passive sampling

Two-phase flow Thermo-Hydro-Mechanical (THM) modelling for a water flooding field case - Liu, Yuhao; Zhang, Fengshou; Weng, Dingwei; Liang, Hong; He, Chunming; Yoshioka, Keita (Rock Mechanics Bulletin, 2024)
Simulation of subsurface energy system involves multi-physical processes such as thermal, hydraulical, and mechanical (THM) processes, and requires a so-called THM coupled modeling approach. THM coupled modeling is commonly performed in geothermal energy production. However, for hydrocarbon extraction, we need to consider multiphase flow additionally. In this paper, we describe a three-dimensional numerical model of non-isothermal two-phase flow in the deformable porous medium by integrating governing equations of two-phase mixture in the porous media flow in the reservoir. To account for inter-woven impacts in subsurface conditions, we introduced a temperature-dependent fluid viscosity and a fluid density along with a strain-dependent reservoir permeability. Subsequently, we performed numerical experiments of a ten-year water flooding process employing the open-source parallelized code, OpenGeoSys. We considered different well patterns with colder water injection in realistic scenarios. Our results demonstrate that our model can simulate complex interactions of temperature, pore pressure, subsurface stress and water saturation simultaneously to evaluate the recovery performance. High temperature can promote fluid flow while cold water injection under non-isothermal conditions causes the normal stress reduction by significant thermal stress. Under different well patterns the displacement efficiency will be changed by the relative location between injection and production wells. This finding has provided the important reference for fluid flow and induced stress evolution during hydrocarbon exploitation under the environment of large reservoir depth and high temperature.
Publisher Copyright: © 2024 Chinese Society for Rock Mechanics & Engineering.
Keywords: Field-scale model; OpenGeoSys; THM coupling; Two phase flow; Water flooding

Effect of Nb incorporation in Mo2BC coatings on structural and mechanical properties—Ab initio modelling and experiment - Zenisek, Jaroslav; Soucek, P.; Ondračka, Pavel; Czigány, Zsolt; Buršíková, V.; Holec, David; Balazsi, K.; Vasina, Petr (Acta materialia, 2024)
This article presents theoretical and experimental findings on the stability of orthorhombic (Mo 1−xNb x) 2BC phase in magnetron sputtered coatings, where molybdenum is gradually replaced by niobium. Magnetron co-sputtering of Mo 2BC and Nb 2BC targets was used to best preserve the metal/non-metal ratio of 1/1. The theoretical calculations were based on replacing Mo atoms in orthorhombic Mo 2BC cell, thus creating a (Mo 1−xNb x) 2BC solid solution. It is predicted to be stable up to 37.5% of Mo atoms replaced by Nb, at which point also the elastic modulus and the shear modulus are the highest. Simultaneously, the enthalpy of formation of this material suggests that it should be more stable than, e.g. the commonly used and studied TiAlN. Experiments have confirmed that orthorhombic (Mo 1−xNb x) 2BC does not form at high Nb contents, and fcc NbC-like structure was observed instead. All coatings were shown to be columnar with grains in the nanometre range with amorphous regions between the columns. This led to reduced stability of the orthorhombic Mo 2BC-like phase compared to the theoretical calculations. At the limit of the stability of the orthorhombic cell, the hardness of the coating was enhanced by 25% and the elastic modulus by 60%. Ab initio calculations indicate that lattice strain is responsible for the mechanical properties’ enhancement.
Publisher Copyright: © 2024 The Authors

Informing deep geothermal reservoir rock mass properties from drilling data - experience from IDDP-1 - Villeneuve, Marlene C.; Kennedy, Ben; Mortensen, Anette; Saubin, Elodie; Hammoud, Aliaa (Krafla Magma Testbed Symposium, 2024)

A sequential lumped kinetic modelling approach for the co-pyrolysis of plastic mixtures with a heavy refinery intermediate product in a tubular reactor - Lorbach, Sebastian-Mark; Lechleitner, Andreas; Schubert, Teresa; Lehner, Markus (Reaction chemistry & engineering, 2024)
The knowledge of reaction rates and reaction pathways is essential for the upscaling of laboratory- and pilot-sized plants to full scale industrial processes. Over the last decades lumped kinetic modelling became the standard modelling approach for cracking reactions of hydrocarbon blends. In this paper a sequential nine-lump kinetic model is developed. The model allows for a fully automatic calculation of the kinetic parameters and efficient implementation in process simulation software like PetroSim. The kinetic parameters were calculated using experiments in a laboratory sized tubular reactor with a mass throughput between 600 g h−1 and 2500 g h−1 and temperatures between 440 °C and 530 °C at a pressure of 15 bar. A feedstock of 30 wt% plastic in different blends (PP, LDPE, HDPE) and 70 wt% carrier medium, a heavy refinery intermediate product, was used for the fitting and evaluation of the kinetic model. The results were evaluated with a set of experimental data, independent from the set used for the fitting. A residual analysis shows that the model has good predictive capabilities and can be used to simulate the cracking reaction of plastics in a plug flow reactor over a broad range of operating conditions.
Publisher Copyright: © 2024 The Royal Society of Chemistry.
Keywords: chemical recycling; plastic waste; plastic to oil; feedstock recycling; co-pyrolysis

Functionalization of PTFE substrates with quaternary ammonium groups - Bandl, Christine; Kern, Wolfgang; Ranz, Matthias; Grabner, Bianca (Applied surface science, 2024)
Hydrogen produced by electrolysis using renewable energy sources offers a zero-emission alternative to fossil-based sources providing high efficiencies in all energy sectors. Anion Exchange Membrane Water Electrolysis (AEM-WE) combines the advantages of the established technologies, alkaline (AEL) and proton exchange membrane (PEM) water electrolysis. However, AEM-WE still requires optimization, especially with regard to the membrane, catalysts and electrode structure. In this contribution we focus on the improvement of PTFE-based binders for AEM-WE membranes, which provide high chemical stability but lack the required ion conductivity. Thus, the functionalization of PTFE towards quaternary ammonium moieties (QAS) was investigated employing two approaches: (i) NH3-plasma treatment and (ii) O2-plasma with subsequent coupling of aminosilanes. Finally, the surface coupled amino groups were converted into QAS via alkylation with iodomethane (CH3-I), introducing ion conductivity. Successful functionalization was proved by X-ray photoelectron spectroscopy (XPS), displaying changes in the surface composition of PTFE surfaces such as the introduction of amino groups at the expense of fluorine, and the increase in surface carbon content upon alkylation. Furthermore, contact angle measurements revealed increased wettability with water due to the introduction of the polar surface functionalities, while zeta potential measurements confirmed the increase of positive surface charges along the modification processes.
Publisher Copyright: © 2024 The Author(s)

Overview of application of automated SEM/EDS measurements for inclusion characterization in steelmaking - Ramesh Babu, Shashank; Michelic, Susanne Katharina (MetalMat (e-only), 2024)
The scanning electron microscope equipped with an energy dispersive spectroscopy (SEM/EDS) is considered as a state-of-the-art characterization tool to determine the morphological features and the chemical composition of non-metallic inclusions in steel. Such a characterization is pivotal to assessing the steel quality, which influences the properties of end products. This paper offers a comprehensive review of the SEM/EDS system, tracing its historical developments and methodological advancements by various research groups which have contributed to non-metallic inclusion analysis. Then the discussions transition to developments that have matured the SEM/EDS platform. The paper highlights selected examples utilizing the SEM/EDS to examine inclusions across various steel grades and at different stages of the metallurgical process. Finally, latest advancements in integrating machine learning techniques to expedite the analysis process were discussed.
Keywords: SEM; non-metallic inclusions; steel; review

Influence of corrosion fatigue on the stress gradient effect of the aluminium alloy EN AW-6082 T6 - Schönowitz, Markus; Maier, Bernd; Grün, Florian (International Journal of Fatigue, 2024)
This study investigates the influence of corrosion fatigue on the fatigue strength of the aluminium alloy EN AW-6082 T6 with regard to the stress gradient. The experimental design involves varying loading conditions and specimen geometries to facilitate testing under three distinct stress gradients: tension/compression (0 mm -1), rotary bending (0.2 mm -1), notched rotary bending (5.3 mm -1). Reference constant loading tests in air as well as continuously irrigated corrosion fatigue tests in a 5 wt% NaCl-solution are conducted with a constant stress ratio of R =−1. The results reveal a substantial reduction in fatigue strength due to corrosion fatigue across all three stress gradients. The slope of the S-N curves drops by a factor of at least two and no second slope of the S-N curves is found within the tested load cycle range (up to 10 7). The study demonstrates a significant increase in the support factor for tests conducted in the corrosive environment. This discrepancy becomes more pronounced towards higher stress gradients and lower load cycle numbers. The application of the support factor derived from tests in a non-corrosive atmosphere is shown to be conservative, emphasizing the significance of accounting for corrosion effects in assessing fatigue behaviour.
Publisher Copyright: © 2024

Survey of Industrial Excess Heat Potentials in Austria - Hammer, Andreas; Lachner, Elisabeth; Kienberger, Thomas (3rd International Sustainable Energy Conference 2024, 2024)
In the research and service study for the Energy Transition 2050 program, the tech-nical excess heat potentials for both energy-intensive and energy-extensive Austrian industry were surveyed. A bottom-up approach for most of the energy-intensive industry and a top-down approach for most of the energy-extensive industry were used by the consortium under the leadership of the Chair of Energy Network Technology EVT of Montanuniversität Leoben. The surveyed potentials were classified according to temperature level of excess heat, origin from the process, spatial occurrence and industry sectors. In order to estimate the future in-dustrial excess heat potentials, a database of the innovation network "New Energy for Industry" (NEFI) was used. For the geographical localization, the results were integrated into the existing Austrian Heat Map, which enables a comparison with heat demand densities and existing heat-ing networks. A technical excess heat potential of about 34 TWh could be identified. Thereof, about 300 companies of the energy-intensive industry, which were mainly calculated by the bottom-up method, account for a technical excess heat potential of about 26 TWh. For the energy-extensive industry, an excess heat potential of about 4 TWh was identified for more than 1500 companies using mostly the statistical top-down method. Due to existing know-how in the consortium, the technical excess heat potentials of more than 600 sewage treatment plants could also be estimated at approx. 4 TWh.
Keywords: excess heat; waste heat; Industry; Excess heat; Waste Heat; Industry

Sustainable Earthquake Preparedness: A Cross-Cultural Comparative Analysis in Montenegro, North Macedonia, and Serbia - Grozdanić, Goran; Cvetković, Vladimir; Lukić, Tin; Ivanov, Aleksandar (sustainability, 2024)
Authorities and governmental bodies strongly emphasize the importance of residents preparing for natural disasters, particularly underscoring the significance of readiness for geophysical hazards like earthquakes. In this study, which represents comparative quantitative research, the levels and predictors of the impact on preparedness for earthquake-induced disasters in South-Eastern European countries such as Montenegro, North Macedonia, and Serbia are examined. Using the snowball sampling technique (online questionnaire), a survey of 1245 respondents (Montenegro (n = 400), North Macedonia (n = 345), and Serbia (n = 500) was conducted from February 2023 to February 2024. The paper is based on the central hypothesis that the most significant predictor of earthquake preparedness in Montenegro, North Macedonia, and Serbia is age, followed by education and gender. Multivariate regression analysis was used to determine the extent to which five scores of the subscales (household preparedness, community preparedness, disaster preparation, earthquake risk awareness, and reinforced house) were associated with seventh demographic and socio-economic variables. In addition to the mentioned analysis, other statistical analyses such as t-test, one-way ANOVA analysis, and Pearson correlation were also utilized. The results indicate that age emerges as a predictor in various aspects of earthquake-induced disaster preparedness and awareness in most models, followed by education and gender. These findings confirm the significance of respondents’ age in determining levels of preparedness and earthquake awareness. Overall, in North Macedonia, respondents recorded the highest ratings (M = 3.52) for household preparedness for earthquakes, compared to Serbia (M = 3.26) and Montenegro (M = 2.98), where the lower ratings were recorded. Research findings, taking into account cultural characteristics, can serve as a basis for the development of targeted interventions, strategies, policies, and programs aimed at improving the level of societal preparedness for earthquake-induced disasters.
Publisher Copyright: © 2024 by the authors.
Keywords: cross-cultural characteristics; earthquake preparedness; Montenegro; natural disaster; North Macedonia; risk; Serbia; sustainable development

Microscopic fracture toughness of notched porous sintered Cu micro-cantilevers for power electronics packaging - Hu, Dong; Du, Leiming; Alfreider, Markus; Fan, Jiajie; Kiener, Daniel; Zhang, Guoqi (Materials Science and Engineering: A, 2024)
To fulfill the high-temperature application requirement of high-power electronics packaging, Cu nanoparticle sintering technology, with benefits in low-temperature processing and high-melting point, has attracted considerable attention as a promising candidate for the die-attach interconnect. Comprehensive mechanical characterization of the sintered layer at a microscale is necessary to deepen the understanding of the fracture behavior and improve the reliable design of materials. In this study, microscale cantilevers with different notch depths were fabricated in a 20 MPa sintered interconnect layer. Continuous dynamical fracture testing of the microcantilevers was conducted in situ in a scanning electron microscope to detail the failure characteristic of the porous sintered structure. The microscopic fracture toughness of different notched specimens was obtained from the J-integral in the frame of elastic-plastic fracture mechanics. Specimens with deeper notches presented higher resistance to crack extension, while geometry factors of notch-to-width ratio between 0.20 and 0.37 exhibited a relatively stable microscopic fracture toughness ranging from 3.2 ± 0.3 to 3.6 ± 0.1 MPa m1/2.
Publisher Copyright: © 2024 The Authors
Keywords: Continuous stiffness testing; Cu nanoparticles sintering; Elastic-plastic fracture mechanics; Microscopic fracture toughness

Valorisation of metallurgical residues via carbothermal reduction - Krammer, Anna; Doschek-Held, Klaus; Steindl, Florian Roman; Weisser, Katharina; Gatschlhofer, Christoph; Juhart, Joachim; Wohlmuth, Dominik; Sorger, Christoph (Waste management & research, 2024)
The decarbonisation of the steel and cement industry is of utmost importance in tackling climate change. Hence, steel production in modern integrated steel mills will be shifted towards electric arc furnaces in the future, in turn causing dwindling supplies of blast furnace slag, which is used as a supplementary cementitious material inter alia to reduce the CO2 emissions of cement production. Achieving a sustainable circular steel and building material economy requires the valorisation of currently landfilled steel slags and investigating utilisation options for electric arc furnace slag, which is increasingly being generated. For this purpose, different metallurgical residues and by-products were treated by carbothermal reduction in an inductively heated graphite crucible and then rapidly cooled by wet granulation, yielding a slag fraction similar to granulated blast furnace slag and a metal fraction valuable as a secondary raw material. A spreadsheet-based model was developed to calculate residue combinations to accomplish target compositions of the slag and metal fractions to fulfil previously identified requirements of the targeted cementitious and ferrous products. The results demonstrate the high accuracy of the model in predicting the properties (e.g. main oxide composition) of the generated slag and metal fraction, which fulfil the needed requirements for their use as (i) a supplementary cementitious material and (ii) a secondary raw material in steel production.
Publisher Copyright: © The Author(s) 2024.
Keywords: carbothermal reduction; circular economy; CO-reduced cement; industrial residue; metal recovery; metallurgical residues; steel slags; Supplementary cementitious material

A Comprehensive Numerical Study of a Wedge-Shaped Textured Convergent Oil Film Gap - Scharf, Raphael; Maier, Michael; Pusterhofer, Michael; Grün, Florian (Lubricants, 2024)
The modification of surface geometries to reduce friction is an omnipresent topic of research. In nature, different low-friction surfaces, such as fish skins, exist. To transfer this knowledge to technical applications, for example, to journal or plain bearings, many numerical and experimental studies of textured surfaces have been performed. In this work, the influence of the geometric parameters (texture length , width , angle and start position ) of a wedge-shaped texture on three different convergent oil film gaps was analyzed in full-film lubrication and compared with untextured oil film gaps. With the aid of a CFD (computational fluid dynamics) model, a comprehensive variation study was conducted, and the best-performing wedge-shaped texture was determined. The results show that an open texture at the inlet provides the largest improvement. Furthermore, it can be observed that the optimal relative texture width and absolute inlet height for the three investigated oil film gaps are similar. In contrast to the volume flow of the untextured geometry, the volume flow of the textured one is significantly higher, especially that perpendicular to the movement direction.

Christian Doppler Laboratory for selective recovery of minor metals using innovative process concepts - Steinlechner, Stefan (Science 4 Technology @MUL, 2024)

Types and quantities of Critical Raw Materials needed to meet growing demands in the European Union and worldwide - Melcher, Frank (2024)

Structure–Property Relations in Pb-Supersaturated Metastable Sn-Rich Pb-Sn Alloys - Friák, Martin; Cipek, Petr; Pavlu, Jana; Zobac, Ondrej; Roupcova, Pavla; Miháliková, Ivana; Holec, David; Msallamova, Sarka; Michalcova, Alena (Metallurgical and materials transactions. A, Physical metallurgy and materials science, 2024)
We have performed a theoretical study of three polymorphs of Pb-supersaturated Sn-rich Pb-Sn alloys with the -Sn, -Sn, and a simple-hexagonal -Sn structure employing quantum-mechanical calculations. We focused on structure–property relations in the case of lattice parameters, thermodynamic stability, elastic properties, and mechanical stability as well as electronic-structure density of states. Compositional trends in structural, thermodynamic, and electronic properties were found nearly linear. Our study also sheds new light on a decades-long controversy surrounding the existence of -phase and -phase supersaturated Sn-rich Pb-Sn alloys. We suggest that the experimental difficulties when synthesizing them are caused by their high formation energy and mechanical instability of the -phase.

Too much consumption – too little resources?! Types and quantities of Critical Raw Materials needed to meet growing demands on the globe - Melcher, Frank (2024)

MetamaterialFinder - Fleisch, Mathias; Thalhamer, Andreas; Schlögl, Sandra; Fuchs, Peter Filipp; Pinter, Gerald; Berer, Michael (Advances in Engineering Software, 2024)
Mechanical metamaterials have gained a lot of research interest over the last years due to their unusual mechanical properties and potential use for structural applications. However, the design and analysis of mechanical metamaterials remains challenging and time-consuming. Herein, we present a software framework for automated generation, finite element modeling and analysis of extruded mechanical metamaterials based on simple closed curves. By generalizing extruded unit cells with pores defined by simple closed curves, a wide variety of existing and novel metamaterials can be created and analyzed. Each pore can either be empty or filled with one or more materials, resulting in single- or multi-material metamaterials. Since part of the mechanical response of a metamaterial is defined by the geometric parameters of a unit cell, parameter studies are directly integrated into the framework. Examples of well-established mechanical metamaterials were used as benchmark structures and compared to their analytical solutions. We also demonstrate how generalized curves can further improve the mechanical properties of these structures, for example the load bearing capabilities and range of Poisson's ratios. Furthermore, newly developed single- and multi-material designs of mechanical metamaterials with tunable Poisson's ratio are presented and analyzed with the proposed framework. The framework is implemented in Python, executed via ABAQUS and allows for unit-cell based homogenization and full-size 2D and 3D simulations. The scripts are made open source and publicly available.
Publisher Copyright: © 2024
Keywords: Automated design; Cellular material; Finite element analysis; Mechanical metamaterials; Poisson's ratio

Methanoldampfreformierung mittels Perowskit-basierter Oxide: Transformation des Energiesektors für eine nachhaltige Zukunft - Berger, Tobias (2024)

NOx Postprocessing for industrial combustion processes - Spijker, Christoph; Swaminathan, Senthilathiban; Raonic, Zlatko; Raupenstrauch, Harald (2024)

Nanoparticles bearing germanium based photoinitiators at their surface: Preparation and use in grafting-from photopolymerization reactions - Müller, Matthias; Drusgala, Manfred; Fischer, Roland C.; Kern, Wolfgang; Haas, Michael; Bandl, Christine (Applied surface science, 2024)
In recent decades, there has been a growing interest in surface modifications utilizing “grafting-from” techniques within both industrial and academic fields. Among others, this technology continues to drive innovation in biomedicine, enabling the design and fabrication of advanced materials and devices with tailored properties for a wide range of applications, from regenerative medicine and drug delivery to diagnostics and therapeutics. This strategy relies on the covalent attachment of (photo)initiating species to surfaces. The coupled initiators are exploited to produce reactive sites such as radicals upon exposure to heat or light. Subsequently, polymerization reactions are induced, leading to surface coupled polymer brushes. In order to provide new perspectives in surface modification techniques, we present a novel and unique method for producing mesoporous organic/inorganic hybrid nanoparticles via the “grafting-from” method. This was accomplished by immobilizing a novel, low-toxic and visible light sensitive photoinitiator (based on triacylgermanium moieties) onto silica nanoparticles. Surface-initiated photopolymerizations of styrene and acrylate monomers were conducted to produce polymer shells on the surface of the nanoparticles. The grafted layers had a thickness in the range of 6–12 nm. Furthermore, the polymer grafting density is discussed in detail ranging between 0.17 and 0.23 chains per square nanometer.
Publisher Copyright: © 2024 The Authors
Keywords: Germanium-based photoinitiators; Initiator immobilization; Low-toxic initiators; Organic–inorganic hybrid materials; Polymeric shell; Silica nanoparticle modification; Surface-initiated photopolymerization

Recovery of Cobalt, Nickel, and Lithium from Spent Lithium-Ion Batteries with Gluconic Acid Leaching Process: Kinetics Study - Gerold, Eva; Lerchbammer, Reinhard; Antrekowitsch, Helmut (Batteries, 2024)
The demand for lithium-ion batteries (LIBs) is driven by environmental concerns and market growth, particularly in the transportation sector. The EU’s push for net-zero emissions and the European Green Deal accentuates the role of battery technologies in sustainable energy supply. Organic acids, like gluconic acid, are explored for the eco-friendly leaching of valuable metals from spent batteries. This study investigates leaching kinetics using gluconic acid (hydrolyzed glucono-1.5-lacton), analyzing factors such as temperature, acid concentration, particle size, and reaction time. Results reveal the temperature’s influence on leaching efficiency for cobalt, nickel, and lithium. The mechanism for Co follows a surface chemical reaction model with an activation energy of 28.2 kJ·mol −1. Nickel, on the contrary, shows a diffusion-controlled regime and an activation energy of 70.1 kJ·mol −1. The reaction of leaching Ni and Co using gluconic acid was determined to be first-order. The process within this environmentally friendly alternative leaching agent shows great potential for sustainable metal recovery.
Publisher Copyright: © 2024 by the authors.
Keywords: gluconic acid; kinetics study; lithium-ion batteries; recycling; sustainability

ConForce - Rettl, Matthias; Frankl, Siegfried Martin; Pletz, Martin; Tauscher, Markus; Schuecker, Clara (SoftwareX, 2024)
ConForce is a tool for evaluating nodal configurational forces (CF) from FEM results. ConForce supports 2D plane strain and 3D volume elements in a solver-independent manner. Furthermore, large displacements in static load cases are considered. ConForce accesses previously generated and compiled C code from Python via a C code binding. This compiled C code is provided for predefined element types, but can be regenerated for other element types. ConForce also includes an Abaqus plug-in with a graphical user interface. This Abaqus plug-in allows to easily add CF to the Abaqus output file.
Publisher Copyright: © 2024 The Authors
Keywords: Abaqus; Configurational forces; Finite element method; Fracture mechanics

Brittleness reduction of low-carbon Al2O3-C refractories with in-situ formation MgAl2O4/CNTs layer between aggregate and matrix - Luo, Jiyuan; Jin, Shengli; Chong, Xiaochuan; Ding, Donghai; Xiao, Guoqing (Journal of the European Ceramic Society, 2024)
This research was supported by the National Natural Science Foundation of China (NO. 52272027, 52372034); Key R&D Project in Shaanxi Province (2022GY-421); Outstanding Doctorate Dissertation Cultivation Fund of Xi'an University of Architecture and Technology (2021XYBPY014); and the China Scholarship Council. The authors would like to thank Dr. Chaowei Guo in Center for Advancing Materials Performance from the Nanoscale of Xi'an Jiaotong University for helping in the SEM observations.
Keywords: In-situ interfacial layer; Low-carbon AlO-C refractories; MgAlO/CNTs; Wedge splitting test

Building Information Modeling in the Execution Phase of Conventional Tunneling Projects - Huymajer, Marco; Melnyk, Oleksandr; Wenighofer, Robert; Huemer, Christian; Galler, Robert (Tunnelling and Underground Space Technology, 2024)
Building Information Modeling (BIM) has become the key technology for the digital transformation of the architecture, engineering, and construction (AEC) sector. The Industry Foundation Classes (IFC), as an open and vendor-neutral data model, play an essential role in this transformation. Despite all the recent advances of BIM, tunneling needs to catch up with other AEC sectors adopting digital technologies. Currently, IFC is mainly used to capture information directly connected to the structural elements of the final tunnel but rarely as a means to document the tunnel excavation and support. This article proposes an IFC-driven process for the execution phase of conventional tunneling projects by extending the usage of IFC to information about the process, labor, equipment, and employed material. The proposed process is evaluated by a case study demonstrating how to represent data from a conventional tunneling project by IFC. The results show that IFC provides the necessary concepts to express the data of the execution phase of conventional tunneling projects. Implementing an IFC-driven process in this phase significantly contributes to the digital transformation of tunneling projects.
Publisher Copyright: © 2024 The Author(s)
Keywords: Building Information Modeling; Tunneling; Industry Foundation Classes; Construction phase; Digitalization; BIM; IFC; Drill and blast; Conventional tunneling

CO2-Nutzbarmachung mit Citizen Scientists – Ein Sparkling Science 2.0 Projekt - Ruh, Thomas; Bartl, Patrizia; Messner, Martina; Jantscher, Andreas; Lorenz, Harald; Erlebach, Christian; Rameshan, Christoph (24. Österreichischer Klimatag 2024, 2024)

CO2-Nutzbarmachung mit Citizen Scientists – Ein Sparkling Science 2.0 Projekt - Ruh, Thomas; Bartl, Patrizia; Messner, Martina; Jantscher, Andreas; Lorenz, Harald; Erlebach, Christian; Rameshan, Christoph (24. Österreichischer Klimatag 2024, 2024)

Digitale Abfallanalytik: Online-Bestimmung der Materialzusammensetzung und Qualität - Kandlbauer, Lisa; Sarc, Renato (Österreichische Abfallwirtschaftstagung, 2024)

Dual-Wavelength Vat Photopolymerization 3D Printing with Hybrid Acrylate-Epoxy Resins - Cazin, Ines; Plevová, Kateřina; Alabiso, Walter; Vidović, Elvira; Schlögl, Sandra (Advanced Engineering Materials, 2024)
Dual-wavelength vat photopolymerization 3D printing represents a convenient technology for the fabrication of objects with heterogeneous and locally controlled mechanical properties. By using two λ-orthogonal cross-linking reactions, it is possible to produce soft and stiff photopolymers with a single resin vat by switching the light source. Herein, hybrid acrylate-epoxy resins are selectively cured by using either visible or UV light. At 405 nm, a free radical curing of the acrylate monomers is induced while irradiation with 365 nm triggers an additional cationic ring opening reaction of the epoxy monomer yielding interpenetrating photopolymer networks. In a comprehensive approach, the influence of the resin composition and the applied wavelength on cure kinetics, film morphology, (thermo)mechanical properties, and printability are studied. Fully separated as well as homogenous network morphologies are obtained depending on the ratio between acrylate and epoxy monomers, cure rate and applied light source (405 vs 365 nm). In general, glass transition temperature, stiffness, and tensile strength of the photopolymers increase with rising epoxy content. In contrast, a higher epoxy concentration in combination with a higher amount of the cationic photoinitiator compromises on the system's orthogonality, giving rise to the important role of the resin composition in dual-wavelength vat photopolymerization 3D printing.
Publisher Copyright: © 2024 Wiley-VCH GmbH.
Keywords: dual-wavelength vat photopolymerization 3D printings; heterogeneous properties; hybrid radical/cationic photopolymers; multi-materials; polymer morphologies

Recycling von verbrauchten Al-Kaffeekapseln - Wibner, Stefan; Samberger, Sebastian; Antrekowitsch, Helmut (2024)

Strategische Flexibilität im Fokus - Zawodnik, Vanessa; Pfleger, Jasmin; Reiter, Jana; Pfleger-Schopf, Kerstin; Zaversky, Martin; Kienberger, Thomas (EnInnov 2024 | 18. Symposium Energieinnovation: "Europas Energiezukunft: Sicher, leistbar, sauber?!", 2024)
Conference code: 18

Strategische Flexibilität im Fokus - Zawodnik, Vanessa; Pfleger, Jasmin; Reiter, Jana; Pfleger-Schopf, Kerstin; Zaversky, Martin; Kienberger, Thomas (Eine qualitative Analyse energieintensiver Industriestandorte in Österreich, 2024)

Subduction zone-related metasomatism of Devonian oceanic lithosphere - Ahmed, Ahmed H.; Hamdy, Mohamed M.; Meisel, Thomas C. (Lithos, 2024)
The serpentinized peridotite bodies found in gneisses of the Sowie Mountains Block (SMB) in the Central Sudetes of SW Poland (NE segment of the Bohemian massif) are significanly metasomatized. Mineral chemical and whole-rock geochemical data combined with Rb-Sr-Sm-Nd-O-H isotope data suggest that these peridotites are refractory oceanic mantle relics from supra-subduction zone to mid-ocean ridge. They and the nearby Devonian (∼400 Ma) ophiolitic ultramafic rocks most probably came from the same mantle source. The studied peridotites are all rich in Ti, LREE and FME, except for a few that are slightly depleted in LREE. Mineralogical changes include formation of metasomatic poikilitic amphiboles and olivine, as well as metamorphic Cpx and Opx. Mixing with metasomatic sulfide-rich liquids and PPGEs (Rh, Pt, and Pd) enrichment are also supposed. The εNd and 87Sr/86Sr ratios are similar to the compositions of HIMU, EM2, and continental basalt, indicating that the depleted mantle protolith was commonly mixed with components of subducted oceanic crust and rare continental crust input. Also, the δ18O values of separated amphiboles are comparable to metasomatic fluids derived from subducted oceanic slab. The contrasting δ18O and δD values of amphibole and serpentine minerals show that serpentinization fluids are not the amphibole-forming agent. The metasomatism of the investigated peridotites most likely occurred as a result of their emplacement in the SMB, concurrently with the SMB's HT-HP metamorphism.
Publisher Copyright: © 2024 Elsevier B.V.
Keywords: Amphibole-bearing peridotites; Metasomatism; Rb-Sr-Sm-Nd-O-H isotope; Sowie Mountains Block (SMB); SW Poland

Towards 3D-printed alumina-based multi-material components with enhanced thermal shock resistance - Schlacher, Josef Christian; Geier, Sebastian; Schwentenwein, Martin; Bermejo, Raul (Journal of the European Ceramic Society, 2024)
A novel architectural design is introduced which utilizes the layer-by-layer capabilities of the vat photopolymerization 3D printing process to fabricate multi-material ceramic components with improved thermal shock resistance. The combination of 3D-printed alumina-zirconia (ZTA) with alumina (A) layers generates compressive residual stresses in the embedded alumina regions during cooling down from sintering. Thermal shock tests in water are performed on samples at different maximum temperatures and the strength degradation of the multi-material design is investigated and compared to the reference monoliths. Experimental results show that the retained strength of the multi-material ceramic after thermal shock is twice as high as that of the monoliths, associated with the crack arrest capability of the embedded layers. The concept is demonstrated on 3D-printed multi-ceramic blades for potential high temperature applications, showing enhanced “damage-tolerance” against thermal shock cracks. These findings open the path for fabricating reliable ceramic components using the vat photopolymerization process.
Publisher Copyright: © 2023 The Authors
Keywords: Additive manufacturing; Multi-material; Residual stresses; Thermal shock; Vat photopolymerization

Tübbinggroßversuche mit optimierter Krafteinleitung - Kühbacher, Manuel; Evangelatos, Alexandros; Galler, Robert (Beton- und Stahlbetonbau, 2024)
Abstract Beim Tunnelbau mittels geschildeter Vortriebsmaschinen dienen Tübbinge zur Sicherung des Hohlraums. Es ist daher unerlässlich, Kenntnis über deren statische Tragfähigkeit und Verhalten bei Belastung vorweisen zu können. Die einzelnen Tübbinge bilden im eingebauten Zustand einen Ring aus, auf welchen die unterschiedlichsten Belastungen aus dem umliegenden Gebirge einwirken. Für die an der Montanuniversität Leoben durchgeführten Großversuche im Realmaßstab wurde eine kombinierte Krafteinleitung nachgebildet, um eine realistische Belastung eines Tübbings zu simulieren. Um die aus dem Ringschluss resultierenden Normalkräfte im Querschnitt hervorzurufen, wird eine Kraft in horizontaler Richtung aufgebracht. Bei Erreichen dieses Belastungsniveaus wird in weiterer Folge die Vertikalkraft bis zum Versagen des Bauteils gesteigert, wobei die horizontale Einspannung konstant gehalten wird. Aufgrund der spezifischen Tübbinggeometrie ist während des Einleitens der Horizontalkraft auch gleichzeitig eine Vertikalkraft notwendig, um ein Ausknicken des Tübbings zu verhindern. Diese erforderliche Kraft kann mit einer numerischen Simulation oder alternativ dazu mittels herkömmlicher statischer Berechnung in vereinfachter Form ermittelt werden, welche in der vorliegenden Arbeit aufgezeigt wird. Es werden unterschiedliche Überlegungen dazu aufgezeigt und anschließend gegenübergestellt.
Publisher Copyright: © 2023 Ernst & Sohn GmbH.
Keywords: Biegemoment; optmierte Versuchsdurchführung; Tübbinge; Tübbinggroßversuch; Tunnelauskleidung

WEGE ZUR KLIMANEUTRALITÄT IN ÖSTERREICHS INDUSTRIE - Gradwohl, Christopher; Kienberger, Thomas (2024)

Impact Characteristics and Repair Approaches of Distinct Bio-Based Matrix Composites: A Comparative Analysis - Ravindran, Bharath; Agathocleous, Timotheos; Oswald-Tranta, Beata; Fauster, Ewald; Feuchter, Michael (Journal of composites science, 2024)
Increasing global concerns regarding environmental issues have driven significant advancements in the development of bio-based fiber reinforced polymer composites. Despite extensive research on bio-composites, there remains a noticeable gap in studies specifically addressing the challenges of repairing bio-composites for circular economy adoption. Traditional repair techniques for impacted composites, such as patching or scarf methods, are not only time-consuming but also require highly skilled personnel. This paper aims to highlight cost-effective repair strategies for the restoration of damaged composites, featuring flax fiber as the primary reinforcement material and distinct matrix systems, namely bio-based epoxy and bio-based vitrimer matrix. Glass fiber was used as a secondary material to validate the bio-based vitrimer matrix. The damage caused specifically by low impact is detrimental to the structural integrity of the composites. Therefore, the impact resistance of the two composite materials is evaluated using instrumented drop tower tests at various energy levels, while thermography observations are employed to assess damage evolution. Two distinct repair approaches were studied: the resin infiltration repair method, employing bio-based epoxy, and the reconsolidation (self-healing) repair method, utilizing the bio-based vitrimer matrix. The efficiency of these repair methods was assessed through active thermography and compression after impact tests. The repair outcomes demonstrate successful restoration and the maintenance of ultimate strength at an efficiency of 90% for the re-infiltration repair method and 92% for the reconsolidation repair method.
Publisher Copyright: © 2024 by the authors.
Keywords: bio-based polymers; bio-composite; compression after impact (CAI); resin reinfiltration; self-healing; vacuum assisted resin infusion (VARI)

The Roles of Impurities and Surface Area on Thermal Stability and Oxidation Resistance of BN Nanoplatelets - Kostoglou, Nikolaos; Stock, Sebastian; Solomi, Angelos; Holzapfel, Damian M.; Hinder, Steven J.; Baker, Mark; Constantinides, Georgios; Ryzhkov, Vladislav; Maletaskic, Jelena; Matovic, Branko; Schneider, Jochen M.; Rebholz, Claus; et al. (Nanomaterials, 2024)
This study considers the influence of purity and surface area on the thermal and oxidation properties of hexagonal boron nitride (h-BN) nanoplatelets, which represent crucial factors in high-temperature oxidizing environments. Three h-BN nanoplatelet-based materials, synthesized with different purity levels and surface areas (~3, ~56, and ~140 m 2/g), were compared, including a commercial BN reference. All materials were systematically analyzed by various characterization techniques, including gas pycnometry, scanning electron microscopy, X-ray diffraction, Fourier-transform infrared radiation, X-ray photoelectron spectroscopy, gas sorption analysis, and thermal gravimetric analysis coupled with differential scanning calorimetry. Results indicated that the thermal stability and oxidation resistance of the synthesized materials were improved by up to ~13.5% (or by 120 °C) with an increase in purity. Furthermore, the reference material with its high purity and low surface area (~4 m 2/g) showed superior performance, which was attributed to the minimized reactive sites for oxygen diffusion due to lower surface area availability and fewer possible defects, highlighting the critical roles of both sample purity and accessible surface area in h-BN thermo-oxidative stability. These findings highlight the importance of focusing on purity and surface area control in developing BN-based nanomaterials, offering a path to enhance their performance in extreme thermal and oxidative conditions.
Publisher Copyright: © 2024 by the authors.
Keywords: hexagonal boron nitride; nanomaterials; nanoplatelets; nanostructures; oxidation resistance; purity; surface area; thermal stability

Deep reinforcement learning algorithm for wellbore cleaning across drilling operation - Keshavarz, Sahar; Elmgerbi, Asad; Thonhauser, Gerhard (2024)
We propose a novel framework for real-time drilling operation planning updates using deep reinforcement learning algorithm, enabling drilling process reactions to be automated. The framework includes a decision tree algorithm to represent the environment dynamic changes based on the imposed actions parallel to a Gaussian process algorithm to quantify the safe operating window in real-time. Combining these two algorithms leads to mounting a Markov Decision Process (MDP) environment for a decision-making system.We demonstrate the effectiveness of our framework by implementing an off-policy deep reinforcement learning algorithm, using a deep Q-learning network to create experiences, and employing synchronous updates on the agent. Given the essence of reinforcement learning, the framework can be efficiently implemented for on-the-spot decision-making, allowing the driller to receive an effective sequence of actions considering company policies.Our algorithm achieves state-of-the-art performance on weight-to-slip hole conditioning operation, a wellbore cleaning operation after drilling a stand before connecting to the next pipe. The performance evaluation exhibits its efficiency in real-time operation overhaul, eliminating non-value-added activities. Our framework thus opens the door for automating the process based on the operating parameters obtained in real-time

Elucidating effects of Eu and P on solidification and precipitation of Al-7Si-0.3Mg based alloys refined by Ta and TiB2 - Spáčil, Ivo; Gehringer, Dominik; Holec, David; Albu, Mihaela; LI, Jiehua (Journal of alloys and compounds, 2024)
Effects of Eu (up to 500 ppm) and P (up to 40 ppm) on solidification and precipitation of Al-7Si-0.3Mg based alloys refined by solute Ta (0.12 wt%) and stochiometric Al-2.2Ti-1B grain refiner were investigated using optical microscopy, differential scanning calorimetry (DSC), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) as well as density functional theory (DFT) calculations. It was found that (i) solute Ta can refine α-Al grains and is unaffected by the addition of Eu and/or P. (ii) 200 ppm Eu is eligible enough to modify eutectic Si although its modification effect can be enhanced with higher Eu additions (up to 500 ppm). (iii) A high P concentration (40 ppm) counteracts the modification effect in the alloy modified with 200 ppm Eu and therefore unmodified structure is obtained. (iv) Even with the addition of Eu and P, the activation energy of stable β-Mg 2Si is calculated to be very low (60–70 kJ/mol), indicating a short time for the precipitation of β-precipitates. Furthermore, one possible nucleation sequence in Al-Si-Mg based alloys modified with Eu or Sr has been proposed based on the lattice mismatch calculation and thermodynamic stability. Finally, DFT calculations suggest that Eu is energetically favourable for TPRE growth mechanism. The present investigation provides new insights into controlling solidification microstructure (mainly for the grain refinement of α-Al and eutectic grains) and precipitation microstructure (mainly for β-MgSi precipitate) of Al-7Si-0.3Mg based alloys via the addition of Ta and TiB 2 as a refiner of α-Al and the addition of Eu and P as a modifier of eutectic Si.
Publisher Copyright: © 2024 The Authors
Keywords: AlSiMg based alloys; DFT; DSC; Grain refinement; Heat treatment; Modification; TEM

A Comprehensive Investigation of the Relationship between Fractures and Oil Production in a Giant Fractured Carbonate Field - Kharrat, Riyaz; Kadkhodaie, Ali; Azizmohammadi, Siroos; Misch, David; Moghadasi, Jamshid; Fardin, Hashem; Saedi, Ghasem; Rokni, Rokni; Ott, Holger (Processes : open access journal, 2024)
This study examines the connections between various fracture indicators and production data with an example from one of the giant fields in the Middle East producing complex fractured carbonate lithologies. The field under study hosts two reservoirs with a long development and production history, including carbonates from the Asmari and Bangestan Formations. A fracture intensity map was generated based on the interpretation of image logs from 28 wells drilled within the field. Mud loss data were collected and mapped based on the geostatistical Gaussian Random Function Simulation (GRFS) algorithm. Maximum curvature maps were generated based on Asmari structural surface maps. Comparing the results shows a good agreement between the curvature map, fault distribution model, mud loss map, fracture intensity map, and productivity index. The results of image log interpretations led to the identification of four classes of open fractures, including major open fractures, medium open fractures, minor open fractures, and hairline fractures. Using the azimuth and dip data of the four fracture sets mentioned above, the fracture intensity log was generated as a continuous log for each well with available image log data. For this purpose, the fracture intensity log and a continuous fracture network (CFN) model were generated. The continuous fracture network model was used to generate a 3D discrete fracture network (DFN) for the Asmari Formation. Finally, a 3D upscaled model of fracture dip and azimuth, fracture porosity, fracture permeability, fracture length, fracture aperture, and the sigma parameter (the connectivity index between matrix and fracture) were obtained. The results of this study can illuminate the modeling of intricate reservoirs and the associated production challenges, providing insights not only during the initial production phase but also in the application of advanced oil recovery methods, such as thermal recovery.
Publisher Copyright: © 2024 by the authors.
Keywords: fractured reservoirs; oil recovery; CFN; DFN; reservoir modeling; stress analysis; image logs; discrete fracture network DFN; continuous fracture network CFN; fractured reservoir

Understanding the Sustainable Development of Community (Social) Disaster Resilience in Serbia: Demographic and Socio-Economic Impacts - Cvetković, Vladimir; Šišović, Vanja (sustainability, 2024)
This paper presents the results of quantitative research examining the impacts of demographic and socioeconomic factors on the sustainable development of community disaster resilience. The survey was carried out utilizing a questionnaire distributed to, and subsequently collected online from, 321 participants during January 2024. The study employed an adapted version of the ‘5S’ social resilience framework (62 indicators), encompassing five sub-dimensions—social structure, social capital, social mechanisms, social equity and diversity, and social belief. To explore the relationship between predictors and the sustainable development of community disaster resilience in Serbia, various statistical methods, such as t-tests, one-way ANOVA, Pearson’s correlation, and multivariate linear regression, were used. The results of the multivariate regressions across various community disaster resilience subscales indicate that age emerged as the most significant predictor for the social structure subscale. At the same time, education stood out as the primary predictor for the social capital subscale. Additionally, employment status proved to be the most influential predictor for both social mechanisms and social equity-diversity subscales, with property ownership being the key predictor for the social beliefs subscale. The findings can be used to create strategies and interventions aimed at enhancing the sustainable development of resilience in communities in Serbia by addressing the intricate interplay between demographic characteristics, socio-economic factors, and their ability to withstand, adapt to, and recover from different disasters.
Cvetković, Vladimir M., and Vanja Šišović. 2024. "Understanding the Sustainable Development of Community (Social) Disaster Resilience in Serbia: Demographic and Socio-Economic Impacts" Sustainability 16, no. 7: 2620. https://doi.org/10.3390/su16072620 Publisher Copyright: © 2024 by the authors.
Keywords: community; demographic; disaster; impact; index; resilience; Serbia; social; socio-economic; sustainable development

Determination of the influence of particle spatial distribution and interface heterogeneity on tensile fracture of ordinary refractory ceramics by applying discrete element modelling - Du, Weiliang; Jin, Shengli; Gruber, Dietmar (Computational particle mechanics, 2024)
The microstructures and local characteristics of ordinary refractory ceramics are heterogeneous. The discrete element (DE) method was used to consider the variation in particle spatial distributions and statistically distributed interface properties (uniform, Weibull) between elements. In addition, three Weibull distributions with different shape parameters were evaluated. A uniaxial tensile test was used to study the effects of particle spatial distributions and interface property distributions on the stress–strain curve, tensile strength, and crack propagation. The results of the test show that the particle spatial distribution significantly influences crack propagation and fracture patterns, and the interface condition plays an important role in mechanical responses, crack propagation, and fracture mechanisms and patterns. The discrete element modelling of uniaxial tensile and compressive tests shows that brittle materials exhibit asymmetric mechanical responses to compression and tension loading including static Young’s modulus.
Publisher Copyright: © The Author(s) 2024.
Keywords: Asymmetric mechanical properties; Discrete element method; Interface property; Refractories; Uniaxial tensile test

Finite element modelling of refractories fracture process zone with gradient enhanced damage models - Ali, Zain; Jin, Shengli; Gruber, Dietmar (Finite elements in analysis and design, 2024)
This study investigates the numerical simulation of fracture behaviour in quasi-brittle materials like magnesia spinel refractories using the Gradient-Enhanced Damage (GED) model. It focuses on the complex modelling of these materials non-linear responses and compares conventional and variant GED models through a wedge splitting test. The results demonstrate that all GED models show a good fit to experimental data. However, the conventional GED model falls short in accurately depicting the fracture process zone. In contrast, the localizing GED model more accurately represents the fracture process zone, limiting spurious damage distribution, but requires finer meshing, elevating computational demands. The stress-based variant reduces spurious damage but is less effective comparatively. The study also assesses the role of heterogeneous strength distribution in replicating realistic crack patterns as observed in experiments.
Publisher Copyright: © 2024 The Authors
Keywords: Finite element analysis; Fracture process zone; Gradient-enhanced damage model; Quasi-brittle materials; Wedge splitting test

Hardness and fracture toughness enhancement in transition metal diboride multilayer films with structural variations - Vidis, Marek; Fiantok, Tomas; Gocnik, Marek; Svec, Peter Jr; Nagy, Stefan; Truchly, Martin; Izai, Vitalii; Roch, Tomas; Satrapinskyy, Leonid; Sroba, Viktor; Meindlhumer, Michael; Grancic, Branislav; et al. (Materialia, 2024)
The simultaneous enhancement of hardness (H) and fracture toughness (K IC) through the formation of superlattice structures challenges the conventional belief that these quantities are mutually exclusive. Here, this approach has been applied to the transition metal diborides, whose inherent brittleness severely restricts their application potential. The mechanical properties of TiB 2/TaB 2 systems as a function of bi-layer period Λ are investigated, combining theoretical and experimental approaches. Density Functional Theory is used to investigate the structural stability and mechanical properties of stoichiometric hexagonal TiB 2/TaB 2 superlattices for Λ = 3.9 – 11.9 nm. The calculations predict the highest H = 38 GPa and K IC (100) of 3.3 MPa.m 1/2 at the value of Λ = 5.2 nm. Motivated by the theoretical results, multilayer films with Λ = 4–40 nm were prepared by direct current magnetron sputtering. Due to the sputtering effects, the deposited diboride films differ significantly from the view of stoichiometry and structure. A detailed structure investigation reveals TiB 2/TaB 2 in form of superlattices exhibiting coherent interfaces for Λ = 4 nm. For higher Λ, parts of TaB 2 layers transform from the crystalline to the disordered phase. These transformations are reflected in the mechanical properties as measured by nanoindentation and micromechanical bending tests. The evolution of hardness follows Hall-Petch behavior, reaching a maximum of 42 GPa at Λ = 6 nm. Enhancing fracture toughness involves more complex mechanisms resulting in two K IC maxima: 3.8 MPa.m 1/2 at Λ = 6 nm and 3.7 MPa.m 1/2 at Λ = 40 nm.
Publisher Copyright: © 2024 The Author(s)
Keywords: Superlattices; Hard films; Fracture toughness; DFT; TiB2/TaB2; DFT; Fracture toughness; Hard films; Superlattices; TiB /TaB

Advancements and Challenges in Photovoltaic Cell Recycling: A Comprehensive Review - Gerold, Eva; Antrekowitsch, Helmut (Sustainability, 2024)
This review examines the complex landscape of photovoltaic (PV) module recycling and outlines the challenges hindering widespread adoption and efficiency. Technological complexities resulting from different module compositions, different recycling processes and economic hurdles are significant barriers. Inadequate infrastructure, regulatory gaps and limited awareness are also hampering progress. In addition, this analysis draws parallels between the development of PV module recycling and recycling technologies for other high-tech products, such as lithium-ion batteries, highlighting similarities in regulatory and technical feasibility challenges. Amid these challenges, however, lie opportunities for a sustainable future. Technological advances, stakeholder collaboration and the adoption of circular economy principles emerge as key ways forward. This review highlights the need for concerted action to overcome barriers and drive the development of efficient and sustainable PV module recycling practices.
Publisher Copyright: © 2024 by the authors.
Keywords: environmental impact of PV module recycling; photovoltaic cell recycling; photovoltaic technology; sustainable technology for energy production

From abandoned mines to carbon sinks - Safaei Farouji, Majid; Misch, David; Sachsenhofer, Reinhard F.; Rauscher, Max; Kostoglou, Nikolaos (International journal of coal geology, 2024)
This study represents the first assessment of CO2 storage potential in Austrian coal seams. Coal samples were taken from Fohnsdorf and Leoben abandoned coal mines, with particular emphasis on the Fohnsdorf coal since Leoben coal reserves were largely mined during previous coal production. Several methods were used to compare coal characteristics, including Rock-Eval pyrolysis (RE), organic petrography, and low-pressure N2 and CO2 sorption measurements. Both Fohnsdorf and Leoben coal samples show low sulfur and ash yields, as well as correspondingly high total organic carbon (TOC) contents. The pyrolysis Tmax and vitrinite reflectance values agree with a low coal rank for both sites. According to the N2 adsorption measurements at 77 K, low-lying mire coals from Fohnsdorf show a higher BET-specific surface area (BET-SSA) and BJH pore volume compared to raised-mire coals from Leoben. However, sapropelic shales and high-ash coals from Leoben show the highest BET-SSA and BJH pore volumes of all investigated samples and considerably exceed the N2 adsorption volumes of pure coals from both locations (N2 uptake up to 16 cm3/g; avg. for all samples 5.4 cm3/g). In contrast, the mean adsorbed CO2 uptake measured at 273 K and ∼ 1 bar followed the order of Fohnsdorf low-lying mire coals > Leoben raised-mire coals > Leoben sapropelic coals and shales, ranging at ∼0.8 mmol/g, ∼0.7 mmol/g, and ∼ 0.2 mmol/g, respectively. This shows that BET-SSA and BJH equations did not allow for adequate estimation of CO2 adsorption capacity trends in the investigated sample set. Furthermore, based on the existence of a hysteresis loop between CO2 adsorption and desorption branches for all investigated samples, the occurrence of weak chemisorption phenomena during CO2 adsorption is indicated. This effect helps to increase CO2 uptake and storage safety since the chemisorption process is not fully reversible upon pressure decrease. Ultimately, the theoretical CO2 sequestration potential of the remaining unmined Fohnsdorf coal reserves was estimated at 4.65 million tons, with an additional potential for enhanced coal bed methane production due to the gas-rich nature of Fohnsdorf coals with an estimated 1.2 billion m3 of CH4 in place.
Publisher Copyright: © 2024 The Authors
Keywords: CO adsorption; Coal; Fohnsdorf; Leoben; Nanopores; Nitrogen adsorption

Industry 4.0 Technologies and their Implications for Environmental Sustainability in the Manufacturing Industry - Kopeinig, Jacob; Woschank, Manuel; Olipp, Nadine (Procedia computer science, 2024)
The advent of Industry 4.0 has revolutionized the manufacturing industry by incorporating interconnectivity, decentralized decision-making, resource optimization, and automation. This transformation has been made possible through the integration of advanced technologies such as Artificial Intelligence, Cyber-Physical Systems, the Internet of Things, Big Data Analytics, and Blockchain Technology. However, while Industry 4.0 has primarily focused on production efficiency and real-time transparency, the need for the transition toward a holistically sustainable environment has become increasingly urgent. As a result, the term Industry 5.0 was devised, merging the concept of Industry 4.0 with sustainability, resilience, and human-centric goals. This paper explores the potential areas of influence these technologies have on the environmental dimension of sustainability. The findings indicate that various Industry 4.0 technologies can contribute to environmental sustainability in manufacturing. These technologies offer opportunities to optimize supply chain performance, improve product traceability, reduce waste, enhance resource management, and minimize overall environmental impact. By understanding the implications of Industry 4.0 for environmental sustainability, researchers, policymakers, and industry practitioners can collaborate to develop strategies that integrate advanced technologies and sustainable practices in the manufacturing sector. The research provides insights into the potential benefits of these technologies for environmental sustainability and calls for further investigation to fully explore their environmental dimensions.
Publisher Copyright: © 2024 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (https://creativecommons.org/licenses/by-nc-nd/4.0)
Keywords: Circular Economy; Digitalization; Green Logistics; Industrial Logistics; Industry 4.0; Industry 5.0; Sustainability

Recycling of Potential Hazardous Stone Wool into a Non-Hazardous New Stone Wool - Sattler, Theresa Magdalena; Doschek-Held, Klaus; Krammer, Anna; Pomberger, Roland; Vollprecht, Daniel (Detritus, 2024)
Mineral wool products are man-made vitreous fibres (MMVFs), such as glass wool and stone wool, mainly used for thermal and acoustic insulation. Demolition of buildings generates mineral wool (MW) waste. With regard to the intended recycling of materials, the European Union's circular economy package currently foresees a landfill ban for certain waste streams by 2030. As a result, Austria will have a landfill ban for MMVFs from 2027. This paper presents an investigated route for the recycling of MW waste into new mineral wool (wool2wool). The recycling route aims to conserve valuable and limited landfill volume and enables the reduction of primary resource consumption and CO2 emissions. The investigation was based on pH-dependent leaching tests of the fibres according to ÖNORM EN 14429 and hydrogeochemical modelling using LeachXS/Orchestra to identify the solubility-controlling mechanisms. The next step was a thermochemical treatment using correction materials to adjust the chemical composition, followed by rapid cooling through a spinning process. Another focus was on the theoretical determination of the dynamic viscosity to ensure suitable flow behaviour during fibre production. The chemical composition of the mineral wool produced was analysed, and it was shown that the target formulation could not be achieved for all elements within the permitted variation. The variations were due to the dissolution of the kiln lining, which had a more significant influence on the experiment than expected. Overall, the recycling pathway showed a high potential for CO2 savings, resource savings and other environmental benefits by recycling waste that is currently landfilled.
Keywords: Mineralwolleabfall; Recycling; gefährlicher; Auslaugverhalten; Wool2wool

The Impact of Competence on Performance in Industrial Engineering and Management - Pacher, Corina; Woschank, Manuel; Zunk, Bernd M. (Procedia computer science, 2024)
Industrial companies are constantly confronted with a variety of challenges caused by competitive pressure, globalization, and changing customer behavior. The discipline of Industrial Engineering and Management (IEM) aims to educate the engineers for tomorrow that balance economic competitiveness, environmental protection, and social acceptance towards facing grand issues of the world, such as climate change, resource scarcity, and energy transition. However, the critical success factors of engineering education remain insufficiently studied. A realignment of engineering education and training requires, on the one hand, a deep understanding of the necessary competences and, on the other hand, an empirically based investigation of the relationship between competences and performance in the actual working environment. This paper conceptualizes a preliminary research model for measuring the impact of competence on the performance of IEM professionals. After discussing the IEM job profile and the core working areas of IEM professionals, the preliminary research model is presented, and future implications are derived.

Comparative Analysis and Prediction of Sustainable Development in Earthquake Preparedness: A Cross-Cultural Perspective on Montenegro, North Macedonia, and Serbia - Grozdanić, Goran; Cvetković, Vladimir M.; Lukić, Tin; Ivanov, Aleksandar (2024)
Authorities and governmental bodies strongly emphasize the importance of residents preparing for natural disasters, particularly underscoring the significance of readiness for geophysical hazards like earthquakes. In this study, which represents comparative quantitative research, the levels and predictors of the impact on preparedness for earthquake-induced disasters in South-Eastern Europe countries such as Montenegro, North Macedonia, and Serbia are examined. Using the snowball sampling technique (online questionnaire), a survey of 1245 respondents (Montenegro (n = 400), North Macedonia (n = 345), and Serbia (n = 500) was conducted from February 2023 to February 2024. The paper is based on the central hypothesis that the most significant predictor of earthquake preparedness in Montenegro, North Macedonia, and Serbia is age, followed by gender and education. Multivariate regression analysis was used to determine the extent to which five scores of the subscales (household preparedness, community preparedness, disaster preparation, earthquake risk awareness, reinforced house) were associated with seventh demographic and socio-economic variables. In addition to the mentioned analysis, other statistical analyses such as T-test, one-way ANOVA analysis, and Pearson correlation were also utilized. The results indicate that age emerges as a predictor in various aspects of earthquake-induced disaster preparedness and awareness in most models, followed by education. These findings confirm the significance of respondents; age in determining levels of preparedness and earthquake awareness. Overall, in North Macedonia, respondents recorded the highest ratings (M = 3.52) for household preparedness for earthquakes, compared to Montenegro (M = 2.98) and Serbia (M = 3.26), where the lowest ratings were recorded. Research findings, taking into account cultural characteristics, can serve as a basis for the development of targeted interventions, strategies, policies, and programs aimed at improving the level of societal preparedness for earthquake-induced disasters.

Investigations on the hydrogen embrittlement tendency of K55 for underground storage applications using hollow probe specimens - Eichinger, Matthias; Zwittnig, Dino; Mori, Gregor Karl (Materials letters, 2024)
The susceptibility of ferritic pearlitic steel K55 to hydrogen embrittlement in high pressure gas atmospheres was investigated using slow strain rate tests with hollow probe specimens. Therefore, the specimens were charged with an internal hydrogen pressure of up to 20 MPa according to planned conditions for underground gas storages. The results show a significant decrease in ductility caused by hydrogen embrittlement yielding a loss in fracture strain of 46 % at 10 MPa and 63 % at 20 MPa hydrogen partial pressure compared to a specimen tested in nitrogen atmosphere. Furthermore, observations on the cross-sections of the tested specimens reveal that pearlite acts as obstacle for hydrogen enhanced crack growth.

Wong–Zakai approximation of a stochastic partial differential equation with multiplicative noise - Hausenblas, Erika; Randrianasolo, Tsiry (Applicable Analysis, 2024)
In this article, we derive the convergence rate for the Wong–Zakai equation of some approximation of stochastic evolution equations with multiplicative noise. To be more precise, the diffusion coefficient in front of the noise is the multiplication operator, and, is therefore not bounded, a situation not treated in the literature. Since our motivation comes from problems in numerical ling, we consider a finite, high-dimensional problem approximating a stochastic evolution equation on a random time grid. By imposing suitable stability conditions on the drift term and the time grid, we achieve a convergence rate in the mean square of order min⁡{1−𝛿,2−2⁢𝛾}, for some 0<𝛿<1 and 0<𝛾<1/2.
Publisher Copyright: © 2024 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: multiplicative noise; partial differential equations with randomness; Stochastic partial differential equations; time-discretization scheme; Wong–Zakai approximation

Energy Efficiency Measurement of Wide Bandgap Based Power Supplies - MacHtinger, Katharina; Zhu, Hongkeng; Makoschitz, Markus; Matioli, Elison; Brueniger, Roland (2024)

Energy saving potential of WBG-commercial power converters in different applications - Spejo, Lucas B.; Nonis, Erik; Schulz, Nicola; Minamisawa, Renato; Makoschitz, Markus (2024)

The Impact of the Bohemian Spur on the Cooling and Exhumation Pattern of the Eastern Alpine Wedge of the European Alps - Heberer, Bianca; Salcher, Bernhard C.; Tari, Gábor; Wessely, Godfrid; Dunkl, István; Sachsenhofer, Reinhard F.; Wagreich, Michael; von Hagke, Christoph (Tectonics, 2024)
Fold and thrust belt architecture may be influenced by basement geometry of the downgoing plate. This influence is notoriously difficult to assess due to a common lack of subsurface constraints and low resolution of exhumation estimates in space and time. The Bohemian Spur is a basement high at the transition from the Alps to the Carpathians. It coincides with narrowing of the foreland basin and an orogen-scale change of strike. Its location in one of the best-studied orogens in the world makes it an ideal case for understanding how basement topography influences fold and thrust belt tectonics. However, since thermochronological studies were mainly focused on the core of the Alps, timing and amount of exhumation remain poorly constrained in these peripheral parts of the orogen. We present new apatite (U-Th)/He and fission track data from the wedge above the Bohemian Spur. Thermally reset ages monitor a so far un(der)appreciated phase of prominent Late Oligocene to Miocene cooling, associated with crustal thickening, uplift and erosion during wedge propagation. Pronounced exhumation on the order of 3–4.5 km can be related to basement steps beneath the advancing wedge. The spur acted as a buttress for foreland-propagating thrusting, pinning deformation and nucleating antiformal stacking and duplexing and thus exhumation above it. We illustrate how along- and across-strike changes of sub-detachment topography impact wedge propagation and control fold and thrust belt geometries. The buttressing effect accounts for most of the exhumation, while deep-seated slab dynamics are of subordinate importance for wedge uplift.
Publisher Copyright: © 2024. The Authors.
Keywords: basement step; Bohemian Spur; Eastern Alps; exhumation; fold and thrust belt; thermochronology

New strategies to improve Recycling and reduce CO2-emission of Aluminum production and processing - Samberger, Sebastian; v. Czarnowski, Peter; Pogatscher, Stefan; Hirsch, Jürgen (Keikinzoku-yōsetsu = Journal of light metal welding, 2024)
https://doi.org/10.11283/jlwa.62.119

Optimizing Size and Number Density of Al3Zr Dispersoids in Al–Zn–Mg–Cu Alloys - Honaramooz, Mohammad Taha; Morak, Roland; Paris, Oskar (Advanced Engineering Materials, 2024)
The formation and temporal evolution of Al3Zr dispersoids in an Al–Zn–Mg–Cu alloy is investigated by in situ small-angle X-ray scattering during different homogenization treatments. The aim is to determine the most effective homogenization parameters for obtaining a high number density and small size of the dispersoids. Nucleation of the dispersoids is found to start above 400 °C and is boosted after isothermal holding at 425 °C. Regardless of the detailed homogenization profile, coarsening of the dispersoids is not observed below 450 °C. The results demonstrate that decreasing the heating rate, prolonging the first isothermal step, or increasing the number of steps are all beneficial regarding an increase of both, the volume fraction, and the number density of the dispersoids. Among the four investigated homogenization profiles, the one with decreasing the heating rate shows the highest impact.
Publisher Copyright: © 2024 The Authors. Advanced Engineering Materials published by Wiley-VCH GmbH.
Keywords: aluminum alloys; homogenizations; in situ small-angle X-ray scattering; phase transformation kinetics

M5 — Mars Magnetospheric Multipoint Measurement Mission - Larkin, Cormac J.K.; Lundén, Ville; Schulz, Leonard; Baumgartner-Steinleitner, Markus; Brekkum, Marianne; Cegla, Adam; Dazzi, Pietro; Iuliis, Alessia De; Gesch, Jonas; Lennerstrand, Sofia; Nesbit-Östman, Sara; Castro Pires, Vasco Daniel; et al. (Advances in Space Research, 2024)
Mars, lacking an intrinsic dynamo, is an ideal laboratory to comparatively study induced magnetospheres, which can be found in other terrestrial bodies as well as comets. Additionally, Mars is of particular interest to further exploration due to its loss of habitability by atmospheric escape and possible future human exploration. In this context, we propose the Mars Magnetospheric Multipoint Measurement Mission (M5), a multi-spacecraft mission to study the dynamics and energy transport of the Martian induced magnetosphere comprehensively. Particular focus is dedicated to the largely unexplored magnetotail region, where signatures of magnetic reconnection have been found. Furthermore, a reliable knowledge of the upstream solar wind conditions is needed to study the dynamics of the Martian magnetosphere, especially the different dayside boundary regions but also for energy transport phenomena like the current system and plasma waves. This will aid the study of atmospheric escape processes of planets with induced magnetospheres. In order to resolve the three-dimensional structures varying both in time and space, multi-point measurements are required. Thus, M5 is a five spacecraft mission, with one solar wind monitor orbiting Mars in a circular orbit at 5 Martian radii, and four smaller spacecraft in a tetrahedral configuration orbiting Mars in an elliptical orbit, spanning the far magnetotail up to 6 Mars radii with a periapsis just outside the Martian magnetosphere of 1.8 Mars radii. We not only present a detailed assessment of the scientific need for such a mission but also show the resulting mission and spacecraft design taking into account all aspects of the mission requirements and constraints such as mass, power, and link budgets. Additionally, different aspects of the mission programmatics like a possible mission timeline, cost estimates, or public outreach are shown. The common requirements for acceptance for an ESA mission are considered. The mission outlined in this paper was developed during the Alpbach Summer School 2022 on the topic of “Comparative Plasma Physics in the Universe”.
Publisher Copyright: © 2023 COSPAR
Keywords: Atmospheric escape; Induced magnetospheres; Magnetic reconnection; Mars; Mission concept proposal; Multi-spacecraft constellation

Device Having a Guide Unit for Guiding a Conveyor Belt - Prenner, Michael; Dünnwald, Wilfried; Koth, Thorsten (2024)
A device for guiding a conveyor belt, having a guide unit with an outer and an inner hollow-cylindrical body, the inner hollow-cylindrical body having a first central axis and being arranged in the outer hollow-cylindrical body, which has a second central axis, and both hollow-cylindrical bodies each have a central axis, with at least one bearing for rotatably mounting the outer hollow-cylindrical body on the inner hollow-cylindrical body and with an articulation body designed for mounting the inner hollow-cylindrical body on a central axle, wherein the articulation body is further designed to allow a horizontal and/or vertical change in angle of the first and/or second central axis relative to a central axis of the central axle. In order to increase the service life of the conveyor belt, the device is equipped according to the invention with a measuring and evaluating system including a sensor unit arranged inside and/or outside the guide unit, wherein the measuring and evaluating system is designed to detect the change in angle. The invention is based on the consideration that from a control behavior of the device, the causes of a fault of the belt run can be identified, deduced or narrowed down. Furthermore, a system for monitoring and guiding a conveyor belt using a device according to the invention is described.

Steel Ladle Slag Zone Lining Optimization Considering Irreversible Material Behavior - Klopf, Maximilian; Hou, Aidong; Jin, Shengli; Gruber, Dietmar (Steel research international, 2024)
The optimization of refractory linings is a complex task due to the many factors that influence the thermomechanical behavior. This study applies the multiparameter optimization method technique for order preference by similarity to the ideal solution to a commercially used slag zone lining of a secondary metallurgical steel ladle, considering the influence of different material models in a finite element (FE) simulation. The dataset is acquired by varying the working lining brick shape, initial expansion allowance (IEA), and isolation layer thickness. The maximum irreversible strain, joint opening at the hot face, and steel shell temperature are determined from the FE simulation results and used as the input values for the optimization. A larger circumferential brick dimension combined with low IEA is favorable for the von Mises creep model. The main contribution is from the IEA (98.53%). The optimized lining for the Drucker–Prager criterion has a brick with a small circumferential dimension and larger IEA. The main influencing factor is the brick shape (85.06%). The differences in the optimization results and factor contributions can be explained by the contribution of the constitutive models to the simulation results before and after the thermal shock.
Publisher Copyright: © 2024 The Authors. Steel Research International published by Wiley-VCH GmbH.
Keywords: lining optimization; magnesia carbon refractory; slag zone; steel ladles; technique for order preference by similarity to the ideal solution

Erdbeobachtungstechnologien im Bergbau - Mavroudi, Maria; Gubaidullina, Rushaniia; Tost, Michael; Teodoro, Ana Cláudia (Berg- und hüttenmännische Monatshefte : BHM, 2024)
Dem Einsatz der Erdbeobachtung im Bergbau fehlt bisher ein systematischer Rahmen, der die Bedürfnisse aller Akteure unterstützen kann. Das EU-Projekt S34I versucht, neue Ansätze für die Analyse von Erdbeobachtungsdaten zu entwickeln, mit dem primären Ziel, den Akteuren im Bergbau Informationen zu liefern. Dabei sollen die durchwegs unterschiedlichen Herausforderungen in den verschiedenen Phasen des Lebenszyklus eines Bergbaus berücksichtigt werden. An sechs verschiedenen Pilotstandorten werden verschiedene Anwendungen getestet, es werden unterschiedliche Sensordaten genutzt und Verarbeitungsmethoden kombiniert. Das Ziel dieser Forschungen geht über den Nutzen einer Entwicklung nur für industrielle Aktivitäten hinaus, sie leisten auch einen wesentlichen Beitrag zur Verbesserung der Sicherheit und Nachhaltigkeit.

Multimodal Human-Autonomous Agents Interaction Using Pre-Trained Language and Visual Foundation Models - Nwankwo, Linus; Rückert, Elmar (19th ACM/IEEE International Conference on Human-Robot Interaction (HRI 2024), 2024)
In this paper, we extended the method proposed in [17] to enable humans to interact naturally with autonomous agents through vocal and textual conversations. Our extended method exploits the inherent capabilities of pre-trained large language models (LLMs), multimodal visual language models (VLMs), and speech recognition (SR) models to decode the high-level natural language conversations and semantic understanding of the robot's task environment, and abstract them to the robot's actionable commands or queries. We performed a quantitative evaluation of our framework's natural vocal conversation understanding with participants from different racial backgrounds and English language accents. The participants interacted with the robot using both spoken and textual instructional commands. Based on the logged interaction data, our framework achieved 87.55% vocal commands decoding accuracy, 86.27% commands execution success, and an average latency of 0.89 seconds from receiving the participants' vocal chat commands to initiating the robot's actual physical action. The video demonstrations of this paper can be found at https://linusnep.github.io/MTCC-IRoNL/